Hawking Radiation as a Manifestation of Spontaneous Symmetry Breaking - Arraut, Ivan (Symmetry, 2024)
We demonstrate that black hole evaporation can be modeled as a process where one symmetry of the system is spontaneously broken continuously. We then identify three free parameters of the system. The sign of one of the free parameters governs whether the particles emitted by the black hole are fermions or bosons. The present model explains why the black hole evaporation process is so universal. Interestingly, this universality emerges naturally inside certain modifications of gravity.
Number: 5 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Hawking radiation; black holes; spontaneous symmetry breaking

Alignment, fitness for purpose, and fidelity in planning, conducting, and reporting research - Morrison, Keith (2024)

Fintech Adoption: A Study of Users in the Guangdong-Macao In-Depth Cooperation Zone in Hengqin (China) - Weng, Chi Lei; Lampo, Alessandro (INTI JOURNAL, 2024)
Intended as an economic and development hub, the Hengqin Cooperation Zone aims to foster collaboration and integration between mainland China, Hong Kong, and Macao, serving as a platform for economic development and innovation among the three regions. The zone's development has increased demand for financial services, often offered through fintech. There is, however, a lack of interoperability between the fintech services currently used in Macao and Hengqin. This may hinder Macao users' adoption of the technology. Thus, our research objective is to identify the factors determining Macao residents' adoption of fintech services in the area and provide insights for service providers, developers, and policymakers. A framework based on the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) was used for this purpose. The responses of 103 Macao residents provided evidence that ease of use significantly and positively impacts the usefulness of the technology. This in turn influences attitudes towards fintech usage. Subjective norms and perceived behavioral control positively impact fintech adoption intentions. The fintech industry and the governments of Macao and Hengqin can work on improving technology's ease of use and usefulness. They can also promote them to Macao users, and provide the resources required for better access to fintech in the zone
Number: 02 Publisher: INTI International University

Life Is not a Walk across a Field - Morrison, Keith (2024)

Enforcement of arbitral awards in Macau - Diakite, Ansoumane Douty (LexisNexis, 2024)
Under Macau Arbitration Law (MAL, art 64.1), an award shall be made in writing and shall be signed by the arbitrator or arbitrators. Furthermore, the law provides that in case of arbitral proceedings with more than one arbitrator, the signatures of the majority of all members of the arbitral tribunal shall suffice, provided that the reason for any omitted signature is stated (MAL, art 64.2).
Publisher: LexisNexis

Diffusion of Technologies: Delivering on the Promises of Battery Electric Vehicles - Lampo, Alessandro; Silva, Susana C. (Walking the Talk? MNEs Transitioning Towards a Sustainable World, 2024)
Battery electric vehicles (BEVs) are living up to their claims as consumers choose them more frequently. The increasing demand for sustainable vehicles translates into the global need for specific components, materials, and infrastructures and drives the regulatory frameworks in each country. While BEVs offer environmental benefits and global business opportunities, the technology has not yet gained mainstream acceptance. Thus, this work aims to investigate the characteristics of BEV users and their role in the diffusion of products to larger segments, as this may vary from country to country. For this purpose, a survey based on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT-2) (Venkatesh et al., 2012) framework and structural equation modeling (SmartPLS) was adopted. The results indicated that, except for the constructs of effort expectancy (EE) and social influence (SI), the predictors in the model performed well in this context. Current users are satisfied with their vehicles and are supportive of BEVs in the future. The analysis also revealed that in addition to the availability of financial resources, early adopters are attracted by new technologies in a way that leads them to make decisions outside of the traditional influence of the other members of society. It is suggested to leverage the perceived benefits of status, differentiation, or uniqueness motives, to appeal to those seeking to appear trendy and tech-savvy in society. Companies and policymakers should acknowledge the peculiarities of early customers in their communication strategies to reach a wider audience around the globe and encourage the adoption of BEV technology.
Keywords: Air quality; Battery electric vehicles; Clean energy technology; Consumer behavior; Diffusion of innovations; Early adopters; International marketing

Machine learning-based cardiac activity non-linear analysis for discriminating COVID-19 patients with different degrees of severity - Ribeiro, Pedro; Marques, João Alexandre Lobo; Pordeus, Daniel; Zacarias, Laíla; Leite, Camila Ferreira; Sobreira-Neto, Manoel Alves; Peixoto, Arnaldo Aires; de Oliveira, Adriel; Madeiro, João Paulo do Vale; Rodrigues, Pedro Miguel (Biomedical Signal Processing and Control, 2024)
Objective: This study highlights the potential of an Electrocardiogram (ECG) as a powerful tool for early diagnosis of COVID-19 in critically ill patients with limited access to CT–Scan rooms. Methods: In this investigation, 3 categories of patient status were considered: Low, Moderate, and Severe. For each patient, 2 different body positions have been used to collect 2 ECG signals. Then, from each collected signal, 10 non-linear features (Energy, Approximate Entropy, Logarithmic Entropy, Shannon Entropy, Hurst Exponent, Lyapunov Exponent, Higuchi Fractal Dimension, Katz Fractal Dimension, Correlation Dimension and Detrended Fluctuation Analysis) were extracted every 1s ECG time-series length to serve as entries for 19 Machine learning classifiers within a leave-one-out cross-validation procedure. Four different classification scenarios were tested: Low vs. Moderate, Low vs. Severe, Moderate vs. Severe and one Multi-class comparison (All vs. All). Results: The classification report results were: (1) Low vs. Moderate - 100% of Accuracy and 100% of F1–Score; (2) Low vs. Severe - Accuracy of 91.67% and an F1–Score of 94.92%; (3) Moderate vs. Severe - Accuracy of 94.12% and an F1–Score of 96.43%; and (4) All vs All - 78.57% of Accuracy and 84.75% of F1–Score. Conclusion: The results indicate that the applied methodology could be considered a good tool for distinguishing COVID-19’s different severity stages using ECG signals. Significance: The findings highlight the potential of ECG as a fast and effective tool for COVID-19 examination. In comparison to previous studies using the same database, this study shows a 7.57% improvement in diagnostic accuracy for the All vs All comparison.
Keywords: Accuracy; COVID-19; ECG signals; Machine learning classifiers; Non-linear analysis; –

Relationships among critical thinking disposition components of Chinese undergraduates: A moderated mediating effect analysis - Zhao, Yangyintao; Liu, Yong; Wu, Hao (International Journal of Educational Research, 2024)
Critical thinking (CT), as a form of higher-order thinking, is intended to help individuals form reasonable reflection and judgment to deal with increasingly severe employment situations. As the primary workforce in the labor market, undergraduates must possess a strong critical thinking disposition (CTD) to make better use of CT. Despite extensive research on components of CTD from the perspective of educational practices, there is limited emphasis on investigating the components and their relationships of CTD in the labor market and the impact of gender differences. Therefore, this study presented an analysis of 1535 Chinese undergraduates (Mage = 20.89; SD = 1.43) using the Employer-Employee-Supported Critical Thinking Disposition Inventory (2ES-CTDI), aiming to explore the CTD that undergraduates should possess before entering the labor market. The relationships among the components were examined using SmartPLS4.0 in conjunction with Partial Least Squares Structural Equation Modeling (PLS-SEM). Additionally, a multigroup analysis (PLS-MGA) with a measurement invariance (MI) test was conducted to validate the moderating effects of gender. The findings indicate that (a) self-efficacy has a significant negative effect on habitual truth-digging, and boys are more affected than girls, instant judgment plays a competitive partial mediating role in this relationship; (b) self-efficacy has a significant positive effect on instant judgment, and boys are more likely to make instant judgments than girls; (c) instant judgment significantly positively affects habitual truth-digging. These findings highlight the dynamic equilibrium among the internal components of CTD in the labor market and call for increased attention from educators to the importance of gender differences in the cultivation process.
Keywords: Critical thinking disposition; Labor Market; Moderated mediation; Undergraduates

Revenue Management in Airlines and External Factors Affecting Decisions: The Harmonic Oscillator Model - Arraut, Ivan; Rosado, Wilson; Leong, Victor (Mathematics, 2024)
The Revenue Management (RM) problem in airlines for a fixed capacity, single resource and two classes has been solved before by using a standard formalism. In this paper we propose a model for RM by using the semi-classical approach of the Quantum Harmonic Oscillator. We then extend the model to include external factors affecting the people’s decisions, particularly those where collective decisions emerge.
Number: 6 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: collective decisions; harmonic oscillator; revenue management; spontaneous symmetry breaking

A Pilot Study for Measuring Complex Problem-Solving in Jordan: Feasibility, Construct Validity, and Behavior Pattern Analyses - Alrababah, Saleh Ahmad; Wu, Hao; Molnár, Gyöngyvér (Sage Open, 2024)
In the 21st century, complex problem-solving (CPS) serves as a key indicator of educational achievement. However, the elements of successful CPS have not yet been fully explored. This study investigates the role of strategic exploration and different problem-solving and test-taking behaviors in CPS success, using logfile data to visualize and quantify students’ problemsolving behavior on 10 CPS problems with different characteristics and levels of difficulty. Additionally, in the present study, we go beyond the limits of most studies that focus on students’ problem-solving behavior pattern analyses in European cultures and education systems to examine Arabic students’ CPS behavior. The results show that computer-based assessments of CPS are feasible and valid in Jordanian higher education. The findings also confirm the structural validity of CPS, indicating that the processes of knowledge acquisition (KAC) and knowledge application (KAP) can be distinguished and separated in the problem-solving process. Large differences were identified in students’ test-taking behavior in terms of the efficacy of their exploration strategy. We identified four latent classes based on the students’ exploration strategy behavior. The study thus leads to a better understanding of how students solve problems and behave during the problem-solving process in uncertain situations.

Matteo Ricci's teaching on the goodness of human nature: its Thomistic and neo‐Confucian sources - Cai, Yilun (The Heythrop Journal, 2024)
Abstract The Jesuit missionary Matteo Ricci's teaching on the goodness of human nature in The True Meaning of the Lord of Heaven represents the fruit of the first encounter between Catholicism and Confucianism. This article will consider the Thomistic and neo‐Confucian sources in Ricci's enunciation of the Catholic doctrine on the goodness of human nature in this Chinese catechism. It will illustrate that Ricci developed his teaching, which is fundamentally Thomistic, with the help of terminology borrowed from the Chinese philosophical tradition. His distinction between the good of nature and the good of virtue leads to prioritising the cultivation of human nature. Ricci's teaching reflects the early modern Jesuits’ appreciation of human freedom. It also displays a Catholic reaction to the sixteenth‐century neo‐Confucian intellectual trend that ignored the importance of moral cultivation.

Design Thinking Methodology and Text-To-Image Artificial Intelligence: A Case Study in the Context of Furniture Design Education - Caires, Carlos Sena; Estadieu, Gerald; Olga Ng Ka Man, Sandra (Perspectives on Design and Digital Communication IV: Research, Innovations and Best Practices, 2024)
The design thinking methodology is a problem-solving approach that involves empathising with end-users, (re)defining problems, brainstorming solutions creatively, and experimenting with prototypes and testing. It has been widely adopted in education to help students develop critical thinking, creativity, and problem-solving skills in design. On the other hand, text-to-image artificial intelligence is a method used to generate images from natural language descriptors (usually referred to as prompts). Design thinking methodology can teach students to think creatively and critically about real-world problems when applied in the classroom. In the context of design teaching at the University of Saint Joseph, Macao, students use the design thinking methodology to develop innovative proposals for furniture design solutions. Combining design thinking methodologies with text-to-image artificial intelligence can further enhance the learning experience by allowing students to generate visual representations of their ideas during the ideation phase. The authors developed a systematic approach to generate images for ideation on furniture design based on prompting text-to-image (PTI). The analysis related students’ results who applied the design thinking methodology without using AI tools and the results generated using a standard text-to-image programme. By combining both methods, teachers can help students develop critical thinking, creativity, and problem-solving skills, while also allowing them to generate visual representations in a different paradigm and, by so, being able to communicate their ideas with the most appropriate support for them.
Keywords: Artificial intelligence; Design thinking; Education quality; Furniture design education; Text-to-image prompt

EDUCATORS' PERSPECTIVE OF STUDENTS WITH SPECIAL EDUCATIONAL NEEDS (SEN) AND THEIR SENSE OF BELONGING, SELF-COMPETENCE, AND AGENCY - Carvalho, Edna Line Henriques de (University of Saint Joseph, 2024)
What strategies did educators use to cultivate a sense of belonging, self-competence, and agency among students with Special Educational Needs (SEN)? Did educators face any challenges in implementing these strategies? Were the findings of this study specific to the inclusive school in Macau, or can they be generalised to other educational settings? This study brings to light educators' inner perspective of students' sense of belonging, self-competence, and agency. Specifically, it aims to uncover the academic and emotional needs of students with SEN and the importance that these may have in promoting a positive educational experience. By gathering the perspectives of educators in an inclusive school in Macau who work side-by-side with these students daily, we can understand how essential these elements are in contributing to their overall development. The purposive sampling approach was used in this study to further investigate various experiences and perspectives of educators within an inclusive classroom setting. The educators interviewed provided insight into an inclusive classroom with students with SEN in full-time attendance. The educators sampled in this study facilitated the search for strategies, challenges and support systems to cultivate a sense of belonging, self-competence and agency, among students with SEN. Findings showed educators' understanding of the importance of students with SEN's sense of belonging, self-competence and agency. The educators' awareness of their students' interactions with peers, and the educators themselves, was prominent, revealing how the sense of belonging for students with SEN affected these relationships. Regarding students' sense of self-competence, according to educators, students with SEN had opportunities to showcase their confidence in specific classroom areas and to exercise independence in the classroom, within the set curriculum and lesson plans. In the findings, educators illuminated the importance of agency in students with SEN. However, they were apprehensive about changes in lesson plans, cultivating a fully independent classroom setting and providing choices to students with and without SEN. The study's implications highlight the educational practices and policies that effectively supplement students with SEN's academic and social environments. The findings of this study aim to guide curriculum developers, educators and parental figures in fostering positive learning experiences for students with diverse learning needs
Keywords: Heutagogy; SEN; Self-competence; Students' agency; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

PSYCHOMETRIC PROPERTIES OF BASIC FAMILY RELATIONS INVENTORY (BFRI) IN MACAO - Chan, Kuai Ian (University of Saint Joseph, 2024)
By discussing various aspects of family functioning, including the intricate nature of family functioning, family dynamics’ impact on adolescent growth and lifelong development, and the COVID-19’s effects on family relationships, it reveals the importance and necessity of assessment instruments in the field of family counselling. And concerning the gap between family research and clinical practice as well as the absence of a singular tool capable of evaluating various family functions comprehensively in the Macao context, the study introduced the Basic Family Relations Inventory (BFRI; or ‘Cuestionario de Evaluación de las Relaciones Familiares Básicas’, CERFB), a self-reported questionnaire based on Linares’ Basic Family Relations Theory. This valuable tool consists of 25 items, assessing simultaneously the quality of family relationships in two basic dimensions—marital and parental functioning. This study aimed to develop the Chinese version of the BFRI and investigate its psychometric properties in the context of Macao. By employing a quantitative research approach, it evaluated the normal distribution, exploratory factor analysis and reliability of the BFRI in a non-clinical snowball and convenience sample of 165 participants with at least one biological child from 12 to 18 years old. In the exploratory factor analysis, the initial factor extraction resulted in four components, reflecting both marital and parental items. This suggested potential overlap and interconnectedness between the marital and parental subsystems. Subsequent analysis identified a three-factor solution, separating marital, negative parental, and positive parental components. This aligned with the factor structure of the original Spanish version of the BFRI. A two-factor solution was also explored, replicating findings from the previous Italian and Portuguese validation of the BFRI despite some inconsistencies in item alignment. The EFA results revealed that the three-factor structure of the Chinese version of the BFRI was the best fitting model for the Macao population. Reliability analysis, assessed through Cronbach’s alpha, indicated satisfactory internal consistency of the scales. The results of the analyses demonstrate promising psychometric properties, supporting the tool’s effectiveness in assessing marital and parental relationships in a Macao population. The study contributed to the development of the valuable family assessment instrument. It suggested that the Chinese version of the BFRI could serve as a useful instrument to concurrently assess the quality of marital and parental relationships and systematically collect the data of family functioning in both dimensions. It’s also believed that this instrument could benefit the evaluation of family dynamics and comprehension of family relations not only in family research studies, but also in counselling intervention and clinical therapy, preventing risks to the health of children as well as promoting healthy family contexts in Macao
Keywords: Basic Family Relations Inventory (BFRI); Marital relationship; Parental relationship; Psychometric properties; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Career trajectory and cross-system mobility: Career planning of doctoral students in Macao - Ge, Yun (Higher Education Quarterly, 2024)
This study investigates career trajectory and work locations of doctoral students trained in Macao and analyses how their career paths are shaped by perceived macro-level factors. Respondents from four applied disciplinary areas were selected for semi-structured in-depth interviews. Research results show that doctoral students who graduated from Macao higher education institutions enjoy good career prospects in Mainland China. Their competitiveness in the research-related job market benefits from having a multi-level support system and a training mode that promotes government–university–industry collaboration. Policies and demand from industrial sectors are involved in students' learning experience through channels such as financial support, project collaboration and networks. Doctoral students in Macao are strategic planners and actors in leveraging their human capital. As Macao becomes an emerging destination for cultivating high-level research labour, findings from this study capture a model of human capital formation in China's cross-system context.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/hequ.12474
Keywords: career trajectory; cross-system mobility; doctoral education; employability; human capital formation

EXPLORING MUSLIM STUDENTS LIVED EXPERIENCES IN MACAU: A PHENOMENOLOGICAL APPROACH - Ho, Kit Ieng (University of Saint Joseph, 2024)
Muslim community is one of the minority groups in Macau SAR China. Muslims are an interesting group in terms of research because of its diversity in respect to language, nationality, social status, and education level. Groups of people migrate for various reasons such as religion, politics, economy, and education. Individuals experience the age in between nineteen and twenty-four, which fall in the category of youth. Studies of Muslim youths have gained more attention in scholarship, statistical data, and research. The study seeks to understand Muslim students’ life and the needs of this minority group and explores how Muslim students perceive Islam and their own ability to cope with school related cultural pressures through qualitative, phenomenological approach, and focuses on exploring the common experiences of Muslim students in this city. This study used a conceptual framework based on critical race theory (CRT). We use in-depth interviews of five Muslim youth, ages between 19 and 24, to investigate their school life experiences and Islamic practices. We also administered questionnaires and field note to understand their social mobility, social capital and to gain a deeper understanding of their daily lives. A thematic analysis of the interview data produced the following themes: 1) Social mobility; 2) Social capital Relationship with friends; 3) Discrimination and micro-aggressions; and 4) Religion Identity. The study found that the Muslim status of the participants did not have a significant impact on their school experience, as they were able to find accommodation in their practice of religion and school life. However, the multiple identities of the participants as Macau citizens and their ethnic backgrounds did affect their social capital and sense of belonging. The study also examined the experiences of the participants within Macau society, including social factors such as racism. The results indicated that language and ethnicity were factors that hindered their integration into the community. In addition to the original themes, the analysis of the participants' stories in this research revealed two counter-narratives that challenge prevailing narratives. These counter-narratives include the deconstruction of oppressed Muslim women's narratives and the influence of local mainstream religious schooling on Muslim students' religious loyalty. These alternative narratives provide new insights into the lives of Muslim youths and challenge conventional stories. The findings of this study have important implications for educators, academics, and members of both Muslim and non-Muslim communities. By allowing youth to establish broader connections with society and increasing their motivation to participate in and contribute to the community, this study highlights the need for inclusive educational environments that support the diverse identities of students. Furthermore, the study provides young Muslims with a voice in society, empowering them to challenge dominant narratives and promote counter narratives that reflect their experiences and perspectives to meet critical race theory ethos of ongoing active struggle
Keywords: Critical Race Theory; Muslim youth; School experience; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Integrating digital technologies during the COVID-19 kindergarten suspension period in Hong Kong. - Hu, X.; Yelland, N.; Leung, W. M. V.; Liang, Y.; Sun, C. R.; Graham, C. R. (Digital Technologies and Early Childhood in China: Policy and Practice, 2024)

澳門小學教師對融合教育態度之研究 =: A Study on Macao Primary School Teachers ’Attitudes towards Inclusive Education - Kwok, Siu Kam (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學教師; 澳門; 融合教育

Aspects that constitute citizens’ trust in e-government - A review and framework development - Lai, Chimeng; Marques, Alexandre Joao Lobo (Multidisciplinary Reviews, 2024)
The extent of citizens' trust in government determines the success or failure of e-government initiatives. Nevertheless, the idiosyncrasies of the concept and the broad spectrum of its approach still present relevant challenges. This work presents a systematic literature review on e-government trust while elaborating and summarizing a conceptual analysis of trust, introducing evaluation methods for government trust, and compiling relevant research on e-government trust and intentional behavior. A total of 26 key factors that constitute trust have been identified and classified into six categories: Government trust, Trust in Internet and technology (TiIT), Trust in e-government (TiEG), Personal Beliefs, Trustworthiness, and Trust of intermediary (ToI). The value added of this work consists of developing a conceptual framework of TiEG to provide a significant reference for future in-depth studies and research on e-government trust.
Keywords: Systematic Literature Review (SLR); framework; trust; trust in e-government

Impacts of Central Bank Digital Currency on Regional Economic Integration: Evidence from the Greater Bay Area of China - Lei, Weng Chi; Wang, Xinru (The Chinese Economy, 2024)
An increasing number of countries have launched their central bank digital currencies (CBDC) in recent years, but the economic impacts of CBDC adoption are underexplored. To empirically assess how CBDC adoption influences regional economic integration, this paper investigates the Greater Bay Area, where China carried out one of its first digital renminbi pilot programs. The Greater Bay Area provides a good example because the growing acceptance of digital renminbi in the area can potentially mitigate transaction costs and risks due to the exchange rate volatility of the Chinese renminbi, Hong Kong dollar, and Macao pataca. CBDC adoption can lead to greater real and financial integrations by facilitating cross-border trade in goods and services. This paper evaluates deviations from uncovered interest rate parity, purchasing power parity, and real interest rate parity across Guangdong, Hong Kong, and Macao based on monthly interest rate and price data from January 2016 to December 2022. The time series have mean values near zero, which validate the parity conditions and indicate high degrees of financial, real, and economic integrations. The Markov regime-switching regression model identifies three regimes: (1) pre-Covid, (2) post-Covid, and (3) post-CBDC. The Covid-19 outbreak brought lower integration and stability, but the launch of the CBDC restored some of the pre-Covid integration and stability. Regimes 1 and 2 are persistent, and transitions from Regime 3 back to Regime 1 are probable. Hence, this study finds evidence that CBDC adoption improves regional economic integration in the short and long run.
Publisher: Routledge _eprint: https://doi.org/10.1080/10971475.2024.2333124
Keywords: Central bank digital currency; Greater Bay Area; digital renminbi; economic integration; financial integration

The Role of Habit in UTAUT-2 Research: A Study of BEV Users - Lampo, Alessandro (Proceedings of the 2023 9th International Conference on Industrial and Business Engineering, 2023)
The UTAUT-2 offers the most comprehensive assessment of individual acceptance and use of technology to date. In particular, the theoretical additions of “hedonic motivation”, “price value”, and “habit”, made the model suitable for studying technology in a consumer context. However, a review of the literature revealed that the construct of habit has been dropped from a large number of studies. There are several reasons for this, including that the technologies examined were relatively new for the respondents to form a routine behavior. Therefore, this study aims to explore whether the construct can be used as a key predictor of future intention to use an innovation rather than an acquired practice among technology users. For this purpose, a conceptual model based on the theoretical additions to the UTAUT-2 is proposed and analyzed with structural equation modeling (SmartPLS). Our results showed significant relationships between the predictors and the behavioral intention to use battery electric vehicles (BEV) technology, and, in particular, depicted the construct of habit as the strongest factor in the decision to adopt the technology. In light of our findings, the construct of habit (HT) should be used in research together with the other UTAUT-2 predictors to assess individuals’ perceptions of possible future habitual behaviors.
Keywords: Battery Electric Vehicles (BEVs); Consumer Behavior; Habit; Process Innovation; Technology Acceptance; UTAUT-2.

Santa Claus is not coming to everyone in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau Business | December 2023 Keith Morrison – Author and educationist
Section: Macau Business

Factors influencing disability inclusion practice on social media - Chan, Joye Wai Peng; Phillips, Jenny O.L. (Proceedings of the 2023 14th International Conference on E-business, Management and Economics, 2023)
Digital inclusion in Macao is in the very beginning stage, and disability inclusion practice on social media in producing and promoting accessible social media content and needs is hard to find. This study aims to analyse the factors that influence communication staff's practice of disability inclusion on social media by using the combined employee behaviour and communication process model to provide suggestions to management who wants to promote disability inclusion practice on social media.The Service Centre for the Deaf of the Macau Deaf Association (MDA) was selected as the object for this case study. The online social media used for MDA's communication was analysed, and semi-structured in-depth interviews with members of the Association were conducted. The research findings showed that, except for the reward structure, factors examined from the work environment in terms of organisation, supervision and co-workers; communication staff themselves; outcomes of accessible social media communication; audience and feedbacks show relations with disability inclusion practices on social media. The delivery of inclusive culture, the influential power of disability stakeholders and the positioning of social media platforms are the key influencing factors.The interesting part of this study is that people without disabilities seem to be excluded from the disability inclusion practice carried out on MDA's Facebook. Their social media content is highly accessible to deaf and hard-of-hearing audiences yet seems not to involve the general public. The study object is a good model for producing accessible content, yet the optimisation of promoting social media accessibility needs further exploration.
Keywords: Accessible Social Media (ASM); Disability Employment; Disability Inclusion; Macau Deaf Association

A Review on Open Innovation and Absorptive Capacity in Small and Medium Enterprises during the last decade - Analyzing Bibliometrics to Understand the Development of the Field - Ip, Chi Hang; Lobo Marques, Joao Alexandre; Dos Santos Silva, Bruno Riccelli; Cortez, Paulo Cesar; Barbosa, Alvaro (Proceedings of the 2023 14th International Conference on E-business, Management and Economics, 2023)
Small and medium-sized enterprises (SMEs) can benefit significantly from open innovation by gaining access to a broader range of resources and expertise using absorptive capacitive, and increasing their visibility and reputation. Nevertheless, multiple barriers impact their capacity to absorb new technologies or adapt to develop them. This paper aims to perform an analysis of relevant topics and trends in Open Innovation (OI) and Absorptive Capacity (AC) in SMEs based on a bibliometric review identifying relevant authors and countries, and highlighting significant research themes and trends. The defined string query is submitted to the Web of Science database, and the bibliometric analysis using VOSviewer software. The results indicate that the number of scientific publications has consistently increased during the past decade, indicating a growing interest of the scientific community, reflecting the industry interest and possibly adoption of OI, considering Absorptive. This bibliometric analysis can provide insights on the most relevant regions the research areas are under intensive development.
Keywords: Absorptive Capacity; Bibliometric analysis; Open innovation; SMEs; VOSviewer

Environmental Concern and the Intention to Use Eco-friendly Technologies: An Analysis of Battery Electric Vehicles in Macau. - Lampo, Alessandro; Silva, Susana C. (Proceedings of the 2023 14th International Conference on E-business, Management and Economics, 2023)
A growing number of people are becoming aware of the environmental footprint that our actions have on the environment. Research indicates that a key factor leading to the adoption of an electric vehicle is consumers’ high environmental concern. Indeed, the environmental concern (EC) construct is commonly associated with the purchase of sustainable and eco-friendly products in literature. Our study challenges this assumption. We examined how the environmental factor influenced the behavioral intention of Macau residents to adopt battery-electric vehicle (BEV) technology. For this purpose, we conducted a study based on the UTAUT-2 framework and used structural equation modeling (SmartPLS) to analyze the data. As a result, the choice of vehicles did not depend on the consumers’ level of concern. It appeared that consumers strongly perceived the benefits of a cleaner environment, however, when it comes to technology, environmental benefits are nice to have, rather than the primary incentive to purchase BEVs. Researchers should consider the role of environmental concern as a background factor in technology acceptance models, rather than a direct predictor of behavior. It is also recommended that marketers correctly consider this element when developing their product communications strategies, to appeal to the desired segment of customers.
Keywords: BEV; Clean Energy Technology; Environmental Footprint; Macau.; Sustainable Transportation; Technology Acceptance

An Exploratory Comparison of Stock Prices Prediction using Multiple Machine Learning Approaches based on Hong Kong Share Market - Lin, Chinyang; Lobo Marques, João Alexandre (Proceedings of the 2023 14th International Conference on E-business, Management and Economics, 2023)
Stock price prediction has always been challenging due to its volatility and unpredictability. This paper performs a preliminary exploratory comparison that utilizes Long Short-Term Memory (LSTM) and Support Vector Machine (SVM) algorithms to forecast the stock market in Hong Kong. It considers a public dataset publicly available and uses feature engineering to extract relevant features. Then, LSTM and SVM algorithms are applied to predict stock prices. Our results show that the proposed machine learning techniques can predict stock prices in Hong Kong's share market with the error metrics presented, and, for this purpose, LSTM achieved better results than SVM, with MSE = 0.0026, RMSE = 0.0508, MAE = 0.0406, and MAPE = 1.325.
Keywords: Long Short-Term Memory (LSTM); Machine Learning; Stock price prediction; Support Vector Machine (SVM); Time-series analysis

Facial expression for marketing and consumer behavior: A Bibliometric analysis from 2013-2023 using Data Visualization Tools - Qian, Cheng; Lobo Marques, Joao Alexandre (Proceedings of the 2023 14th International Conference on E-business, Management and Economics, 2023)
The classification of emotions based on facial expressions have been a new topic of research in recent years, especially in marketing and consumer behavior areas. However, there is lack of studies to understand how the research topic is developed in terms of bibliometric data. Therefore, the purpose of this work is to provide a bibliometric analysis of the research on the analysis of facial expressions for marketing and consumer behavior, identifying the state of the art, the latest research direction, and other indicators. We extracted data from Web of Science (WOS) platform, considering its core database, resulting in a total of 117 articles. The software Vosviewer was used to analyze the data and graphically visualize the results. This study indicates some of the most influential authors citations and coupling analysis in this specific field, identifies journals with the most published articles, and provide trends of the research area based on the analysis of keywords and corresponding number of articles per year. The results shows that 11 articles (9.4%) were cited more than 100 times, and the two most prolific authors published 5 articles, and the two most influential authors are Bouaziz Sofien and Pauly mark(270 citations) in this field. Of the 117 articles retrieved by WOS, more than 70% were published in high impact journals. The bibliometric analysis of the existing work in this study provides a valuable and reliable reference for researchers in this field and makes a reasonable prediction of the research direction trends.
Keywords: Bibliometric analysis; Consumer; Facial expression; Marketing; Research; VOSviewer

Neuromarketing As A Tool To Measure And Evaluate The Consumer Behaviour Of Guanding Teahouse's Social Media Advertisement - Zeng, Ian Mei; Lobo Marques, Joao Alexandre (Proceedings of the 2023 14th International Conference on E-business, Management and Economics, 2023)
This research aims to evaluate a Macau tea brand's social media advertising effectiveness with neuromarketing tools, including physiological monitoring that can measure emotional arousal. This research bridges the gap of social media marketing on Instagram for brands through the neuromarketing method. Data from 40 respondents were collected with iMotions software using neuroscientific tools. This research uses the stimuli of Guanding Teahouse, a newly established Macau tea brand, to evaluate social media advertising effectiveness. The neuroscientific tools – Galvanic Skin Response (GSR) sensors, Eye-tracking, Facial Expression Analysis (FEA) and emotion analysis are used to do the experiment. The data analysis was drawn from one representative respondent to measure the emotions and attention on the Instagram advertisements. Video 1 recorded 9 GSR peaks and Video 2 recorded 12 GSR peaks, both videos attention is ranging between 96-98 indexes. Results show that advertising videos should focus more on the products than the model. Moreover, the participant is more interested in Video 2, but the effectiveness of advertising is showing a lower focus on the brand and the tea. Future studies should consider comparing the video advertising effectiveness of Instagram stories and Instagram reels to prevent disruption of video on the stories ad.

Categorization of Foreign Aid Donors: A Critical Review of the Criteria in Light of China's Reemergence as a Donor - Diakite, Ansoumane Douty; Marques, João Alexandre Lobo (Journal of Global South Studies, 2023)
Over the past several decades, the dichotomy between traditional and emerging donors has been based upon the notion that emerging donors (such as China) support authoritarian regimes and use foreign aid to pursue their economic interests at the expense of the poor in the recipient countries. Accordingly, Western donors, media, and scholars portray Chinese aid as non-poverty-focused. This study aims to review and analyze whether the dichotomy between traditional and emerging donors is still relevant in the current aid system and to propose a new and rigorous criterion for recategorizing donors. In terms of methodology, this study relies on secondary data, including scholarly works on traditional and emerging donors and foreign aid policy documents. Conclusions based on the research indicate that the divide between traditional donors and (re)emerging donors is becoming more ambiguous. The literature review indicates that the two donors’ aids had a mixed impact and that their approaches were similar. This paper highlights the importance of developing different recategorization criteria depending on the impact of aid.
Number: 2
Keywords: China and development assistance committee donors; aid policies; categorization of donors; sustainable development goal; traditional and emerging donors

Fr. Yves Raguin, S.J. and Interreligious Dialogue - Duraj, Jaroslaw (2023)

Tracing Modern Macau’s Evolving Global Role Views from Transnational Archives - Roberts, Priscilla (2023)

Comment on ''Generalized James' effective Hamiltonian method'' - Rosado, W.; Arraut, Ivan (Physical Review A, 2023)
In the paper carried out by Wenjun et al. [Phys. Rev. A 95, 032124 (2017)], a generalization of the James effective dynamics theory based on a first version of the James method was presented. However, we contend that this is not a very rigorous way of deriving the effective third-order expansion for an interaction Hamiltonian with harmonic time-dependence. In fact, here we show that the third-order Hamiltonian obtained by Wenjun et al. is not Hermitian for general situations when we consider time dependence. Its non-Hermitian nature arises from the foundation of the theory itself. In this comment paper, the most general expression of the effective Hamiltonian expanded up to third order is obtained. Our derived effective Hamiltonian is Hermitian even in situations where we have time dependence.
Publisher: American Physical Society

The Role of the Volatility in the Option Market - Arraut, Ivan; Lei, Ka-I. (AppliedMath, 2023)
We review some general aspects about the Black–Scholes equation, which is used for predicting the fair price of an option inside the stock market. Our analysis includes the symmetry properties of the equation and its solutions. We use the Hamiltonian formulation for this purpose. Taking into account that the volatility inside the Black–Scholes equation is a parameter, we then introduce the Merton–Garman equation, where the volatility is stochastic, and then it can be perceived as a field. We then show how the Black–Scholes equation and the Merton–Garman one are locally equivalent by imposing a gauge symmetry under changes in the prices over the Black–Scholes equation. This demonstrates that the stochastic volatility emerges naturally from symmetry arguments. Finally, we analyze the role of the volatility on the decisions taken by the holders of the options when they use the solution of the Black–Scholes equation as a tool for making investment decisions.
Number: 4 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Black–Scholes equation; Merton–Garman equation; decision theory; option price; stock market; volatility

Connecting Neuromarketing and AI - a path to new insights and analysis - Marques, J. A. L. (2023)

Unsettling Exiles: Chinese Migrants in Hong Kong and the Southern Periphery During the Cold War Angelina Y. Chin. New York: Columbia University Press, 2023. 320 pp., $35.00; £30.00, ISBN 9780231209991. - Roberts, Priscilla (The China Quarterly, 2023)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0305741023001406/resource/name/firstPage-S0305741023001406a.jpg
Publisher: Cambridge University Press

Perspectives of Local Communities on the Impact of Chinese Aid: A Case Study of China's Aid Projects in the Education Sector in Guinea - Diakite, Ansoumane Douty (Journal of Globalization Studies, 2023)
China's re-emergence as an aid donor has attracted the attention and criticism from Western donors, academia, and the media. In contrast to traditional donors, China's aid has been portrayed as anti-poverty aid, mainly due to its combination with other instruments, such as investment, and the absence of any political or economic conditions. This paper examines the impact of Chinese aid projects in Guinea's education sector from the perspective of the beneficiaries. The author collected data from both primary (interviews) and secondary (document analysis) sources. The present study concludes that China's aid projects in the education sector have received both positive and negative feedback, mainly because the recipients' needs have not been appropriately targeted. This study contributes to the literature on China's role in Africa. More specifically, it discusses the conditions for aid effectiveness in the field of education. Moreover, in the context of the globalization of aid practices, the study proposes best practices for China to adopt in order to improve the practices of its aid delivery. The novelty of this study lies in the methodology (qualitative method) used to understand China's aid from the perspective of the beneficiaries of its aid.

Static recording apparatus for soundscape analysis in Macau - Estadieu, Gerald; Cheung, Yin Yan; Pestana, Pedro Duarte; Barbosa, Alvaro (INTER-NOISE and NOISE-CON Congress and Conference Proceedings, 2023)
The concept of Soundscape was initially proposed to study the relationship between humans and their sonic environment. It has gathered momentum from academia to environmentalists and policymakers throughout the years. The study and characterisation of Soundscapes can be complex as it tries to take a holistic and qualitative approach rather than simply quantifying sound pressure levels. This paper introduces a comprehensive Soundscape study process in an ongoing research project in Macao (China), a small territory (32.9 km2) and one of the most densely populated areas in the world. The paper seeks to show a first version of a technical solution to systematically capture the local soundscape, analyse it, classify it, and ultimately deliver a dataset library and the intangible qualities of the environmental sound. This implementation, including technical documentation, code, and sound library with strong labelling, is presented under an open-source license to encourage future collaborative research. Finally, the paper offers suggestions on further developing the apparatus to reach a systematic and near real-time soundscape analysis with the development of a machine learning system.

Macau's First Modern University: Exploring the Early History of the University of East Asia - Roberts, Priscilla (2023)

Higher Education students' perceptions towards Information Literacy: a study in Macau - Sanches, Tatiana; Chan, Emily (Ibersid: revista de sistemas de información y documentación, 2023)
Integrating information literacy into learning improves student performance and, for that reason, academic librarians can play a significant role by collaborating in the design and training programs in these areas. In Macao, there is no known study on the information literacy performance of higher education students, so we seek to diagnose this area. For that purpose, a survey was applied to higher education students to assess students' perception of information literacy and their self-characterization regarding the use of resources and the type of skills needed for academic work. A semi-structured interview was also carried out with teachers about the same reality. Students perceive themselves to have a low level of confidence in the performance of their academic tasks, which affects their fulfilment. Faculty are aligned with this diagnosis, revealing the students’ weaknesses in the information search and presentation. Overall, information needs are evident among students as also is the use of preferred information resources in pursuit of their studies. The training aimed at students in search, retrieval, analysis, and use of information seems to be essential, which is why the construction of a tailormade training program in Information Literacy is anticipated.
Number: 2
Keywords: Macao

Beyond Physical Boundaries—Organising a Virtual Exhibiton with NFTs for an International Conference - Estadieu, Gerald; Ng, S.O.K.M.; Martins de Abreu, F.; Farinha, D.F. (11th International Conference on Digital and Interactive Arts (ARTECH 2023), 2023)

Re-experiencing Street Signage with Augmented Reality around the City of Macau - Lio, Si Weng; Martins de Abreu, F. (Proceedings of the 11th International Conference on Digital and Interactive Arts (ARTECH2023), 2023)

Exploring EEG Signal Features for Predicting Post Cardiac Arrest Prognosis - Guilherme Cunha Santos, Antonio; Alexandre Lobo Marques, Joao; Rigo Jr., Luis; Paulo Madeiro, João (2023)

Linguistic and economic capital in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau wisely looks to mainland China, South-East Asia, and Portuguese-speaking countries, as part of its economic diversification. However, to be a player on the international stage and world-wide market, it must look wider, and, hence, the standard of English in Macau must improve dramatically and urgently.
Section: MAG

Neurofinance: Exploratory Analysis Stock Trader's Decision-Making Process by Real-Time Monitoring of Emotional Reactions - Hsu, Hsin-Tzu; Marques, João Alexandre Lobo (European Conference on Management Leadership and Governance, 2023)
Human emotions can be associated with decision-making, and emotions can generate behaviors. Due to the fact that it could be biased and exhaustively complex to examine how human beings make choices, it is necessary to consider relevant groups of study, such as stock traders and non-traders in finance. This work aims to analyze the connection between emotions and the decision-making process of investors and non-investors submitted to the same set of stimuli to understand how emotional arousal might dictate the decision process. Neuroscience monitoring tools such as Real-Time Facial Expression Analysis (AFFDEX), Eye-Tracking, and Galvanic Skin Response (GSR) were adopted to monitor the related experiments of this paper and its accompanying analysis process. Thirty-seven participants attended the study, 24 were classified as stock traders, and 13 were non-traders; the mean age for the groups was 35 and 25, respectively. The designed experiment initially disclosed a thought-provoking result between the two groups under the certainty and risk-seeking prospect theory; there were more risk-takers among non-investors at 75%, while investors were inclined toward certainty at 79.17%. The implication could be that the non-investing individuals were less complex in thought and therefore pursued higher returns besides a high probability of losing the game. In addition, the automatic emotion classification system indicates that when non-investors confronted a stock trending chart beyond their acquaintance or knowledge, they were psychologically exposed to fear, anger, sadness, and surprise. On the contrary, investors were detected with disgust, joy, contempt, engagement, sadness, and surprise, where sadness and surprise overlapped in both parties. Under time pressure conditions, 54.05% of investors or non-investors tend to make decisions after the peak(s) of emotional arousal. Variations were found in the deciding points of the slopes: 2.70% were decided right after the peak(s), 37.84% waited until the emotions turned stable, and 13.51% were determined as the emotional indicators started to slide downwards. Several combinations of emotional responses were associated with decisions. For example, negative emotions could induce passive decision-making, in this case, to sell the stock; nevertheless, it was also examined that as the slope slipped downwards to a particular horizontal point, the individuals became more optimistic and selected the "BUY" option. Future works may consider expanding the study to larger sample size, different demographic groups, and other biometrics for further analysis and conclusions.
Number: 1

Leadership and Neurosciences - The analysis of emotional arousal during decision-making processes with decision-makers exposed to acute stress - Marques, Joao Alexandre Lobo (European Conference on Management Leadership and Governance, 2023)
Corporate leaders are constantly dealing with stress in parallel with continuous decision-making processes. The impact of acute stress on decision-making activities is a relevant area of study to evaluate the impact of the decisions made, and create tools and mechanisms to cope with the inevitable exposure to stress and better manage its impact. The intersection of leadership and neurosciences techniques is called Neuroleadership. In this work, an experiment is proposed to detect and measure the emotional arousal of two groups of business professionals, divided into two groups. The first one is the intervention/stress group, n=30, exposed to stressful conditions, and the control group, n=14, not exposed to stress. The participants are submitted to a sequence of computerized stimuli, such as watching videos, answering survey questions, and making decisions in a realistic office environment. The Galvanic Skin Response (GSR) biosensor monitors emotional arousal in real-time. The experiment design implemented stressors such as visual effects, defacement, unfairness, and time-constraint for the intervention group, followed by decision-making tasks. The results indicate that emotional arousal was statistically significantly higher for the intervention/stress group, considering Shapiro and Mann-Whitney tests. The work indicates that GSR is a reliable stress detector and may be useful to predict negative impacts on executive professionals during decision-making activities.
Number: 1

Neuromarketing: Evaluating Consumer Emotions and Preferences to Improve Business Marketing Management - Zeng, Ian Mei; Marques, João Alexandre Lobo (European Conference on Management Leadership and Governance, 2023)
The invention of neuroscience has benefited medical practitioners and businesses in improving their management and leadership. Neuromarketing, a field that combines neuroscience and marketing, helps businesses understand consumer behaviour and how they respond to advertising stimuli. This study aims to investigate the consumer purchase intention and preferences to improve the marketing management of the brand, based on neuroscientific tools such as emotional arousal using Galvanic Skin Response (GSR) sensors, eye-tracking, and emotion analysis through facial expressions classification. The stimuli for the experiment are two advertisement videos from the Macau tea brand “Guanding Teahouse” followed by a survey. The experiment was conducted on 40 participants. 76.2% of participants that chose the same product in the first survey responded with the same choice of products in the second survey. The GSR peaks in video ad 1 measured a total of 60. On the other hand, video ad 2 counted a total of 55 GSR peaks. The emotions in ad1 and ad2 have similar responses, with an attention percentage of 76%. The results showed that ad1 has a higher engagement time of 11.1% and ad2 has 9.6%, but only 19 of the respondent’s conducted engagement in video ad1, and 31 showed engagement in video ad2. The results demonstrated that although ad 1 has higher engagement rates, the respondents are more attracted to video ad 2. Therefore, ad2 has better marketing power than ad 1. Overall, this study bridges the gap of no previous research on measuring tea brand advertisements with the neuroscientific method. The results provide valuable insights for marketers to develop better advertisements and marketing campaigns and understand consumer preferences by personalising and targeting advertisements based on consumers' emotional responses and behaviour of consumers' purchase intentions. Future research could explore advertisements targeting different demographics.
Number: 1

Challenging arbitral tribunal jurisdiction in Macau [Practice Notes] - Diakite, Ansoumane Douty (LexisNexis, 2023)
This Practice Note considers challenges to the jurisdiction of arbitral tribunals under the Macau Arbitration Law, the scope of challenge before national courts and tribunals.
Publisher: LexisNexis

Interim remedies in Macau arbitration proceedings [Practice Note] - Diakite, Ansoumane Douty (LexisNexis, 2023)
This Practice Note provides an overview of the powers of tribunals and courts to issue interim remedies including an anti-suit injunction pursuant to the Arbitration Law and the Civil Procedure Code of Macau and provisions dealing with emergency arbitrator appointments pursuant to the Macau Arbitration Law.
Publisher: LexisNexis

Radial String Chimes: A Behavioural Driven Tangible Instrument Derived from Networked Music Performance Practices - Barbosa, Alvaro; Olga Ng Ka Man, Sandra; Estadieu, G (Proceedings of UbiMus2023, II- Ubiquitous Music Symposium, 2023)
Research in ubiquitous networked music systems has unveiled the potential of behavioural-driven interaction interfaces as an effective model to cope with network communication delays in remote musical performances. Most of the techniques developed under these premises are based on digital music interfaces implemented on laptop computers or tablet devices, where a certain degree of gestural control comes as an added dimension. The purpose of this paper is to present an implementation of such type of interfaces in the form of a physical tangible musical instrument, contemplating multiple expressive possibilities. This is viable at the current stage of technological development thanks to leveraging 3D printing and laser cutting technologies for effective prototyping and testing of such a device. The paper seeks to demonstrate that this approach opens a wide range of possibilities for creating musical instruments with versatility and expressiveness beyond what is usually accomplished in traditional instruments. This implementation, entitled “Radial String Chimes,” is presented with its advantages, the challenges it faces, and the methods used to create it. Finally, the paper will offer suggestions for further developing such an instrument to unlock its potential.

The Tully-Fisher law and dark matter effects derived via modified symmetries - Arraut, Ivan (Europhysics Letters, 2023)
In any physical system, when we move from short to large scales, new spacetime symmetries emerge which help us to simplify the dynamics of the system. In this letter we demonstrate that certain variations on the symmetries of general relativity at large scales generate the effects equivalent to dark matter ones. In particular, we reproduce the Tully-Fisher law, consistent with the predictions proposed by MOND. Additionally, we demonstrate that the dark matter effects derived in this way are consistent with the predictions suggested by MOND, without modifying gravity.
Publisher: EDP Sciences, IOP Publishing and Società Italiana di Fisica

Reciprocity in a school-university partnership project: Towards a Macau-based Give-Get Model - Chu, K. W.; Mak, M. C. K.; Ng, M. H.; Wong, U. W. K.; Cheng, P. W.; Tse, T. P. M.; Ho, G. W. S (2023)

澳門特殊與融合教育的發展及教師培訓 - Ge, Rochelle Yun (2023)

Dreaming of diversification - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Once upon a time there was a cockerel who succumbed to flattery when a wily fox told him that he had the most magnificent singing voice, especially when he sang with his eyes closed tightly.
Section: MAG

SOUNDSCAPE.AI - A Sonic Perspectives on Macau - Estadieu, G (2023)

Death of a salesman? the new junket regulation and practice in macau - Ho, Hong-Wai; Phillips, Jenny (Gaming Law Review, 2023)
This review article is among the first to examine the new junket regulations in the Macau gaming industry. Particular emphasis is on the legal and regulatory framework governing the junket activity of gaming promoters and their associates. The recent changes to Macau gaming laws have resulted in stronger licensing requirements for local junket participants and precipitated the collapse of the VIP room system in casinos. Furthermore, this article highlights the policy and managerial implications of the current junket environment for the gaming industry in Macau and possibly other regional gaming jurisdictions. The effects of the new legal environment for Macau junkets could also provide insights into the implementation of similar legislation in other jurisdictions.
Publisher: Mary Ann Liebert, Inc., publishers
Keywords: Macao; VIP room; gambling; gaming regulation; international gaming; junket operation

From ‘Mixed Methods’ to ‘Integration’ in Social Science Research - Morrison, Keith (2023)

Java面向对象程序设计 - 梁胜彬 (清华大学出版社, 2023)
结合实用案例讲解Java语法、面向对象程序设计技术和核心API。 全书共10章，内容涵盖Java概述、Java语法基础、面向对象基础、面向对象高级技术、 Java API、异常处理机制、Java I/O流、多线程、Java GUI编程和Java网络编程等知识要点。案例丰富，以JDK 17和IntelliJ IDEA等流行的开发环境为依托，力求让读者通过案例 掌握Java编程技术。另一个特色是在阐释专业内容的同时自然融入思政元素， 具有鲜明的时代性和引领性。 可作为普通高等院校计算机、软件工程、人工智能等专业“面向对象程序设计”“Java程序设计”课程的教材，也适 合编程爱好者自学和培训使用。

Conditional internationalism in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Just when diversification is the name of the game in Macau, and with the manifold benefits of diversity that internationals can bring, how sensible is it to treat its international non-resident workers so poorly, and with lamentable transparency and accountability?
Section: MAG

A medical text classification approach with ZEN and capsule network - Liang, Shengbin; Sun, Fuqi; Sun, Haoran; Chen, Tingting; Du, Wencai (The Journal of Supercomputing, 2023)
Text classification is an important topic in natural language processing, with the development of social network, many question-and-answer pairs regarding health-care and medicine flood social platforms. It is of great social value to mine and classify medical text and provide targeted medical services for patients. The existing algorithms of text classification can deal with simple semantic text, especially in the field of Chinese medical text, the text structure is complex and includes a large number of medical nomenclature and professional terms, which are difficult for patients to understand. We propose a Chinese medical text classification model using a BERT-based Chinese text encoder by N-gram representations (ZEN) and capsule network, which represent feature uses the ZEN model and extract the features by capsule network, we also design a N-gram medical dictionary to enhance medical text representation and feature extraction. The experimental results show that the precision, recall and F1-score of our model are improved by 10.25%, 11.13% and 12.29%, respectively, compared with the baseline models in average, which proves that our model has better performance.
Keywords: Capsule network; Medical text classification; Text mining; ZEN model

Games of chance - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Here we are, back in full-throttle summer tourism in tiny Macau, with visitors galore, lines of tourist coaches everywhere, and the casinos back on course to welcome gamblers. However, gambling reaches much wider than Macau’s casinos.
Section: Macau Business

Acceptance of Insects as Food: An Exploratory Study of Young Consumers in Macau - Lampo, Alessandro; Sun, Hou Tong (Indian Journal of Entomology, 2023)
Substitute foods are increasingly popular to reduce our environmental footprint and promote food security. As the world population is expected to grow and food resources become scarce, insects as food have recently gained attention as a viable alternative. In the present study, a model grounded on the Theory of Planned Behavior (TPB) is proposed and analyzed through structural equation modeling software (SmartPLS) to assess consumers intentions toward insects as food. Except for subjective norm, both attitude and perceived behavioral control were key determinants of intention and, in turn, of actual use behaviour. Despite insects being consumed in nearly 1/4 of the sample (for instance in Chinese medicine), the study found that respondents were on average relatively unwilling to use them as a dietary habit. Also, it appeared that men were more likely to consume insects as food than women. The insights of our study have important implications for practitioners and policymakers seeking to promote sustainable nutritional practices among consumers. This study is particularly relevant for Macau, as the city positions itself as a "UNESCO Creative City of Gastronomy" with the aim to develop internationally a unique and sustainable food image.

Influencing Companies’ Green Governance Through the System of Legal Liability for Environmental Infractions in China and Brazil: Lighting the Way Toward BRICS Cooperation - Wei, D.; Rafael, A. P. (BRICS Law Journal, 2023)
Peer-rewieved journal
Number: 2

Gauge symmetries and the Higgs mechanism in Quantum Finance - Arraut, Ivan (Europhysics Letters, 2023)
By using the Hamiltonian formulation, we demonstrate that the Merton-Garman equation emerges naturally from the Black-Scholes equation after imposing invariance (symmetry) under local (gauge) transformations over changes in the stock price. This is the case because imposing gauge symmetry implies the appearance of an additional field, which corresponds to the stochastic volatility. The gauge symmetry then imposes some constraints over the free parameters of the Merton-Garman Hamiltonian. Finally, we analyze how the stochastic volatility gets massive dynamically via Higgs mechanism.
Publisher: EDP Sciences, IOP Publishing and Società Italiana di Fisica

Do students in different courses of study think the same way in complex problem solving? [Poster presentation] - Wu, H.; Molnár, G. (2023)

LatinX in AI research - Banda, Juan M.; Ruiz-Garcia, Ariel; Montoya, Laura N.; Arraut, Ivan (Neural Computing and Applications, 2023)
We are delighted to present this special issue editorial for Neural Computing and Applications special issue on LatinX in AI research. This special issue brings together a collection of articles that explore machine learning and artificial intelligence research from various perspectives, aiming to provide a comprehensive and in-depth understanding of what LatinX researchers are working on in the field. In this editorial, we will introduce the overarching theme of the special issue, highlight the significance of the selected papers, and offer insights into the contributions made by the authors. The LatinX in AI organization was launched in 2018, with leaders from organizations in Artificial Intelligence, Education, Research, Engineering, and Social Impact with a purpose to together create a group that would be focused on “Creating Opportunity for LatinX in AI.” The main goal is to increase the representation of LatinX professionals in the AI industry. LatinX in AI Org and programs are volunteer-run and fiscally sponsored by the Accel AI Institute, 501(c)3 Non-Profit.

Sunshine and shadows - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | The recent euphoria over Macau’s economic resurrection should not mask the long-standing challenges facing its society and values. Sunshine creates shadows in which can lurk a range of pathologies.
Section: Macau Business

A Multi-Channel Text Sentiment Analysis Model Integrating Pre-training Mechanism - Liang, Shengbin; Jin, Jiangyong; Du, Wencai; Qu, Shenming (Information Technology and Control, 2023)
The number of tourist attractions reviews, travel notes and other texts has grown exponentially in the Internet age. Effectively mining users’ potential opinions and emotions on tourist attractions, and helping to provide users with better recommendation services, which is of great practical significance. This paper proposes a multi-channel neural network model called Pre-BiLSTM combined with a pre-training mechanism. The model uses a combination of coarse and fine- granularity strategies to extract the features of text information such as reviews and travel notes to improve the performance of text sentiment analysis. First, we construct three channels and use the improved BERT and skip-gram methods with negative sampling to vectorize the word-level and vocabulary-level text, respectively, so as to obtain more abundant textual information. Second, we use the pre-training mechanism of BERT to generate deep bidirectional language representation relationships. Third, the vectors of the three channels are input into the BiLSTM network in parallel to extract global and local features. Finally, the model fuses the text features of the three channels and classifies them using SoftMax classifier. Furthermore, numerical experiments are conducted to demonstrate that Pre-BiLSTM outperforms the baselines by 6.27%, 12.83% and 18.12% in average in terms of accuracy, precision and F1-score.
Number: 2
Keywords: Pre-training mechanism

Chatting about chatting - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Many employers in Macau expect their employees to have received higher education (HE). This returns to the endless question of what HE is for; is it for job knowledge and skills acquisition, attitude development, thinking abilities, creativity, problem solving, how to learn, or what? What and whose knowledge?
Section: Macau Business

Machine learning over the free-parameters of the Black-Scholes equation: Stock market and Option market - Arraut, Jorge Mario; Arraut, Ivan; Lei, Ka I. (2023)
The Black-Scholes equation is famous for predicting values for the prices of Options inside the stock market scenario. However, it has the limitation of depending on the estimated value for the volatility. On the other hand, several Machine learning techniques have been employed for predicting the values of the same quantity. In this paper we analyze some fundamental properties of the Black-Scholes equation and we then propose a way to train its free-parameters, the volatility in particular. This with the purpose of using this parameter as the fundamental one to be learned by a Machine Learning system and then improve the predictions in the stock market.

Exploring the Current Landscape and Future Directions of Information Technology in Dance Education - Du, Wencai; Chen, Jiao; Xu, Simon (2023 26th ACIS International Winter Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD-Winter), 2023)
Dance education has undergone significant changes with the integration of information technology. Traditional dance pedagogy is now complemented by innovative digital software tools and applications. This work surveys the diverse applications of information technology in dance education at college or university level and the impact it has on teaching and learning processes. We discuss the integration of technology in various aspects of dance education, including skill development, choreography, performance analysis, VR/AR, online virtual learning, and collaborative learning. Additionally, the benefits and challenges associated with the use of information technology are also examined and the future research directions for research and practice in this field are proposed.
Keywords: College and University Education; Dance Education; Education; Federated learning; Humanities; Information Technology; Interactive; Surveys; Technical requirements; Training; Visualization; applications

課程變革的趨勢和具澳門特色的課程發展 - Ge, Rochelle Yun (2023)

Enhancing Health and Public Health through Machine Learning: Decision Support for Smarter Choices - Rodrigues, Pedro Miguel; Madeiro, João Paulo; Marques, João Alexandre Lobo (Bioengineering, 2023)
In recent years, the integration of Machine Learning (ML) techniques in the field of healthcare and public health has emerged as a powerful tool for improving decision-making processes [...]
Number: 7 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: n/a

China’s Approach to Sustainable Development in Free Trade Agreements - Wei, Dan; Rafael, Ângelo Patrício (Law and Development Review, 2023)
The question of how to adequately integrate environment and labor provisions in free trade agreements is still a difficult one for both States and academicians. This article explores China’s approach to environment and labor issues in free trade agreements. For reference and comparison, it relies on the European Union’s and the United States’ approaches in their respective FTAs. The article identifies China’s preference for a case-by-case approach to the inclusion of environmental chapters in its FTAs. Additionally, in most FTAs it avoids to include provisions on labor standards. These two preferences represent major divergences from the European Union’s and the United States’ approaches, characterized by inclusion of chapters on environment and labor in all their modern FTAs. The article also finds that China’s FTAs rely solely on consultations and cooperation for the implementation of environmental and labor provisions, within the framework of Joint Committees and avoid the inclusion of civil society mechanisms. Moreover, resolution of disputes relies exclusively on consultations, in a diverse procedure than the one applicable to trade disputes. Despite alignment with the European Union model, this is another major point of divergence with the United States’ model, which applies the same enforcement mechanism for both environment and labor issues and trade issues and includes the possibility of applying sanctions. Finally, the article concludes that China’s options with regards to the treatment of environment and labor concerns in its free trade agreements aligns with both its domestic governance approach and its approach to international cooperation.
Publisher: De Gruyter
Keywords: China; environment and trade; free trade agreements; labor and trade; sustainable development

Intelligent Data Fusion System for Assessing and Classifying the Long-Term Effects of Exposure to COVID-19 in Pregnancy (Long Covid): Associated Neurophysiological and Epigenetic Mechanisms and Consequences for Infant Development - Lobo Marques, J. A. (2023)

Arbitration as a dispute resolution method in Macau [Practice Notes] - Diakite, Ansoumane Douty; Cheok, Si Leung (LexisNexis, 2023)
The following Arbitration practice note provides comprehensive and up to date legal information on Arbitration as a dispute resolution method in Macau

Gauge symmetries and the Higgs mechanism in Quantum Finance - Arraut, Ivan (arXiv, 2023)
By using the Hamiltonian formulation, we demonstrate that the Merton-Garman equation emerges naturally from the Black-Scholes equation after imposing invariance (symmetry) under local (gauge) transformations over changes in the stock price. This is the case because imposing gauge symmetry implies the appearance of an additional field, which corresponds to the stochastic volatility. The gauge symmetry then imposes some constraints over the free-parameters of the Merton-Garman Hamiltonian. Finally, we analyze how the stochastic volatility gets massive dynamically via Higgs mechanism.
arXiv:2306.03237 [q-fin]
Keywords: Quantitative Finance - General Finance

The role of environmental concern and technology show-off on electric vehicles adoption: the case of Macau - Lampo, Alessandro; Silva, Susana C.; Duarte, Paulo (International Journal of Emerging Markets, 2023)
Purpose Research on battery electric vehicles (BEVs) has typically considered environmental concern a key determinant of behavioral intention that leads individuals to prefer electric vehicles. This paper challenges this assumption and argues that technology frameworks may require new variables to capture consumers' preferences. A UTAUT2-based study has been developed to assess the role of environmental concern in the BEVs context and put forward the technology show-off (TS) concept to explain the technology's acceptance. Design/methodology/approach A quantitative and cross-sectional look at behavioral intention is adopted. The study uses structural equation modeling to analyze a sample of 236 Macau residents to determine the relevance of the factors behind the choice to adopt BEVs. Findings The findings indicate that environmental concern and price may be relevant to explain behavioral intention to adopt the BEVs technology. Furthermore, the UTAUT2 framework seems to benefit from adding new variables, with TS playing a pertinent role in explaining technology acceptance. Social implications The findings show that environmental concern fails to build an argument for the shift to full electric mobility and promote the desired behavioral change toward adopting BEVs. Herein lies the necessity to consider new variables that can better describe the characteristics of modern society. Originality/value This paper proposes the TS construct, combining visibility and trialability as significant determinants of behavioral intention to use technology. The study also stresses the need to reconsider the role of environmental concerns' impact on consumer decision-making.

Diagnóstico à literacia da informação de estudantes de ensino superior: um estudo de caso em Macau - Chan, Emily; Sanches, Tatiana (Actas do Congresso Nacional de Bibliotecários, Arquivistas e Documentalistas, 2023)
O presente estudo faz parte de uma investigação mais alargada que pretende i) estudar, numa população estudantil de ensino superior, as suas necessidades e comportamento perante a informação e ii) desenvolver um programa de formação em literacia da informação, integrando este conhecimento e os contributos dos diversos intervenientes (estudantes, docentes, bibliotecários). Sabemos hoje que a integração da literacia da informação nas aprendizagens melhora o desempenho dos estudantes e que, por esse motivo, os bibliotecários académicos podem desempenhar um papel importante ao colaborarem no desenho e formação de programas nestas áreas. Esta comunicação apresenta a primeira fase deste estudo. Trata-se da aplicação de um inquérito por questionário a uma população de estudantes de graduação, no ensino superior, em Macau. Os resultados demonstram as perceções dos estudantes relativamente às suas necessidades de informação, bem como o uso dos recursos informativos preferidos na prossecução dos seus estudos. A formação destes estudantes na pesquisa, recuperação, análise e uso da informação parece ser essencial. A construção de programas de formação em literacia da informação deve ser concebida à medida, recorrendo-se a um diagnóstico próximo e efetivo. A par, é importante continuar a desenvolver ambientes físicos e virtuais que disponibilizem informação credível e que deem resposta às necessidades informacionais dos que os utilizam, apoiando a aprendizagem.
Number: 14
Keywords: Estudantes

Perceções das competências requeridas a futuros bibliotecários: um estudo internacional - Sanches, Tatiana; Chan, Emily (14: Comunidades e Profissionais para o Futuro, 2023)
Resumo Os bibliotecários são profissionais que se devem manter constantemente atualizados, procurando ativamente o desenvolvimento das suas competências profissionais, pelas próprias características das funções que desempenham. Porém, é importante perceber o que pensam estes atores acerca da sua atual formação de base, concretamente se esta tem vindo a acompanhar as tendências de atualização. Assim, partindo de uma análise prévia ao conteúdo de diversos documentos orientadores, emanados de associações internacionais, no sentido de encontrar as competências preconizadas para a área de atuação, é realizado um questionário ao nível nacional e internacional a futuros profissionais, estudantes na área das ciências documentais. O principal objetivo é o de procurar entender, comparativamente, que habilidades e competências são valorizadas para o futuro desempenho profissional. O questionário foi aplicado a grupos de estudantes de ciências da documentação e informação em Portugal, Macau e República Checa, evidenciando-se as perspetivas comuns entre os inquiridos sobre as competências necessárias e aquelas que são recebidas na formação inicial, concluindo-se que existem ainda algumas assimetrias entre as necessidades da profissão e a formação recebida, na perspetiva dos futuros profissionais, independentemente do território a que pertencem.

The Hawking Radiation in Massive Gravity: Path Integral and the Bogoliubov Method - Arraut, Ivan; Segovia, Carlos; Rosado, Wilson (Universe, 2023)
We prove the consistency of the different approaches for deriving the black hole radiation for the spherically symmetric case inside the theory of Massive Gravity. By comparing the results obtained by using the Bogoliubov transformations with those obtained by using the Path Integral formulation, we find that in both cases, the presence of the extra-degrees of freedom creates the effect of extra-particles creation due to the distortions on the definitions of time defined by the different observers at large scales. This, however, does not mean extra-particle creation at the horizon level. Instead, the apparent additional particles perceived at large scales emerge from how distant observers define their time coordinate, which is distorted due to the existence of extra-degrees of freedom.
Number: 5 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Bogoliubov transformation method; Hawking radiation; Massive Gravity; Path Integral method; extra-degrees of freedom

在教育中促進無偏見和可靠的人工智能:賦能學生認知能力 [Presentation] - Wu, H. (2023)

Neuromarketing and Global Branding Reaction Analysis Based on Real-Time Monitoring of Multiple Consumer's Biosignals and Emotions - Goncalves, Marcus; Lobo Marques, Joao Alexandre; Silva, Bruno Riccelli Santos; Luther, Valorie; Hayes, Sydney (Journal of International Business and Management, 2023)
Consumers' selections and decision-making processes are some of the most exciting and challenging topics in neuromarketing, sales, and branding. From a global perspective, multicultural influences and societal conditions are crucial to consider. Neuroscience applications in international marketing and consumer behavior is an emergent and multidisciplinary field aiming to understand consumers' thoughts, reactions, and selection processes in branding and sales. This study focuses on real-time monitoring of different physiological signals using eye-tracking, facial expressions recognition, and Galvanic Skin Response (GSR) acquisition methods to analyze consumers' responses, detect emotional arousal, measure attention or relaxation levels, analyze perception, consciousness, memory, learning, motivation, preference, and decision-making. This research aimed to monitor human subjects' reactions to these signals during an experiment designed in three phases consisting of different branding advertisements. The nonadvertisement exposition was also monitored while gathering survey responses at the end of each phase. A feature extraction module with a data analytics module was implemented to calculate statistical metrics and decision-making supporting tools based on Principal Component Analysis (PCA) and Feature Importance (FI) determination based on the Random Forest technique. The results indicate that when compared to image ads, video ads are more effective in attracting consumers' attention and creating more emotional arousal.

AI-based Multimodal Qualitative Mapping of Macao Soundscape - Estadieu, G; Cheung, Y.Y. (2023)

The business of social justice in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | As Macau rebuilds its post-pandemic economy, one could be forgiven for believing that the good life for all has arrived, as evidenced in the manifest opulence on display in its up-market shopping malls. However, this is not the case; social justice needs attention in Macau.
Section: Macau Business

China’s Aid policy approach to Poverty Alleviation in the recipient country: A Case study of the Republic of Guinea - Diakite, Ansoumane Douty (Journal of Social Studies (JSS), 2023)
This paper examines the extent to which China’s aid policies integrate poverty alleviation as a goal of their aid in general, particularly in Guinea. More specifically, the paper analyzed how aid donors focus on poverty alleviation and which policies and mechanisms are in place to address poverty in the countries receiving aid. Regarding the methodology, the author collected data from secondary sources, including government declarations of donors, policy documents at both the donor and recipient levels, as well as from scholarly publications. The following findings resulted from study: China’s aid policies have progressively incorporated poverty alleviationobjectives and identified sectors for intervention against poverty. However, the limitations of China approach to poverty is that China adopts a top-down approach to poverty reduction and lacks of an impact evaluation mechanism based on poverty alleviation.
Number: 1
Keywords: Aid policy; China; Guinea; Poverty alleviation; Strategy

Relationship between Student Teachers' Beliefs and Practices on Early Chinese Literacy Instruction - Sun, Chunrong; Ho, Ka Lee Carrie (Universal Journal of Educational Research, 2023)
This study explores the relationship between student teachers' beliefs and practices in early Chinese literacy instruction. Semi-structured interviews, classroom observation, and document analysis were conducted with six student teachers during their teaching practices. Findings indicated that the student teachers believed explicitly teaching literacy skills and imperceptible acquisition of literacy abilities through communication and meaning-making processes are essential in Chinese early literacy learning. However, they mainly taught Chinese literacy skills in their practices, which means the student teachers still needed to practice what they preached fully. The study suggests that possible reasons for the discrepancies include 'direct teaching' and 'rote learning' might be much easier for student teachers to design and conduct a lesson. Student teachers have limited abilities and experiences in conducting an ideal lesson, and the kindergarten curriculum and onsite supervisors highly influenced their teaching practices. The findings from this study suggested that more operational activities (such as designing lesson plans and conducting micro-teaching) should be used during pre-service training. Furthermore, the communication of educational beliefs between the university supervisor and the onsite supervisor should be strengthened.
Publisher: Horizon Research Publishing

A reserva territorial dos aborígenes potiguaras do Brasil: um locus simbólico - Simões, José Manuel (Revista Internacional em Língua Portuguesa, 2023)
The various volumes coordinated by Pierre Nora to pursue a history of the places of memory in France have become a multidisciplinary theoretical reference for those who, like us, seek to reconstruct the memories with which the land of the Potiguara aborigines of Brazil is organized today. In the introduction to the voluminous work that he directed for eight years, Nora explained his epistemic understanding of the notion of “places of memory”, stressing that a “lieu de mémoire” is any significant entity that, material or immaterial in nature, through a human will or the wear and tear of time, has become a symbolic element of a community's memorial heritage. The French historian also added that, since memory is the fundamental structure of this generally lengthy process, it was convenient to understand it as a phenomenon of emotions and magic that only accommodates the facts that feed it. Strictly speaking, memory is always vague, and reminiscent, stirring both general impressions and fine symbolic details. Furthermore, memory is always vulnerable to transference, repressed and imagined memories, censorship, and all kinds of projections. (Nora, 1984). In this article, we try to understand that the places of memory are also almost always what comes to us, stays, and selects the past. The reserve where they live appears as a symbolic locus to which the Potiguara aborigines cling with all their strength to preserve what remains of their past.
Keywords: aborígenes Potiguara; censuras; locus simbólico; lugares de memória; preservar o passado; reconstrução das memórias

An Improved Dual-Channel Deep Q-Network Model for Tourism Recommendation - Liang, Shengbin; Jin, Jiangyong; Ren, Jia; Du, Wencai; Qu, Shenming (Big Data, 2023)
Keywords: context-aware; deep reinforcement learning; dual-channel; tourism recommendation

A model of integrating convolution and BiGRU dual-channel mechanism for Chinese medical text classifications - Li, Xiaoli; Zhang, Yuying; Jin, Jiangyong; Sun, Fuqi; Li, Na; Liang, Shengbin (PLOS ONE, 2023)
Recently, a lot of Chinese patients consult treatment plans through social networking platforms, but the Chinese medical text contains rich information, including a large number of medical nomenclatures and symptom descriptions. How to build an intelligence model to automatically classify the text information consulted by patients and recommend the correct department for patients is very important. In order to address the problem of insufficient feature extraction from Chinese medical text and low accuracy, this paper proposes a dual channel Chinese medical text classification model. The model extracts feature of Chinese medical text at different granularity, comprehensively and accurately obtains effective feature information, and finally recommends departments for patients according to text classification. One channel of the model focuses on medical nomenclatures, symptoms and other words related to hospital departments, gives different weights, calculates corresponding feature vectors with convolution kernels of different sizes, and then obtains local text representation. The other channel uses the BiGRU network and attention mechanism to obtain text representation, highlighting the important information of the whole sentence, that is, global text representation. Finally, the model uses full connection layer to combine the representation vectors of the two channels, and uses Softmax classifier for classification. The experimental results show that the accuracy, recall and F1-score of the model are improved by 10.65%, 8.94% and 11.62% respectively compared with the baseline models in average, which proves that our model has better performance and robustness.
Publisher: Public Library of Science
Keywords: Convolution; Deep learning; Machine learning; Memory recall; Neural networks; Recurrent neural networks; Semantics; Syntax

Macau 2.0: New Gaming Law and its Implications for Casino Market - Ho, Hong-Wai; Phillips, Jenny (Gaming Law Review, 2023)
This article discusses the new gaming law in Macau with emphasis on the critical aspects concerning the gaming operators, concession regime, and other regulatory obligations.1 Thanks to the gaming liberalization commenced in 2001,2 Macau has experienced tremendous economic growth. The past two decades have seen the rapid development of large-scale integrated resorts, and Macau now ranks among the world's major gaming jurisdictions.3 Policy and regulatory challenges have also emerged along with the growth of the junket-driven VIP business in casinos.4 With the recent amendment of Law No. 16/2001 and the subsequent enactment of Law No. 16/2022, Macau has strengthened the legal underpinnings of its system of gaming regulation to oversee various groups involved in casinos and their industry practices. The present study is among the first to review the scope and impact of the revised gaming law, and associated managerial and operational implications for Macau casinos. Topics covered include policy directions, concession requirements, industry participants, gaming taxes, and fair business practices. This study could provide insights into the “Macau 2.0” project and how casinos are to be operated and managed over the next decade. This article could also provide practical guidance for policy makers charged with formulating gaming policy and regulation in other jurisdictions.
Publisher: Mary Ann Liebert, Inc., publishers
Keywords: Macao; concession; economic diversification; gaming regulation; junket; operation

Quantification of insecticides in commercial seafood sold in East Asian markets: risk assessment for consumers - Ivorra, Lucia; Cardoso, Patricia G.; Chan, Shek Kiu; Cruzeiro, Catarina; Tagulao, Karen (Environmental Science and Pollution Research, 2023)
The extraction of 21 insecticides and 5 metabolites was performed using an optimized and validated QuEChERS protocol that was further used for the quantification (GC–MS/MS) in several seafood matrices (crustaceans, bivalves, and fish-mudskippers). Seven species, acquired from Hong Kong and Macao wet markets (a region so far poorly monitored), were selected based on their commercial importance in the Indo-Pacific region, market abundance, and affordable price. Among them, mussels from Hong Kong, together with mudskippers from Macao, presented the highest insecticide concentrations (median values of 30.33 and 23.90 ng/g WW, respectively). Residual levels of fenobucarb, DDTs, HCHs, and heptachlors were above the established threshold (10 ng/g WW) for human consumption according to the European and Chinese legislations: for example, in fish-mudskippers, DDTs, fenobucarb, and heptachlors (5-, 20- and tenfold, respectively), and in bivalves, HCHs (fourfold) had higher levels than the threshold. Risk assessment revealed potential human health effects (e.g., neurotoxicity), especially through fish and bivalve consumption (non-carcinogenic risk; ΣHQLT > 1), and a potential concern of lifetime cancer risk development through the consumption of fish, bivalves, and crustaceans collected from these markets (carcinogenic risk; ΣTCR > 10–4). Since these results indicate polluted regions, where the seafood is collected/produced, a strict monitoring framework should be implemented in those areas to improve food quality and safety of seafood products.
Keywords: Bivalves; Crustaceans; Health risk assessment; Mudskippers; Organochlorine pesticides

Understanding Chinese Model of Government-University-Industry Collaborations in Research and Education: The Case of Macau SAR. - Ge, Yun (2023)
Higher Education in Macau has been benefiting from a multi-layered institutional environment under China’s One-Country-Two-Systems. This presentation introduces research and education policies and practices of Macau universities under China’s national plan of the Greater Bay Area development. It aims to demonstrate and analyze how higher education actors collaborate with local and regional governments and industrial sectors in human capital formation and research innovations.

Monitoring PM2.5 at a Large Shopping Mall: A Case Study in Macao - Lei, Thomas M. T.; Chan, Yan W. I.; Mohd Nadzir, Mohd Shahrul (Processes, 2023)
Employees work long hours in an environment where the ambient air quality is poor, directly affecting their work efficiency. The concentration of particulate matters (PM) produced by the interior renovation of shopping malls has not received particular attention in Macao. Therefore, this study will investigate the indoor air quality (IAQ), in particular of PM2.5, in large-scale shopping mall renovation projects. This study collected on-site PM data with low-cost portable monitoring equipment placed temporarily at specific locations to examine whether the current control measures are appropriate and propose some improvements. Prior to this study, there were no measures being implemented, and on-site monitoring to assess the levels of PM2.5 concentrations was non-existent. The results show the highest level of PM2.5 recorded in this study was 559.00 μg/m3. Moreover, this study may provide a reference for decision-makers, management, construction teams, design consultant teams, and renovation teams of large-scale projects. In addition, the monitoring of IAQ can ensure a comfortable environment for employees and customers. This study concluded that the levels of PM2.5 concentration have no correlation with the number of on-site workers, but rather were largely influenced by the processes being performed on-site.
Number: 3 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: air pollution; construction dust; health exposure; indoor air quality; particulate matter

AN ANALYSIS OF CRITICAL MANAGERIAL CHALLENGES IN MACAU - Lampo, Alessandro (Revista Gestão em Análise, 2023)
Macau has long been considered to be an example of remarkable economic growth. With the opening of the gaming sector in 2002, the casino and hospitality sector flourished, creating employment opportunities but also imposing several challenges on managers. Since Macau endeavors to be positioned as the center for international business with Portuguese-speaking countries and a platform for trading with China’s Greater Bay Area (GBA), it becomes essential for international enterprises to understand the local dynamics. In light of the limited research available, this study aims to identify management challenges from the perspectives of senior executives in different industries based in Macau. Our findings point out that managers must contend with several issues, such as the lack of a skilled local talent pool, high turnover rates, employees' work attitudes, and a tightly controlled immigration policy. It is also imperative for international managers to nurture relationships and pay attention to the local culture. Our results suggest that Macau has to develop a highly skilled local workforce to attract international companies, while local organizations also have to create an attractive working environment to compete in the marketplace.
Number: 1
Keywords: Macau; casinos; greater bay area; management; managerial challenges

EFFECTIVENESS ANALYSIS OF WATERFALL AND AGILE PROJECT MANAGEMENT METHODOLOGIES – A CASE STUDY FROM MACAU'S CONSTRUCTION INDUSTRY - Marques, Joao Alexandre Lobo; Morais, João José Bragança dos Reis; Alves, José; Gonçalves, Marcus (Revista Gestão em Análise, 2023)
The adoption of project management techniques is a crucial decision for corporate governance in construction companies since the management of areas such as risk, cost, and communications is essential for the success or failure of an endeavor. Nevertheless, different frameworks based on traditional or agile methodologies are available with several approaches, which may create several ways to manage projects. The primary purpose of this work is to investigate the adequate project management methodology for the construction industry from a general perspective and consider a case study from Macau. The methodology considered semi-structured interviews and a survey comparing international and local project managers from the construction industry. The interviews indicate that most construction project managers still follow empirical methods with no specific methodology but consider the adoption of traditional waterfall approaches. In contrast, according to the survey, most project managers and construction managers agree that the project's efficacy needs to increase, namely in planning, waste minimization, communication increase, and focus on the Client's feedback. In addition, there seems to be a clear indication that agile methodology could be implemented in several types of projects, including hospitality development projects. A hybrid development approach based on the Waterfall and Agile methodologies as a tool for the project management area may provide a more suitable methodology for project managers to follow.
Number: 1
Keywords: PMBOK; agile; construction industry; project management methodologies

An Exploratory Study of Macao's Role as an Arbitration Seat and Venue for Sino-Luso Commercial Disputes - Si, Leung Cheok; Diakite, Ansoumane Douty (Revista Opinião Jurídica (Fortaleza), 2023)
Objective: Over the past decade, arbitration has grown in popularity as a method of resolving commercial disputes worldwide. However, this practice is relatively new in Macao SAR. Recently, official plans were announced to make Macao as a seat of arbitration for commercial disputes between China and Portuguese-speaking countries (Hereinafter PSCs). This article is dedicated to explores the possibility of Macao undertaking and implementing such a role. Accordingly, this article addresses the following issues: What are the strengths and weaknesses of Macao as a seat and eventually as venue for hosting international commercial arbitration between Chinese and PSCs entrepreneurs?Methodology: A mixed-method approach of legal doctrinal and empirical research was used in this article. We first included a thorough study of the concept of arbitration followed by analysis of various legal journals and legislations, including Macao, China, and PSCs’ arbitration laws. An empirical research was then used to collect data by surveying and interviewing with both lawyers and arbitration practitioners from Macao, China and PSCs.Results: This article argues that the strength of Macao resides in the similarities between its legal system and that of the China and PSCs and the languages advantage (Chinese and Portuguese both official languages). In spite of this, arbitration is still relatively underutilized in the region, and there is a limited number of arbitrators and legal professionals with bilingual proficiency.Contributions: This article contributes to the identification of the opportunities and challenges that Macao faces in its potential future development as a seat/venue of arbitration between China and the PSCs.
0 citations (Crossref) [2023-02-08] Number: 36
Keywords: China; Macao; arbitraje internacional comercial; international commercial arbitration; participante y anfitrión de arbitraje; países de habla portuguesa; portuguese-speaking countries; seat and venue of arbitration

Developing programs for preschool children to enhance Chinese literacy: A Macau-based example. - Chu, K. W.; Mak, M. C. K.; Tse, T. P. M.; Cheng, P. W.; Ho, G. W. S; Ng, M. H. (2023)

Developing programs for preschool children to enhance Chinese literacy: A Macau-based example - Chu, K. W.; Mak, M. C. K; Tse, T. P. M.; Cheng, P. W.; Ho, G. W. S.; Ng, M. H.; Ng, S. K. (2023)

COVID-19 Detection by Means of ECG, Voice, and X-ray Computerized Systems: A Review - Ribeiro, Pedro; Marques, João Alexandre Lobo; Rodrigues, Pedro Miguel (Bioengineering, 2023)
Since the beginning of 2020, Coronavirus Disease 19 (COVID-19) has attracted the attention of the World Health Organization (WHO). This paper looks into the infection mechanism, patient symptoms, and laboratory diagnosis, followed by an extensive assessment of different technologies and computerized models (based on Electrocardiographic signals (ECG), Voice, and X-ray techniques) proposed as a diagnostic tool for the accurate detection of COVID-19. The found papers showed high accuracy rate results, ranging between 85.70% and 100%, and F1-Scores from 89.52% to 100%. With this state-of-the-art, we concluded that the models proposed for the detection of COVID-19 already have significant results, but the area still has room for improvement, given the vast symptomatology and the better comprehension of individuals’ evolution of the disease.
Number: 2 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: COVID-19; artificial intelligence; computerized diagnostic systems; image processing; signal processing

Effects of a High-Fat Diet on Intestinal and Gonadal Metabolism in Female and Male Sea Cucumber Apostichopus japonicus - Zhang, Shuangyan; Ru, Xiaoshang; Zhang, Libin; Gonçalves, David; Yang, Hongsheng; Xu, Jialei (Biology, 2023)
Parental nutrient reserves are directly related to reproductive performance in sea cucumbers. This study focused on the lipid requirements of male and female sea cucumbers Apostichopus japonicus during the reproductive stage and analyzed their physiological responses to a high-fat diet (HFD). The intestinal lipid metabolites and microbiome profile changed significantly in animals fed with the HFD, as given by an upregulation of metabolites related to lipid metabolism and an increase in the predominance of Proteobacteria in the microbiome, respectively. The metabolic responses of male and female sea cucumbers to the HFD differed, which in turn could have triggered sex-related differences in the intestinal microbiome. These results suggest that the lipid content in diets can be differentially adjusted for male and female sea cucumbers to improve nutrition and promote reproduction. This data contributes to a better understanding of the reproductive biology and sex differences of sea cucumbers.
Number: 2 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: high-fat diet; intestinal microbes; physiological metabolic responses; sea cucumber; sex differences

Stock Market Prediction Using Artificial Intelligence: A Systematic Review of Systematic Reviews - Lin, Coka Chinyang; Marques, Joao Alexandre Lobo (2023)
There are many systematic reviews on predicting stock. However, each of them reveals a different portion of the hybrid AI analysis and stock prediction puzzle. The principal objective of this research was to systematically review and conclude the systematic reviews on AI and stock to provide particularly useful predictions for making future strategies for stock markets. Keywords that would fall under the broad headings of AI and stock prediction were looked up in two databases, Scopus and Web of Science. We screened 69 titles and read 43 systematic reviews which include more than 379 studies before retaining 10 of them.
Keywords: Deep Learning; Long Short-Term Memory (LSTM); Machine Learning; Neural Networks (NN); Support Vector Machines (SVM)

How is Technology Accepted? Fundamental Works in User Technology Acceptance from Diffusion of Innovations to UTAUT-2 - Lampo, Alessandro (Proceedings of the 8th International Conference on Industrial and Business Engineering, 2023)
The decision to accept and use technology innovations has long been a source of debate across disciplines due to the complexity involved in predicting behavior. Recognizing that the subject is vast and fragmented, this paper examines the mainstream technology works to assist researchers to understand, conceptualize and select the most appropriate theoretical framework for their study. Starting with the pioneering effort on Diffusion of Innovations (DOI/IDT), the analysis considers the Theory of Reasoned Action (TRA), the Theory of Planned Behavior (TPB), the Technology Acceptance Model (TAM/TAM-2/TAM-3), the Value-based Acceptance Model (VAM), and the Unified Theory of Acceptance and Use of Technology (UTAUT/UTAUT-2) among the most important. A review of the key literature is vital to assessing and identifying research trends, as well as contributing to the discussion of emerging technologies such as Artificial Intelligence (AI), Augmented Reality (AR), Blockchain, Cloud Computing, Internet of Things (IoT), Mobile Apps, etc. Suggestions for future research paths are also provided.
Keywords: Acceptance and Use of Technology; Product Innovation; Technology Acceptance; Technology Adoption; Technology Innovation

The solution to the Hardy's paradox - Arraut, Ivan (arXiv, 2023)
By using both, the weak-value formulation as well as the standard probabilistic approach, we analyze the Hardy's experiment introducing a complex and dimensionless parameter ($\epsilon$) which eliminates the assumption of complete annihilation when both, the electron and the positron departing from a common origin, cross the intersection point $P$. We then find that the paradox does not exist for all the possible values taken by the parameter. The apparent paradox only appears when $\epsilon=1$; however, even in this case we can interpret this result as a natural consequence of the fact that the particles can cross the point $P$, but at different times due to a natural consequence of the energy-time uncertainty principle.
arXiv:2106.06397 [physics]
Keywords: Physics - General Physics

A risky new year - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Despite the welcome optimism expressed at the government’s plans to resurrect Macau’s economy, its economic recovery will continue to suffer from having had the rug pulled from under its feet by the zero-Covid policy, however well intentioned.
Section: Macau Business

Examination of sex-related differences in intestinal and gonadal lipid metabolism in the sea cucumber Apostichopus japonicus - Zhang, Shuangyan; Ru, Xiaoshang; Zhang, Libin; Gonçalves, David; Yang, Hongsheng (Aquaculture, 2023)
Reproduction of the sea cucumber Apostichopus japonicus is critical for aquaculture production. Gonadal development is the basis of reproduction, and lipids, which are among the main nutrients required for gonadal development, directly affect reproduction. We investigated whether gonadal and intestinal lipid metabolism differed between male and female A. japonicus. Transcriptome analysis of the intestines of sexually mature male and female wild-caught individuals revealed differences in gene expression, with 27 and 39 genes being up-regulated in females and males, respectively. In particular, the expression of the fatty acid synthase gene was higher in males than in females. Metabolome analysis of the gonads identified 141 metabolites that were up-regulated and 175 metabolites that were down-regulated in the testes compared with the ovaries in the positive/negative mode of an LC-MS/MS analysis. A variety of polyunsaturated fatty acids were found at higher concentrations in the testes than in the ovaries. 16 s rDNA sequencing analysis showed that the composition and structure of the intestinal microbiota were similar between males and females. These results suggest that sex differences in intestinal metabolism of A. japonicus are not due to differences in the microbiota, and we speculate that gonadal metabolism may be related to intestinal morphology. This information might be useful in improving the reproductive efficiency of sea cucumbers in captivity.
Keywords: Gonads; Intestines; Lipid metabolism; Sea cucumber; Sex differences

Serpentinization and its implications for ultramafic-hosted sulfide mineralization: A case study at the Tianzuo hydrothermal field, 63.5°E, Southwest Indian Ridge - Ding, Teng; Dias, Ágata Alveirinho; Wang, Jia; Tan, Tingting; Liang, Jin; Wu, Bin; Tao, Chunhui (Marine Geology, 2023)
Reaction of ultramafic rocks with seawater and subsequent serpentinization has been considered one of the most important factors controlling the formation of ultramafic-hosted seafloor massive sulfide (UM-SMS) deposits. However, the mineralization processes responsible for these deposits remain poorly understood, in particular because they are less abundant as compared with their basaltic counterparts. In this work, serpentinites with different alteration grades collected at the Tianzuo hydrothermal field (THF), Southwest Indian Ridge, were studied. Mineralogical and chemical analyses were performed in the secondary opaque minerals resulting from serpentinization to understand the role of this process during the formation of UM-SMS deposits. Our results show that these opaque minerals mainly consist of magnetite, hematite, pentlandite, and minor pyrite, suggestive of high but varying oxygen and sulfur fugacities. The hematite is characterized by an enrichment in Mg, Si, Ni, and Co as compared with magnetite. Pentlandite associated with hematite has elevated and consistent Ni contents as compared with that associated with magnetite. These results indicate that breakdown and decomposition of primary silicate and sulfide minerals during serpentinization has controlled the sources of ore-forming materials. Concentrations of Te are variable and show a positive correlation with Ni in pentlandite associated with magnetite or hematite, suggesting that gabbroic intrusions provided additional material to the hydrothermal system. Oxidation and sulfidation conditions are ideal for the formation of trisulfur ion S3− in THF, which can significantly improve the capability of hydrothermal fluids for leaching ore-forming metals from the wall rocks, promoting the formation of THF. In addition of reduced systems, hydrothermal fluids with high oxygen and sulfur fugacities triggered by extensive seawater infiltration can most likely also develop in ultramafic-hosted systems. These results suggest that the areas with well-developed fractures are promising candidates for further exploration of UM-SMS deposits along mid-oceanic ridges.
0 citations (Crossref) [2022-12-25]
Keywords: Opaque minerals; Oxidation and sulfidation; Sulfide mineralization; Tianzuo hydrothermal field; Ultramafic rocks

The transformation of government employees’ behavioural intention towards the adoption of E-government services: An empirical study - Iong, Kit Yeng; Phillips, Jenny O. L. (Social Sciences & Humanities Open, 2023)
Electronic government is increasingly dominant in the study of public administration. In analysing people's behavioural factors towards the adoption of e-services, most previous studies targeted the adult population, while those on government employees are minimal. Government employees have an essential function in the process of government operation; they can be regarded as the principal medium of communication between the service provider (government) and the end-users (citizens). This study was designed to understand the government employees' behavioural factors on their intentions towards adopting e-government services. A set of semi-structured interview questions was developed based on the prior literature on the Theory of Planned Behaviour (TPB) and e-government studies. Ten in-depth interviews were conducted in Macao SAR (Special Administrative Region). In addition to analysing the three primary constructs of TPB, the factor of Trust and some enablers and hindrances were identified. Significant findings were yielded while investigating how the government employees perceived the e-services and how they regarded the general public's perception of this issue. This contextualisation would help policymakers look at this issue from different perspectives and design feasible interventions according to group alignment strategies.
Keywords: Electronic government; Government employees; In-depth interviews; The Theory of Planned Behaviour

How Immigrant Parents and Local Parents Were Involved in Children's Education in Macau - Ng, Shun W.; Cheong, Ka W. (International Journal of Educational Reform, 2023)
The objective of this case study is to analyze how two groups of parents, a group who have newly arrived in Macau from Mainland China and the other who have resided in Macau for more than three decades, interact with the class teachers at the levels of ?two-way communication,? ?supervision of children at home,? and ?participating in decision making? in a secondary school. The findings will redound to the benefits of school leaders, teachers, and indirectly the parents in a sense that looking closely at the ethnic and cultural differences between parents can promote effective cooperation between parents and teachers.
Publisher: SAGE Publications Inc

Histórias do Brasil de 1550: na oca do cacique “Luz Lilás” | José Manuel Simões - Simões, José Manuel (InComunidade, 2023)
Sinã, conhecido entre os seus parentes pelo nome de “Luz Lilás”, homem de um imenso metro e noventa, cacique, mandou reunir a sua comunidade na oca central, a maior, situada no ponto mais alto do cimo da falésia, feita de massaranduba e sucupira – as madeiras mais resistentes – entrelaçadas com cipós de fogo. Pintaram-lhe o longo rosto com traços firmes, a geometria dos signos direcionada ao céu e à terra, protetores das suas gentes. Dessa vez as linhas marcadas na face de “Luz Lilás” eram mais simétricas do que o habitual, as tintas extraídas das sementes de urucu […]

Coral empire: underwater oceans, colonial tropics, visual modernity: by Ann Elias Durham: Duke University Press, 2019, 296 pages ISBN: 9781478003182 (hbk) 99.95 USD, 9781478003823 (pbk) 26.95 USD, 9781478004462 (ebook) 26.95 USD - Zuev, Dennis (Visual Studies, 2023)

Application of ANN, XGBoost, and Other ML Methods to Forecast Air Quality in Macau - Lei, Thomas M. T.; Ng, Stanley C. W.; Siu, Shirley W. I. (Sustainability, 2023)
Air pollution in Macau has become a serious problem following the Pearl River Delta’s (PRD) rapid industrialization that began in the 1990s. With this in mind, Macau needs an air quality forecast system that accurately predicts pollutant concentration during the occurrence of pollution episodes to warn the public ahead of time. Five different state-of-the-art machine learning (ML) algorithms were applied to create predictive models to forecast PM2.5, PM10, and CO concentrations for the next 24 and 48 h, which included artificial neural networks (ANN), random forest (RF), extreme gradient boosting (XGBoost), support vector machine (SVM), and multiple linear regression (MLR), to determine the best ML algorithms for the respective pollutants and time scale. The diurnal measurements of air quality data in Macau from 2016 to 2021 were obtained for this work. The 2020 and 2021 datasets were used for model testing, while the four-year data before 2020 and 2021 were used to build and train the ML models. Results show that the ANN, RF, XGBoost, SVM, and MLR models were able to provide good performance in building up a 24-h forecast with a higher coefficient of determination (R2) and lower root mean square error (RMSE), mean absolute error (MAE), and biases (BIAS). Meanwhile, all the ML models in the 48-h forecasting performance were satisfactory enough to be accepted as a two-day continuous forecast even if the R2 value was lower than the 24-h forecast. The 48-h forecasting model could be further improved by proper feature selection based on the 24-h dataset, using the Shapley Additive Explanations (SHAP) value test and the adjusted R2 value of the 48-h forecasting model. In conclusion, the above five ML algorithms were able to successfully forecast the 24 and 48 h of pollutant concentration in Macau, with the RF and SVM models performing the best in the prediction of PM2.5 and PM10, and CO in both 24 and 48-h forecasts.
Number: 6 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Macau; air pollution; air quality; air quality forecast; machine learning

A STUDY OF GREEN FINANCIAL TECHNOLOGY ACCEPTANCE IN TONGZHOU DISTRICT OF BEIJING - An, Bo Yang (University of Saint Joseph, 2023)
China’s economy has entered a critical period of structural adjustment. The developing green industries and the transforming traditional industries have increasing demand for finance, making ""green finance"" increasingly essential. While China's green finance is in the development stage, some newly developed zones serve as pilots for the launch of green financial products. An example is Tongzhou District of Beijing, which aims to expand Beijing’s space, promote the coordinated development of Beijing-Tianjin-Hebei, and explore the optimal development mode of the densely populated economic areas. This thesis aims to study consumer acceptance of green financial technology (fintech) in the case of Tongzhou District. This thesis extended the commonly applied theoretical model for the problem of study, the Energy Augmented Technology Acceptance Model (EA-TAM), to analyze the impacts of perceived usefulness, perceived ease of use, attitude toward use, intention, usage intention, environmental awareness, and green knowledge on the acceptance of green fintech in Tongzhou District. The survey collected 403 valid responses from people that had been active in Tongzhou District. The quantitative analysis is based on structural equation modeling techniques, including reliability analysis, validity analysis, standard method deviation test, and hypothesis testing. The analytical results show that all the hypothesized factors are significant. In addition, the sample is divided into different gender groups and education groups, so that the impacts of the socio-demographic characteristics can be explored. Males’ environmental awareness and green knowledge are insignificant in determining their acceptance of green fintech. The low-educated group’s acceptance of green fintech does not significantly depend on environmental awareness and perceived usefulness
Keywords: Fintech; Green Gintech; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Message Hidden Behind in "SQUID GAME" research on the Level of Reception between the Message conveyed by the Drama and the Audience in Southeast Asia - Angela, Choi Nga Ieng (University of Saint Joseph, 2023)

THE RELATIONSHIP BETWEEN INTERNALISING PROBLEMS, ACADEMIC ACHIEVEMENT, SCHOOL ADAPTATION, AND GENDER, AS VIEWED FROM THE PERSPECTIVES OF BOTH TEACHERS AND STUDENTS - Ao, Hoi Ian (University of Saint Joseph, 2023)
The present study aimed to analyse the differences in the internalising problems (anxiety, depression, somatic complaints), assessed by different informants (teachers and students), according to the level of academic achievement and school adaptation level in secondary students. Furthermore, we examine the gender difference in the level of internalising symptoms. Finally, we analyzed the differences between teacher-rated and adolescents' self-reported internalising symptoms. The Achenbach System of Empirically Based Assessment (ASEBA) was used for collecting informants’ data. The sample consisted of 882 secondary students (349 males and 473 females), while 50 came from public schools and 772 from private schools. No significant differences are found in internalising problems according to the level of academic achievement from both teachers’ and students’ perspectives. Generally, students who are well-adapted to the school context have the least symptoms of internalising problems compared to average and less-adapted groups from the teachers' perspective. In addition, from students’ perspectives, adolescent females present more internalising problems than males. Finally, teachers rated fewer internalising problems when compared to the students. In conclusion, the low level of awareness of teachers towards the internalising problems of students arouse attention. It is suggested that teachers should attend professional development programs in order to address to students’ internalising problems
Keywords: Internalising problems; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; academic achievement; gender differences; school adaptation

The 50 Reasons for Voluntary Turnover: A Qualitative Exploration of Factors Contributing to Former Teacher Attrition in Macau - Ao, I. Leng (University of Saint Joseph, 2023)
Teacher turnover is a global issue that has not received much research attention in Macau despite studies indicating that teachers in the region experience high levels of stress and burnout. Given that private school teachers account for a significant proportion (88.6%) of the non-tertiary education system in Macau, this qualitative study focused on this specific group who voluntarily resigned from their positions. Through in-depth interviews with 13 former teachers from different kindergartens, primary, and secondary schools, the research identified 50 reasons categorized into 15 factors under three categories. Although schoolrelated factors account for the most, personal reasons were found to be the primary driver. The findings of the study highlight the complex nature of teacher turnover which can be attributed to both single and multiple factors, in both direct and indirect forms. The factors could also interplay in both unidirectional and mutual relationships. A conceptual framework for teacher turnover in Macau was developed to address the 15 contributing factors and the complex interplay of these factors. This study could fill the gap in the literature and serve as a valuable resource for policymakers and school leaders seeking to reduce teacher attrition rates in the region
Keywords: Macau; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; leavers; teacher turnover

Plugin Program Reconfigurable Architecture System For Sustainable Future - Au Yeung, Kam Sheung (University of Saint Joseph, 2023)
The primary research focus of this dissertation revolves around the concept of a "plugin" program. It raises a fundamental question about whether a building can attain long-term usability through metabolic flexibility (plugin units and their reconfigurable space), promoting adaptability (accommodating various program transfers), and meeting sustainable future criteria. Specifically, this dissertation inquires whether this "plugin" building design, with its reconfigurable units and metabolic system, can adapt to different spatial programs and become sustainable architecture
Keywords: Building program transfer; Metabolism Architecture; Plugin capsule units; Reconfigurable; Sustainable Architecture; Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph

How digital technology changes our way to interact with others at the workplace in Macau - Pre and post-pandemic - Austin, Lei Iat Pong (University of Saint Joseph, 2023)

Segmentation of CT-Scan Images Using UNet Network for Patients Diagnosed with COVID-19 - Bernardo Gois, Francisco Nauber; Lobo Marques, Joao Alexandre (Computerized Systems for Diagnosis and Treatment of COVID-19, 2023)
The use of computational tools for medical image processing are promising tools to effectively detect COVID-19 as an alternative to expensive and time-consuming RT-PCR tests. For this specific task, CXR (Chest X-Ray) and CCT (Chest CT Scans) are the most common examinations to support diagnosis through radiology analysis. With these images, it is possible to support diagnosis and determine the disease’s severity stage. Computerized COVID-19 quantification and evaluation require an efficient segmentation process. Essential tasks for automatic segmentation tools are precisely identifying the lungs, lobes, bronchopulmonary segments, and infected regions or lesions. Segmented areas can provide handcrafted or self-learned diagnostic criteria for various applications. This Chapter presents different techniques applied for Chest CT Scans segmentation, considering the state of the art of UNet networks to segment COVID-19 CT scans and a segmentation experiment for network evaluation. Along 200 epochs, a dice coefficient of 0.83 was obtained.

Classification of COVID-19 CT Scans Using Convolutional Neural Networks and Transformers - Bernardo Gois, Francisco Nauber; Lobo Marques, Joao Alexandre; Fong, Simon James (Computerized Systems for Diagnosis and Treatment of COVID-19, 2023)
COVID-19 is a respiratory disorder caused by CoronaVirus and SARS (SARS-CoV2). WHO declared COVID-19 a global pandemic in March 2020 and several nations’ healthcare systems were on the verge of collapsing. With that, became crucial to screen COVID-19-positive patients to maximize limited resources. NAATs and antigen tests are utilized to diagnose COVID-19 infections. NAATs reliably detect SARS-CoV-2 and seldom produce false-negative results. Because of its specificity and sensitivity, RT-PCR can be considered the gold standard for COVID-19 diagnosis. This test’s complex gear is pricey and time-consuming, using skilled specialists to collect throat or nasal mucus samples. These tests require laboratory facilities and a machine for detection and analysis. Deep learning networks have been used for feature extraction and classification of Chest CT-Scan images and as an innovative detection approach in clinical practice. Because of COVID-19 CT scans’ medical characteristics, the lesions are widely spread and display a range of local aspects. Using deep learning to diagnose directly is difficult. In COVID-19, a Transformer and Convolutional Neural Network module are presented to extract local and global information from CT images. This chapter explains transfer learning, considering VGG-16 network, in CT examinations and compares convolutional networks with Vision Transformers (ViT). Vit usage increased VGG-16 network F1-score to 0.94.

TPOT Automated Machine Learning Approach for Multiple Diagnostic Classification of Lung Radiography and Feature Extraction - Bernardo Gois, Francisco Nauber; Lobo Marques, Joao Alexandre; Fong, Simon James (Computerized Systems for Diagnosis and Treatment of COVID-19, 2023)
This chapter describes an AUTO-ML strategy to detect COVID on chest X-rays utilizing Transfer Learning feature extraction and the AutoML TPOT framework in order to identify lung illnesses (such as COVID or pneumonia). MobileNet is a lightweight network that uses depthwise separable convolution to deepen the network while decreasing parameters and computation. AutoML is a revolutionary concept of automated machine learning (AML) that automates the process of building an ML pipeline inside a constrained computing framework. The term “AutoML” can mean a number of different things depending on context. AutoML has risen to prominence in both the business world and the academic community thanks to the ever-increasing capabilities of modern computers. Python Optimised ML Pipeline (TPOT) is a Python-based ML tool that optimizes pipeline efficiency via genetic programming. We use TPOT builds models for extracted MobileNet network features from COVID-19 image data. The f1-score of 0.79 classifies Normal, Viral Pneumonia, and Lung Opacity.

SENIOR LEARNERS, ANDRAGOGY, GERAGOGY, AND SYNTHETIC PHONICS: A CASE STUDY - Bhroin, Aine Ni (University of Saint Joseph, 2023)
Although there is a substantial body of research on the second language acquisition of adults, there is little specific research on the learning experiences of senior and very senior adults. This thesis investigates and discovers the experience of being a senior from a traditional Confucian Heritage Culture aged between 55 and 75 years old, learning English as a foreign language through various interventions, including, the introduction of an adapted version of synthetic phonics to improve pronunciation, alongside the use of andragogical and geragogical principles to accommodate and encourage the development of agency and self-directed learning. This research adopted a case study methodology to investigate the lived experiences of seniors, and investigated the participants’ subjective constructions of the situation, learning experiences, challenges, circumstances, needs, and wants with regard to the situation. Therefore, an open and exploratory case study design was selected to understand the participants and report the findings. Furthermore, this thesis identifies the challenges faced by senior and very senior learners who are post-work and post-family rearing to make recommendations from the findings to complement, enhance and empower their learning
Keywords: ANDRAGOGY; GERAGOGY; SENIORS; SYNTHETIC PHONICS; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph

Student engagement, higher education, and social justice: beyond neoliberalism and the market - Bramley, Corinna; Morrison, Keith (Routledge, 2023)
"Student engagement is a catch-all term, irresistible to educators and policy makers, and serving many agendas and purposes. This ground-breaking book provides a powerful theory of student engagement, rooted in critical theory and social justice. It sets out a compelling argument for student engagement to promote social justice and to repel neoliberalism in, and through, higher education, addressing three key questions: -Student engagement in what? -Student engagement for what? -Student engagement for whom? The answers draw on Habermas, Honneth, Gramsci, Foucault, and Giroux in examining ideology, power, recognition, resistance, and student engagement, with examples drawn from across the world. It sets out key features, limitations and failures of neoliberalism in higher education, and indicates how student engagement can resist it. Student engagement calls for higher education institutions to be sites for challenge, debate on values and power, action for social justice, and for students to engage in the struggle to resist neoliberalism, taking action to promote social justice, democracy, and the public good. This book is essential reading for educators, researchers, managers and students in higher education, social scientists and social theorists. It is a call to reawaken higher education for social justice, human rights, democracy and freedoms"–
Keywords: Active learning; Education; Higher; Neoliberalism; Social aspects; Social justice and education

Noise Detection and Classification in Chagasic ECG Signals Based on One-Dimensional Convolutional Neural Networks - Caldas, Weslley Lioba; Do Vale Madeiro, João Paulo; Pedrosa, Roberto Coury; Gomes, João Paulo Pordeus; Du, Wencai; Marques, João Alexandre Lobo (Computer and Information Science, 2023)

Noise Detection and Classification in Chagasic ECG Signals Based on One-Dimensional Convolutional Neural Networks - Caldas, Weslley Lioba; do Vale Madeiro, João Paulo; Pedrosa, Roberto Coury; Gomes, João Paulo Pordeus; Du, Wencai; Marques, João Alexandre Lobo (Computer and Information Science, 2023)
Continuous cardiac monitoring has been increasingly adopted to prevent heart diseases, especially the case of Chagas disease, a chronic condition that can degrade the heart condition, leading to sudden cardiac death. Unfortunately, a common challenge for these systems is the low-quality and high level of noise in ECG signal collection. Also, generic techniques to assess the ECG quality can discard useful information in these so-called chagasic ECG signals. To mitigate this issue, this work proposes a 1D CNN network to assess the quality of the ECG signal for chagasic patients and compare it to the state of art techniques. Segments of 10 s were extracted from 200 1-lead ECG Holter signals. Different feature extractions were considered such as morphological fiducial points, interval duration, and statistical features, aiming to classify 400 segments into four signal quality types: Acceptable ECG, Non-ECG, Wandering Baseline (WB), and AC Interference (ACI) segments. The proposed CNN architecture achieves a $$0.90 \pm 0.02$$accuracy in the multi-classification experiment and also $$0.94 \pm 0.01$$when considering only acceptable ECG against the other three classes. Also, we presented a complementary experiment showing that, after removing noisy segments, we improved morphological recognition (based on QRS wave) by 33% of the entire ECG data. The proposed noise detector may be applied as a useful tool for pre-processing chagasic ECG signals.
Keywords: Chagas disease; Deep learning; ECG quality assessment

"The Never-Ending Task": A case study on Performing Arts with People with Intellectual Disabilities in Macau - Carol, Wong Weng Si (University of Saint Joseph, 2023)

Sudden cardiac death multiparametric classification system for Chagas heart disease's patients based on clinical data and 24-hours ECG monitoring - Cavalcante, Carlos H. L.; Primo, Pedro E. O.; Sales, Carlos A. F.; Caldas, Weslley L.; Silva, João H. M.; Souza, Amauri H.; Marinho, Emmanuel S.; Pedrosa, Roberto C.; Marques, João A. L.; Santos, Hélcio S.; Madeiro, João P. V.; Cavalcante, Carlos H. L.; et al. (Mathematical Biosciences and Engineering, 2023)
About 6.5 million people are infected with Chagas disease (CD) globally, and WHO estimates that $ > million people worldwide suffer from ChHD. Sudden cardiac death (SCD) represents one of the leading causes of death worldwide and affects approximately 65% of ChHD patients at a rate of 24 per 1000 patient-years, much greater than the SCD rate in the general population. Its occurrence in the specific context of ChHD needs to be better exploited. This paper provides the first evidence supporting the use of machine learning (ML) methods within non-invasive tests: patients' clinical data and cardiac restitution metrics (CRM) features extracted from ECG-Holter recordings as an adjunct in the SCD risk assessment in ChHD. The feature selection (FS) flows evaluated 5 different groups of attributes formed from patients' clinical and physiological data to identify relevant attributes among 57 features reported by 315 patients at HUCFF-UFRJ. The FS flow with FS techniques (variance, ANOVA, and recursive feature elimination) and Naive Bayes (NB) model achieved the best classification performance with 90.63% recall (sensitivity) and 80.55% AUC. The initial feature set is reduced to a subset of 13 features (4 Classification; 1 Treatment; 1 CRM; and 7 Heart Tests). The proposed method represents an intelligent diagnostic support system that predicts the high risk of SCD in ChHD patients and highlights the clinical and CRM data that most strongly impact the final outcome.
Cc_license_type: cc_by Number: mbe-20-05-402 Primary_atype: Mathematical Biosciences and Engineering Subject_term: Research article Subject_term_id: Research article

澳門私立融合教育學校中資源教師現況與問題之研究 =: A RESEARCH STUDY ON THE CURRENT SITUATION AND FACING PROBLEMS OF RESOURCE TEACHERS IN PRIVATE INCLUSIVE EDUCATION SCHOOLS IN MACAO - Chan, Lok In (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 澳門; 私立融合教育學校; 融合教育; 資源教師

The attractiveness of Taobao: why do people always come back despite negative feedback - Chan, Nga Man (University of Saint Joseph, 2023)
Online shopping in Macau has developed rapidly in recent years. And the success of Taobao is significantly hard to not notice. Its’ sales are breaking the record every year. However, there are a lot of negative comments towards Taobao. Various researches and data have shown that live-streaming is one of the biggest contributions towards Taobao’s sales and record breaking. This research aims to investigate deeply to understand how Taobao counters those issues and the role of live-streaming in relation to it. Based on a review of the literature in the relevant areas , qualitative methodology is adopted after thorough considerations. A small sample size of 10 were selected to conduct semi-structured in-depth interviews and the participants agreed to respond to answer the original interview questions and the follow-up questions. Analysis of the responses demonstrated e-customer service is the most influential variable towards repurchase intention. Live-streaming strategy can effectively and directly reduce constomer’s uncertainty of products and increase the efficiency of responsiveness. And product uncertainty and responsiveness speed are variables that impact purchase intention. The result demonstrated live-streaming's effectiveness in combating multiple negative aspects of Taobao and strengthening the positive aspects. On this basis, live-streaming is an impactful method to combat Taobao. In addition, e-service in terms of sufficiency of the staff’s communication skill have been found important towards customer’s satisfaction. A gap related to such an issue has been recommended in the further research recommendations along with other factors or sample groups, which are needed to explore deeply in the future
Keywords: Authenticity; Customer satisfaction; E- Service quality; Repurchase intention; Taobao; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

THE RELATIONSHIP BETWEEN PSYCHOPATHOLOGY AND RESILIENCE OF SECONDARY SCHOOL STUDENTS IN MACAO - Chan, Ngan Ieng (University of Saint Joseph, 2023)
School-age children and adolescents face several psychological conditions frequently associated with negative consequences on behavioral and mental problems. Their level of mental resilience may affect their responses to academic or interpersonal issues and coping with challenges, which in turn affects their mental health. This study aims to characterize the current status of the psychopathology and resilience of secondary students and to analyze the relationship between psychopathology and resilience in a sample of 80 girls aged 12–18 was selected by cluster sampling from one private secondary school with six grades in Macao. In this study, we used the Achenbach System of Empirically Based Assessment (ASEBA) to assess behavioral and emotional problems and the Resilience Scale for Chinese Adolescents to assess resilience. A total of 78 valid questionnaires were obtained for CBCL, 78 for TRF, 80 for YSR, and 77 for Resilience Scale and data were analyzed by using SPSS. The results reveal that clinical prevalence of Total Problems (YSR, 27.5% > CBCL, 19.2% > TRF, 15.4%) and Internalizing Problems (YSR, 22.5% > CBCL, 17.9% > TRF, 11.5%) from the perspective of adolescents was higher than that from the perspectives of parents and teachers. Senior students exhibited higher frequency on the borderline clinical range than Junior students. (χ2(2, N=80) =14.56, p<.001). The average score of resilience is 3.24±0.51, which is above the middle level. Regarding the YSR scale and Resilience scale, we found that the score of Affect Control is significantly negatively correlated with the score of Internalizing Problems (r = -.354, p<.01). Family Support is also significantly negatively correlated with the score of Internalizing Problems (r = -.302, p<.01). Good affect control and family support can reduce various emotional and behavioral problems. The results of the study found the resilience level can negatively affect internalizing problem behaviors and externalizing problem behaviors. The results are promising and can give clues for preventing and promoting measures regarding mental health issues to both family and school education contexts, as creating a sustainable development strategy of improving adolescents’ mental resilience quality
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; psychopathology; resilience; secondary students

METAVERSE: A STUDY OF CONSUMER PERSPETIVE IN MACAU - Chan, Vanda Cardoso (University of Saint Joseph, 2023)
Technology is an essential and valuable tool nowadays. New technology and innovations are introduced to the public day by day. Metaverse will be a new trend, as the Macau government has been trying to promote this technology since the COVID-19 pandemic is still here. Before this technology goes deeply to the public, this paper attempts to examine the consumer’s perspective of Metaverse and understand the cognition of Macau people about Metaverse. And bring out what factors and conditions will make them accept this technology. A qualitative research method will address the questions and problem to understand consumer perspectives towards this technology. Entrepreneurs, managers, and professionals will be invited to take part in this research. Ten interviews will be carried out in this research for data analysis, which may provide a board overview of this technology in Macau and give recommendations to local entrepreneurs. In conclusion, consumers think it is still not a well-developed technology and is not globally used at this stage. In contrast, if this technology is ready-to-use, it will be a helpful assistant in their businesses. They expect the metaverse to be fully developed in ten or more years
Keywords: Consumer perspective; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; augmented reality; extended reality; marketing strategy; virtual reality

INDOOR AIR QUALITY (IAQ) MANAGEMENT IN MACAO: MONITORING PARTICULATE MATTER (PM10 AND PM2.5) AT THE RENOVATION SITE IN LARGE SHOPPING MALLS - Chan, Weng Ian (University of Saint Joseph, 2023)
"Over time, the large shopping malls in Macao will require some changes to improve space utilization, resulting in renovation projects that affect indoor particulate matter (PM10 and PM2.5) concentrations. Employees work long hours in an environment where the ambient air quality is poor, directly affecting their work efficiency. Nonetheless, the concentration of PM produced by the interior renovation of shopping malls has yet to receive particular attention. Therefore, this study will investigate IAQ, in particular, PM10 and PM2.5 in large-scale shopping mall renovation projects in three different indoor locations (i.e., public, renovation, and construction areas) to understand the causes of indoor PM10 and PM2.5. This study will collect on-site PM data for analysis, examine whether the current control measures are appropriate and propose some improvements. The data collected will be compared with IAQ standards from the World Health Organization (WHO) and the Macao Meteorological and Geophysical Bureau (SMG), specifically PM concentrations. The research results can provide a reference guide for decision-makers, management, construction teams, design consultant teams and renovation teams of large-scale projects. In addition, the monitoring of IAQ can ensure a comfortable environment for employees and customers."
Keywords: Construction Dust; Health Exposure; PM Monitoring; Particulate Matter; Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Gender Differentiated Parenting and Family Characteristics Affecting Parent-Adolescent Relationship in Macao: Che Iok Seng a.k.a Matthew - Che, Iok Seng (University of Saint Joseph, 2023)
This study aims to investigate gender-differentiated parenting and the factors that affect parent-adolescent relationships in Macao families. The study will address the following research questions: A) Does gender-differentiated parenting exist in Macao families? B) How does the academic level of parents relate to conflict resolution and acceptance levels? C) How does the length of time parents have lived together relate to conflict resolution and acceptance levels? D) How does the sibling position of adolescents relate to conflict resolution and acceptance levels? The study employed a quantitative research approach with a purposive and convenient sample of parents with children aged between 12 to 18 years old in Macao. The data were collected using the Parent-Child Interaction Questionnaire—Revised-Parent version (PACHIQ-R-P) through a questionnaire survey from May to August 2022. Out of the 172 completed questionnaires, seven were invalid, resulting in 165 valid questionnaires. The findings showed that gender differentiation in parenting was confirmed, with significant results showing that fathers had lower acceptance and conflict resolution levels when their child was a boy. Mothers showed similar acceptance and conflict resolution levels regardless of their child's gender. Furthermore, the study found that parents' acceptance of their children was influenced by their academic level, length of time living together, and the child's sibling position. This study is the first of its kind in Macao and could provide valuable insights for family and adolescent services in the region
Keywords: Adolescents; Conflict Resolution; Gender differences; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

ONLINE IMPULSE BUYING BEHAVIOR: A STUDY OF MACAU CONSUMERS - Cheong, I. Lam (University of Saint Joseph, 2023)
Due to the expansion of the Internet and advancements in technology, e-commerce has been frequently and widely used nowadays. The popularity of online shopping continues to develop and become increasingly common, yet, the concept of impulsive buying has consistently drawn significant attention over the years. In order to fit into the current shopping trend, recognizing the needs and wants of online shoppers as well as providing appropriate approaches are essential tasks for companies to achieve. The question of how to attract consumers to make purchases has been a concern for a long time, and in fact, it is necessary to explore consumers’ online purchase decisions in relation to their impulse buying behavior. In accordance with current academic knowledge, the main objective of this study is to investigate factors that influence consumers' online impulsive buying behavior based on external stimuli (such as sales promotions and websites characteristics) and the elements of marketing mix strategy (product, price, place, and promotion). According to the analysis, the promotion strategy has been identified as the most significant influence on consumers’ decision to make an online impulsive purchase. Therefore, the findings from this study are beneficial for companies and marketers to build a framework in order to develop suitable and effective strategies in order to encourage and stimulate consumers' desire for purchases. Furthermore, the research applies the qualitative methodology by conducting semi-structured interviews with 11 consumers who have previously experienced an online impulse buying
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; e-commerce; external stimuli; marketing mix strategy; online impulse buying; online shopping

COMMUNICARE - an Interactive Multisensory Application to Care for Trees in Macao - CHEONG, WENG IAN (University of Saint Joseph, 2023)

Challenges and Possibilities of Cultural Heritage: The Case of Portuguese Tiles (Azulejos) in Macau - Chu, Hou Man (University of Saint Joseph, 2023)
Macao is a city of culture, and history and culture are the wealth of Macao. Over the centuries, the exchange and transmutation of Chinese and Western cultures have given Macao a unique cultural charm, and have also formed and preserved a considerable amount of cultural heritage. Cultural heritage has received increasing attention from all sectors of the community in the tourism industry in Macao, the promotion of the preservation and transmission of cultural heritage through tourism development has become a new issue in the tourism sector. As an independent art form in the urban public space, tile painting has both practical and aesthetic functions, and is a special vehicle for the convergence of multiple cultures in the urban cultural ecology. It is also a medium through which the city's cultural message can be fully disseminated. The paper presents a detailed analysis of the strengths, weaknesses, opportunities and challenges of the development of Macao's cultural heritage tile murals, based on an introduction to the existing status of Macao's cultural heritage tile murals, using the SWOT analysis method, which provides a reference for Macao's cultural heritage tourism
Keywords: Azulejo; Cultural heritage; Macao; SWOT analysis; Strategy; Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Comparative study: The Human rights situation in China, the USA and Europe - Chu, Pok Tou; Lao-Phillips, Jenny Oliveros (University of Saint Joseph, 2023)
This thesis mainly discusses and compares the human rights situation and the problems in China, the USA and the UK. Also, the thesis will give the solution of how to make the world's human rights situation more fairly. Because we sometimes listen to these countries use cruel ways to suppress the opponents from the news. So I think this will be very suitable for understanding the current human rights situation, problems and movements in these countries. This thesis mainly uses the secondary data analysis method to collect and analyse the data. After analysing the data, three main issues affecting human rights were identified. These issues are race, religion, and network privacy. Other important factors still influence human rights, but this dissertation focused on the three issues identified. Finally, I will give two to three recommendations to practice human rights more fairly. Although the step will be very small, we can greatly improve the fair human rights in the future
Keywords: China; Europe; Human rights; Human rights situation; Thesis and Dissertations Master of Government Studies (MGS); USA; United Kingdom; University of Saint Joseph

CHARACTERIZARION OF ENVIRONMENTAL NOISE IN MACAO S.A.R. OVER THE PAST DECADE: IMPLICATIONS FOR NOISE POLLUTION MANAGEMENT - Deng, Ziyang (University of Saint Joseph, 2023)
With the rapid urban development, Macao SAR has become one of regions with the with highest population density in the world, characterized by high traffic flow and dense building aggregations. Noise has become one of the major environmental problems in Macao. Besides having an impact on human health and wellbeing, noise pollution is known to impact ecological systems and the image of a place. Before proposing a plan to reduce noise pollution, it is necessary to have a general understanding of the current noise levels in Macao, how they have changed over time and the main noise pollution sources and environmental concerns. This dissertation relies on the publicly available data from DSPA (Macao Environmental Protection Bureau) monitoring stations concerning noise levels over the past decade. The main research goals were: 1) Characterize changes in noise levels from 2010 to 2021 during daytime, nighttime, and full-day from multiple noise stations located in Macao, Taipa, and Coloane Peninsula; and 2) associate changes in noise levels with potential factors such as location, number of residents/tourists, number of vehicles, among others. This work provides an important framework for future studies concerning noise monitoring and mitigation strategies
Keywords: Environmental policies; Legislation; Master of Environmental Sciences and Management (MESM); Noise management; Noise pollution; University of Saint Joseph; mitigation

TO EXPLORE SMOKING BEHAVIORS OF ADULTS IN MACAO: DISCOVERIES BY QUANTITATIVE AND QUALITATIVE STUDIES - Dias, Luis Borges (University of Saint Joseph, 2023)
The purpose of the study was to explore the smoking behaviour of the smokers living in Macao. I was part of the 1st group of doctors to have chosen to initiate smoking cessation in Macau. In addition to my diverse academic background of study in laws- a dissertation about the effect of tobacco control program in Macao (submitted in 2011), a master in Public Administration, and five years of working experiences as an Inspector Assistant of tobacco, I had the conviction that I have to write to share my experience and knowledge about smoking cessation to contribute to the field of counselling and psychotherapy as there is little research data concerning smoking prevalence and demographics in Macao. This study consists of two parts – PART I presents the quantitative data collected by a questionnaire-survey over 1378 smokers and PART II qualitative data from semi-structured interviews with 10 adult smokers to explore their experiences of smoking and smoking cessation in Macao. Quantitative data analysis was conducted with the SPSS, while qualitative analysis with coding and theme identification by following the grounded theory procedures. The study found that about 85% smoker surveyed consumed more than half a pack of cigarette per day and about 31% reported various symptoms like irritability, fatigue, loss of appetite and difficulties in concentration. The qualitative study has identified major positive factors related to initiation and maintenance of smoking cessation, namely health concerns, financial concerns and family support. Major negative factors related to relapse of smoking are peer influences, smoking of family members, and impacts of stressful life events. Based on findings of the study, it is argued that preventive anti-smoking education should be implemented among young people. Promotion of health education and preventive anti-smoking strategist and policy in Macao are discussed. The data collected indicate the fact that individuals who have pathologies of the cardiovascular system as a motivating factor for contemplating or taking actions for smoking cessation. Moreover, financial problems, gender (male predominantly), married with family support, higher educational level, without psychological diseases, better economic status, lower nicotine dependent are predictors to success in quit smoking. It also raises the possible need to deepen some evaluation parameters hither to be only superficially addressed. Therefore, and by limitations inherent to the study, this hypothesis needs further investigation. I argue that non-pharmacological treatment methods alone have proven to be effective in the smoking cessation process. However, it is argued that this combined with pharmacological therapy, in particular in specialized consultations, would be more effective and capable in increasing success rates in smoking cessation
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; grounded theory; relapse; smoking behaviour; smoking cessation

Covid-19 Detection Based on Chest X-Ray Images Using Multiple Transfer Learning CNN Models - dos Santos Silva, Bruno Riccelli; Cesar Cortez, Paulo; Crosara Motta, Pedro; Lobo Marques, Joao Alexandre (Computerized Systems for Diagnosis and Treatment of COVID-19, 2023)
The gold standard to detect SARS-CoV-2 infection considers testing methods based on Polymerase Chain Reaction (PCR). Still, the time necessary to confirm patient infection can be lengthy, and the process is expensive. In parallel, X-Ray and CT scans play an important role in the diagnosis and treatment processes. Hence, a trusted automated technique for identifying and quantifying the infected lung regions would be advantageous. Chest X-rays are two-dimensional images of the patient’s chest and provide lung morphological information and other characteristics, like ground-glass opacities (GGO), horizontal linear opacities, or consolidations, which are typical characteristics of pneumonia caused by COVID-19. This chapter presents an AI-based system using multiple Transfer Learning models for COVID-19 classification using Chest X-Rays. In our experimental design, all the classifiers demonstrated satisfactory accuracy, precision, recall, and specificity performance. On the one hand, the Mobilenet architecture outperformed the other CNNs, achieving excellent results for the evaluated metrics. On the other hand, Squeezenet presented a regular result in terms of recall. In medical diagnosis, false negatives can be particularly harmful because a false negative can lead to patients being incorrectly diagnosed as healthy. These results suggest that our Deep Learning classifiers can accurately classify X-ray exams as normal or indicative of COVID-19 with high confidence.

Lung Segmentation of Chest X-Rays Using Unet Convolutional Networks - dos Santos Silva, Bruno Riccelli; Cesar Cortez, Paulo; Gomes Aguiar, Rafael; Rodrigues Ribeiro, Tulio; Pereira Teixeira, Alexandre; Bernardo Gois, Francisco Nauber; Lobo Marques, Joao Alexandre (Computerized Systems for Diagnosis and Treatment of COVID-19, 2023)
The gold standard to detect SARS-CoV-2 infection consider testing methods based on Polymerase Chain Reaction (PCR). Still, the time necessary to confirm patient infection can be lengthy, and the process is expensive. On the other hand, X-Ray and CT scans play a vital role in the auxiliary diagnosis process. Hence, a trusted automated technique for identifying and quantifying the infected lung regions would be advantageous. Chest X-rays are two-dimensional images of the patient’s chest and provide lung morphological information and other characteristics, like ground-glass opacities (GGO), horizontal linear opacities, or consolidations, which are characteristics of pneumonia caused by COVID-19. But before the computerized diagnostic support system can classify a medical image, a segmentation task should usually be performed to identify relevant areas to be analyzed and reduce the risk of noise and misinterpretation caused by other structures eventually present in the images. This chapter presents an AI-based system for lung segmentation in X-ray images using a U-net CNN model. The system’s performance was evaluated using metrics such as cross-entropy, dice coefficient, and Mean IoU on unseen data. Our study divided the data into training and evaluation sets using an 80/20 train-test split method. The training set was used to train the model, and the evaluation test set was used to evaluate the performance of the trained model. The results of the evaluation showed that the model achieved a Dice Similarity Coefficient (DSC) of 95%, Cross entropy of 97%, and Mean IoU of 86%.

X-Ray Machine Learning Classification with VGG-16 for Feature Extraction - dos Santos Silva, Bruno Riccelli; Cortez, Paulo Cesar; da Silva Neto, Manuel Gonçalves; Lobo Marques, Joao Alexandre (Computerized Systems for Diagnosis and Treatment of COVID-19, 2023)
The Covid-19 pandemic evidenced the need Computer Aided Diagnostic Systems to analyze medical images, such as CT and MRI scans and X-rays, to assist specialists in disease diagnosis. CAD systems have been shown to be effective at detecting COVID-19 in chest X-ray and CT images, with some studies reporting high levels of accuracy and sensitivity. Moreover, it can also detect some diseases in patients who may not have symptoms, preventing the spread of the virus. There are some types of CAD systems, such as Machine and Deep Learning-based and Transfer learning-based. This chapter proposes a pipeline for feature extraction and classification of Covid-19 in X-ray images using transfer learning for feature extraction with VGG-16 CNN and machine learning classifiers. Five classifiers were evaluated: Accuracy, Specificity, Sensitivity, Geometric mean, and Area under the curve. The SVM Classifier presented the best performance metrics for Covid-19 classification, achieving 90% accuracy, 97.5% of Specificity, 82.5% of Sensitivity, 89.6% of Geometric mean, and 90% for the AUC metric. On the other hand, the Nearest Centroid (NC) classifier presented poor sensitivity and geometric mean results, achieving 33.9% and 54.07%, respectively.

Book of Proceedings of ARTeFACTo 2022 Macao, Third International Conference on Digital Creation in Arts, Media and Technology - Emerging Extended Realities - Estadieu, G; Martins de Abreu, F.; Caires, Carlos; Fernandes Marco, A. (IEEE, 2023)

Framework proposition for identification, impact analysis and intervention on causes of delay in construction projects in the Greater Bay based on descriptive analytics and artificial intelligence - Felix, Fung Ka Chun (University of Saint Joseph, 2023)

EVALUATING SATISFACTION OF LOCAL ROAD USERS OF MACAU - Fong, Chi Cheng; Pinheiro, Francisco Vizeu; Lei, Weng Chi (University of Saint Joseph, 2023)
"Macau's rapid economic development in recent decades and relatively low usage of public transportation have put considerable pressure on the city's carrying capacity. Improving the transportation system has been a major policy goal of Macau's urban planners. To deepen the understanding of the perspectives of local road users, this dissertation's main research question is: what factors determine the satisfaction of local road users of Macau? After collecting responses using an online questionnaire, quantitative research methods were adopted to analyze travel patterns, satisfaction toward different road usage dimensions, and sociodemographic characteristics of local residents. 145 responses were collected and quota samples were generated to match the distribution of each sociodemographic feature of the population. Most respondents used private vehicles to travel during peak hours on weekdays for work or for school and to travel during the entire afternoon and evening on weekends for shopping necessities and for leisure. The most traveled districts were Baixa de Taipa, Costa & Ouvidor Arriaga, and Baixa de Macau. It was found that the mean overall satisfaction score inclined to the dissatisfaction side (below 3). Only clarity of traffic lights and number of road signs (measuring infrastructure) and temperature and price of fares (measuring public transportation) had mean satisfaction scores that were significantly higher than 3, indicating higher satisfactions. Meaningful hypotheses regarding the differences of different road user groups were set out, then Kruskal-Wallis ANOVA tests and Mann-Whitney U tests were run. The significant findings were such that the elderly aged 65 or above were less satisfied and the unemployed were more satisfied with road usage. The better educated were more satisfied with the environment, and the unemployed were more satisfied with the public transportation. Drivers were less satisfied with transportation costs, and peakhour road users were less satisfied with the infrastructure. The Spearman correlation analyses found that infrastructure had moderately positive correlation with facilities and with travel safety. Based on the findings and their policy implications, policy suggestions could be made. The policies suggested in this study should have favorable short-term and long-term effects on more than one road usage aspects."
Keywords: Public transport; Survey questionnaire; Thesis and Dissertations Master of Government Studies (MGS); Traffic congestion; Transportation; Transportation services; University of Saint Joseph

THE POWER OF SCENT MARKETING: INFLUENCING CONSUMERS TO PURCHASE - Fong, Un I. (University of Saint Joseph, 2023)
Examining consumer perceptions of scent marketing in Macau's retail setting is the goal of this study. The study focuses on the following two primary uses of scent marketing in retail environments: subliminal application and application as a component of branding strategy. Qualitative research methodology is used. A total of ten consumer interviews produced the data. The findings show that consumers are in favor of scent marketing's use in retail settings. The use of scent marketing as a tool for establishing brands is preferred, and consumers find this approach to scent marketing to be more acceptable than its subliminal application. Although consumers believe that other factors, such as price, are typically more significant than scent when making purchases, the use of subliminal scents was not always evaluated negatively. Unless occasionally when making an unplanned purchase, consumers do not think that a subliminal scent can significantly impact their purchasing behavior
Keywords: Consumer behavior; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; branding; consumer opinion; marketing strategy; scent marketing; subliminal advertising

(Un)directed Reading: Selected Students' Work Directed Reading 2020/21 University of Saint Joseph, Macao, China - Olga Ng Ka Man, Sandra (University of Saint Joseph, 2023)
Keywords: Literature

Malaria Blood Smears Object Detection Based on Convolutional DCGAN and CNN Deep Learning Architectures - Gois, Francisco Nauber Bernardo; Marques, João Alexandre Lobo; de Oliveira Dantas, Allberson Bruno; Santos, Márcio Costa; Neto, José Valdir Santiago; de Macêdo, José Antônio Fernandes; Du, Wencai; Li, Ye (Computer and Information Science, 2023)
Fast and efficient malaria diagnostics are essential in efforts to detect and treat the disease in a proper time. The standard approach to diagnose malaria is a microscope exam, which is submitted to a subjective interpretation. Thus, the automating of the diagnosis process with the use of an intelligent system capable of recognizing malaria parasites could aid in the early treatment of the disease. Usually, laboratories capture a minimum set of images in low quality using a system of microscopes based on mobile devices. Due to the poor quality of such data, conventional algorithms do not process those images properly. This paper presents the application of deep learning techniques to improve the accuracy of malaria plasmodium detection in the presented context. In order to increase the number of training sets, deep convolutional generative adversarial networks (DCGAN) were used to generate reliable training data that were introduced in our deep learning model to improve accuracy. A total of 6 experiments were performed and a synthesized dataset of 2.200 images was generated by the DCGAN for the training phase. For a real image database with 600 blood smears with malaria plasmodium, the proposed Deep Learning architecture obtained the accuracy of 100% for the plasmodium detection. The results are promising and the solution could be employed to support a mass medical diagnosis system.

Malaria Blood Smears Object Detection Based on Convolutional DCGAN and CNN Deep Learning Architectures - Gois, Francisco Nauber Bernardo; Marques, João Alexandre Lobo; De Oliveira Dantas, Allberson Bruno; Santos, Márcio Costa; Neto, José Valdir Santiago; De Macêdo, José Antônio Fernandes; Du, Wencai; Li, Ye (Computer and Information Science, 2023)

INTEGRATING VARIATION THEORY WITH MULTILINGUAL INSTRUCTION IN MULTILINGUAL CLASSROOMS: BRIDGING THEORY AND PRACTICE IN FOREIGN LANGUAGE ACQUISITION - Gomes, Nuno Miguel Alves dos Santos Teixeira; Correia, Ana Maria; Thota, Neena Jawaharlal (University of Saint Joseph, 2023)
This thesis explores language teaching and language acquisition by multilingual learners using a Variation Theory approach and multilingual teaching in a university setting in Macao, China. It includes three case studies applied to students of the Spanish language in the introductory level which took place from late August to early December of the year 2017. The first study describes Macao’s multilingual language learners in the University of Macao in 2017. Based on the LEAP-Q questionnaire, a questionnaire was created to inquire all Spanish language students about their languages´ background, their motivations to learn new languages, as well as their learning strategies. The second study shows how the usage of Variation Theory techniques and multilingual teaching techniques boosted the teaching and the learning during the semester. This study employs a case study methodology, by analysing in-class multiple interactions gathering information on how multilinguals´ language background affects the pedagogical process. It analyses a total of 28 classes of 1 hour and 15 minutes. The third study presents the analysis of a questionnaire to 82 students of the initial level of Spanish language in the University of Macao, along with the analysis of interviews from 10 selected multilingual students about their linguistic background and how they experienced the semester. These interviews collected more information about the effectiveness of the Variation Theory in the semester in terms of in-class teaching and learning. From the triangulation of these three studies, some conclusions have been drawn about the advantages of using Variation Theory and multilingual teaching techniques for multilingual students, for the language teacher and ultimately also into the curricular design of foreign language teaching. In sum, that the linguistic background of students plays a major role in how they acquire a new language and, that applying Variation Theory techniques can be an immensely effective technique in a language classroom setting; suggesting that multilingual students will gain from being previously identified and placed in a separate class where these variation techniques were applied. Since this thesis focuses solely on an introductory language course, there is ground to explore this same approach on more advanced multilingual language learners
Keywords: Foreign language teaching; Multilingualism; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph; Variation Theory

A DCRC Model for Text Classification - Hao, Zhaoquan; Jin, Jiangyong; Liang, Shengbin; Cheng, Suying; Shen, Yanqing (Computer and Information Science, 2023)
Traditional text classification models have some drawbacks, such as the inability of the model to focus on important parts of the text contextual information in text processing. To solve this problem, we fuse the long and short-term memory network BiGRU with a convolutional neural network to receive text sequence input to reduce the dimensionality of the input sequence and to reduce the loss of text features based on the length and context dependency of the input text sequence. Considering the extraction of important features of the text, we choose the long and short-term memory network BiLSTM to capture the main features of the text and thus reduce the loss of features. Finally, we propose a BiGRU-CNN-BiLSTM model (DCRC model) based on CNN, GRU and LSTM, which is trained and validated on the THUCNews and Toutiao News datasets. The model outperformed the traditional model in terms of accuracy, recall and F1 score after experimental comparison.
Keywords: BiGRU; BiLSTM; CNN; Text classification

Effective Promotion for Old Tea Restaurant Base On Marketing Mix Approach After Covid-19 Pandemic In Macau - Ho, Ka Ian (University of Saint Joseph, 2023)
This research paper analyses the marketing efforts and important attributes of Macau tea restaurants that have been open for more than 20 years, especially the digital methods that tea restaurants have used to sustain their business and meet customers' needs in the era of digital transition after the onset of the 2019 Covid 19 pandemic year. Using online marketing channels nowadays become an important tool for communicating with customers today. Despite the old Tea Restaurants in Macau did not put much efforts on digital channels for communication yet, to find out how tea restaurants survive in the rival restaurant industry in Macau, qualitative and quantitative methods were used to see how they meet the needs of their customers. For the quantitative method, an online survey questionnaire in bilingual English and Traditional Chinese was conducted with 280 respondents on customer purchase habits, importance of restaurants’ attributes and social media insights on tea restaurants, and the data was analysis by SPSS for the relationship and significance. For the qualitative method, 7 interviews were conducted with the business owners of the old tea restaurants which that have been opened for more than 20 years, including marketing efforts and their attitudes towards digitalization. To find out the marketing strategy of Macau’s old tea restaurants in the digital transformation era, it was found that “place” and “product” are the most important marketing mix for customers. Tea restaurant owners focus on product quality, and generate “word-of-mouth” which is customer-generated marketing, and is an effective way to influence customers for local tea restaurants. Meanwhile business owners will consider digitalize in the near future as well to match the new young customers’ online habits and the need for “place” such as online delivery platform
Keywords: Macau; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; digitalization; marketing mix; tea restaurant

HOW DO FOOD INFLUENCERS ON INSTAGRAM AFFECT CONSUMERS’ VISIT INTENTION TO RESTAURANTS IN MACAU? - Ho, Pui I. (University of Saint Joseph, 2023)
This dissertation examines consumers' perceptions of food influencer content on Instagram and the relationship between exposure to food influencer reviews and consumers' intention to visit restaurants in Macau. A mixed-method research design was employed, combining quantitative survey data from 301 responses with qualitative insights from one focus group session involving six participants. The findings suggest that consumers find food influencer content entertaining and inspiring for dining out and exploring new culinary experiences, but they express concerns over its credibility. While food influencer content has a good exposure to consumers, it has a moderate impact on consumers’ restaurant choices, with various factors affecting the relationship. The results highlight the importance of perceived trustworthiness and enjoyability of food influencer content, the visual appeal of food and restaurant environments in photos, and personal relationships in shaping Macau consumers' visit intention to restaurants. The findings can serve as a basis for future research on credibility perceptions of food influencers, the enjoyability of influencer content, and the visual appeal of food and restaurant environments on Instagram. Practically, food influencers should prioritize transparency, authenticity, appealing photos, engaging captions, and leverage the role of personal relationships to increase their impact on consumers' restaurant choices
Keywords: Instagram; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; food influencers; influencer marketing; social media

Food Waste Management In Macau: Assessing Public Awareness, Recycling Facilities, And Policy Implementations In Comparative Perspective - Hoi, Hang Ian (University of Saint Joseph, 2023)
Food waste has become an increasingly pressing issue worldwide, and Macau is no exception. A substantial portion of municipal solid waste in Macau is comprised of organic waste, with household food waste being a significant contributor. This can be attributed to households purchasing excessive food, preparing more than necessary, or not consuming items before they spoil, leading to detrimental resource and environmental impacts, particularly in the form of greenhouse gas emissions. It is crucial for Macau to develop a sustainable food waste management system that fosters prevention and responsible consumption and to develop food waste recycling habits among its residents. This study employed a two-pronged approach: a literature review of food waste source separation policies and practices in four neighboring regions to identify adaptable good practice examples for Macau, and a questionnaire survey completed by 143 local residents. The survey aimed to comprehend residents' behaviors and awareness regarding food waste prevention and treatment, evaluate their satisfaction with Macau's existing food waste recycling program, examine their resistance and motivation toward participating in the recycling program, and assess their attitudes toward implementing a polluter-pays-principle system in Macau. The survey aimed to provide insights into the current state of household food waste in Macau and inform future waste management policies and strategies of stakeholders. The survey findings highlight the need for enhanced public awareness and education on food waste prevention. Additionally, upgrading recycling facilities may encourage residents to participate more actively in food waste recycling. Ultimately, implementing suitable policies can help prevent food loss and waste and regulate food waste generation and elevate recycling rates. This study offers preliminary recommendations for policymakers or government entities as a orientation for future planning
Keywords: Food Loss and Waste (FLW); Food Waste Hierarchy; Food Waste Management; Food Waste Separation; Sustainable Development Goals (SDGs); Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

VALUE-BASED ADOPTION OF MOLECULAR CHINESE MEDICINE (MCM): AN EXPLORATORY INVESTIGATION - Hong, Chi Kit (University of Saint Joseph, 2023)
The world we live in today is constantly changing, with new technologies and innovations being introduced all the time. Through the continuation and innovation of Chinese medicine theories, scientific research methods, and progress, Traditional Chinese Medicine continues to evolve and develop more innovative Modern Chinese Medicine. In this research, Molecular Chinese Medicine is studied as a new form of Chinese medicine, intended to provide a more pleasant and safe experience for consumers. Thus, the objective of this study is to identify both positive and negative perceptions that contribute to the adoption of innovative technologies and their related products. In order to reach this goal, a robust value-based theoretical model is used. To examine behavioural intentions to adopt Molecular Chinese Medicine (MCM) in Macau, this study combines quantitative and qualitative methods. Thus, a Value-based Acceptance Model (VAM) was used to determine Macau citizens' attitudes towards Molecular Chinese Medicine, including their perceptions of its usefulness, enjoyment, technicality, and perceived fee, in relation to the perceived value of the product, which may ultimately determine adoption intentions. Structural Equation Modeling (SEM) was used to process a sample of 194 Macau residents. The data analysis supported our model's explanatory and predictive power and helped describe the characteristics of the local population. Our results provide insight into the acceptance of innovative products that may be useful in designing more accurate strategies and facilitating the introduction of MCM to Macau and similar markets. It was found that low perceived fees demonstrated a relatively strong positive correlation with potential users' perceived value, whereas usefulness and enjoyment showed a medium-strong positive correlation. Also, a strong positive correlation was found between potential consumers' perception of the value of Molecular Chinese Medicine and their intention to adopt it
Keywords: Molecular Traditional Medicine (MCM); SmartPLS; Technology Adoption; Thesis and Dissertations Master of Business Administration (MBA); Traditional Chinese Medicine (TCM); University of Saint Joseph; Value-based Adoption Model (VAM)

NEUROFINANCE - ANALYZING AND UNDERSTANDING STOCK TRADER’S DECISION-MAKING PROCESS BASED ON REAL-TIME MONITORING OF EMOTIONAL REACTIONS - Hsu, Hsin-Tzu (University of Saint Joseph, 2023)
Human emotions can be meticulously associated with decision-making, and emotion can generate behaviours. Due to the fact that it could be bias and exhaustively complex to examine how human beings make choices, important groups of study in finance are stock traders and non-traders. The objective of this work is to analyze the connection between emotions and the decision-making process of investors and non-investors to understand how emotional arousal might dictate the process of deciding policy. As facial expressions are fleeting, neuroscience tools such as AFFDEX (Real-Time Facial Expression Analysis), Eye-Tracking, and GSR (galvanic skin response) were adopted to facilitate the experiment and its accompanying analysis process. Thirty-seven participants attended the study, ranging from 18 to 72 years old; the distribution of investors and non-investors was twenty-four and thirteen, respectively. The experiment initially disclosed a thought-provoking result between the two groups under the certainty and risk-seeking prospect theory; there were more risk-takers among non-investors at 75%, while investors were inclined toward certainty at 79.17%. The implication could be that the non-investing individuals were less complex in thought and therefore pursued higher returns besides a high probability of losing the game. In addition, the automatic emotion classification system indicates that when non-investors confronted a stock trending chart beyond their acquaintance or knowledge, they were psychologically exposed to fear, anger, sadness, and surprise. Investors, on the contrary, were detected with disgust, joy, contempt, engagement, sadness, and surprise, where sadness and surprise overlapped in both parties. Under time pressure conditions, 54.05% of investors or non-investors tend to make decisions after the peak(s) of emotional arousal. Variations were found in the deciding points of the slopes: 2.70% were decided right after the peak(s), 37.84% waited until the emotions turned stable, and 13.51% were determined as the emotional indicators started to slide downwards. Several combinations of emotional responses were associated with decisions. For example, negative emotions could induce passive decision-making, in this case, to sell the stock; nevertheless, it was also examined that as the slope slipped downwards to a particular horizontal point, the individuals became more optimistic and selected the "BUY" option. The support of physiological monitoring tools makes it possible to capture the individuals' responses and discover the science of decision-making. Future works may consider expanding the study to more significant demographic populations for further discoveries
Keywords: Decision-making; Emotions; Investors; Physiological Monitoring; Stock Trading; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Primary teachers' burnout at the inclusive education schools in Macao - Ieong, Iek Kuan (University of Saint Joseph, 2023)
"In 2021/2022 academic year, there are 2,244 SEN students in Macau and its growth rate is 36% in ten years. However, at the present, there are 38 schools providing the related education to them. Admittedly, this is an unbalanced supply and demand. In fact, the teachers who work at inclusive education schools are bearing all responsibility to teach SEN students and their mental health is worth to attention. Moreover, there are 1,224 SEN students in primary (2021/2022 academic year), it accounting for 55% of all. That is, the numbers of their teachers are the most and they are representative. Therefore, exploring primary teachers’ burnout at inclusive education schools becomes the topic of this study, even more important, it is including to compare normal and resource teachers. This topic is rarer currently in Macau. On the one hand, emotional exhaustion, depersonalization and (reduced) personal accomplishment are dimensions of burnout (Maslach et al., 1996). These become the dependent variables of this study. According Ecological Systems Theory (Bronfenbrenner, 1979) and the factors of self-efficacy in inclusive education (Sharma et al., 2012), the following hypotheses are provided to guide this study: (1) normal teachers’ emotional exhaustion, depersonalization and reduced personal accomplishment are higher than those in resource teachers; (2) teachers’ attitudes into inclusive education, (3) teachers’ self-efficacy to use inclusive instruction (SEII), (4) teachers’ self-efficacy in collaboration (SEC) and (5) teachers’ self-efficacy in v managing behavior (SEMB) both are negatively related to emotional exhaustion, depersonalization and reduced personal accomplishment; (6) teachers’ stress of Covid19 is positively related to emotional exhaustion, depersonalization and reduced personal accomplishment. On the other hand, quantitative methodology, and snowball sampling are used in this research. At last, 132 responds are collected, including 100 normal teachers and 32 resource teachers. They are from 48 inclusive education schools in Macau. All data were analyzed by SPSS 25.0. The results of this study are followed: (1) teachers’ emotional exhaustion level is middle, their depersonalization and reduced personal accomplishment levels both are low; (2) resource teachers’ emotional exhaustion and depersonalization are higher than normal teachers; (3) teachers’ attitudes into inclusive education negatively related to depersonalization but positively related to reduced personal accomplishment; (4) in the factors of self-efficacy, only SEII is negatively related to reduced personal accomplishment; (5) teachers’ stress of Covid-19 is positively related to emotional exhaustion, depersonalization and reduced personal accomplishment."
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門家校合作中的親師溝通: 以某小學為例 =A STUDY ON PARENT-TEACHER COMMUNICATION IN HOME-SCHOOL COOPERATION IN A PRIMARY SCHOOL IN MACAU - Io, In Chi (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 家校合作; 小學; 澳門; 親師溝通

Exploring Features and Behaviors of 'GUNDAM MOBILE SUIT' Enthusiasts in China 's Online Digital Society - Joel, Chao Chou U (University of Saint Joseph, 2023)

ORGANIZATIONAL JUSTICE AND PSYCHOLOGICAL WELL-BEING AMONG HEALTHCARE WORKERS IN MACAO - Kaewmanee, Celina dos Santos (University of Saint Joseph, 2023)
This study examined the relationships between organizational justice, job satisfaction, and subjective well-being of medical doctors and nurses in Macao. It applied a quantitative methodology through a cross-sectional applying self-response questionnaires to 149 healthcare workers. Consistent with the group-engagement model (Tyler & Blader, 2003), findings indicate that organisational justice and job satisfaction improve subjective well-being. Yet, inconsistent with the model and our hypotheses, organizational justice did not affect work satisfaction. Finally, nurses experienced less positive justice perceptions than doctors. The study provides insights into the relationship between organizational justice, job satisfaction, and subjective well-being among healthcare professionals, which might help enhance working conditions. Healthcare organizations should prioritize promoting job satisfaction and justice perceptions to increase healthcare personnel's subjective well-being. The cross-sectional design limits causal inferences about variable relationships, and the self-reported data may have social desirability or response biases. Still, the originality and value of this paper lie in its contribution to the literature on the well-being of healthcare workers, particularly in the unique context of Macao. To our knowledge, this is the first study in Macao to examine the relationship between organizational justice, job satisfaction, and subjective well-being among healthcare workers
Keywords: Healthcare; Job Satisfaction; Organizational Justice; Subjective well-being; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

澳門融合教育下資源老師心路歷程之質性研究 =: A QUALITATIVE STUDY ON THE SPIRITUAL JOURNEY OF RESOURCE TEACHERS IN INCLUSIVE EDUCATION IN MACAO - Ke, Li Ping (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 心路歷程; 融合教育; 資源老師; 質性研究

THE MODERATING EFFECTS OF POWER DISTANCE ON THE RELATIONSHIP BETWEEN PERCEPTIONS OF ORGANISATIONAL POLITICS AND ORGANISATIONAL JUSTICE - Kong, Fion Ming Ying (University of Saint Joseph, 2023)
The aim of this research is to investigate how power distance orientation effects the relationship between perceptions of organisational politics and perceptions of organisational justice. A quantitative cross-sectional study was conducted on 172 full time workers in Macau, where respondents self-responded to questionnaires that were translated back-to-back into Chinese in order to accommodate the populations native language. This study found that power distance was contrary to our initial hypothesis of high-power distance equals to high politics and low justice. It was found that high power distance in facts equates to lower political perceptions and higher justice perceptions. This study contributes to understanding power distance in Macau as it is not noted in the Hofstede cultural dimensions. We also learned that having a longer distance between a position of power can contribute to less political activity and more sense of justice for the employees
Keywords: Organisational Justice; Organisational Politics; Power Distance; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

Externalizing Behaviour in Macao: Gender and Parental Participation - Kuok, Oi Lou (University of Saint Joseph, 2023)
There are gaps in the research on gender differences and parental participation and the interaction between gender and parental participation in non-Western cultural contexts, particularly the Macao context. The current study aims to fill these gaps by examining gender and parental participation (i.e., father only, mother only, or both) differences and interactions in externalizing behaviour (oppositional defiant disorder and conduct disorder) during late childhood and adolescence (i.e., from age 10 to 18) in Macao. The methodological approach for the current study was a cross-sectional design with a quantitative methodology based on self-rated questionnaires. In certain items, we did discover gender differences. More boys than girls appeared to concur that they occasionally misbehave at school or start fires. And it appeared that girls were more likely than boys to concur that they occasionally exhibit unexpected mood or emotion changes and strong tempers. The children in the groups where only the mother or father participated tended to agree more than they prefer to hang out with older kids than kids their own age. This is in contrast to the group with more parental participation, which is represented by both parents submitting the questionnaire. Although none of the hypotheses proposed were supported, our outcomes implied culture and subculture may play important roles on youths’ externalizing behaviour
Keywords: Externalizing behaviour; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; gender; parental participation

IDENTIFICATION OF CRITICAL FACTORS TO DETERMINE THE INTENTION OF GOVERNMENT SERVICE MINI-PROGRAM ADOPTION THROUGH MOBILE PAYMENT PLATFORMS IN MACAU AND THE GREATER BAY AREA - Lai Chi Meng; Marques, João Alexandre Lobo (University of Saint Joseph, 2023)
Government service mini-programs have become an integral component of eGovernment in the Greater Bay Area, and successful eGovernment is necessary for building a smart city. Service quality and citizens' trust play a vital role in urban integration and in-depth cooperation in the Bay Area. The ubiquitous nature of mini-programs based on WeChat and Alipay provides excellent flexibility in accessing government services. Technology advantages, mutual recognition of cross-border data, and online transactions bring value and benefits to citizens. However, the mechanism of mini-program adoption has not been elaborated. Homogenization, conflict of regulations, and policy effectiveness are issues of great concern. This study employed Self-Determination Theory and Motivation Theory, proposed an empirical model based on the extended SOR paradigm, and aimed to identify the critical factors determining the intention of government service mini-program adoption from the user’s perspective. Six hundred and nine valid samples were collected from Macau, Hong Kong, Guangzhou, and Shenzhen through online survey platforms. The findings suggested that service quality, trust in eGovernment, ubiquity, and social influence constituted the determinants of intention to adopt. Service quality and ubiquity were salient determinants, and a great extent of service quality and ubiquity could promote perceived value and intention. Citizens' trust in government service mini-programs was reasonable, where benevolence, integrity, and competence were crucial indicators of trust. Social influence amplified and transmitted risk perception while perceived risk significantly reduced intention. Perceived value positively associated with the four determinants and enhanced user intention; it acted as a mediator with high explanatory power in the model. Government support received positive ratings from citizens; it negatively regulated the relationship between intention and the determinants respectively, implying that excessive intervention from the government could lead to inhibition. Finally, we proposed relevant implications and suggestions for the GBA government agents and policymakers
Keywords: Thesis and Dissertations PhD in Government Studies (D-GS); University of Saint Joseph

澳門普通班教師與資源教師合作教學現況與改進建議之個案研究 =: A CASE STUDY OF CO-TEACHING PRACTICES AND IMPROVEMENT SUGGESTIONS AMONG GENERAL EDUCATION TEACHERS AND RESOURCE TEACHERS IN MACAO - Lai, Chong Weng (University of Saint Joseph, 2023)
Keywords: Inclusive education; Resource teacher; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 合作教學; 澳門; 融合教育; 資源教師

Exploring Macau Primary School Teachers’ Understanding and Practices of Educational Innovation - Lai, Hoi In (University of Saint Joseph, 2023)
Teaching methods are not enough in today's social environment. By studying the understanding and practice of innovative education by primary school teachers in Macao, we can find a direction to promoting educators' demand for educational innovation. This research aims to understand the attitudes of primary school teachers in Macao toward innovative education, as well as the feasibility and necessity of developing a creative curriculum, through in-depth interviews with the experiences and reactions of primary school teachers in Macao. Simultaneously, encourage primary school teachers in Macao to implement effective and innovative educational methods so that Macao society can rethink the importance of educational innovation. The significance of the research lies in improving teachers' awareness of educational innovation and promoting teachers' understanding of education. In education, innovation includes new teaching theories, methods, techniques, and resources. Therefore, the education innovation is to think about things creatively, and innovation is to do creative things. By interviewing eleven local primary school teachers in Macau, we learned their views on innovative education teaching methods. Although, a limitation of the study is that only a few faculty members were selected, which may not represent the entire primary teacher in Macau. The study draws four main conclusions, the first of which is the view of primary teacher in local education, it can know that Macao primary school teachers understanding and cognition of educational innovation. Though of understanding of Macau’s primary teacher’s attitude in innovation teaching, which can find the feasibility of innovation teaching in Macau. At the same time, understanding of the impact factor in Macau innovation education, it clarifies the main challenging of primary teacher practice innovation teaching in Macau. On the other hand, thought of understanding of teacher’s attitude, we can more understanding the real situation in Macau’s educational innovation and encourage the teacher promoted educational innovation in Macau
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Perception on occupational stress in the Hospitality Industry in Macau - Lam Chi Ieng (University of Saint Joseph, 2023)
Employees in the hospitality industry, in particular, face difficult conditions such as overwork, job security, understaffing, and work-life imbalance in today's fast-paced society. Because of that, employees in the hospitality industry experience high levels of occupational stress. Severe conditions of occupational stress may not only lead to health issues for the employee but also affect their work performance. In order to get a better grasp of how occupational stress affects the employees in the hospitality industry in Macau, the research questions are: 1) What are the sources of stress in the Macau hospitality industry? 2) How does the COVID-19 pandemic change the perception of occupational stress among employees in the Macau hospitality industry? How do the companies help the employees in the Macau hospitality industry cope with occupational stress? have been formulated. Semi-structured interviews were conducted with eleven participants working in the hospitality industry, with a median age of 39 years and a median range of 13 years. Based on these interviews, participants expressed their perceptions of occupational stress under the categories of distress and eustress, while coding schemes were applied to all semi-structured interviews. The results on distress showed that reactions from employees and their working conditions, in particular, were the two most important determinants of occupational stress, while motivation helped people grow and develop their confidence. For the changes in occupational stress due to the pandemic, mental reactions from employees were the most significant determinant of occupational stress in the Macau hospitality industry during the changes brought about by the pandemic in these years, closely followed by employee job insecurity. In order to cope with occupational stress, employees should take responsibility for coping with their stress, but employers also have a role to play in this process, like providing good communications and proactive assistance to the employees. Finally, employees' responses were described as more negative as a result of their experience. Further research could focus on more methods for employees to cope with occupational stress in both physical and mental ways
Keywords: Stress; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; hospitality industry; occupational stress; stress management interventions

NATURAL HAZARDS AND THE ROLE OF MANGROVES AS A NATURE-BASED SOLUTION FOR COASTAL PROTECTION IN MACAO SAR - Lam, Sut Ieng (University of Saint Joseph, 2023)
The inundation problem in Macao is getting more attention recently, especially after the destructive impacts of typhoons Hato (2017) and Mangkut (2019). The inundation caused by storm surges is getting more severe with the rapid sea-level rise in Macao. Moreover, the potential threat of a tsunami in Macao, may be enhanced with rising sea-level. This research evaluated the risk of coastal hazards in Macao by analyzing the local meteorological data. The results of the analysis indicate a rising trend in the tropical cyclone intensity and more severe storm surges are expected to occur in the future. Moreover, this research explores the potential of Nature-based Solutions (NbS), particularly mangroves, to address the inundation problem in Macao. The study included a preliminary laboratory-based experiment and the application of local mangroves data in numerical models. The results of the experiment and numerical models demonstrate the ability of mangroves to attenuate waves. These findings, although preliminary, indicate that mangroves could be a promising NbS to address inundation issues in Macao. To effectively implement this NbS, further field investigations are needed to measure attenuation in-situ, as well as determine optimal locations for mangrove restoration projects
Keywords: Inundation; Mangroves; Master of Environmental Sciences and Management (MESM); Nature-based solutions; Sealevel rise; Storm surges; University of Saint Joseph; Wave attenuation

EVALUATION OF MANGROVE BLUE CARBON AS A POTENTIAL FOR CLIMATE CHANGE MITIGATION IN MACAU - Lao, Hio Wai (University of Saint Joseph, 2023)
Climate change is a global issue but its impact can be felt locally. Macau SAR has been rapidly developing since the single shift towards a gaming industry-dominated economy, the overwhelming anthropogenic activities contributing to increasing pollution. Mangroves, which play an essential role as the blue carbon system with a high carbon sequestration rate could be a natural base solution to the pollution. This study aims to determine 1) the total organic Carbon (TOC) in the soil of Macau mangrove sites, 2) comparison with the methodology evaluating the organic Carbon, and 3) organic Carbon comparison between Macau and other regions. Soil sampling were processed under the Blue Carbon Initiative guideline, and the samples were divided into two parts for determining the TOC%, combustion method from Hong Kong, and methodology of ashing in our laboratory. The overall estimated TOC% of Macau mangrove sites was 1.29%. There are still a lot of potentials in Carbon storage and for climate change mitigation in Macau
Keywords: Carbon sequestration; Mangroves; Master of Environmental Sciences and Management (MESM); University of Saint Joseph; blue Carbon

THE VALUATION OF MCDONALD’S CORPORATION (NYSE: MCD) - Lao, Hong U. (University of Saint Joseph, 2023)
This paper analyses the valuation of McDonald's Corporation (MCD) as of December 31, 2021. An estimate of the Company's intrinsic value will also be provided. In addition, the internal company factors and external market conditions influencing company valuations and share prices will be discussed. The study has two main objectives: Determine the intrinsic value of McDonald's common stock as of December 31, 2021, and compare it to the actual stock market price on the same date. An assessment of the stock’s market price should represent the Company's true value on that day. Research can then verify whether it was overvalued or undervalued on that day. Identify internal company factors and external market environment factors that affect the Company's operations. This information will be used to gain a deeper understanding of the sensitivity analysis results. Possible scenarios will be discussed to reflect how these factors stimulate macroeconomic, industry, and business developments, as well as the strategic responses of industry players or competitors. McDonald's possible strategic responses to these scenarios will also be assessed. In this paper, a combination of qualitative and quantitative research methods will be employed. Data collection and analyses in Chapters 2 to 5 will use a qualitative approach, which includes data related to McDonald's, industry, and economic analyses. Chapters 5 to 8 will apply qualitative and quantitative data collection and analysis methods. Data will be collected from McDonald's annual report for the fiscal year from December 2017 to December 2021
Keywords: Intrinsic Value; McDonald's; Sensitivity Analysis; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

The Collaboration and Challenges Faced by Therapists within Professional Inclusive Education Teams in Macau =: 澳門治療師在融合教育專業團隊中的合作情況及挑戰 - Lao, Pek San (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 合作模式; 團隊合作; 治療服務; 澳門治療師

Actio Ecclesiae: The Participation of the Lay Christian Faithful in the Liturgy of the Hours (c. 1174 Sec. 2) - Law, Cyril Jerome (The Jurist: Studies in Church Law and Ministry, 2023)

探討教師及家長視角下澳門推行生命教育之現況 =: EXPLORING THE CURRENT SITUATION OF LIFE EDUCATION IN MACAU FROM THE PERSPECTIVES OF TEACHERS AND PARENTS - Lei, Choi In (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 教師自我效能; 生命教育; 親社會行為

FEMALE EMPLOYEES’ PERCEPTIONS OF WORK-LIFE BALANCE AND TURNOVER INTENTIONS IN MACAO - Lei, Hon Nei; Silva, Maria Rita (University of Saint Joseph, 2023)
"This study explored the relationships of work-life balance and turnover intentions of full-time employees in Macao, and role of gender, parenting, and elderly care. Namely: (1) What is the relationship between work-life balance perceptions and turnover intentions? (2) What is the moderating role of gender in the relationship between work-life balance perceptions and turnover intentions? (3) What is the moderating role of parenting (i.e., having children or not) in the relationship between work-life balance perceptions and turnover intentions? And, (4) what is the moderating role of care for elderly family members (i.e., having to provide care or not) in the relationship between work-life balance perceptions and turnover intentions?"
Keywords: Elderly Care; Gender; Parenting; Thesis and Dissertations Master of Organisational Psychology (MOP); Turnover Intention; University of Saint Joseph; Work-Life Balance

Green Roof, Nature-based Solutions, Biodiversity, Sustainability, Macao SAR, China - Lei, Man Sao (University of Saint Joseph, 2023)
According to the United Nations (UN) World Urbanization Prospects 2018, cities are growing in both size and number, posing challenges for sustainable development. With urbanization, the increase of impermeabilization and landscape fragmentation urges for territorial planning and resources management. To promote resilient and resourceful cites, strategic planning where nature-based solutions (NBS) are included into the built environment, counteracting the negative effects of urbanization through the provision of ecosystem services, should be considered. Green roofs (GR) are an example of NBS that provide a panoply of ecosystem services at the level of the building and city, besides contributing for climate change mitigation and adaptation. This NBS can be included in the urban planning agenda in the new building or as a retrofit solution in the existing built environment. Macao SAR (here mentioned as Macao) is the second more densely populated city in the world, according to the UN Department of Economic and Social Affairs Population Division. The present study aims to assess the inclusion of GR in Macao and assess the ecosystem services that they may provide in a holistic approach aligned with the city’s sustainable development. For this purpose, an extensive GR implemented in Taipa Island of Macao was monitored in terms of associated biodiversity and carbon cycle assessment. Further on, it was carried out a comparison between this GR and a conventional roof (CR) in terms of surface thermal buffering. The results of this study have shown to be very promising in terms of the applicability of GR in Macao and on the relevant ecosystem services that they can provide. First, data loggers were installed in the GR and CR to assess the impact on temperature mitigation. The GR had a significant effect in decreasing and buffering temperature at the surface, with temperatures of 35.6 ºC in the GR substrate comparing with temperatures of 57.7 ºC in the CR surface. The results show that GR can be a cost-efficiency strategy to reduce heating of buildings and their associated environmental and economic costs with cooling. Second, the biodiversity of plants and animals was assessed using a combination of methods. It was observed a high level of biodiversity under a low maintenance and low disturbance of GR vegetation, with 23 species of plants and 34 species of animals identified. This shows that GR can contribute to increase biodiversity in cities. Third, an experiment was run with leaf litter bags to investigate the role of macrofauna (e.g., insects) in the decomposition of organic matter. With macrofauna activity, the decomposition rate increased 17 % when compared to decomposition rates without macrofauna, suggesting that the animals harboured in GR, in particular insects, play a key role in organic matter decomposition and thus on the carbon cycle in cities. This work is, to our knowledge, the first empirical GR study in Macao. The results support the application of GR in Macao for temperature mitigation, biodiversity increase and carbon sequestration, promoting the integration of this NBS in the future urban planning and policy of the city. More generally, the work supports the use of GR as an important NBS to mitigate the impact of climate change in urban settings
Keywords: Biodiversity; China; Green Roof; Macao SAR; Nature-based Solutions; Sustainability

Consumer purchase intention towards floral products: a study based on the five consumption values - Lei, Si Nga (University of Saint Joseph, 2023)
This dissertation focused on the consumers’ consumption behavior in Macau flower retailers. It revealed what factors affect consumers’ choice of flower shops during purchase. Also, what contributes to the customers’ loyalty towards a flower retailer by having interviews with the female target groups aged between 20 to 50 who work in the office. This study is important to the flower business owner because the result can allow them to understand the thoughts and feelings of their consumer. By interviewing 11 heavy users of floral products with 16 questions based on the five consumption values, we can communicate with the consumers directly and learn the reasons behind their purchasing behavior. Questions have been divided into 5 consumption values according to the previous research by (Sheth, Newman, & Gros, 1991), including functional, conditional, social, emotional, and epistemic values. The research has collected data on how and at what level these values may affect consumer consumption choices individually. The finding part analyzed the reason why those values affect consumers’ choices. Most of the interviewees stated that service is the most important compared to quality because the owner should be enthusiastic to provide product information and understand the consumer very well to impress and retain them with good personal service
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; consumption behavior; floral product; purchase intention

INTEGRATING ROBOTS INTO READING IN AN INCLUSIVE ESL CLASSROOM AT LOWER PRIMARY - Lei, Ut Wa (University of Saint Joseph, 2023)
Establishing and improving the independent reading ability of middle school students has become one of the critical topics in the world, especially for second language learners. The cultivation of independent reading ability has specific challenges. This action research investigated the effectiveness of integrating robot-assisted teaching in reading lessons at lower primary grades. A group of third-grade students (n=15) participated in this research. The instruments include the pre-and post-test of a reading competency test (RCT) and motivational index (MI), a teacher reflection journal, and focus group discussion with parents. The whole intervention is conducted in two cycles, and requires the completion of four 40-minute lessons each week per cycle. The findings support the view that integrating robot-assisted teaching in the classroom can improve students' learning motivation to a certain extent, and that intervention programs positively impact students' learning motivation and independent reading ability in English. This study provides suggestion for the design of English reading instruction, and encourages English teachers to pay more attention to improving students' independent reading ability
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; independent reading skills; learning motivation; robot-assisted teaching

Digital Renminbi: Impacts on Economic Integration of the Greater Bay Area - Lei, Weng Chi; Wang, Xinru (Economics and Finance Readings, 2023)
The degree of economic integration in the Guangdong-Hong Kong-Macau Greater Bay Area (GBA), as reflected in the mobility of trade and capital flows, has been strengthened by free trade agreements, but obstacles including border effects, capital controls, differences of exchange rate systems and inadequate cross-regional coordination remain. Digital renminbi (e-CNY) has been tested in Shenzhen, a core GBA city since April 2020. If e-CNY is adopted in the GBA, the area will effectively become a single currency zone. Whether the GBA constitutes an “optimum currency area” (OCA) depends on its degree of economic integration. This paper computes real interest rate differential (RID), uncovered interest rate differential (UID) and deviation from purchasing power parity (PPD) of each regional pair based on data of interest rates, exchange rates and price indexes from 2016M2 to 2022M7. All UID, PPD and RID series have means within about 1 percent point from 0, indicating high degrees of financial integration, real integration and economic integration. With the exception of Guangdong-Macau RID, all series are stationary, implying mean-reverting behavior. Hence, the parities are expected to hold both in the short run and in the long run, which is a condition for an OCA in the GBA. Furthermore, the regression analysis finds that the test launch of e-CNY in Shenzhen (adjusted for the COVID-19 outbreak) has significant impacts on all RIDs, Guangdong-Macau PPD and Hong Kong-Macau PPD. With merely two and a half years of test launch, the introduction of e-CNY already had impacts on overall economic integration in the GBA.
Keywords: Economic development policy; Economic integration; Exchange rate regime; Financial integration; Greater Bay Area; Optimum currency area

職業技術教育導向的特殊教育課程實施成效及其對學生生涯準備的影響之個案研究 =: The Effectiveness of Vocational Education Program for Students with Special Educational Needs and its Impact on their Career Preparation: A Case Study - Leong Hio Man (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Promoting Future Elderly Social Participation In Macau: An exploratory Analysis - Leong Kai Chong; Ho, Jacky (University of Saint Joseph, 2023)
"The purpose of the research aimed to explore the challenges and future possiblities of ways of promoting elderly social participation in Macau. As lack of related research has been conduted in Macau, this community services and government policies and to provide suggestions for improving the direction of sustainable development and future possible research topics in this area. The research adopts a qualitative and phenomenological approach to explore the current situations, difficulties and ideas through the industry experience and insights. Nine in-depth interviews with 9 representatives of elderly social service providers subsidised by Macau SAR Government from late April to July 2022 in Macau. The content analysis using open coding to collect inductive data. Throughout themetic analysis identified by four levels: individials, community and social services, governmental policies and infrastructures. Overall, the study found that the autonomy trend of future social participation of the elderly in Macao is enhanced by education and self-health concerns and they are more independent, but the participation of male elders and female elders is unbalanced. Social service providers for the elderly provide a large number of repetitive services and are too passive and dependent on government policies andsupport, resulting in a lack of innovative thinking. The infrastructure design promoted by the government does not consider the continuous health and activity development of the elderly. This study looks at the ability of the elderly in Macau to continue to develop their strengths in the future, and suggests the need to strengthen individual retirement life planning and development for the elderly, personal health monitoring improvement, diversification of social services, elderly-led community programs, private social enterprise capital, and elderly volunteering The urgency of the number of elderly people, more practical and effective elderly inclusive urban planning."
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Do job satisfaction and supervisory support affect burnout among security guards in Macao? - Leong, Chi Ian (University of Saint Joseph, 2023)
We see security guards around in Macao in our daily lives and they are the ones who are responsible for protecting people’s safety and properties. Most security guards are non-local workers and might have different workplace stress levels. This study’s main aim is to investigate how job satisfaction and supervisory support are related to burnout among security guards in Macao. The research is carried out through a quantitative questionnaire to collect data and deliver it to the local and non-local security guards working in Macao. A total of 132 questionnaires were collected. It is expected that when security guards have higher job satisfaction and more supervisory support, they will experience less burnout. This intention enables the organization to make some changes to help the security guards from burnout due to job dissatisfaction and no supervisory support. The practical implication for reducing stress is introducing training courses such as mindfulness-based stress training programs. Future research will investigate other support like organizational support, peer support, and family and friends support on security guards
Keywords: Burnout; Job satisfaction; Supervisory support; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

澳門幼稚園非特教專業教師在融合教育班級經營的困難與應對策略之研究 =: Challenges and Strategies in the Management of Integrated Education Classes: Insights from Non-certified Kindergarten Special Education Teachers in Macau - Leong, Choi Cheng (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 澳門幼稚園; 班級經營; 融合教育; 非特教專業教師

LSDA-APF: A Local Obstacle Avoidance Algorithm for Unmanned Surface Vehicles Based on 5G Communication Environment - Li, Xiaoli; Jiao, Tongtong; Ma, Jinfeng; Duan, Dongxing; Liang, Shengbin (Computer Modeling in Engineering & Sciences, 2023)
In view of the complex marine environment of navigation, especially in the case of multiple static and dynamic obstacles, the traditional obstacle avoidance algorithms applied to unmanned surface vehicles (USV) are prone to fall into the trap of local optimization. Therefore, this paper proposes an improved artificial potential field (APF) algorithm, which uses 5G communication technology to communicate between the USV and the control center. The algorithm introduces the USV discrimination mechanism to avoid the USV falling into local optimization when the USV encounter different obstacles in different scenarios. Considering the various scenarios between the USV and other dynamic obstacles such as vessels in the process of performing tasks, the algorithm introduces the concept of dynamic artificial potential field. For the multiple obstacles encountered in the process of USV sailing, based on the International Regulations for Preventing Collisions at Sea (COLREGS), the USV determines whether the next step will fall into local optimization through the discrimination mechanism. The local potential field of the USV will dynamically adjust, and the reverse virtual gravitational potential field will be added to prevent it from falling into the local optimization and avoid collisions. The objective function and cost function are designed at the same time, so that the USV can smoothly switch between the global path and the local obstacle avoidance. The simulation results show that the improved APF algorithm proposed in this paper can successfully avoid various obstacles in the complex marine environment, and take navigation time and economic cost into account.
Publisher: Tech Science Press

The VALUATION OF TENCENT HOLDINGS LIMITED - Lo, Hao Weng (University of Saint Joseph, 2023)
This study analyzed Tencent Holdings Limited’s internal and external factors and future strategies, forecasted the financial statements of the Company for the next ten years, and measured the intrinsic value of the Company on December 31, 2021 and compared it with the stock market price on the same date. The share price’s sensitivity analysis was also conducted to understand the Company's capital structure and profitability, and the sensitivity analysis can be used to reflect the impact of these factors and strategies on the future share price, which can have a high impact on investors' future investment decisions. This study also used the SWOT Analysis and Michael Porter's Five Forces Analysis to analyze the Company's strengths, weaknesses, opportunities and threats and the Five Competitive Forces that shape the technology industry to evaluate the Company's external and internal environment and enrich the management with a more intuitive analysis leading to recommendations
Keywords: PEST Analysis; SWOT Analysis; Technology Industry; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The (non) standardized classroom - the analysis of three different cultures in the higher education systems - Angola, Brazil and Macau SAR, China - Lobo Marques (Disentangled Vision on Higher Education: Preparing the Generation Next, 2023)
This book offers an objective and dispassionate analysis of modern educational architecture allowing us to notice gaps. The fundamental question addressed is whether our education system will embrace knowledge-based society and have the foresight to better prepare future generations. If educators around the world step back for a moment, it is not difficult to notice that unanswered questions about education are looming everywhere. The existent academic literature on education is abundant and embracing. In consequence, one can ask why is this book necessary? Indeed, this book is the result of senior university professors sharing their learnings and anticipating the pivotal issues facing all education professionals. According to the United Nations, by 2050, 68% of the world’s population will be living in urban areas. This fact cannot be ignored as it is one of the drivers of the profile of the future students. The reasons to organize this publication are many, but among them three stand out which also function as the driving forces behind this project: (1) University professors teach future generations based on models grounded on knowledge advanced by past experiences; (2) The decisive requirement to understand the needs of the new generations of university millennial students; and (3) What are the critical challenges of global societies? "This book problematizes the issues concerning education, and its main contribution is to answer the need to rethink education, face contemporary challenges, and reorganize the way public policies address education. It critically analyses the challenges of global societies in a decentralized perspective, not only reflecting a western perspective of education and knowledge production. The project's originality comes from the contemporaneity of the topics covered, from the interdisciplinary perspective, and from the specific attention given to trends around education." —Cátia Miriam Costa, Researcher and Invited Assistant Professor, Centre for International Studies, Perfil Ciência

Computerized Systems for Diagnosis and Treatment of COVID-19 - Lobo Marques, Joao Alexandre; Fong, Simon James (Springer International Publishing, 2023)
Keywords: Artificial Intelligence; Biofeedback; Computerized Diagnostic Support; Covid-19; Signal and Image Processing

Technology Developments to Face the COVID-19 Pandemic: Advances, Challenges, and Trends - Lobo Marques, Joao Alexandre; Fong, Simon James (Computerized Systems for Diagnosis and Treatment of COVID-19, 2023)
The global pandemic triggered by the Corona Virus Disease firstly detected in 2019 (COVID-19), entered the fourth year with many unknown aspects that need to be continuously studied by the medical and academic communities. According to the World Health Organization (WHO), until January 2023, more than 650 million cases were officially accounted (with probably much more non tested cases) with 6,656,601 deaths officially linked to the COVID-19 as plausible root cause. In this Chapter, an overview of some relevant technical aspects related to the COVID-19 pandemic is presented, divided in three parts. First, the advances are highlighted, including the development of new technologies in different areas such as medical devices, vaccines, and computerized system for medical support. Second, the focus is on relevant challenges, including the discussion on how computerized diagnostic supporting systems based on Artificial Intelligence are in fact ready to effectively help on clinical processes, from the perspective of the model proposed by NASA, Technology Readiness Levels (TRL). Finally, two trends are presented with increased necessity of computerized systems to deal with the Long Covid and the interest on Precision Medicine digital tools. Analyzing these three aspects (advances, challenges, and trends) may provide a broader understanding of the impact of the COVID-19 pandemic on the development of Computerized Diagnostic Support Systems.

Exploratory Data Analysis on Clinical and Emotional Parameters of Pregnant Women with COVID-19 Symptoms - Lobo Marques, Joao Alexandre; Macedo, Danielle S.; Motta, Pedro; dos Santos Silva, Bruno Riccelli; Carvalho, Francisco Herlanio Costa; Kehdi, Renata Castro; Cavalcante, Letícia Régia Lima; da Silva Viana, Marylane; Lós, Deniele; Fiorenza, Natália Gindri (Computerized Systems for Diagnosis and Treatment of COVID-19, 2023)
The scientific literature indicates that pregnant women with COVID-19 are at an increased risk for developing more severe illness conditions when compared with non-pregnant women. The risk of admission to an ICU (Intensive Care Unit) and the need for mechanical ventilator support is three times higher. More significantly, statistics indicate that these patients are also at 70% increased risk of evolving to severe states or even death. In addition, other previous illnesses and age greater than 35 years old increase the risk for the mother and the fetus, including a higher number of cesarean sections, higher systolic and diastolic maternal blood pressure, increasing the risk of eclampsia, and, in some cases, preterm birth. Additionally, pregnant women have more Emotional lability/fluctuations (between positive and negative feelings) during the entire pregnancy. The emotional instability and brain fog that takes place during gestation may open vulnerability for neuropsychiatric symptoms of long COVID, which this population was not studied in depth. The present Chapter characterizes the database presented in this work with clinical and survey data collected about emotions and feelings using the Coronavirus Perinatal Experiences—Impact Survey (COPE-IS). Pregnant women with or without COVID-19 symptoms who gave birth at the Assis Chateaubriand Maternity Hospital (MEAC), a public maternity of the Federal University of Ceara, Brazil, were recruited. In total, 72 mother-infant dyads were included in the study and are considered in this exploratory analysis. The participants have undergone serological tests for SARS-CoV-2 antibody detection and a nasopharyngeal swab test for COVID-19 diagnoses by RT-PCR. A comprehensive Exploratory Data Analysis (EDA) is performed using frequency distribution analysis of multiple types of variables generated from numerical data, multiple-choice, categorized, and Likert-scale questions.

A Financial Valuation of Starbucks (SBUX) - Lok, Ka Ian (University of Saint Joseph, 2023)
Starbucks Corporation (hereinafter “Starbucks” or “the Company”) is a worldwide coffee retailer, which operates over 33,000 stores located in over 83 countries nowadays. The purpose of the study is to estimate Starbucks’ intrinsic value as of December 31, 2021 and identify whether the Company was overvalued or undervalued. Several analyses give investors and shareholders an insight into how the Company may develop or identify the ability to generate positive returns from investing in Starbucks. This study is mainly separated into two aspects. The first part specifically discusses the Company overview, industry analysis, and economic outlook, which includes SWOT analysis, PESTEL analysis, Porter's five forces analysis, and value chain analysis to identify external and internal factors that may influence the Company. The second part focuses on financial analyzes, including both historical and forecasted financial statement. Three valuation models and a sensitive analysis are applied to understand the Company’s financial conditions and performance. Starbucks’ intrinsic value is derived from the three discounted cash flow models, indicating the market overvalued the Company’s stock price as of December 31, 2021. Finally, investors and shareholders can understand more about Starbucks’ capital structure, financial highlights, and intrinsic value, because this set of information is critical for existing investors and potential investors to make investment decisions
Keywords: Starbucks; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; financial valuation; value valuation

MONITORING THE CONCENTRATION OF PARTICULATE MATTER (PM10 AND PM2.5) IN SEVERAL ROADSIDE LOCATIONS IN MACAO - Ma, Fa Chong (University of Saint Joseph, 2023)
Road transportation is one of the main sources of air pollution in Macao. This study mainly explores four major roadside locations with high traffic flow in Macao from March to May 2022 and measures their pollutant concentrations (PM10 and PM2.5), traffic flow and their fuel type, as well as considering the meteorological parameters and pollutant concentration of SMG Macao to analyze the relationship between traffic flow and pollutants on roadside locations. Under the measuring distance between 3 and 6 meters, showing that the four locations had a good correlation with the roadside station data provided by SMG on both weekdays and weekends/holidays (PM2.5: R2 is 0.59 to 0.81 on weekdays and 0.79 to 0.88 on weekends/holidays, p<0.01; PM10: R2 is 0.33 to 0.82 on weekdays and 0.30 to 0.58 on weekends/holidays, p<0.05), the overall PM2.5 is 41 to 86% higher than that of the same period of Macao roadside station (SMG), and 68 to 186% higher than that of Taipa Ambient (SMG), indicating that it is more harmful to daily pedestrians. The overall relationship between PM concentration and traffic flow is small on the long-term scale (PM2.5: R2 is 0.01 to 0.13; PM10: R2 is 0.00 to 0.02). This study also analyzed air quality on EBL, the overall PM2.5 and PM10 decreased by 12.3% to 24.8% compared with non-EBL during the period, so that is indeed beneficial to the reduction of pollutant concentrations. In addition, narrower roads were overall higher when road widths added for comparison. Lastly, meteorological data added for comparison, except for relative humidity, it can be found that there is a significant correlation with long-term pollutants (p<0.05). While previous studies have found that single-day traffic flow is related to the increase in PM concentration, this paper is more inclined to their two-way effect when exploring their long-term relationship
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph; air pollution; monitoring campaign; particulate matter; traffic characterization

Foreword - Ma, J.; Du, W.; Lu, W. (Studies in Computational Intelligence, 2023)
ISBN: 9783031121265

Investigating the influence of Instagram on the local foodservice sector in Macau: A Consumers' Perspective - Mac, Hoi Kuan (University of Saint Joseph, 2023)
Nowadays marketers and practitioners recognize the importance of social marketing as a strategy to acquire customers. Accordingly, the enterprises and brands are embracing the use of social network in communicating with potential consumers ad actual consumers, in order its performance so as to increase its sales. Among all those social media platforms, Instagram is one of the platforms which is image orientated and can easily connect with users and provide information with photos and images. As Macau is small‐sized city where there are abundant small to medium‐sized enterprises, the local small firms are switching their marketing strategies by utilizing the Instagram to promote their product online. In order to get a better grasp of how Instagram affects the promotion of the food and beverage product in Macau, the research question has been formulated: “To what extend can the local food sectors in Macau use Instagram as a marketing tool to engage purchasing intention and strengthen their brand equity? From the perspective of customers.” Semi‐structured interviews were conducted with 13 participants who are the Instagram users, with diverse situations of engagement on Instagram. According to the interviews, participants expressed that how Instagram can associate effects with arousal and brand equity (brand awareness, brand image, perceived quality and brand loyalty) and formation of purchase intention eventually through the Instagram marketing activities. The results showed that Instagram marketing activities strongly correlated the brand equity (brand awareness, brand image, and perceived quality while which in turn led to purchasing intention towards the brand. This research comprehensively illustrates the influences of Instagram marketing activities on customer‐based brand equity. The findings of this study will enable local food brands to more accurately forecast the future purchasing behaviors of their customers through Instagram marketing activities and provide a guide in managing brand equity as well
Keywords: Brand Equity; Instagram; Purchase Intention; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Can The Organisation Help? Exploring The Relationship Between Emotional Intelligence, Resilience And Burnout Among Counselling Professionals With Organisational Socialisation As Moderator - Mak, Sin Kei (University of Saint Joseph, 2023)
The phenomenon of burnout has been recognised as a worldwide occupational health issue after being vastly studied for decades. Trait Emotional Intelligence (trait EI) and resilience have been identified as personal protective factors (Gutierrez & Mullen, 2016; Listopad et al., 2021), while organisational socialisation is suggested to be an organisational factor in helping people in preventing burnout (Taormina & Law, 2000). With the purpose of 1) investigating the phenomenon in the counselling profession, as well as 2) exploring how trait EI and resilience are related to burnout and whether organisational socialisation might impose moderating effects in between, the present study examined 115 counselling professionals currently employed and working in organisational settings in Macau by snowball sampling, using a quantitative and cross-sectional approach through self-reported online questionnaires. From the data obtained, different burnout patterns were observed according to job titles and work settings, indicating that counselling professionals with different specialties and work in different settings have unique sources of stress, which resulting in differences in their burnout patterns. No between-group differences were observed in age and work experience, while male participants have a higher burnout perception than female participants in the current study. On the other hand, current results suggested trait EI and four components of resilience (determination, endurance, adaptability and recuperability) are negatively correlated to counselling professionals’ burnout perception, providing supportive evidence that trait EI and resilience are protective factors against burnout. Moderation analysis results revealed that organisational socialisation has some moderating effects on the relationship between trait EI, resilience and burnout. However, differences in direction and intensity indicated that the moderating effects of organisational socialisation might be influenced by individual differences. Further studies are needed to better the understanding of the moderating effect of organisational socialisation. Limitations of the current research and implications for counselling professionals and organisations were also discussed in the study
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; burnout; counselling professionals; organisational socialisation

Editorial Preface - Marcos, Aderito; Caires, Carlos; Estadieu, Gerald; Mendes, Daniel; Rodrigues, Nuno (International Journal of Creative Interfaces and Computer Graphics, 2023)

A FINANCIAL VALUATION OF ORACLE CORPORATION - Maung, Ye Thu Anug (University of Saint Joseph, 2023)
Oracle Corporation (hereinafter referred to as Oracle, ORCL, or ‘the Company’) is an American multinational company that provides solutions of products and services that serve the enterprises’ information technology (IT) environment. This thesis is to conduct a business analysis of the Company from a financial perspective, determining the Company’s intrinsic value as of May 31, 2021, and comparing it with the respective market value. Thus, this thesis will study, evaluate, and present an overview of the Company, an analysis of the Company’s market, industry, strategy, financial performance, including external and internal factors, a ten-year pro forma financial statement forecast, and the techniques of using the three discounted cash flow models to estimate the intrinsic value of Oracle. The obtained results from the three valuation models, including the Enterprise Discounted Cash Flow (EDCF) model, the Adjusted Present Value (APV) model, and the Discounted Economic Profit (DEP) model, show that the Company’s intrinsic values were estimated at $74.57, $75.21, and $74.82, respectively. When the results were used to compare with the market price of Oracle’s shares as of May 31, 2021, at $78.74, it reflects that the Company was overvalued
Keywords: Analysis; Financial Valuation; Oracle Corporation; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

MULTICULTURAL CAREGIVER TEAMS IN ELDERLY CENTRES IN MACAO: COMMUNICATION AND PERCEIVED SERVICE QUALITY - Mejia Dominguez, Victor Alejandro (University of Saint Joseph, 2023)
This study explored the effect of communication (i.e., among staff, and between staff and clients) and of cultural diversity on job satisfaction (i.e., intrinsic, extrinsic, and general) and perceived service quality of formal caregivers working in elderly services in Macao. We applied a quantitative methodology, based on a cross-sectional design using a self-response questionnaire to 162 staff in six elderly centres in Macao. Based on an extensive review of the literature, we proposed that: H1) cultural diversity is negatively related to (a) intrinsic job satisfaction, (b) extrinsic job satisfaction, (c) general job satisfaction, and (H5) negatively related to perceived competence and service quality; (H2) communication (a) among staff and (b) between staff and clients is positively related to intrinsic job satisfaction (H3) extrinsic job satisfaction, (H4) general job satisfaction, and (H6) perceived service quality; and finally that (H7) intrinsic, (H8) extrinsic, and (H9) general job satisfaction mediate the relationship between (a) cultural diversity, (b) communication among staff and (c) communication between staff and clients, and perceived service quality. We found that more communication among staff was related to higher intrinsic, extrinsic and general job satisfaction, and perceived competence and service quality. And intrinsic job satisfaction mediated the positive effect of communication among staff on perceived service quality. Opposite to predicted communication between staff and clients was related to lower levels of job satisfaction. And cultural diversity was positively related to satisfaction, as well as perceived competence and service quality. The theoretical and practical implications of findings, as well as limitations and suggestions for future research were discussed
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; caregivers; communication; elderly services; job satisfaction; multicultural teams; service quality

‘Culture and identity – nationality and nationalism: indications for a theological reflection’ - Morgan, Stephen (Memory and Identity: the proceedings of the 28th ASEACCU Annual Conference, 2023)

Memory and Identity: the proceedings of the 28th ASEACCU Annual Conference - Morgan, Stephen (USJ University Press, 2023)

Pope John Paul II, ‘Memory and Identity: conversations at the dawn of a millennium’ - Morgan, Stephen (Memory and Identity: the proceedings of the 28th ASEACCU Annual Conference, 2023)

The Roman Mass: From Early Christian Origins to Tridentine Reform by Uwe Michael Lang - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2023)

To realize an everyday holiness”: Newman, imagination, and the virtue of religion - Morgan, Stephen (A Guide to the Life and Thought of John Henry Newman, 2023)

Human capital investment outflanked by Macau's needs - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | As Macau strives to revive its post-pandemic economy and to reinject life into its ailing society, calls for investment in human capital resurface, alongside endless mantras of economic diversification which, for years, seem to have fallen on deaf ears, and together with plans for further infrastructure development and construction which have already turned Macau into a concrete jungle.
Section: Macau Business

The international recruitment obstacle race in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau’s development of international and tertiary sector industries is the watchword for its long-overdue diversification. Is Macau ready for this?
Section: Macau Business

COVID-19 Classification Using CT Scans with Convolutional Neural Networks - Motta, Pedro Crosara; Cesar Cortez, Paulo; Lobo Marques, Jao Alexandre (Computerized Systems for Diagnosis and Treatment of COVID-19, 2023)
Even with more than 12 billion vaccine doses administered globally, the Covid-19 pandemic has caused several global economic, social, environmental, and healthcare impacts. Computer Aided Diagnostic (CAD) systems can serve as a complementary method to aid doctors in identifying regions of interest in images and help detect diseases. In addition, these systems can help doctors analyze the status of the disease and check for their progress or regression. To analyze the viability of using CNNs for differentiating Covid-19 CT positive images from Covid-19 CT negative images, we used a dataset collected by Union Hospital (HUST-UH) and Liyuan Hospital (HUST-LH) and made available at the Kaggle platform. The main objective of this chapter is to present results from applying two state-of-the-art CNNs on a Covid-19 CT Scan images database to evaluate the possibility of differentiating images with imaging features associated with Covid-19 pneumonia from images with imaging features irrelevant to Covid-19 pneumonia. Two pre-trained neural networks, ResNet50 and MobileNet, were fine-tuned for the datasets under analysis. Both CNNs obtained promising results, with the ResNet50 network achieving a Precision of 0.97, a Recall of 0.96, an F1-score of 0.96, and 39 false negatives. The MobileNet classifier obtained a Precision of 0.94, a Recall of 0.94, an F1-score of 0.94, and a total of 20 false negatives.

Macau Ambient Air Pollutants Forecasting By Pollutant Time Series And Meteorological Data Using Machine Learning Methods - Ng, Chung Wang (University of Saint Joseph, 2023)
" Air pollution in Macau has become a serious problem following the Pearl River Delta’s (PRD) rapid industrialization that began in the 1990s. While there has been continual improvement in recent years, harmful air pollutant concentration levels are still common, impacting Macau residents' health and creating long-term medical costs to local society. With this in mind, Macau needs an air quality forecast system that accurately predicts pollutant concentration and an early alert system instead of only daily real-time reminders. Some scholars have previously carried out studies to develop an air quality forecast for Macau by successfully using statistical models. Therefore, pursuant to the outcomes of previous studies, this dissertation aims to build upon research results and explore further possibilities of building a better ML air quality forecast model based on the time series of air pollutants concentration and meteorological data. Four different state-of-the-art ML algorithms were used to create predictive models to forecast PM2.5, PM10, and carbon monoxide (CO) concentrations for the next 24 and 48-hour. These were Support Vector Machine (SVM), Artificial Neural Networks (ANN), Random Forest (RF), and Extreme Gradient Boosting (XGBoost). In addition, Multiple Linear Regression MLR, a standard ML model, was used for this dissertation as a baseline reference for performance comparison. The daily measurements of air quality data in Macau from 2016 to 2021 were collected for this dissertation. The 2020 and 2021 datasets were used for model testing while the four-year data prior to 2020 and 2021 were used to build and train the ML models. The results showed that SVM, ANN, RF, and XGBoost were able to provide a very good performance in building up a 24-hour forecast with higher R2 and lower RMSE, MAE, and BIAS. Meanwhile, all ML models in 48-hour forecasting performance were satisfactory enough to be accepted as a two-day continuous forecast even if the R2 value was lower than the 24-hour forecast. The 48-hour forecasting model could be further improved by proper feature selection based on the 24-hour dataset, using the SHAP value test, and the adjusted R2 value of the 48-hour forecasting model."
Keywords: Air pollution; Macau; Machine Learning; Meteorological features; Thesis and Dissertations Master of Environmental Sciences and Management (MESM); Transboundary pollutants; University of Saint Joseph

澳門小學非特教專業教師對融合教育之態度研究 =: A study on the Attitudes of the Non-specialized Teachers of Primary Schools in Macau towards Inclusive Education - Ng, Ka Man (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學; 融合教育; 非特教專業教師

INFORMAL RECYCLING IN MACAU: CHALLENGES AND OPPORTUNITIES FOR SUSTAINABLE DEVELOPMENT - Ng, Sut Wa (University of Saint Joseph, 2023)
Informal recycling plays a crucial role in municiapl solid waste management in many cities, particularly in the global South. This study examines the practices, challenges, and opportunities of informal recycling in Macau, a small city and Self Autonomous Region (S.A.R.) in China. Using qualitative research methods, including semi-structured interviews, this study explores the motivations and strategies of informal recyclers, the challenges they face, and the potential for collaboration with formal waste management systems. The findings of this study reveal that informal recycling in Macau is a complex and multifaceted reality and practice that involves a range of actors, from waste pickers to small-scale processors to exporters, all with their specific challenges. Informal recyclers are motivated by economic necessity, and they employ a variety of strategies to collect and process recyclable materials. However, they also face significant challenges, including high rental and transportation costs, lack of manpower, China’s waste import policies and ensuing restrictions, fluctuating global price rates of materials and the unstable income as serious consequence, accompanied by limited support from the local Government. This study also identifies opportunities for sustainable development of informal recycling in Macau, supported by the analysis of data collected via questionnaire survey regarding Macau citizens’ waste separation habits and their willingness to pay for resource separation and recovering process. The identified oppurtunities include establishing partnerships between informal and formal waste management actors, improving the infrastructure, and introducing environmental levy system and consistent policies and regulations. Overall, this study contributes to a better understanding of the role of informal recycling sector in waste management in Macau and provides insights into potential strategies for improving the sustainability of resource and waste management practices in the city
Keywords: Circular Economy (CE); Informal Recycling; Integrated Solid Waste Management (ISWM); Recycline Rate; Sustainable Development Goals (SDGs); Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph; Waste Hierarchy

學以致用中文課程（演講）對疑似中文資優學生中文素養提升之研究 ——以澳門某中學高中學生為例 =: A Study On The Improvement Of Chinese Literacy Of Suspected Gifted Chinese Students In The Course Of Learning-to-Use Chinese (Speech) – Taking Senior High School Students Of A Middle School In Macau As An Example - O, Chi Wa; 姚小雪 (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 中文素養; 學以致用中文課程; 演講; 疑似中文資優; 資優教育

Empirical Studies on the Conditions of Achieving Interactive Mindfulness Through Virtual Reality Single User Experience in Macao - Olga Ng Ka Man, Sandra; Caires, Carlos Sena (Entertainment Computing – ICEC 2023, 2023)
Virtual reality, a computer-generated 3D environment, allows one to navigate and possibly interact, resulting in real-time simulation of one or more of the user’s five senses (Gutierrez et al., 2008; Vince, 2004). Virtual tours and places have swiftly become popular in education, professional training, arts, exhibitions, and medication and rehabilitation. The empirical studies derived from the PhD thesis research aim to identify the conditions for Macao’s single-user experience to achieve mindfulness in virtual reality through immersion and interactivity.
Keywords: Single user experience; immersion; interactivity; mindfulness; virtual reality

Training Strategies for Covid-19 Severity Classification - Pordeus, Daniel; Ribeiro, Pedro; Zacarias, Laíla; de Oliveira, Adriel; Marques, João Alexandre Lobo; Rodrigues, Pedro Miguel; Leite, Camila; Neto, Manoel Alves; Peixoto, Arnaldo Aires; do Vale Madeiro, João Paulo (Bioinformatics and Biomedical Engineering, 2023)
The COVID-19 pandemic has posed a significant public health challenge on a global scale. It is imperative that we continue to undertake research in order to identify early markers of disease progression, enhance patient care through prompt diagnosis, identification of high-risk patients, early prevention, and efficient allocation of medical resources. In this particular study, we obtained 100 5-min electrocardiograms (ECGs) from 50 COVID-19 volunteers in two different positions, namely upright and supine, who were categorized as either moderately or critically ill. We used classification algorithms to analyze heart rate variability (HRV) metrics derived from the ECGs of the volunteers with the goal of predicting the severity of illness. Our study choose a configuration pro SVC that achieved 76% of accuracy, and 0.84 on F1 Score in predicting the severity of Covid-19 based on HRV metrics.
Keywords: COVID-19; Electrocardiogram (ECG); Heart Rate Variability (HRV); disease severity classification; signal processing

Classification of Severity of COVID-19 Patients Based on the Heart Rate Variability - Pordeus, Daniel; Ribeiro, Pedro; Zacarias, Laíla; Paulo Madeiro, João; Lobo Marques, Joao Alexandre; Miguel Rodrigues, Pedro; Leite, Camila; Alves Neto, Manoel; Aires Peixoto Jr, Arnaldo; de Oliveira, Adriel (Computerized Systems for Diagnosis and Treatment of COVID-19, 2023)
The continuous development of robust machine learning algorithms in recent years has helped to improve the solutions of many studies in many fields of medicine, rapid diagnosis and detection of high-risk patients with poor prognosis as the coronavirus disease 2019 (COVID-19) spreads globally, and also early prevention of patients and optimization of medical resources. Here, we propose a fully automated machine learning system to classify the severity of COVID-19 from electrocardiogram (ECG) signals. We retrospectively collected 100 5-minute ECGs from 50 patients in two different positions, upright and supine. We processed the surface ECG to obtain QRS complexes and HRV indices for RR series, including a total of 43 features. We compared 19 machine learning classification algorithms that yielded different approaches explained in a methodology session.
Keywords: COVID-19; Electrocardiogram (ECG) signal; Heart Rate Variability (HRV) indices; Severity; Signal processing

Evaluation of ECG Non-linear Features in Time-Frequency Domain for the Discrimination of COVID-19 Severity Stages - Ribeiro, Pedro; Pordeus, Daniel; Zacarias, Laíla; Leite, Camila; Alves Neto, Manoel; Aires Peixoto Jr, Arnaldo; de Oliveira, Adriel; Paulo Madeiro, João; Lobo Marques, Joao Alexandre; Miguel Rodrigues, Pedro (Computerized Systems for Diagnosis and Treatment of COVID-19, 2023)
In 2020, the World Health Organization declared the Coronavirus Disease 19 a global pandemic. While detecting COVID-19 is essential in controlling the disease, prognosis prediction is crucial in reducing disease complications and patient mortality. For that, standard protocols consider adopting medical imaging tools to analyze cases of pneumonia and complications. Nevertheless, some patients develop different symptoms and/or cannot be moved to a CT-Scan room. In other cases, the devices are not available. The adoption of ambulatory monitoring examinations, such as Electrocardiography (ECG), can be considered a viable tool to address the patient’s cardiovascular condition and to act as a predictor for future disease outcomes. In this investigation, ten non-linear features (Energy, Approximate Entropy, Logarithmic Entropy, Shannon Entropy, Hurst Exponent, Lyapunov Exponent, Higuchi Fractal Dimension, Katz Fractal Dimension, Correlation Dimension and Detrended Fluctuation Analysis) extracted from 2 ECG signals (collected from 2 different patient’s positions). Windows of 1 second segments in 6 ways of windowing signal analysis crops were evaluated employing statistical analysis. Three categories of outcomes are considered for the patient status: Low, Moderate, and Severe, and four combinations for classification scenarios are tested: (Low vs. Moderate, Low vs. Severe, Moderate vs. Severe) and 1 Multi-class comparison (All vs. All)). The results indicate that some statistically significant parameter distributions were found for all comparisons. (Low vs. Moderate—Approximate Entropy p-value = 0.0067 < 0.05, Low vs. Severe—Correlation Dimension p-value = 0.0087 < 0.05, Moderate vs. Severe—Correlation Dimension p-value = 0.0029 < 0.05, All vs. All—Correlation Dimension p-value = 0.0185 < 0.05. The non-linear analysis of the time-frequency representation of the ECG signal can be considered a promising tool for describing and distinguishing the COVID-19 severity activity along its different stages.
Keywords: COVID-19; ECG signals; Non-linear analysis; Statistical analysis

The Spread of Buddhism in Japan and The Spirit of Japanese Tea Ceremony - Rosa, Alfredo Augusto da (University of Saint Joseph, 2023)
Buddhism was founded by Shakyamuni, and this religion has appeared in opposition to Brahmanism's caste system since its inception. Shakyamuni emphasized the important concept of “all beings are equal” from the very beginning. Buddhism spread from India to other regions, and was introduced to China through Central Asia. In China, Buddhism merged the two native cultures of Confucianism and Taoism and finally produced the socalled Chinese Buddhism. Buddhism and its value of equality were also developed and extended in China, and finally spread to Japan. After Buddhism was spread to Japan, it developed rapidly due to official support. Different Buddhist sects have established their own temples in Japan, and among them, Zen Buddhism has the greatest influence among all social classes in this country. Later, after years of development, Zen Buddhism penetrated into many aspects of Japanese culture, such as religion, aesthetics, garden design, samurai spirit and tea ceremony. With the spread of Zen Buddhism, the core value of Buddhism which is “Buddhist concept of equality” was also spread to Japan. The tea ceremony is precisely the place where this value of equality can be detected. This dissertation explains the many processes that reflect this value no matter inside or outside the tea room, and argues that the spirit of the tea ceremony is to pursue the value of equality
Keywords: Buddhism; Equality; Tea Ceremony; Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

ISOLATION AND CHARACTERISATION OF PLASTIC POLYETHYLENE TEREPHTHALATE (PET) DEGRADING AND POLYHYDROXYALKANOATES (PHAs) PRODUCING BACTERIA FROM SOIL AND WATER - Saidu, Muhammad Bashir (University of Saint Joseph, 2023)
The demand for plastic has led to enormous plastic waste in the environment, which persist and negatively impact the ecosystems. Polyethylene terephthalate (PET) is one of the most common thermoplastic polymers available on the market. The concerns about plastic waste generated an interest in strategies to enhance its biodegradation and finding alternative polymers. In this work was investigated the possibility of using bacteria to degrade PET and to produce bioplastics (Polyhydroxyalkanoates, PHAs). Finally, the integration of the two processes was tested. Overall, the work aimed to investigate the potential to recycle PET into bioplastic using bacteria. The potential of bacterial consortia from various environmental samples to degrade PET granules in liquid matrix was investigated. . The results revealed maximum PET granules degradation of 1.1 % by one of the tested consortia. PET degradation intermediate terephthalic acid (TPA) was not detected at the end of 55 days. Fourier-transform infrared spectroscopy (FTIR) results showed major spectral peak shifts and bends on PET chemical structure compared to non-inoculated control. The biodegradation of PET films buried in the soil (A), with mangrove plants (B), and bioaugmented with a bacterial consortium (C) was also investigated. The experiments were conducted for 270 days at ambient conditions. The results revealed no difference between treatments in the degradation, with a maximum weight loss of 0.118 % in the bioaugmented treatment. Nevertheless, Scanning Electron Microscope (SEM) and FTIR results indicated significant surface changes, spectral peak shifts, and stretches in PET chemical structures. Bacterial consortia isolated from the soil of the experimental treatments were assessed for degradation of PET monomers, TPA and monoethylene glycol (MEG), and intermediate Bis(2-hydroxyethyl) terephthalate (BHET). The consortia were inoculated in flasks containing minimal media with 1000 mg/L TPA or BHET or1113 mg/L MEG as the sole carbon source. Results showed complete degradation of TPA and significant degradation of BHET (96.09%), and MEG (83.65%) by the consortia. In the second part of the study, bacteria were isolated from various environmental samples and screened for PHA production using Sudan Black B staining on colonies and smeared glass slides. Transmission Electron Microscope images were captured to confirm the intracellular PHA inclusions. A total of 35 isolates were screened for PHA, and 22 showed positive staining. The isolate showing higher levels of PHA synthesis (EC2-30-3) was identified based on 16S rRNA gene sequence as Bacillus sp. and selected for PET monomers degradation and fermentation cultures for PHA production. It was cultured in minimal (Moreira et al., 2013) media with 1000 mg/L TPA and 1113 mg/L MEG as the carbon source for eight days. The isolate grew better in media containing MEG, which was selected as a substrate model for PHA fermentation. To integrate PET monomers biodegradation and production of PHA, the isolate was cultured in 0.2 % MEG. A control with 0.2 % of glucose was prepared, and the cultures were incubated for 96 hours. Bacillus sp. EC2-30-3 showed higher PHA accumulation in media supplied with MEG (40.31%) than glucose (25.53%). This is the first report showing that Bacillus sp. uses PET monomer as carbon source to produce a biopolymer. FTIR results of the extracted PHA identified its functional units as C–H, CH3, C=O, and C–O groups. The absorption bands obtained are closely related to the structure of PHB. The study thus confirmed the ability of the isolated bacteria to degrade PET monomers and produce biopolymers. The results of this work open the possibility for upscaling the use of bacteria to mitigate the impact of PET on the environment while producing environmentally friendly bioplastics
Keywords: Biodiversity; China; Green Roof; Macao SAR; Nature-based Solutions; Sustainability; Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph

Sustainable Practices in Hotel Chains—A Comparative Analysis of Official Annual Hospitality Sustainable Reports from Listed Companies in Macau SAR, China - Santos, Ana Sofia Kong; Marques, João Alexandre Lobo (New Perspectives and Paradigms in Applied Economics and Business, 2023)
In the last few years, the tourism industry has experienced rapid expansion and diversification, making it one of the fastest-growing financial industries in the world. Consequently, the hotel industry has significantly affected the environment's long-term viability. Many hotels have begun voluntarily implementing environmentally sustainable practices as they become more aware of their ecological footprint. There has been a great deal of discussion about the effects of hotel operations on the environment and tourism sustainability in Macau. It is because of these negative impacts that hoteliers have adopted green practices in an attempt to minimize them. By developing sustainability reports, hotels can set goals, measure performance, and manage change, resulting in better sustainability. It could also be viewed as a strategy to enhance the company’s sustainability reporting to ensure stakeholders know what the company does. The objective of this study is twofold based on the analysis of the official sustainability reports of four major hotel chains. Firstly, seven categories of sustainable practices effectively adopted by these chain hotels are identified and clusterized. Second, it is presented in which areas some hotels performed more efficiently than others, considering the UN Sustainable Development Goals (SDGs) as a reference. The results allow a comprehensive clusterized analysis of the industry in a highly developed gaming and entertainment area of South China and create a clear comparison between relevant players and their concerns about sustainability practices.
Keywords: Environmentally sustainable practices; Macau hotels; Sustainable development goals (SDGs); Sustainable reports; Tourism industry

Human Resource Management and Employee Relations in Angola: Challenges and Opportunities - Silva, Maria Rita (Employee Relations and Trade Unions in Africa: A Critical Approach, 2023)
This chapter presents a systematic review of research on human resources management (HRM) and employee relations (ER) in Angola to identify the main challenges and opportunities presented. To achieve that goal, this chapter characterises research conducted in the country, investigates its main findings, and proposes some directions for the future. Based on a bibliographic search in the EBSCO Discovery database of empirical articles about HRM and ER in Angola, we collected a sample of 28 studies published between 2009 and 2022. Most studies have focused on the development and retention of human resources. Other topics included diversity management, workplace attitudes and behaviours, scale validations, leadership and decision-making, performance appraisal, quality assessment, corporate social responsibility, and expatriates. We identified three main challenges and opportunities in HRM and ER in Angola. First, the policies and the planning, implementing, and evaluating processes of human resources development and retention strategies should be improved. Second, effective leadership and participation should be promoted while navigating the tensions between autocratic and participative leadership styles. Finally, positive ER and employee well-being should be promoted. Understanding these challenges and opportunities may contribute to the development of human capital in Angola and, ultimately, the country’s socioeconomic development.

Guide to Street Art in Macau. - Simões, Filipa (CURB Center for Architecture and Urbanism, 2023)

SOCIAL PERSPECTIVES ABOUT CANTONESE OPERA IN MACAO ACROSS GENERATIONS: CULTURAL IDENTITY AND SOCIAL BONDING - Sin, Shuk Ching; Silva, Maria Rita (University of Saint Joseph, 2023)
"Cantonese opera (CO) represents an art form that had its golden time in Macao during the mid-twentieth century. CO still has many loyal fans but they mainly are in the older generation. The purpose of this study was to explore if CO is considered a cultural capital heritage in Macao, related to cultural identity and transmitted across generations to support social bonding. Applying a qualitative methodology, a script for exploring participants’ experiences and opinions about CO was designed, and different groups of individuals were recruited for semi-structured interviews and focus groups. The data collected was analysed by a thematic analysis of the verbatim transcripts. Findings show that in the past first contacts with CO happened in family and related social context, mainly during participants’ developing age. However, currently CO is no longer passed on to the next generation. Despite that the young generations acknowledging their cultural identities in CO, mainly in terms of Cantonese culture and Cantonese language, older individuals engaged with CO seemed to perceive their cultural identities more in depth in its history, literacy and music. Actually, engagement is an important factor that generates social bonds. The CO leisure practitioners, no matter young or old, experienced the effects of social bonding during the ritual of enquiry in the process of learning and practising CO. To improve CO’s preservation in Macao, the adoption of strategies such as developing new productions, crossover with other media, innovations in promotion targeting the young audiences, and absorbing audiences in the Great Bay area were proposed. Finally, the potential use of CO as a tool in counselling and community work is discussed. "
Keywords: Cantonese Opera; Cultural Identity; Individual Well-being; Social Bonding; Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

Medical Information Extraction of Clinical Notes and Pictorial Visualisation of Electronic Medical Records Summary Interface - Singh, Praveen; Chaudhary, Gopal; Lobo Marques, Joao Alexandre (Smart Distributed Embedded Systems for Healthcare Applications, 2023)

A financial Valuation Study for Moody’s Corporation - Sio, Lai Teng (University of Saint Joseph, 2023)
This study presents the intrinsic value of Moody’s Corporation, a leading credit rating agency in the U.S. The results of the valuation were compared to the market value of Moody’s Corporation of the same date. The aim of the research is to provide a perspective to the investors on whether the actual value of the Company was overvalued or undervalued in the market, and how much the volatility of the stock price by the change of some factors. Both qualitative and quantitative analyses were applied in the research. The historical data, economic outlook, and the Company’s strategies were collected to be the metrics to determine the intrinsic value and provide an analysis of the prospects of Moody’s Corporation. Three valuation models were applied in the research to estimate the intrinsic value of the Company’s common stock. The cost of debt, cost of equity, the weighted average cost of capital, and the market risk premium were introduced and calculated in the research as they were the critical components in the valuation process. Since the valuation was based on assumptions and historical data to determine future growth, which indicates that the results could be changed due to uncertain factors. This study demonstrates that there was some discrepancy between the stock’s market price and the intrinsic value per share of Moody’s Corporation as of December 31, 2021
Keywords: Intrinsic Value; Moody's; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

Assisting the Creative Processes in Visual Merchandising for Luxury Fashion Retail - Soares, Patricia Alexandra Ferreira (University of Saint Joseph, 2023)
This dissertation aims to research the need and viability of creating a digital platform that assists the creative processes naturally linked to Visual Merchandising. Through the proposal of a digital platform that works as a co-creative tool for display archives and a co-creative tool for display set-ups through mood boards, we will aim at improving the teamwork in retail and provide a unique, fast-forward platform for information sharing and input under the direction of Visual Departments. Building on rich source materials such as bibliography, scientific papers, news, and articles, and interviewing Visual Merchandisers actively working in the field, we will show the importance of creativity in Luxury Retail and what are the most common challenges in the field that we will propose a solution to. We will focus on the study of concepts, reviewing digital application tools being used by professionals and their best features and improvement opportunities. By gathering this information, we hope to provide accurate insights and information that proves the viability of this proposal and understand what features could serve best the target audience. Finally, we will present a conceptual idea in the form of sketches with functions of this digital application tool to be fully developed in the future and hopefully build a consistent well, designed commercial web-based application
Keywords: Luxury Retail; Thesis and Dissertations Master of Design (MDG); University of Saint Joseph; VM Digital Platform; VM Display Archives; VM Moodboard; Visual Merchandising

Emotional Support Influence Work Engagement and Mental Well-being in Macau: The Moderating Effect of Self-reflection - Sou, Kam Chan; Kuok, Angus C. H. (University of Saint Joseph, 2023)
The purpose of this study is to examine work engagement and mental well-being in Macau, specifically after more than three years of COVID. Examine whether external factors such as emotional support from supervisors, co-workers, and family members have a positive impact on work engagement and mental well-being, and whether the internal factor self-reflection with its three aspects of need for self-reflection, engagement in self-reflection, and insight from self-reflection moderates the relationship between emotional support, work engagement, and mental well-being. The target audience consists of Macau's integrated resort, hospitality, and gaming industry employees. According to the Affective Event Theory (AET), affective events at work generate emotional responses that influence the attitudes and behavior of employees in the workplace. In this study, this theoretical framework was used to clarify the interplay of variables that explain emotional support from supervisors, co-workers, and family members, work engagement, and mental well-being. An online self-response survey (N=325) was used to conduct quantitative and cross-sectional research. There was also a combination of simple random sampling, convenience sampling, and referral sampling. All variables were found to be correlated, and while perceived supervisor support was a significant predictor of all aspects of work engagement and mental well-being, family and co-worker support only predicted certain aspects of these variables. Self-reflection partially moderated the positive effects of certain emotional support on work engagement and mental well-being
Keywords: Co-worker Support; Emotional Support; Family Support; Mental Well-being; Perceived Supervisor Support; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; Work Engagement

LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE INFLUENCE ON EMPLOYEES’ ORGANIZATIONAL COMMITMENT UNDER THE PANDEMIC SITUATION - Sun Leung, Wai Chai (University of Saint Joseph, 2023)
The aim of this study is to investigate the influence of leadership styles and organizational cultures to employee’s organizational commitment under the pandemic situation in Macao. The dependent variables comprise of the three dimensions of organizational commitment. Among those three, affective commitment and continuance commitment are considered to be analyzed in this study. The leadership styles concept and organizational cultures are applied as the independent variables. The objectives are achieved using quantitative research method with questionnaires in Likert scale scores. The two significance reveals that laissez-faire leadership style had a positive relationship with continuance organizational commitment (H4) and innovative culture had a positive correlation with continuance organization commitment (H6). Such outcomes were extended to a qualitative study with qualitative approach on discourse analysis to explore the potential factor and a leadership discourse analysis was initiated. While the findings on influence of leadership and culture on organizational commitment is not a major concern for Macao employees in the pandemic situation, the significance of specific leadership style and culture rationalizes the transformation and status of Macao employees’ views towards leadership and employers’ perspective on organizational culture. The data collected in this study may also provide valuable resources for future study and training programs for the coming batch of employees in the coming new phase of Macao in entering the 2nd round of gaming licensing. Create the right leadership and culture for the organization to bring back the passion of Macao employees
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

SURVIVAL, MORPHOLOGY AND REPRODUCTION OF ENHALUS ACOROIDES (L.f.) ROYLE IN THE BOLINAO-ANDA REEF SYSTEM, NW PHILIPPINES: EFFECTS OF VARYING LIGHT CONDITIONS - Tagulao, Karen Araño (University of Saint Joseph, 2023)
Seagrasses play a critical role in coastal ecosystems worldwide, providing various ecosystem services based on their region and genus. In Southeast Asia, where seagrass biodiversity and extents are at their highest, the livelihoods and food security of many coastal communities depend on these plants. Despite their ecological and economic importance, seagrasses face global threats from human activities such as pollution and land use changes. Enhalus acoroides, a widely distributed seagrass species in the tropical Indo-Pacific region, is particularly valuable for coastal management and conservation efforts due to its size and provision of various ecosystem services. Although previous research has indicated that it is less sensitive to environmental changes than other tropical seagrass species, recent reports highlight its vulnerability to siltation and eutrophication. This dissertation aimed to examine how Enhalus responds and adapts to changes in light availability, taking into account both morphological adaptation and phenotypic plasticity. Field surveys, reciprocal transplantation field experiments, and investigations of sexual reproductive effort were conducted in the Bolinao-Anda Reef system (NW Philippines) to evaluate the impact of long-term environmental changes on Enhalus populations. The findings of this study revealed that Enhalus has the capacity to adapt its traits and survive changes in depth, light gradients, and different habitat types. This is evidenced by larger shoots in low-light environments, which is apparently a response to the reduction in light availability, as evidenced in both in situ and experimental setups. Larger leaf surface area in light-reduced setups also had higher concentration of chlorophylls a and b pigments. Transplants from light-reduced environments, although morphologically large, appeared more vulnerable (with low survival values) to environmental changes associated with translocation. Being morphologically large is therefore likely a stress response to light reduction, allocating more energy on light harvesting than sexual reproduction. Reciprocal transplantation experiments indicated a high survival rate, suggesting the potential of Enhalus for use in rehabilitation. However, despite having wider plasticity to adapt to light-limitation, they can be wiped out when threshold is reached. This thesis underscores the need for further research on Enhalus' response to stressors, genetic variation, and adaptive capacity to address conservation and management challenges
Keywords: Enhalus acoroides; Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph; light availability; phenotypic plasticity; seagrass; transplantation

融合班中特殊教育需求學生和普通學生共同學習的過程與效果﹕來自老師和家長的反饋 The Process and Effects of Collaborative Learning of Students in Inclusive Class: Voices from Teachers and Parents - Tam, Sin Leng (譚倩鈴) (University of Saint Joseph, 2023)

THE RELATIONSHIP BETWEEN PARENTING STYLES, ACADEMIC ACHIEVEMENT AND BEHAVIORAL PROBLEMS OF PRIMARY STUDENTS IN MACAO - Tang, I. Sam (University of Saint Joseph, 2023)
"Parenting styles may have various effects on children’s development and educational outcomes, particularly a relationship with behavioral problems and academic achievement. This study examines the relationship of between parenting styles, behavioral problems and academic achievement. A cross-sectional and questionnaire-design (Parenting Style Scale (Saunders et al., 2013); Strength and Difficulties Questionnaire (Goodman & Goodman, 2009; Goodman, 1999; Goodman, 1997)) study was used with a sample total of 98 parents with the eldest child of the family aged between six to twelve. Results of the findings are mainly inconsistent with the majority of literature. Indulgent and authoritative parenting are the predominant parenting styles, yet parenting styles does not relate to academic achievement. On the other hand, the correlation between behavioral problems, specifically prosocial behaviors and academic achievement are moderate. Furthermore, there is no difference between the type of behavioral problems according to gender. In further studies, a larger sample size, teachers and students as informants, and the inclusion of the analysis of other factors that could be influencing parenting styles, behavioral problems and academic achievement are suggested to be considered. "
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

UNITING - FRAGMENTED SPACES ARCHITECTURE CENTRALIZING HERITAGE INTERPRETATION - Un, Cheng Wai (University of Saint Joseph, 2023)
For many people, an art museum is a place to display artifacts, artworks, and the temporaryhistory of a community or country. It also advocates for an artist’s viewpoints on art. In fact,museum design is closely related to politics. The purpose for building a museum in a city is toexhibit information about the development of the local culture. Moreover, high culturalvalue land is usually built with museums displaying their heritage nearby, so that people canexplore and learn more about the local historical background and artifacts of the place.The abandoned Iec Long Firecracker Factory in Taipa Center, Macau has been on hold formany years and has also been used as a war game venue that resulted in scratches on thewalls of the dilapidated old heritage buildings. Recently, the Macau government has finalizedits plans for the revitalization of this local heritage site. Due to its dispersed layout andsurrounding landscape, there are some design constraints around the preservation of thisimportant heritage site. The design for high cultural value land should not only consider thepreservation and renovation of old buildings but also consider more ways to effectively usethe site as an important public venue for the city.For developing the methodologies of this project, several concepts and case studies wereanalyzed to extract ideas that can be referenced and to unveil strategies for designing apossible solution to this problem. This dissertation intends to create a model for developingand integrating architectural design into this heritage site and will study the spacearrangements for both the indoor space and the outdoor space within the concept of afragmented space integration. Fragmented space, means that a place is designed using adecentralized layout. This conceptualization of a design can preserves the original appearance of the cultural value of land and at the same time, the space can be used moreefficiently to create a circulation for the public to visit and enjoy the location
Keywords: Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph; articulation architecture; decentralized layout; functional museum; integration with architecture; spatial narrative

Neuronal Mechanisms of Behavioural Plasticity in the Peacock Blenny Salaria Pavo - Vieira, Pedro Cachapa (University of Saint Joseph, 2023)
"Adult neurogenesis, i.e., the production of new neurons in the adult brain, has been studied intensively in the past years, both in humans and in animal models, as the understanding of this process can have major clinical implications. The study of neurogenesis in fish has been receiving more attention as, unlike mammals, they possess remarkably high levels of adult neurogenesis and a high capability for neuronal regeneration and replacement where neuronal death has occurred. Less is known, however, on the importance of adult neurogenesis for behavioural plasticity, i.e., for the capacity to change behaviour according to context. As a product of the brain, behaviour relies on functional neuronal networks and it may be expected that more permanent changes in behavioural states imply structural reorganization of neuronal circuits, with the integration of new neurons. Interestingly, the high level of brain plasticity of fish is paralleled by a high degree of behavioural plasticity, with many examples of species that change, either reversibly or irreversibly, their behavioural phenotype during their lifetime, as illustrated by species with functional sex-change and alternative reproductive phenotypes. Flexibility in behaviour may thus require a reorganization of neuronal networks underlying these behaviours with recruitment of new neurons. In this thesis, the link between brain and behavioural plasticity was studied in a small marine fish that inhabits the Mediterranean and adjacent Atlantic coasts, the peacock blenny Salaria pavo. In this species, males adopt nests in rock crevices and attract females into the nest for egg laying, with the male taking care of the eggs until hatching. In some populations, a scarcity of nest sites drives smaller and young males to adopt an alternative reproductive tactic to reproduce. These “sneaker” males mimic the females’ morphology and reproductive behaviour in order to illude the larger nesting males and parasitically fertilize eggs during mating events. Sneaker males later transition into the nesting male phenotype, and this major behavioural transformation in the same animal, first courting males and afterwards courting females, may imply significant reorganization of brain areas associated with reproductive behaviour. During the study, a brain atlas for the species was developed and the main cell proliferation regions, i.e. niches of stem cells birth that may differentiate into cells of the nervous system, characterized. Proliferative areas were observed throughout the whole brain and paralleled the pattern described for other teleosts. Proliferative cells were abundant namely in areas like the olfactory bulbs (granular and glomerular), the anterior subdivision of the dorsomedial telencephalon (DMa), the dorsal and ventral part of the ventral subdivision of the dorsomedial telencephalon (DMvd and DMvv), the dorsal part of the dorsal subdivision of the dorsomedial telencephalon (DMdd), the posterior subdivision of the dorsolateral telencephalon (DLp), the posterior zone of the dorsal telencephalic area (DP), the preoptic area (POA), the dorsal, supracommissural and ventral nucleus of the ventral telencephalic area (Vd, Vs and Vv), the optic tectum and its periventricular grey zone (TeO and PGZ), the ventral zone of the periventricular hypothalamus (Hv), the cerebellum, mainly the molecular layer (CCeM) and the caudal lobe (LCa). A study of the brain nuclei activated during female courtship events using immediate early-genes suggested that some of the areas of the social behaviour network (SBN), a set of brain nuclei underlying the expression of social behaviour across vertebrates, are implicated in female courtship, in particular nuclei in the ventral telencephalic regions. This was followed by an experiment to investigate the possible link between cell proliferation and male tactic switch. Nest availability was manipulated to allow a fraction of sneaker males to adopt a nest and start the transition to nesting males. Ten days after the experiment, some of the smaller males had indeed started switching into nesting males, adopting a nest and starting to develop male secondary sexual characters. The pattern of brain proliferation was studied in these fish to try to confirm that the irreversible behavioural transition would be associated with the reorganization of brain nuclei, assuming that cell proliferation relates to neurogenesis and structural reorganization. Transitional males had elevated cell proliferation levels, as compared to males that remained sneakers, in the dorsolateral anterior and posterior telencephalic regions, thought to be homologous to the hippocampus in mammals. Cell proliferation levels were generally elevated in ventral and ventromedial telencephalic nuclei in both sneakers and transitional males, as compared with nesting males and females, areas considered to be homologous to nuclei of the amygdaloid complex of mammals. There was large variation in proliferation levels within transitional males, and in particular one male more advanced in the transition had higher numbers of BrdU-positive cells than the others. This suggests that a longer time-window for detecting the peak in brain cell proliferation associated with tactic transition in some fish may have been needed. Overall, the study supports the hypothesis that behavioural transition in males of this species is paralleled by an increase in cell proliferation in nuclei potentially relevant for the expression of reproductive behaviours, and establishes the peacock blenny as a new relevant model for the study of neuronal plasticity in vertebrates."
Keywords: Behavioural Plasticity; Neurogenesis; Peacock Blenny; Phenotypic Plasticity; Teleost Fish; Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph

THE EFFECTS OF TEACHER SELF-EFFICACY AND PERCEIVED AUTONOMY ON TEACHER WORK ENGAGEMENT: THE MEDIATING EFFECT OF PERCEIVED ORGANISATIONAL SUPPORT - Wan, Sok Leng (University of Saint Joseph, 2023)
The aims of the present study are to investigate the level of work engagement of the inclusive teachers in Macau and what potential factors would contribute to the increase of their level of work engagement. In this research, the framework of the self-determination theory developed by Ryan and Deci in 2000 was partially employed. I suggested the inclusive teachers’ self-efficacy and perceived autonomy to act as the independent variables, while perceived organisational support was involved as the mediating variable. Quantitative method was applied in this study by using an online self-response questionnaire (N= 150). The stratified sampling strategy was applied as well in order to ensure the representativeness. No gender difference of work engagement level was found among Macau inclusive teachers. Positive correlations were found among all variables. Besides, perceived organisational support was expressing positive mediating effects on the relationships between independent and dependent variables under some specific circumstances. For example, the relationship between efficacy to use inclusive instructions and emotional and physical work engagement; the relationship between perceived autonomy and cognitive, emotional, and physical work engagement. Theoretical and practical implications for the non-tertiary schools and inclusive teachers can be found in this study. Future studies should be continued to investigate the limitations and suggestions of this field of research
Keywords: PERCEIVED ORGANISATIONAL SUPPORT; TEACHER PERCEIVED AUTONOMY; TEACHER SELF-EFFICACY; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; WORK ENGAGEMENT

Impacts of Policies and Infrastructure on the Usage of Electric Vehicles in Macao - Weng Chi Lei; Tai, On Teng (2023)
Publisher: Unpublished

Study on User Acceptance on Customer Behavior for Online Payment in Macau: MPAY Case Study - Wong, Chi Cheng (University of Saint Joseph, 2023)
With the rapid expansion of mobile e-commerce, an increasing number of businesses have jumped into the fray in all facets of the mobile electric commerce industry chain. The payment link is the most competitive. From the norm in the sector to the consumer market, telecom operator rivalry, as well as third-party payment between different companies, never ceases. In the context of mobile e-commerce, however, competition has shifted from traditional product-centered to customer- centered, and business success frequently rests on the customer. As a result, the competition in the mobile e-commerce payment industry is essentially about competing for users. Mpay is characteristic of mobile e-commerce payment firm representatives; on the basis of theoretical analysis, combined with the reality of the economic background, the study chose Mpay mobile payment users as research subjects and analyzed the major variables of user acceptability. The model was built on the basis of an extensive evaluation of past research results of user acceptance model and reference to UTAUT model. The model considered performance expectancy, effort expectancy, and social influence, facilitating condition as independent variables determining user behavior intention, Based on the conceptual model, the paper conducted an empirical investigation as a case study of a Mpay mobile payment user using data from a questionnaire, while also conducting a separate discussion of the impact of perceived risk and trust on user acceptance. The empirical results indicate that for mobile payment users, performance expectancy has the greatest positive effect on behavior intention, while facilitating conditions, social influence, perceived risk, effort expectancy, and trust have no effect. In addition, gender and age were discovered to influence user acceptance
Keywords: Online mobile payment; SmartPLS; Thesis and Dissertations Master of Business Administration (MBA); UTAUT model; University of Saint Joseph; user acceptance

PROJECT MANAGEMENT ADOPTION AND MATURITY LEVEL IN INFORMATION TECHNOLOGY INDUSTRY OF MACAU AND HENGQIN - Wong, Ka Seng (University of Saint Joseph, 2023)
Projects are tactical and operational initiatives, and achieving specific outcomes through projects can help organizations achieve strategic goals. The effective use of project management tools and techniques is essential to achieve successful results, since the goal is to maximize the realization of the project's plan by effectively using the budget, time, and resources provided by the project owner to achieve the project's original purpose. The Project Management Maturity Model (PMMM) is a tool for measuring project management capabilities and is essential to improve project and portfolio performance in different industries. The main objective of this research is to analyze and characterize the maturity level and capacity of the IT industry in Macau and HengQin based on the assessment of the PMMM. The research also aims to assess and compare the maturity level in the IT industry in Macau and HengQin. An online survey was conducted and sent to IT project managers from Macau and HenqQin. A total of 34 responses were collected, divided into 3 different parts: Part I - General Information, Part II - Project Management Areas, and Part III - Perception. The results indicate that, in general, Project Managers state that their companies do not follow Project Management standards and best practices, classifying as Low and Very Low essential PM areas such as Planning and Scheduling (68%), Scope (61%) and Communications (64%). From a comparison perspective, project managers in Macau follow less formal frameworks than Hengqin in managing the triple constraints of the project. The collected data also indicate that Macau's communication management and stakeholder engagement are less mature than Hengqin's. Furthermore, the data indicate that maturity level is not necessarily related to education level, which means not higher education has a higher maturity level. Recommendations are provided for the IT industry in both areas, and specific comments are provided for each group or professionals. In conclusion, this work allows a novel characterization and a better understanding of the Project Management adoption and maturity level of the IT Industry in Macau and Hengqin
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; information technology; maturity level; project management; project management maturity model; project maturity assessment

Exploratory Analysis of Project Management Adoption and Maturity Level of IT Companies–A Comparison between Macao and Hengqin - Wong, Ka Seng; Lobo Marques, João Alexandre (Journal of Advanced Management Science, 2023)

自閉譜系障礙之兒童透過即興劇表達社會情感之個案研究 =: A case study on using drama improvisation as a social emotional intervention for a child with ASD - Wong, On Na; Ho, Ka Lee Carrie (University of Saint Joseph, 2023)
"Abstract The core concept of drama education is the integration and int- ernalization of experience. In the empirical content of the improvis- ational drama, it lays a profound foreshadowing for future life prac- tice through different physical behaviors and facial perceptions. Through drama education, children with autism spectrum disorder can be emotionally adjusted. Emotional and social behavior is essent- ial for children with autism spectrum disorders. The use of improvis- ational drama to study children's emotions with autism spectrum diso- rders is not yet found in Macau. Therefore, this study aimed to inve- stigate the intervention strategies for children with autism spectrum disorders through improvisational drama to fill the research gap. A case study of emotional interventions as a ten-day improvisa- tional drama with an autism spectrum disorder in Macau. The following findings were obtained: 1. The study found that improvisational drama was used to address the theoretica deficits of the mind of children with autism spectrum disorders. 2. Improvisational drama supports the understanding of self-emotions in children with autism spectrum disorder with positive behavior. 3. Shared attention cultivated by improvisational drama can develop social interaction behavior. 4. The improvisational drama techniques can deal with children with autism spectrum disorder and peer conflict. Based on these results, the researcher identified three main is sues in the use of improvisational drama to deal with the emotions of VII children with autism spectrum disorders in Macau: 1. The relative lack of knowledge on the use of improvisational drama as a strategy to support children with autism in Macau. 2. The number of hours and sessions of the Macao training course is too small to be satisfied with frontline teachers' use of improvi- sational drama to provide quality teaching to children with an au- tism spectrum disorder. 3. Failing to understand the emotional needs of children with autism frontline teachers must practice improvisational drama teaching, failing to understand it’s core subjects in depth. Therefore, researchers on the emotions of children with an aut- ism spectrum disorder in improvisational drama. The proposal is divi- ded into three main areas, which are proposed to the government, sch- ools, and teachers: I. Suggestions to the government: 1. Improve the special education policy 2. Increase the number of training courses II. Suggestions for schools: 1. Increase the teaching content of the curriculum for children wi- th autism spectrum disorders III. Suggestions for teachers: 1. Children should lead the curriculum with autism spectrum disord- ers. 2. The curriculum should enhance the cooperation between children VIII with autism spectrum disorders and their peers. This study has identified feasible intervention strategies to he- lp further improve the Macau government's special education policy. The study also aims to help schools to adapt their teaching cont- ents better to suit the needs of children with autism spectrum disord ers. Finally, the study aims to provide teachers with a better unders- tanding of the characteristics and social-emotional behaviors of ch- ildren with autism spectrum disorders to help each other practice education effectively. Only one child with autism spectrum disorder were studied in Mac- ao. As a result, this study failed to represent all children in Macao in practicing emotional interventions in improvisational drama. This study aimed to promote -improvisational comedy strategies in Macau to help children with aut-ism spectrum disorders to understand and expre ss their emotions appr-opriately. It is also expected that the Macau SAR government will re-cognize the importance of drama education for children with autism spectrum disorders and develop policies and ada- pt the content of the curriculum framework to enable the effective i- mplementation of drama education in teaching emotions to children wi- th autism spectrum disorders."
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 即興戲劇; 情緒; 戲劇教育; 自閉譜系障礙兒童

Evaluating the Acceptance of Portuguese Residents Towards Chinese Electric Vehicles: the Role of the Country-of-Origin Effect - Xian, Si Tong (University of Saint Joseph, 2023)
This study identifies Portuguese residents’ behavioural intention towards Chinese electric vehicles from the perspective of the Country-of-Origin Effect (COE) and uses the Unified Theory of Acceptance and Use of Technology 2 (UTAUT-2) as a guide to design interview questions. According to the existing literature, UTAUT-2, a comprehensive technology acceptance model, has not been used to assess the Portuguese electric vehicle market, and no relevant research has been found to apply the method of combining the COE into the UTAUT-2 framework. The purpose of this study is exploratory in nature, it uses qualitative methods to identify the behavioural intention of Portuguese residents towards the acceptance of Chinese electric vehicles. Data from 16 Portuguese residents was collected through semi-structured interviews and analyzed with qualitative methodology. The study found that factors such as performance expectations, environmental concerns, effort expectations, hedonic motivation, and social influence have a positive impact on Portuguese residents' purchase of electric vehicles, while price value, habits, and convenience conditions have a neutral or negative impact. Regarding COE, apart from social influence, it has no impact on other factors. To increase the popularity and sales of Chinese electric vehicles in Portugal, it is recommended that advertising and marketing efforts focus on price, charging services, after-sales service, and design
Keywords: Consumer Behavior; Country of Origin Effect; Electric Vehicles; Environmental Awareness; Portugal; Sustainability; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A review on multimodal machine learning in medical diagnostics - Yan, Keyue; Li, Tengyue; Marques, João Alexandre Lobo; Gao, Juntao; Fong, Simon James; Yan, Keyue; Li, Tengyue; Marques, João Alexandre Lobo; Gao, Juntao; Fong, Simon James (Mathematical Biosciences and Engineering, 2023)
Nowadays, the increasing number of medical diagnostic data and clinical data provide more complementary references for doctors to make diagnosis to patients. For example, with medical data, such as electrocardiography (ECG), machine learning algorithms can be used to identify and diagnose heart disease to reduce the workload of doctors. However, ECG data is always exposed to various kinds of noise and interference in reality, and medical diagnostics only based on one-dimensional ECG data is not trustable enough. By extracting new features from other types of medical data, we can implement enhanced recognition methods, called multimodal learning. Multimodal learning helps models to process data from a range of different sources, eliminate the requirement for training each single learning modality, and improve the robustness of models with the diversity of data. Growing number of articles in recent years have been devoted to investigating how to extract data from different sources and build accurate multimodal machine learning models, or deep learning models for medical diagnostics. This paper reviews and summarizes several recent papers that dealing with multimodal machine learning in disease detection, and identify topics for future research.
Cc_license_type: cc_by Number: mbe-20-05-382 Primary_atype: Mathematical Biosciences and Engineering Subject_term: Review Subject_term_id: Review

Hierarchical Medical Classification Based on DLCF - Yao, Mingyuan; Sun, Haoran; Liang, Shengbin; Shen, Yanqing; Yukie, Niki (Computer and Information Science, 2023)
Medical classification is affected by many factors, and the traditional medical classification is usually restricted by factors such as too long text, numerous categories and so on. In order to solve these problems, this paper uses word vector and word vector to mine the text deeply, considering the problem of scattered key features of medical text, introducing long-term and short-term memory network to effectively retain the features of historical information in long text sequence, and using the structure of CNN to extract local features of text, through attention mechanism to obtain key features, considering the problems of many diseases, by using hierarchical classification. To stratify the disease. Combined with the above ideas, a deep DLCF model suitable for long text and multi-classification is designed. This model has obvious advantages in CMDD and other datasets. Compared with the baseline models, this model is superior to the baseline model in accuracy, recall and other indicators.
Keywords: Dual channel; Hierarchical classification; LSTM-CNN; Medical classification; RF

Occurrence and precipitation mechanism of silver in pyrite from chimney fragments in the Edmond hydrothermal field, Central Indian Ridge - Zhang, Huichao; Chen, Kean; Tao, Chunhui; Alveirinho Dias, Ágata; Liang, Jin; Yang, Weifang; Liao, Shili; An, Fang; Yin, Bohao; Sun, Chuanqiang (Ore Geology Reviews, 2023)

將CRA教學法融入澳門小學融合班數學課程 之行動研究-以二年級兩位數減法單元為例 =: An Action Study of Integrating Concrete-to-Representational-to-Abstract (CRA) into the Mathematics Learning of Integrated Classes in Macao Primary Schools - Taking the Two-digit Subtraction Unit of Grade 2 as an Example Concrete-to-Representational-to-Abstract (CRA) - Zhuang, YanYan (University of Saint Joseph, 2023)
Keywords: CRA教學策略; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 兩位數减法; 小學數學課程; 融合生; 行動研究

Visuality and Infrastructure: The Case of the Belt and Road Initiative - Zuev, Dennis (The Palgrave Handbook of Globalization with Chinese Characteristics, 2023)

A Christmas present worth having - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | When the casino resorts applied for the first licenses to operate in Macau, one of the commitments that they made was to serve the Macau society. Many of them have honoured those commitments outstandingly well, and continue to do so, and in ways too many and diverse to list here.
Section: Macau Business

Consumers' Adoption of Molecular Chinese Medicine (MCM) in Macau: A Value-based approach - Hong, Chi Kit; Lampo, Alessandro (Proceedings of the 17th International Conference of the Academy of Global Business Research and Practice (AGBRP 2022), 2022)
Molecular Chinese Medicine (MCM) is a recent method of manufacturing and dosing prescriptions that brings several advantages when compared with Traditional Chinese Medicine (TCM). For instance, MCM is highly dissoluble, tastes better than the usual decoction, and the active principles are easily absorbed. Also, the manufacturing process is subject to better quality control. In spite of these benefits, consumers' intentions remain unclear due to the novelty of this technique. Therefore, an assessment of individuals' perceptions is relevant since molecular medicine is redefining how scientists understand and treat diseases, and it can be considered a medical innovation. To fill the research gap, the Value-based Acceptance Model (VAM) (Kim et al., 2007) is used to assess the individuals' perceptions of value and intention to accept MCM. Data from a sample of Macau residents are analyzed by means of structural equation modeling (SmartPLS). The results support the use of the model in our context, thus extending the applicability of the VAM to other settings. Except for 'technicality', the constructs of 'usefulness', 'enjoyment', and 'perceived fee' had a significant impact on the overall 'perceived value' of MCM, and in turn on the behavioral intention to use the innovation. To facilitate the diffusion of this dosage method in the marketplace, it is suggested that communications strategies consider the proposed sources of value when promoting MCM. To further explain the adoption process, it is recommended to include additional factors that may affect consumers' intention to adopt the innovation and extend the analysis to the actual usage.
Best Research Paper Award: https://www.usj.edu.mo/en/news/fbl-student-hong-chi-kit-and-prof-alessandro-lampo-received-the-best-research-paper-award-at-the-17th-international-conference-of-agbrp/

No reino dos sentidos - Simões, José Manuel (Aspectus. Revista de Arte & Ciência, 2022)
José Manuel Simões

A Model of Integrating Bert and BiGRU+ Attention Dual-channel Mechanism for Investor Sentiment Analysis of Stock Price Forecast - Ma, Huawei; Ma, Jixin; Liang, Shengbin; Du, Wencai (2022 IEEE/ACIS 23rd International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD), 2022)

Emotional Intelligence, Work Satisfaction, and Affective Commitment: An Occupational Health Study of Social Workers - Kuok, A. C. H. (Journal of Work and Organizational Psychology, 2022)
Social workers’ work engagement and burnout were tested in relation to (a) personal variable, i.e., emotional intelligence; (b) organizational variables, i.e., work satisfaction and affective commitment. Regressions revealed emotional intelligence - controlling self – negatively predicted depersonalization and reduced personal accomplishment and positively predicted three facets of work engagement. Emotional intelligence - understanding others – was a negative predictor of reduced personal accomplishment. In addition, work satisfaction negatively predicted three components of burnout and positively predicted emotional work engagement. Affective commitment was a positive predictor of three facets of work engagement and negatively predicted reduced personal accomplishment. Implications for management are discussed.
Company: Colegio Oficial de Psicologos de Madrid (copmadrid) Distributor: Colegio Oficial de Psicologos de Madrid (copmadrid) Institution: Colegio Oficial de Psicologos de Madrid (copmadrid) Label: Colegio Oficial de Psicologos de Madrid (copmadrid) Publisher: Colegio Oficial de Psicologos de Madrid Section: research-article

Jornalismo e Qualidade no Mundo de Expressão Portuguesa - Camponez, Carlos; Simões, José Manuel; Christofoletti, Rogério (University of Saint Joseph, 2022)
"Jornalismo e Qualidade no Mundo de Expressão Portuguesa"propõe uma análise sobre a paisagem do jornalismo nos oitopaíses de língua oficial portuguesa - Portugal, Angola, Brasil, Cabo Verde, Moçambique, Guiné-Bissau, São Tomé e Príncipee Timor-Leste - e na Região Autónoma Especial de Macau. Olivro é uma reflexão sobre a legislação, o plano jurídico-constitucionalque enquadra os media no espaço lusófono, os contextosde mercado, as especificidades inscritas em fatoreshistóricos e económicos, em percursos políticos, bem comosobre as relações entre os media e os jornalistas e estes e opoder regulador do Estado.Os trabalhos reunidos nesta obra escrita por autores que partilhamentre si um dos idiomas mais falados do planeta, mostram as diferentes realidades do jornalismo no espaço dalíngua portuguesa, nomeadamente as suas redes de conhecimento, de empenho na promoção da qualidade da informação, de intercompreensão entre povos e culturas, de novas einovadoras formas de parcerias sociais com vista à partilha e àconstrução de mundividências.

澳門課程改革與發展: 政策與實務 - Ge, Yun (2022)

A Model of Integrating Bert and BiGRU+ Attention Dual-channel Mechanism for Investor Sentiment Analysis of Stock Price Forecast - Ma, Huawei; Ma, Jixin; Liang, Shengbin; Du, Wencai (2022 IEEE/ACIS 23rd International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD), 2022)
Investor sentiment and emotions have a strong impact on financial markets. In recent years there has been increasing interest in analyzing the sentiment of investors for stock price prediction using machine learning. Existing prediction models mostly depend on the analysis of trading data and company profit. few prediction theories have been built based on individual investors' sentiments. The fundamental reason is the difficulty to measure individual investors' sentiment.
ISSN: 2693-8421

Investigation on citizen trust towards e-government services in GBA – A study on WeChat and Alipay government service mini-programs - Lai, Chimeng; Joao, Alexandre Lobo Marques (2022 13th International Conference on E-business, Management and Economics, 2022)
Citizens' trust in eGovernment is crucial for the successful implementation of new electronic services. This relationship in the Greater Bay Area (GBA) plays an essential role since the Government services rely on mobile mini-programs This study investigates the trust towards government service mini-programs in WeChat and Alipay. A user feedback questionnaire was designed, and a total of 609 valid samples were collected from Shenzhen, Guangzhou, Hong Kong, and Macau. The findings imply that competence, integrity, and benevolence are the key components of trust in e-government (TIEG). TIEG positively influences perceived value (PV), which positively affects citizens' Intention to adopt service mini-programs. PV significantly mediates the relationship between TIEG and Intention. Although TIEG does not effectively reduce perceived risk (PR), risk issues cannot be ignored in the adoption process. Finally, this article proposes relevant implications and suggestions for the GBA government agents and policy makers.
0 citations (Crossref) [2023-03-15]

How Social Influence and Image Impact on the Intention to Use a Technology: A Study from the Battery Electric Vehicle Domain - Lampo, Alessandro; Silva, Susana C. (2022 13th International Conference on E-business, Management and Economics, 2022)
Technology research offers several theories and models to explain how individuals accept and use technology innovations. While these often focus on the technical aspects of the innovation, they tend to downplay the affective component of technology. Recognizing that the adoption of technology is also determined by what it means and represents to the users, this paper aims to fill the gap in the literature by studying the effects of social influence and image on the behavioral intention to adopt a technology. We used structural equation modeling (SmartPLS) to analyze data collected from 238 self-administrated surveys regarding the behavioral intention of Macau residents to use battery electric vehicles. The result showed significant relationships among the variables in the model and depicted the construct of image as a strong factor in the adoption decision. Our findings suggest that social influence may not exhibit substantial impact in the case of innovations in their initial phase and, more importantly, the construct of image could be included as a key predictor of behavioral intention in technology acceptance models, particularly in contexts where the choices that consumers make are public, and therefore subject to judgments from the members of the community.
Best Oral Presentation Award: https://www.usj.edu.mo/en/news/dr-alessandro-lampo-receives-best-oral-presentation-award-at-the-iceme-2022/
Keywords: Battery Electric Vehicles; Image; SmartPLS; Social Influence; Technology Acceptance

Economic Integration in the GBA: a Price-Based Assessment of Real and Financial Integration in the Greater Bay Area - Lei, Weng Chi; Wang, Xinru (2022 13th International Conference on E-business, Management and Economics, 2022)
The Guangdong-Hong Kong-Macau Greater Bay Area (GBA) was first conceptualized in 2016, which aimed to facilitate trade and finance liberalization among the three regions. The trade and financial environment of the GBA is unique. Due to the “one country, two systems” principle, Mainland China, Hong Kong and Macau are considered to be trading partners bounded by WTO rule, but bilateral free trade agreements have been signed between Mainland China and Hong Kong, and between Mainland China and Macau, but not between Hong Kong and Macau. Furthermore, each of the three regions circulates a local currency subject to its own exchange rate policy, with Hong Kong Dollar and Macau Pataca currently pegged to the US Dollar. These affect the mobility of trade and capital flows in the area. Hence, this paper applies the widely-used price-based approach due to Cheung et al. [5] to analyze the degrees of real and financial integration in the GBA based on interest rates, exchange rates, and price indexes data from January, 2016 to November, 2021. The real interest differential (RID), uncovered interest differential (UID) and the deviation from purchasing power parity (PPD) between each regional pair have means that are statistically and economically close to zero, implying high real and financial integration in the GBA. The unit root tests for stationarity also confirm that the time series are mean-reverting, so the economic integration in the GBA in the long run is foreseeable.
0 citations (Crossref) [2023-03-15]
Keywords: Economic development policy; Economic integration; Financial Integration; Greater Bay Area

The future of Cosmetics Advertisement Strategy: A Neuromarketing Study using Electrodermal Activity (EDA) as a measure of Emotional Arousal - Neto, Andreia; Lobo Marques, Joao Alexandre (2022 13th International Conference on E-business, Management and Economics, 2022)
Neuromarketing lies at the intersection of three main disciplines: psychology, neuroscience, and marketing, and it has been a successful neuroscientific approach for the study of real-life choices such as consumer behavior [1]. A current gap in the cosmetics field is the lack of published research studies, considering the marketing investment done yearly in this category. With the rapid economic expansion and the rise of social media in China, consumers' interest in beauty is growing. Even though the Chinese cosmetics sector is rapidly expanding, no studies have been done with Chinese consumers. This study aims to employ the same approach as previously done in consumer neuroscience studies to evaluate cosmetic brands' marketing strategy to understand better if immediate emotional responses can be measured using Electrodermal Activity (EDA). Here, we focus on cosmetics products advertisement as a model to understand consumer preference formation and choice. Eighteen Chinese female consumers were recruited between 19 and 37 years old. From the results obtained, it was understood that none of the participants have voted for the product advertisement for which they showed higher emotional arousal. However, it appears that the participants' preference is for the products for which the brand awareness is stronger since the product advertisements with more votes are the ones for the Korean brand used. The product advertisements with Asian faces were the ones with more votes, suggesting that Asian faces have engaged consumer preference. However, the product advertisements for the Brazilian brands, unknown to the Chinese public, were the ones with fewer votes, although, those product advertisements were the ones with more emotional arousal per minute. Those advertisements were also those with non-Asian faces, suggesting that this feature influenced voting decisions. From this study, it has been observed that Electrodermal Activity is a measure of emotional arousal that by itself cannot be translated into consumer engagement. Therefore, it is also proposed to evaluate brand awareness in future studies related to product advertisements. The physical features of the people included in the advertisements is also suggested to be further evaluated in future studies since a different cultural background seems to influence the consumers' engagement. Furthermore, using EDA to complement other neurophysiological tools like facial expression analysis is also suggested for future studies to have evidence about the nature of the emotions raised.
Keywords: advertisement; consumer behavior; consumer neurosciences; cosmetics; marketing; neuromarketing

Entrepreneurial Process of SMEs in Macau - Phillips, Jenny O. L.; Oliveira, Nelio (2022 13th International Conference on E-business, Management and Economics, 2022)
In recent years, entrepreneurship and innovation have been highly propagandised for Macau's economic development, diversification, and the Greater Bay Area (GBA). Since 2013, efforts have been exerted by the Macau government to encourage and support entrepreneurship, from the launching of the Young Entrepreneurs' Aid Scheme in 2013 and the Macau Young Entrepreneur Incubation Centre in 2015. While the failure rate of startups has been considered high in most parts of the world, the rate was only as low as 14% in Macau, with many businesses created every year. This research aims to study the unique entrepreneurial environment for small-to-medium enterprises (SMEs) starting up in Macau from the experience of local entrepreneurs who are benefactors of government support. In-depth interviews were conducted to understand the experience and perceptions of these entrepreneurs as they go through each stage of the entrepreneurial process. Existing research on entrepreneurial processes varies from the two-stage process, which focuses on the beginning of an enterprise, to the different models of various stages from ideas generation to exit or long-term development. From the consolidation of the literature on the entrepreneurial process, five key stages were taken to guide this qualitative research. Findings suggested that idea validation at the start of the entrepreneurial process is almost non-existent amongst our research subjects. Yet it does not affect the implementation and growth of these SMEs. The growth strategies tend to be steady and for the long term, with most SMEs having no consideration of an exit plan.
0 citations (Crossref) [2023-03-15]
Keywords: Economic diversification; Entrepreneurial process; Government entrepreneurship aids

The Application of Nudge Theory in Ensuring Change Acceptance in the Hospitality-Gaming Industry – A Case Analysis from Macau SAR, China - Tagulao, Thea Clarice Saavedra; Marques, Joao Alexandre Lobo (2022 13th International Conference on E-business, Management and Economics, 2022)
As the rate of change increases exponentially, organizations must adapt quickly to the business landscape's volatility, uncertainty, complexity, and ambiguity (VUCA). As a result, organizations must implement agile strategies and practices to ensure their responsiveness and readiness to any changes brought about by internal or external factors. With a greater number of changes, change agents are tasked with implementing various change management methodologies to ensure that change recipients accept change initiatives. This research will look at one of the methodologies used by change agents, the use of nudges from Thaler and Sunstein's Nudge Theory, which is a subtle intervention to influence an individual's decision-making with the goal of steering them towards a specific desired outcome; and analyze their effectiveness towards the change recipients when implemented. Change agents were interviewed on the application of Nudge Theory to change recipients when managing to change initiatives within their respective organizations. The results indicate that the use of nudges created by the change agents can significantly impact the level of resistance from the change recipients. If used correctly, the Nudge Theory can mitigate change resistance, and the success of a change initiative is higher. But, if change recipients are forced to comply, their resistance will be greater, affecting the organization overall.
0 citations (Crossref) [2023-03-15]
Keywords: Change Initiatives; Change Resistance; Nudge Theory; Organizational Behavior; Organizational Change Management

A contribution to Paulo Freire’s theory and practice: The ‘Cultural Extension Service/University of Recife’ (1962–64) - Gerhardt, Heinz Peter (Educational Philosophy and Theory, 2022)
This contribution to the special issue is an historical account of Paulo Freire’s pedagogical and administrative praxis before his forced exile in 1964. It relies on interviews collected during a field trip in 1976, a conversation with Paulo Freire in Geneva one year later and on the secondary literature up to date. Being the head of the first Extension Service of a major Brazilian university in the early 1960s gave Freire and his collaborators the space and time to experiment with the today world famous literacy method bearing his name. The concept of ‘Field of Cultural Production’ (Bourdieu) is used to elucidate better Freire and his team’s avant-gardist production within the spaces opened up by Brazil’s popular movements in the early sixties. The contribution shows how the ‘Paulo Freire System’ developed in the praxis of a cultural movement and received its academic consecration in an incremental and eclectic style.
Publisher: Routledge _eprint: https://doi.org/10.1080/00131857.2022.2129007
Keywords: Bourdieu; Brazil; Paulo Freire; University of Recife; extension service; literacy

Histórias do Brasil de 1550: Bispo Sardinha assado na brasa | José Manuel Simões - Incomunidade, Revista (InComunidade, 2022)
HISTÓRIAS DO BRASIL DE 1550: BISPO SARDINHA ASSADO NA BRASA Recostado na sua poltrona de madeira maciça, forrada a veludo grená, Mem de Sá decidiu autorizar um combate de vingança contra os índios que tinham esquartejado e comido assado o bispo Sardinha. O objetivo seria apanhá-los para os forçarem a trabalhar nas plantações de cana-de-açúcar, mas os soldados, na ânsia do desforço, dispararam sem descrição. Dos 12 mil catecúmenos das terras do extremo Norte da Paraíba sobraram pouco mais de mil. O fidalgo, nascido em 1500, tinha sido nomeado Governador-Geral do Brasil para pacificar a colónia, meter água […]

Examining the impact of behavioral factors on the intention of adopting E-government services: An empirical study on the hard-to-reach groups in Macao SAR, China - Iong, Kit Yeng; Phillips, Jenny O. L. (Technology in Society, 2022)
In government studies, electronic government has become a hot topic in recent decades. Many scholars believe that soon, the government might not be able to operate smoothly without the help of ICTs as the Internet has been overwhelming people's daily lives already. In analyzing people's behavioral factors towards adopting e-government services, most studies targeted the adult population, while those in the hard-to-reach groups are minimal. This study was designed especially to understand the behavioral factors of the younger generation aged between 18 and 24 and the senior citizens above 60 on their adoption of e-government services in Macao SAR. Sixteen in-depth interviews were conducted based on the semi-structured interview questions developed from the prior literature on the Theory of Planned Behavior and e-government studies. Six significant findings are yielded, which could serve as an important reference for policymakers designing e-government policy and promoting its implementation strategy. These behavioral factors also contribute empirical data to support the theoretical framework of TPB in the context of Macao SAR e-government services.
0 citations (Crossref) [2022-09-21]
Keywords: Electronic government; Hard-to-reach groups; In-depth interviews; The theory of planned behavior

Career Planning of Doctoral Students in Macau: Linking Individual Experience to Macro Picture - Ge, Yun (2022)

Developing Neuromarketing Innovative Research - Lobo Marques, J. A. (2022)

Hydrothermal remobilization of subseafloor sulfide mineralization along mid-ocean ridges contributes to the global oceanic zinc isotopic mass balance - Liao, Shili; Tao, Chunhui; Wen, Hanjie; Yang, Weifang; Liu, Jia; Jamieson, John W.; Dias, Ágata Alveirinho; Zhu, Chuanwei; Liang, Jin; Li, Wei; Ding, Teng; Li, Xiaohu; et al. (Geochimica et Cosmochimica Acta, 2022)
Hydrothermal activity on mid-ocean ridges is an important mechanism for the delivery of Zn from the mantle to the surface environment. Zinc isotopic fractionation during hydrothermal activity is mainly controlled by the precipitation of Zn-bearing sulfide minerals, in which isotopically light Zn is preferentially retained in solid phases rather than in solution during mineral precipitation. Thus, seafloor hydrothermal activity is expected to supply isotopically heavy Zn to the ocean. Here, we studied sulfide-rich samples from the Duanqiao-1 hydrothermal field, located on the Southwest Indian Ridge. We report that, at the hand-specimen scale, late-stage conduit sulfide material has lower δ66Zn values (−0.05 ± 0.15 ‰; n = 19) than early-stage material (+0.13 ± 0.15 ‰; n = 10). These lower values correlate with enrichments in Pb, As, Cd, and Ag, and elevated δ34S values. We attribute the low δ66Zn values to the remobilization of earlier sub-seafloor Zn-rich mineralization. Based on endmember mass balance calculations, and an assumption of a fractionation factor (αZnS-Sol.) of about 0.9997 between sphalerite and its parent solution, the remobilized Zn was found consist of about 1/3 to 2/3 of the total Zn in the fluid that formed the conduit samples. Our study suggests that late-stage subsurface hydrothermal remobilization may release isotopically-light Zn to the ocean, and that this process may be common along mid-ocean ridges, thus increasing the size of the previously identified isotopically light Zn sink in the ocean.
Keywords: Hydrothermal activity; Mid ocean ridge; Subsurface remobilization; Zinc isotopic mass balance

A dose of lateral thinking - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | The late psychologist, business and management consultant Edward de Bono gained a worldwide reputation for ‘lateral thinking’, which included his ‘six thinking hats’ and ‘tools for thinking’. Though his work is arguably only plausible pseudoscience, his ‘tools for thinking’ remain interesting. Consider some of these from his Cognitive Research Trust (CoRT), in approaching planning, e.g.: CAF (Consider All Factors); EBS (Examine Both Sides); and OPV (consider Other People’s Views). Here I apply them to Macau.
Section: Macau Business

Behavioural and endocrine responses to non-interactive live and video conspecifics in males of the Siamese fighting fish - Alex, Deepa; Cardoso, Sara D; Ramos, Andreia; Gonçalves, David (Current Zoology, 2022)
The physiological mechanisms underlying variation in aggression in fish remain poorly understood. One possibly confounding variable is the lack of standardization in the type of stimuli used to elicit aggression. The presentation of controlled stimuli in videos, a.k.a. video playback, can provide better control of the fight components. However, this technique has produced conflicting results in animal behaviour studies and needs to be carefully validated. For this, a similar response to the video and an equivalent live stimulus needs to be demonstrated. Further, different physiological responses may be triggered by live and video stimuli and it is important to demonstrate that video images elicit appropriate physiological reactions. Here, the behavioural and endocrine response of male Siamese fighting fish Betta splendens to a matched for size conspecific fighting behind a one-way mirror, presented live or through video playback, was compared. The video playback and live stimulus elicited a strong and similar aggressive response by the focal fish, with a fight structure that started with stereotypical threat displays and progressed to overt attacks. Post-fight plasma levels of the androgen 11-ketotestosterone were elevated as compared to controls, regardless of the type of stimuli. Cortisol also increased in response to the video images, as previously described for live fights in this species. These results show that the interactive component of a fight, and its resolution, are not needed to trigger an endocrine response to aggression in this species. The study also demonstrates for the first time in a fish a robust endocrine response to video stimuli and supports the use of this technique for researching aggressive behaviour in B. splendens.

Attentive recurrent adversarial domain adaptation with Top-k pseudo-labeling for time series classification - He, Qi-Qiao; Siu, Shirley Weng In; Si, Yain-Whar (Applied Intelligence, 2022)
The key challenge of Unsupervised Domain Adaptation (UDA) for analyzing time series data is to learn domain-invariant representations by capturing complex temporal dependencies. In addition, existing unsupervised domain adaptation methods for time series data are designed to align marginal distribution between source and target domains. However, existing UDA methods (e.g. R-DANN Purushotham et al. (2017), VRADA Purushotham et al. (2017), CoDATS Wilson et al. (2020)) neglect the conditional distribution discrepancy between two domains, leading to misclassification of the target domain. Therefore, to learn domain-invariant representations by capturing the temporal dependencies and to reduce the conditional distribution discrepancy between two domains, a novel Attentive Recurrent Adversarial Domain Adaptation with Top-k time series pseudo-labeling method called ARADA-TK is proposed in this paper. In the experiments, our proposed method was compared with the state-of-the-art UDA methods (R-DANN, VRADA and CoDATS). Experimental results on four benchmark datasets revealed that ARADA-TK achieves superior classification accuracy when it is compared to the competing methods.
Keywords: Adversarial training; Attentive; Domain adaptation; Pseudo-labeling; Time series classification

Understanding of base-10 concept and its application: a cross-cultural comparison between Japan and Singapore - Marcruz, Ong Yew Lee; Carrie, Ho Ka Lee; Manabu, Kawata; Mayumi, Takahashi; Kumpei, Mizuno (International Journal of Early Years Education, 2022)
It has become increasingly clear that the early use of decomposition for addition is associated with later mathematical achievement. This study examined how younger children execute a base-10 decomposition strategy to solve complex arithmetic (e.g. two-digit addition). 24 addition problems in two modalities (WA: Written Arithmetic; OA: Oral Arithmetic) with sums less than 100 were administered to 22 Japanese and 22 Singaporean 6-year-old kindergarteners. Our findings reveal that they were able to solve complex addition. For instance, Japanese kindergarteners tended to solve complex arithmetic using base-10 decomposition across the modality, whereas Singaporean kindergarteners used standard algorithms and basic counting to solve complex WA and OA problems, respectively. We speculate that Japanese kindergarteners might have a clearer understanding of the base-10 concept and were able to use this knowledge more readily than Singaporean kindergarteners. Mathematical experiences in kindergarten and number-naming systems have been put forward as two of the crucial contributors for such cross-cultural differences. This study also provides new directions for future research on the understanding of the base-10 concept and its application among young children.
Publisher: Routledge _eprint: https://doi.org/10.1080/09669760.2020.1848525
Keywords: Base-10 concept; decomposition strategy; kindergarten; mathematical experiences; number-naming system

Recent Progress in the Discovery and Design of Antimicrobial Peptides Using Traditional Machine Learning and Deep Learning - Yan, Jielu; Cai, Jianxiu; Zhang, Bob; Wang, Yapeng; Wong, Derek F.; Siu, Shirley W. I. (Antibiotics, 2022)
Antimicrobial resistance has become a critical global health problem due to the abuse of conventional antibiotics and the rise of multi-drug-resistant microbes. Antimicrobial peptides (AMPs) are a group of natural peptides that show promise as next-generation antibiotics due to their low toxicity to the host, broad spectrum of biological activity, including antibacterial, antifungal, antiviral, and anti-parasitic activities, and great therapeutic potential, such as anticancer, anti-inflammatory, etc. Most importantly, AMPs kill bacteria by damaging cell membranes using multiple mechanisms of action rather than targeting a single molecule or pathway, making it difficult for bacterial drug resistance to develop. However, experimental approaches used to discover and design new AMPs are very expensive and time-consuming. In recent years, there has been considerable interest in using in silico methods, including traditional machine learning (ML) and deep learning (DL) approaches, to drug discovery. While there are a few papers summarizing computational AMP prediction methods, none of them focused on DL methods. In this review, we aim to survey the latest AMP prediction methods achieved by DL approaches. First, the biology background of AMP is introduced, then various feature encoding methods used to represent the features of peptide sequences are presented. We explain the most popular DL techniques and highlight the recent works based on them to classify AMPs and design novel peptide sequences. Finally, we discuss the limitations and challenges of AMP prediction.
Number: 10 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: antimicrobial peptide; classification; deep learning; machine learning; medicine; regression; therapeutic peptide

Getting the agenda right for higher education in Macau - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Here we are, at the start of a new academic year in Macau’s higher education (HE). What will students learn? What kind of people are the institutions turning out? For example, look at the thousands of students studying business and technology in Macau, the big recruiters in HE.
Section: Macau Business

How social media affects the purchase intentions of female consumers in Macao - watching beauty and cosmetics product experience videos on YouTube - Chan, Velda; Silva, Susana C.; Lampo, Alessandro (Revista Gestão em Análise, 2022)
YouTube has become increasingly popular for marketing purposes. As corporate and user-generated content is widely available on this platform, beauty-related professionals need to understand how to create videos that make their products more appealing and stand out from the clutter. In this study, we examine four factors (i.e., perceived usefulness of the information, perceived credibility of the information, attitude toward the purchase, and perceived video characteristics) that affect the purchase intentions of female consumers. After viewing beauty-related videos, a sample of 204 female consumers was analyzed by structural equation modeling. The findings showed that videos with more views, likes, and comments tend to have a greater effect on the respondents' intentions to purchase. Also, the factors of perceived usefulness of the information, perceived credibility of the information, and attitude toward the purchase exhibited a significant effect on the intention to buy beauty-related products. The result showed that perceived video characteristics (such as quality and visuals) did not significantly influence the purchase intention, however, there is evidence that this factor should not be ignored by content creators. Finally, our research provides insights, strategies, and future directions for industry practitioners and marketers.
Number: 3
Keywords: YouTube beauty products; YouTube marketing; beauty and cosmetics marketing; purchase intention

Visual Studies of Infrastructure: the case of the Belt and Road Initiative* (CLBrief, 2022)
Dennis Zuev* The Belt and Road Initiative (BRI) has become the largest infrastructure program in history, and has become a symbol of growing significance of China and its power.

Diversity and Variation in China's Yao Ancient Wood Frame Structures Through Genetic Algorithms: - Afonso, Filipe; Jedenov, Kirill; Januário, Pedro Gomes; Almeida, Paulo (International Journal of Creative Interfaces and Computer Graphics, 2022)
This study, focusing on the China's Yao minority community, investigates the feasibility to create a generative computational method to replicate the diversity of the existing Yao traditional wood buildings, addressing the critical issues currently facing computational design methods, in the attempt to adapt genetic-generative algorithms to the study of local ancient architecture. The project develops a computational tool to generate a network of three-dimensional prototypes, or building structures, derived from traditional wood frame village houses. It studies possible housing structures that illustrate some of the key working methods available in digital systems such as ‘generating' and ‘compositing' taking as a starting point computational strategies oriented towards geometry and where a set of local variables play a decisive role: available local technologies, use of raw materials, and the dimensioning of timber components based on data collected from Yao architecture.

A Critical Look at Blockchain-Interactive Generative Art - Farinha, Daniel Filipe (International Journal of Creative Interfaces and Computer Graphics, 2022)
Artists are increasingly using blockchain as a tool for trading digital artwork as non-fungible tokens (NFTs); however, some are also beginning to experiment with the blockchain as a medium for generative art, using it as a seed for a generative process or to continuously modify an evolving piece. This paper surveys, reviews, and classifies the state-of-the-art in blockchain-interactive NFTs and presents a liberal-arts critique of the opportunities and threats posed by this technology, whilst addressing existing criticism on the broader topic of art-related NFTs. The paper examines some of the most experimental pieces minted on the Hic et Nunc (HEN) and Teia NFT marketplaces, for which a purpose-built research tool was developed. The survey reveals some reliance on centralised infrastructure, namely blockchain indexers, placing undesired trust on third parties which undermines the potential longevity of the artwork. The paper concludes with recommendations for artists and NFT platform designers for developing more resilient and economically sustainable architectures.
Keywords: Art Preservation; Blockchain; Crypto Art; Dynamic NFT; Generative Art; Non-Fungible Token; Provenance

The effect of time regime in noise exposure on the auditory system and behavioural stress in the zebrafish - Wong, Man Ieng; Lau, Ieng Hou; Gordillo-Martinez, Flora; Vasconcelos, Raquel O. (Scientific Reports, 2022)
Anthropogenic noise of variable temporal patterns is increasing in aquatic environments, causing physiological stress and sensory impairment. However, scarce information exists on exposure effects to continuous versus intermittent disturbances, which is critical for noise sustainable management. We tested the effects of different noise regimes on the auditory system and behaviour in the zebrafish (Danio rerio). Adult zebrafish were exposed for 24 h to either white noise (150 ± 10 dB re 1 μPa) or silent control. Acoustic playbacks varied in temporal patterns—continuous, fast and slow regular intermittent, and irregular intermittent. Auditory sensitivity was assessed with Auditory Evoked Potential recordings, revealing hearing loss and increased response latency in all noise-treated groups. The highest mean threshold shifts (c. 13 dB) were registered in continuous and fast intermittent treatments, and no differences were found between regular and irregular regimes. Inner ear saccule did not reveal significant hair cell loss but showed a decrease in presynaptic Ribeye b protein especially after continuous exposure. Behavioural assessment using the standardized Novel Tank Diving assay showed that all noise-treated fish spent > 98% time in the bottom within the first minute compared to 82% in control, indicating noise-induced anxiety/stress. We provide first data on how different noise time regimes impact a reference fish model, suggesting that overall acoustic energy is more important than regularity when predicting noise effects.
0 citations (Crossref) [2022-09-21] Number: 1 Publisher: Nature Publishing Group
Keywords: Ecology; Neuroscience; Physiology; Zoology

Anti-epileptic Kunitz-like peptides discovered in the branching coral Acropora digitifera through transcriptomic analysis - Chen, Hanbin; Siu, Shirley Weng In; Wong, Clarence Tsun Ting; Qiu, Jianwen; Cheung, Alex Kwok-Kuen; Lee, Simon Ming Yuen (Archives of Toxicology, 2022)
Approximately 50 million people are suffering from epilepsy worldwide. Corals have been used for treating epilepsy in traditional Chinese medicine, but the mechanism of this treatment is unknown. In this study, we analyzed the transcriptome of the branching coral Acropora digitifera and obtained its Kyoto Encyclopedia of Genes and Genomes (KEGG), EuKaryotic Orthologous Groups (KOG) and Gene Ontology (GO) annotation. Combined with multiple sequence alignment and phylogenetic analysis, we discovered three polypeptides, we named them AdKuz1, AdKuz2 and AdKuz3, from A. digitifera that showed a close relationship to Kunitz-type peptides. Molecular docking and molecular dynamics simulation indicated that AdKuz1 to 3 could interact with GABAA receptor but AdKuz2–GABAA remained more stable than others. The biological experiments showed that AdKuz1 and AdKuz2 exhibited an anti-inflammatory effect by decreasing the aberrant level of nitric oxide (NO), IL-6, TNF-α and IL-1β induced by LPS in BV-2 cells. In addition, the pentylenetetrazol (PTZ)-induced epileptic effect on zebrafish was remarkably suppressed by AdKuz1 and AdKuz2. AdKuz2 particularly showed superior anti-epileptic effects compared to the other two peptides. Furthermore, AdKuz2 significantly decreased the expression of c-fos and npas4a, which were up-regulated by PTZ treatment. In addition, AdKuz2 reduced the synthesis of glutamate and enhanced the biosynthesis of gamma-aminobutyric acid (GABA). In conclusion, the results indicated that AdKuz2 may affect the synthesis of glutamate and GABA and enhance the activity of the GABAA receptor to inhibit the symptoms of epilepsy. We believe, AdKuz2 could be a promising anti-epileptic agent and its mechanism of action should be further investigated.
0 citations (Crossref) [2022-09-21]
Keywords: Anti-epileptic; GABAA; Kunitz peptide; Transcriptome

Using Machine Learning Methods to Forecast Air Quality: A Case Study in Macao - Lei, Thomas M. T.; Siu, Shirley W. I.; Monjardino, Joana; Mendes, Luisa; Ferreira, Francisco (Atmosphere, 2022)
Despite the levels of air pollution in Macao continuing to improve over recent years, there are still days with high-pollution episodes that cause great health concerns to the local community. Therefore, it is very important to accurately forecast air quality in Macao. Machine learning methods such as random forest (RF), gradient boosting (GB), support vector regression (SVR), and multiple linear regression (MLR) were applied to predict the levels of particulate matter (PM10 and PM2.5) concentrations in Macao. The forecast models were built and trained using the meteorological and air quality data from 2013 to 2018, and the air quality data from 2019 to 2021 were used for validation. Our results show that there is no significant difference between the performance of the four methods in predicting the air quality data for 2019 (before the COVID-19 pandemic) and 2021 (the new normal period). However, RF performed significantly better than the other methods for 2020 (amid the pandemic) with a higher coefficient of determination (R2) and lower RMSE, MAE, and BIAS. The reduced performance of the statistical MLR and other ML models was presumably due to the unprecedented low levels of PM10 and PM2.5 concentrations in 2020. Therefore, this study suggests that RF is the most reliable prediction method for pollutant concentrations, especially in the event of drastic air quality changes due to unexpected circumstances, such as a lockdown caused by a widespread infectious disease.
0 citations (Crossref) [2022-09-21] Number: 9 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: COVID-19; air pollution; air quality; air quality forecast; gradient boosting; multiple linear regression; random forest; support vector regression

And the award goes to... - Morrison, Keith (Macau Business, 2022)
Macau, MNA, Opinion | The Macau government recently approved its first reading of a new bill to attract Macau locals to return to Macau to work. Simultaneously, Macau’s Secretary for Social Affairs and Culture was reported as saying that if Macau could create a better environment and conditions, then ‘local talents who are abroad will surely be interested in returning to Macau’.
Section: MNA

IoT-based smart health system for ambulatory maternal and fetal monitoring - Lobo Marques, J. A. (2022)

What's behind Macau's business disaster? - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Business 101. When companies plan their business models, typically they must consider, amongst other matters: their products and/or services; demand; market(s) and their environments (economic, political, cultural, social); existing, potential, and likely competition; start-up and ongoing costs and expenses; emergency funding; marketing and promotion; income streams, revenue, and delayed profit; sales; distribution; cash flow; profit margins, gross and net; liabilities; risk analysis, evaluation, and handling; constraints and the ‘what if’ factor; flexibility, adaptability, and adjustment.
Section: Macau Business

Modulações em português de imagens, experiências e estesias orientais: revisão das razões do fascínio de alguma dicção poética chinesa e japonesa como utopia da poesia - Borges, Vera (Alea: Estudos Neolatinos, 2022)
Resumo O fascínio do Ocidente pela dicção poética oriental está atestado em várias latitudes e línguas, e resultou numa profícua produção na área da poesia. Sabe-se que a reinvenção da poesia chinesa da autoria de Pound, em grande medida na origem da sua proposta de revolução do idioma poético, nas primeiras décadas do séc. XX, assentou, na verdade, numa falácia; numa concepção errada da natureza da escrita chinesa (e japonesa) como essencialmente pictográfica e ideogramática, na base de propriedades expressivas reconhecidas na poesia que resultariam numa particular eficácia na apreensão e tradução do real. Pessanha enaltece, em termos similares aos da exaltação poundiana, a escrita da poesia chinesa clássica. Interessa-nos rever alguns inventários dos traços da dicção poética chinesa e japonesa que explicam que ela seja tomada como metonímia e metáfora da poesia, ou como meta e utopia da poesia, para perceber o que terá levado autores muito díspares a tentar a mão nos haikus, processo em que sondaremos algumas formulações poéticas em língua portuguesa. Consideramos também que esse fascínio por uma (sonhada) origem da dicção poética, quando cruzada com o habitar (não metafórico, neste caso) do pequenino enclave de Macau, de autores que nele lançaram raízes, resultou em alguns exercícios poéticos particularmente felizes e singulares. Serão trazidos à colação nesta abordagem poemas de Eugénio de Andrade, Sophia de Mello Breyner Andresen, José Tolentino Mendonça, Yao Feng, Fernanda Dias e Fernando Sales Lopes.
Publisher: Programa de Pos-Graduação em Letras Neolatinas, Faculdade de Letras -UFRJ
Keywords: Macau; Pound; falácia; haiku; poesia; poesia chinesa; trocar de voz

Brasil: pela mansidão da Paraíba, de Ponta do Seixas a São Francisco | José Manuel Simões - Simoes, José Manuel (InComunidade, 2022)
Nessa noite decidiram hospedar-se num motel pois queriam acordar às 3.45 para ver o primeiro sol das Américas na Ponta de Seixas, João Pessoa, Paraíba. Subiram à torre do Nazareno às 4.45 e, quando já pensavam que as nuvens não iam deixar assistir ao nascer de mais um dia aprazível, eis que ele, o senhor rei dos dias, surge do mar. Enquanto os olhos brilhavam ao sol, lembrou-se que Chico César era dali perto, do interior da Paraíba, para as bandas de Campina Grande. Recordou que a primeira vez que tentou olhá-lo nos olhos percebeu que ele estava envolvido numa […]

Multi-Branch-CNN: Classification of ion channel interacting peptides using multi-branch convolutional neural network - Yan, Jielu; Zhang, Bob; Zhou, Mingliang; Kwok, Hang Fai; Siu, Shirley W. I. (Computers in Biology and Medicine, 2022)
Ligand peptides that have high affinity for ion channels are critical for regulating ion flux across the plasma membrane. These peptides are now being considered as potential drug candidates for many diseases, such as cardiovascular disease and cancers. In this work, we developed Multi-Branch-CNN, a CNN method with multiple input branches for identifying three types of ion channel peptide binders (sodium, potassium, and calcium) from intra- and inter-feature types. As for its real-world applications, prediction models that are able to recognize novel sequences having high or low similarities to training sequences are required. To this end, we tested our models on two test sets: a general test set including sequences spanning different similarity levels to those of the training set, and a novel-test set consisting of only sequences that bear little resemblance to sequences from the training set. Our experiments showed that the Multi-Branch-CNN method performs better than thirteen traditional ML algorithms (TML13), yielding an improvement in accuracy of 3.2%, 1.2%, and 2.3% on the test sets as well as 8.8%, 14.3%, and 14.6% on the novel-test sets for sodium, potassium, and calcium ion channels, respectively. We confirmed the effectiveness of Multi-Branch-CNN by comparing it to the standard CNN method with one input branch (Single-Branch-CNN) and an ensemble method (TML13-Stack). The data sets, script files to reproduce the experiments, and the final predictive models are freely available at https://github.com/jieluyan/Multi-Branch-CNN.
3 citations (Crossref) [2022-09-21]
Keywords: Classification; Deep learning; Drug discovery; Ion channel; Multi-Branch-CNN; Peptides

The Role of University in High-Level Human Capital Cultivation in China’s West Greater Bay Area - Ge, Yun (2022)

Material Source of Sediments from West Clarion–Clipperton Zone (Pacific): Evidence from Rare Earth Element Geochemistry and Clay Minerals Compositions - Qiu, Zhongrong; Tao, Chunhui; Ma, Weilin; Dias, Ágata Alveirinho; Hu, Siyi; Shao, Yuexiao; Yang, Kehong; Zhang, Weiyan (Journal of Marine Science and Engineering, 2022)
The geochemistry and mineralogy of sediments provide relevant information for the understanding of the origin and metallogenic mechanism of ferromanganese nodules and crusts. At present, there are still few studies on the sediment origin of the Clarion–Clipperton Zone (CCZ) of the east Pacific, particularly on the systematic origin of sediments with a longer history/length. Here, bulk sediment geochemistry and clay mineral compositions were analyzed on a 5.7 m gravity core (GC04) obtained at the CCZ, an area rich in polymetallic nodules. The results indicate that the average total content of rare earth elements (REE), including yttrium (REY), in sediments is 454.7 ppm and the REEs distribution patterns normalized by the North American Shale Composite of samples are highly consistent, with all showing negative Ce anomalies and more obvious enrichment in heavy REE (HREE) than that of light REE (LREE). Montmorillonite/illite ratio, discriminant functions and smear slide identification indicate multiple origins for the material, and are strongly influenced by contributions from marine biomass, while terrestrial materials, seamount basalts and their alteration products and authigenic source also make certain contributions. The REY characteristics of the sediments in the study area are different from those of marginal oceanic and back-arc basins, and more similar to pelagic deep-sea sediments. Based on LREE/HREE-1/δCe and LREE/HREE-Y/Ho diagrams, we conclude that samples from the study area had pelagic sedimentary properties which suffered from a strong “seawater effect”.
Number: 8 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Clarion–Clipperton Zone; material source; rare earth elements; sediments geochemistry

Mentes abertas, artenativa e um novo Camões - Simões, José Manuel (Aspectus. Revista de Arte & Ciência, 2022)

Nestes tempos, precisamos aprender a amar de novo - Simões, José Manuel (Aspectus. Revista de Arte & Ciência, 2022)

Intersectoral Linkages in Booming Sector Economies - Gomes, Sérgio Ricardo Santos; Marques, Joao Alexandre Lobo; Reis, Ricardo Ferreira (2022 13th International Conference on E-business, Management and Economics, 2022)

Instance-based deep transfer learning with attention for stock movement prediction - He, Qi-Qiao; Siu, Shirley Weng In; Si, Yain-Whar (Applied Intelligence, 2022)
Stock movement prediction is one of the most challenging problems in time series analysis due to the stochastic nature of financial markets. In recent years, a plethora of statistical methods and machine learning algorithms were proposed for stock movement prediction. Specifically, deep learning models are increasingly applied for the prediction of stock movement. The success of deep learning models relies on the assumption that massive training data are available. However, this assumption is impractical for stock movement prediction. In stock markets, a large number of stocks do not have enough historical data, especially for the companies which underwent initial public offering in recent years. In these situations, the accuracy of deep learning models to predict the stock movement could be affected. To address this problem, in this paper, we propose novel instance-based deep transfer learning models with attention mechanism. In the experiments, we compare our proposed methods with state-of-the-art prediction models. Experimental results on three public datasets reveal that our proposed methods significantly improve the performance of deep learning models when limited training data are available.
0 citations (Crossref) [2022-09-21]
Keywords: Attention mechanism; Deep transfer learning; Instance-based; Stock movement prediction

Trying a board game intervention on children with autism spectrum disorder in Macau: how do they react? - Lok, Ka Ieong; Chiang, Hsu-Min; Lin, Yueh-Hsien; Jiang, Chunlian (International Journal of Developmental Disabilities, 2022)
Limited special education and related services are available for children with autism spectrum disorder (ASD) in Macau, especially those who are educated in general education classrooms. No intervention study has been conducted on these children. This study was conducted to explore the relationship between a board game play intervention and board game play behaviors and social communication of children with ASD educated in general education classrooms in Macau. A repeated measures design was used and the results of this study showed the mean occurrence of unprompted board game play behaviors per session during intervention was not significantly different from that during pre- or post-intervention. The mean occurrence of social communication per session during intervention was significantly higher than that during pre- and post-intervention. These findings suggest a positive relationship existed between the board game intervention used in this study and social communication of children with ASD.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/20473869.2022.2095861
Keywords: Autism Spectrum Disorder; Macau; board game; play; social communication

Temporary transnational labour mobility and gendered individualization in Europe - Harsløf, Ivan; Zuev, Dennis (Mobilities, 2022)
In a context of a new transnational division of labour, temporary international labour mobility is on the rise in Europe. In particular, recent decades have seen considerably more women seeking work experience abroad. Observers have been concerned with how such mobility is related to individualization, and in particular how it may challenge collective institutions, communities and families. The aim of this study is to explore such issues among women and men with international work experience. Using data from European Social Survey, the paper investigates previously mobile workers in terms of their current working and living conditions. Across genders, we consider different forms of individualization that may be associated with transnational labour mobility. While both women and men with transnational work experience generally feature strong strategic individualization, this is most pronounced among men. Hence, men's mobility is among other things associated with increased autonomy in working life, while – in contrast to women – it does not seem to hamper their integration in the sphere of social reproduction.
0 citations (Crossref) [2022-11-10] Publisher: Routledge _eprint: https://doi.org/10.1080/17450101.2022.2092417
Keywords: Europe; Temporary labour mobility; individualization; sphere of production; sphere of social reproduction; transnational division of labour

Ockham on the Side of the Angels: Why a Classical Theist Shouldn't be Moved by Oppy's Argument from Simplicity - McNabb, Tyler; DeVito, Michael (New Blackfriars, 2022)
0 citations (Crossref) [2022-09-21]

A Neuropeptide Y/F-like Polypeptide Derived from the Transcriptome of Turbinaria peltata Suppresses LPS-Induced Astrocytic Inflammation - Chen, Qian; Liang, Zirong; Yue, Qian; Wang, Xiufen; Siu, Shirley Weng In; Pui-Man Hoi, Maggie; Lee, Simon Ming-Yuen (Journal of Natural Products, 2022)
Neuropeptides are a group of neuronal signaling molecules that regulate physiological and behavioral processes in animals. Here, we used in silico mining to predict the polypeptide composition of available transcriptomic data of Turbinaria peltata. In total, 118 transcripts encoding putative peptide precursors were discovered. One neuropeptide Y/F-like peptide, named TpNPY, was identified and selected for in silico structural, in silico binding, and pharmacological studies. In our study, the anti-inflammation effect of TpNPY was evaluated using an LPS-stimulated C8-D1A astrocyte cell model. Our results demonstrated that TpNPY, at 0.75–3 μM, inhibited LPS-induced NO production and reduced the expression of iNOS in a dose-dependent manner. Furthermore, TpNPY reduced the secretion of proinflammatory cytokines. Additionally, treatment with TpNPY reduced LPS-mediated elevation of ROS production and the intracellular calcium concentration. Further investigation revealed that TpNPY downregulated the IKK/IκB/NF-κB signaling pathway and inhibited expression of the NLRP3 inflammasome. Through molecular docking and using an NPY receptor antagonist, TpNPY was shown to have the ability to interact with the NPY Y1 receptor. On the basis of these findings, we concluded that TpNPY might prevent LPS-induced injury in astrocytes through activation of the NPY-Y1R.
0 citations (Crossref) [2022-09-21] Publisher: American Chemical Society

The wonderland of Macau's talent development - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | The world is full of interesting paradoxes that befuddle the mind. Or, as the delightful chapter in Alice in Wonderland put it: ‘‘curiouser and curiouser!’’.
Section: Macau Business

A metamorphic devolatilization model for the genesis of the Baiyun gold deposit in the North China Craton: A novel Fe-S isotopes perspective - Liu, Shuaijie; Chen, Bin; Zheng, Jiahao; Wu, Yafei; Bao, Chuang; Zhao, Guochun (Gondwana Research, 2022)
The Mesozoic gold deposits in the North China Craton (NCC) were hosted by the Precambrian basement and Mesozoic intrusions. Thus, most researchers consider that these gold deposits were genetically linked to the Mesozoic intrusions. However, we suggest that a metamorphic devolatilization model provides an alternative based on a combined Fe and in-situ S isotopes study on auriferous pyrites from the Baiyun gold deposit in the NCC. The Triassic Baiyun gold deposit contains the quartz vein and altered rock ores that were developed in the Paleoproterozoic metavolcanic-sedimentary rocks (the Liaohe Group). Our in-situ S isotopic analyses show that pyrites from the quartz vein ores are characterized by negative δ34S values (-10.7 ∼ -5.5‰), while those from the altered rock ores have two distinct groups of δ34S values, one being positive (+13.5 ∼ +16.2‰) and the other negative (-10.6 ∼ -3.0‰). We suggest that pyrite grains with positive δ34S values should be relicts from the host rocks, because they show comparable δ34S values with those from the host rocks schists (+3.3 ∼ +16.1‰). Thus, only the negative δ34S values of pyrites in ores (-10.7 ∼ -3.0‰) and the Fe isotopes of the quartz vein ores (δ56Fe = +0.30 ∼ +0.48‰) can represent the isotopic characteristics of ore-forming fluids at Baiyun. Our study shows that the sulfur were probably from the pyritic volcanic-sedimentary sequences of the Liaohe Group, rather than from magmas. The calculated δ56Fe values of the ore-forming fluids (-0.78 ∼ -0.37‰; pyrite-fluid isotope fractionation) could be modelled in a metamorphic devolatilization model with Fe-species (pyrite&magnetite) of the Liaohe Group as sources. Therefore, our combined S- and Fe- isotope data indicate that the metamorphic devolatilization of the Liaohe Group could account for the genesis of the Baiyun gold deposit.
Keywords: Baiyun gold deposit; Fe isotope; Metamorphic devolatilization model; Orogenic gold deposits; S isotope

Experience the Past in the Present with Immersive Technologies - Chang, Tin Lan; Martins de Abreu, F. (Instituto Politécnico de Portalegre, 2022)
Countless historical sites worldwide have become unrecognisable based on their historical context. Many are cultural heritage structures with significant historical and aesthetic importance. The majority have not been well preserved; worse, some were demolished (Stenning, 2015). Furthermore, structures are part of a dynamic and changing environment, and their location within the original landscape is not always clear. People have gradually forgotten cultural traditions as environments where historical stories took place, and the look and feel have been corrupted. Immersive Virtual Reality (V.R.) allows us to relive and explore the past. However, in the Pearl River Delta Region, specifically Macau S.A.R., V.R. is still in its infancy and is not frequently used for reproducing historical sceneries. Our research focuses on reproducing heritage structures and scenery based on scarce historical information. It shows how to incorporate facts and memories into the design and create engaging, immersive experiences in V.R. scenery that takes place, both inside and outside of a cultural heritage site that has lost its original appearance. Following this, a prototype was created with specific parameters relating to past and present sceneries. We partially reproduced an existing building complex currently being used for creative and commercial purposes, but it was a shelter for the poor and a house for old ladies to live in. There were not enough facts or images linked to the inner space in the past. Inadequate information allows audiovisual scene creators to be more imaginative. The prototype focuses on a functional design that integrates cultural traits tied to local industries. The researcher used image processing software, and web 3D tools (A-Frame 1.1.0). Users can navigate by virtually “walking” and starting the visual tour; simultaneously, the story unfolds as the timeline progresses. After entering, the users jump from the present to a specific era in the past. With audio guidance, users enter the private space, shared areas, working space, etc. Users can interact with objects from the virtual scenes while the interface displays relevant audiovisual introductions. Users could utilise the virtual system to learn how the old ladies led their daily lives in the Pearl River Delta Region and grasp the local single ladies’ group lifestyle at a specific time in the past (Kwong, 2020). The interactive experience enhances the users’ interest; additionally, the users become more familiar with the region’s traditional customs. With this approach, we can create old stories using modern technology. A-Frame provides users with great convenience and can be used by any Internet browser without relying on professional V.R. devices. The content from this usage provides a greater understanding of our heritage buildings and their historical context to the wider community. This could be used in other heritage sites worldwide to reproduce and maintain structural qualities over time. This immersive experience could be a means to navigate the past while in the present. This application could benefit exhibition developers, and visitors, notably in exhibition guided tours, virtual tours inside museums, or educational assisted historical storytelling.

Macao Soundscape as an Analysis Tool for Sound Quality Assessment - Pestana, Pedro; Barbosa, Alvaro; Estadieu, Gerald (Instituto Politécnico de Portalegre, 2022)
Macao SAR, China is one of the more densely-populated territories in the world, and as such necessarily struggles with Soundscape quality. Nonetheless, the territory has already been identified as a unique location for to function as a Soundscape living lab (Cordeiro et al., 2014), since it has a very small manageable area that includes many types of geographical varieties, from extremely high density urban areas to natural environments with dense vegetation highland or varied water front typologies. In addition, Macao has extremely wide multicultural population with a broad range of subjects that have diverse cultural perceptions and thresholds in regards to sonic cognition. The potential impact of this diversity has already been noticed in both tourism (To & Chung, 2019) and research (Chung et al., 2016). The concept of Soundscape itself is garnering increased awareness as a viable alternative to assess the quality of the sonic environment, of use to policy management and legislation, shown not only by the increasing numbers of scientific articles on the subject (Moscoso et al., 2018), but also by recent international standardisation efforts in measuring it (ISO,2018). In this talk we shall give a preliminary description and illustration of the Soundscape in a territory that is rich in diversity and has huge potential for citizen participation. This includes approaches like noise mapping, sound mapping, Soundwalks, grounded theory efforts for detailed descriptions of the environment and use of alternative objective metrics. We will describe how to use the richness of this gathered data in developing artificial-intelligence algorithms to autonomously assess and predict the evaluation of a given Soundscape based on recordings alone. This goal will alleviate the intense human effort in subjective assessment, and may prove to be an effective and substantial diagnostics tool in planning the soundscape for prospective built environments, functioning not only as an analysis and diagnostics tool, but as a design strategy for a sustainable sonic future.

Geochemistry, sulfur and lead isotopic composition of hydrothermal sulfide from the Duanqiao hydrothermal field on the Southwest Indian Ridge: implications for ore genesis - Yang, Weifang; Liao, Shili; Alveirinho Dias, Ágata; Liang, Jin; Li, Wei; Ding, Teng; Tao, Chunhui (International Geology Review, 2022)
Hydrothermal activities on ultraslow-spreading ridges exhibit diverse characteristics, long histories with multiple participants, and might form large-scale, high-grade sulfide deposits. The Duanqiao hydrothermal field (DHF) is located at the segment with the thickest oceanic crust and a large axial magma chamber on the Southwest Indian Ridge, providing unique perspective of sulfide metallogenesis on ultraslow-spreading ridges. Previous studies revealed that DHF sulfide exhibits distinct features of enrichment of ore-forming elements in comparison with those of hydrothermal fields on sediment-starved mid-ocean ridges. However, the genesis and processes responsible for such differences remain poorly constrained. In this study, mineralogical, geochemical and S and Pb isotopic analyses were performed on relict sulfide mound samples to characterize DHF formation. The samples show clear concentric mineral zonation from the interior to the exterior wall. Assemblages of chalcopyrite, sphalerite, and pyrite are distributed mainly in the interior wall, whereas pyrite and marcasite are distributed mainly in the exterior wall. The low Cu content and Pb isotopic composition of the sulfide indicate that the metals are derived mainly from basement basalts. The δ34S values exhibit positive values distributed over a reasonably narrow range (2.42‰–7.97‰), which suggests approximately 62.1%–88.5% of S with basaltic origin. Compared with most hydrothermal fields along the sediment starved mid-ocean ridges, the DHF sulfide shows particularly high contents of Pb (263–2630 ppm), As (234–726 ppm), Sb (7.32–44.3 ppm), and Ag (35.2 to >100 ppm). The δ34S values exhibit an increasing tendency from the sample exterior to the interior. We propose that these features probably reflect the existence of a subsurface zone refining process. Our results provide new insight into the sulfide formation process and contribute to understanding the metallogenic mechanism of hydrothermal sulfides on ultraslow-spreading ridges.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/00206814.2022.2081937
Keywords: Hydrothermal sulfide; geochemistry; southwest Indian ridge; sulfur isotope; zone refining

Self-Efficacy, Stress and Job Satisfaction among Pre-Service, Novice and Experienced English Teachers: A Study of their Occupational Health - Lam, Stacy; Kuok, A. C. H.; Sze, Tat Ming (Health Psychology Report, 2022)
Background This study aimed to investigate English teachers’ self-efficacy for student engagement, classroom management, instructional strategies and literacy instruction, as well as to discover teacher stress and job satisfaction can play a role in interfering their occupational health (in terms of self-efficacy). In addition, this is one of the first studies to understand the differences in self-efficacy among pre-service, novice and experienced in-service teachers in a Chinese society, where English is positioned as a foreign language. Participants and procedure 271 English teachers (90 pre-service, 181 in-service) with mean teaching experience of 5.57 months for per-service, and 98.51 months for in-service were participated in this quantitative research study, as the targets were not be able to approach randomly, the English teachers were approaching individually though referral sampling, informing that the purpose of the study and receive their consent. Results It discovered both pre-service and novice in-service teachers posses lowest self-efficacy. Moreover, teachers’ stress from classroom predicted their self-efficacy for student engagement and classroom management negatively. On the other hand, teachers’ job satisfaction predicts their self-efficacy for student engagement, instructional strategies and literacy instruction positively. Conclusions Implications (based on the findings) are discussed in order to provide insights for for schools and education departments to strengthen the teachers’ capability of teaching and their occupational health.
0 citations (Crossref) [2022-10-30]

Uma Questão de Arquitectura: Luz (Café da Manhã, 2022)

A positivist approach to work engagement: moderating effects of perceived organizational support - Kuok, A. C. H; Taormina, Robert J. (Dynamic Relationships Management Journal, 2022)
0 citations (Crossref) [2022-10-30]

Mind your own business - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Across the world, a civil service job pays well and is secure. Not bad if you can get it, with competitive entry to it by hordes of applicants.
Section: Macau Business

Internationalisation of higher education: new players in a changing scene - Ge, Yun (Educational Research and Evaluation, 2022)
0 citations (Crossref) [2022-09-21] Publisher: Routledge _eprint: https://doi.org/10.1080/13803611.2022.2041850

Belt and Road Initiatives: implications for China’s internationalisation of tertiary-level education - Ge, Yun; Ho, Kong Chong (Educational Research and Evaluation, 2022)
Since the launch of the One Belt and One Road Initiative (BRI) in 2013, the internationalisation of China’s tertiary education has entered a new stage. Central to the BRI is investment and strategic planning for talent cultivation, knowledge production, and transmission. This paper explains how the BRI redirects, reinforces, and intensifies China’s strategic planning and actions for internationalising its education. It adopts a policy analysis approach and reviews three key aspects of development and shifting emphasis of internationalisation under the impact of the BRI: international education networks along the Six BRI Economic Corridors, vocational colleges as new players in international education, and promotion of the Chinese language as a new global language. The analysis captures an important moment in which international education processes are being visibly altered through China’s strategies to take the lead in economic globalisation and to compete for a central place in the world via the BRI.
0 citations (Crossref) [2022-09-21] Publisher: Routledge _eprint: https://doi.org/10.1080/13803611.2022.2041858
Keywords: Belt and Road Initiatives; Chinese language; Internationalisation of higher education; vocational education

International Student Diversity Experiences in their Host Cities - Ge, Yun; Ho, Kong Chong (National University of Singapore and Université Paris Cité, 2022)

Pavilhão de Bambu Intertwine – Preservação, Inovação e Promoção do Património Imaterial de Macau - Soares, Nuno (2022)

La terre des autochtones potiguara du brésil: une construction sociale et politique - Simões, José Manuel (E-Journal of Intercultural Studies, 2022)
The land of the potiguara indians of Brazil: a social and political construction The space in which the potiguaras of Brazil live is, today as in the past, the result of a longterm process, many negotiations and well-managed refuges. Paradoxically, despite their recurrent discourse invoking the ancestry of their lands of origin, the Potiguara fight and continue to fight politically for the return to the spaces where their colonial refuge took place.

Measuring Specific Traditional Chinese Values in Relation to Satisfaction of the Five Maslow Needs - Taormina, Robert J.; Gao, Jennifer H.; Kuok, A. C.H. (Psychological Thought, 2022)
To determine whether living according to specific traditional Chinese cultural values was associated with satisfaction of the five needs in Maslow’s motivational hierarchy and overall life satisfaction, a mixed-method approach was employed, with an empirical questionnaire and supplemental interviews. The questionnaire assessed the hypothesized relationships that traditional Chinese values had with personal life outcomes, including health, employment, satisfaction of the five needs from Maslow’s hierarchy, and life satisfaction. The interviews examined the relationships that several demographic variables had with living by traditional Chinese values. The results of the empirical data revealed that most Chinese people today are still living according to the traditional Chinese cultural values, and that living by those traditional values are strongly associated with satisfaction of all five of the human needs in the Maslow hierarchy, as well as with overall life satisfaction. Additionally, the results of the qualitative interviews readily supported the empirical findings, and also revealed that the time during which inter-generational transmission of the Chinese cultural values occurs is when parents teach those values to their children at a very early age, that is, between 3 and 8 years old, before the children start primary school.
0 citations (Crossref) [2022-10-30]

The evolutionary argument against naturalism: a Wittgensteinian response - DeVito, Michael; McNabb, Tyler (International Journal for Philosophy of Religion, 2022)
In this essay, we put forth a novel solution to Plantinga’s Evolutionary Argument Against Naturalism, utilizing recent work done by Duncan Pritchard on radical skepticism. Key to the success of Plantinga’s argument is the doubting of the reliability of one’s cognitive faculties. We argue (viz. Pritchard and Wittgenstein) that the reliability of one’s cognitive faculties constitutes a hinge commitment, thus is exempt from rational evaluation. In turn, the naturalist who endorses hinge epistemology can deny the key premise in Plantinga’s argument and avoid the dilemma posed on belief in the conjunction of naturalism and evolution.
0 citations (Crossref) [2022-09-21]

From Maximum Illud 1919 to the First National Synod Primum Concilium Sinensis 1924 in Shanghai: Historical & Theological Perspectives - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2022)
Section: Articles

Minimising Maximum Illud: Early Resistance to Missionary Inculturation in China - Law, Cyril Jerome (Orientis Aura: Macau Perspectives in Religious Studies, 2022)
Section: Articles

A Deep Neural Network Based on Circular Representation for Target Detection - Lin, Cong; Chen, Zhoujian; Huang, Yiquan; Jiang, Haoyu; Du, Wencai; Chen, Qiong (Journal of Sensors, 2022)
Convolutional neural network (CNN) model based on deep learning has excellent performance for target detection. However, the detection effect is poor when the object is circular or tubular because most of the existing object detection methods are based on the traditional rectangular box to detect and recognize objects. To solve the problem, we propose the circular representation structure and RepVGG module on the basis of CenterNet and expand the network prediction structure, thus proposing a high-precision and high-efficiency lightweight circular object detection method RebarDet. Specifically, circular tubular type objects will be optimized by replacing the traditional rectangular box with a circular box. Second, we improve the resolution of the network feature map and the upper limit of the number of objects detected in a single detect to achieve the expansion of the network prediction structure, optimized for the dense phenomenon that often occurs in circular tubular objects. Finally, the multibranch topology of RepVGG is introduced to sum the feature information extracted by different convolution modules, which improves the ability of the convolution module to extract information. We conducted extensive experiments on rebar datasets and used AB-Score as a new evaluation method to evaluate RebarDet. The experimental results show that RebarDet can achieve a detection accuracy of up to 0.8114 and a model inference speed of 6.9 fps while maintaining a moderate amount of parameters, which is superior to other mainstream object detection models and verifies the effectiveness of our proposed method. At the same time, RebarDet’s high precision detection of round tubular objects facilitates enterprise intelligent manufacturing processes.
0 citations (Crossref) [2022-09-21]

Escape from Macau - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau used to be very appealing to expatriates from across the world. Its low tax rate (and zero tax for low-paid expatriates), blends of cultures, business opportunities, life style, history, unique features and a host of other attractions fuelled an ongoing supply of foreign nationals to this small, unusual city. It is an interestingly idiosyncratic place in which to live. For many expatriates, Macau has been home, in many cases reaching back more than one generation. This is perhaps unsurprising, as people here are typically exquisitely polite, a delight to be with, and very accepting. Its acceptance of differences in values is an example to countries across the world. Macau is a safe place to live.
Section: Macau

Noise-induced hearing loss correlates with inner ear hair cell decrease in larval zebrafish - Lara, Rafael A.; Breitzler, Lukas; Lau, Ieng Hou; Gordillo-Martinez, Flora; Chen, Fangyi; Fonseca, Paulo J.; Bass, Andrew H.; Vasconcelos, Raquel O. (Journal of Experimental Biology, 2022)
Anthropogenic noise can be hazardous for the auditory system and wellbeing of animals, including humans. However, very limited information is known on how this global environmental pollutant affects auditory function and inner ear sensory receptors in early ontogeny. The zebrafish (Danio rerio) is a valuable model in hearing research, including investigations of developmental processes of the vertebrate inner ear. We tested the effects of chronic exposure to white noise in larval zebrafish on inner ear saccular sensitivity and morphology at 3 and 5 days post-fertilization (dpf), as well as on auditory-evoked swimming responses using the prepulse inhibition (PPI) paradigm at 5 dpf. Noise-exposed larvae showed a significant increase in microphonic potential thresholds at low frequencies, 100 and 200 Hz, while the PPI revealed a hypersensitization effect and a similar threshold shift at 200 Hz. Auditory sensitivity changes were accompanied by a decrease in saccular hair cell number and epithelium area. In aggregate, the results reveal noise-induced effects on inner ear structure–function in a larval fish paralleled by a decrease in auditory-evoked sensorimotor responses. More broadly, this study highlights the importance of investigating the impact of environmental noise on early development of sensory and behavioural responsiveness to acoustic stimuli.
2 citations (Crossref) [2022-09-21]

Mangroves as a nature-based solution for a cleaner and safer Macao - Tagulao, Karen (2022)

Neuromarketing and Global Branding Reaction Analysis Based on Real-Time Monitoring of Multiple Consumer's Biosignals and Emotions - Goncalves, Marcus V.; Marques, Joao Alexandre Lobo; Silva, Bruno Riccelli Santos; Luther, Valorie; Hayes, Sydney (2022)
Consumers' selections and decision-making processes are some of the most exciting and challenging topics in neuromarketing, sales, and branding. Multicultural influences and societal conditions are also crucial aspects to consider from a global perspective. Applying neuroscience tools and techniques in international marketing and consumer behavior is an emergent and multidisciplinary field that aims to understand consumers' thoughts, reactions, and selection processes in branding and sales. This study focuses on real-time monitoring of different physiological signals using eye-tracking, facial expressions recognition, and Galvanic Skin Response (GSR) acquisition methods to analyze consumers' responses, detect emotional arousal, measure attention or relaxation levels, analyze perception, consciousness, memory, learning, motivation, preference, and decision-making. The primary purpose of this research was to monitor human subjects' reactions to these signals during an experiment designed in three phases consisting of different types of branding advertisements. The non-advertisement exposition was also monitored during the gathering of survey responses at the end of each phase. A feature extraction module was implemented with a data analytics module to calculate statistical metrics and decision-making supporting tools based on Principal Component Analysis (PCA) and Feature Importance (FI) determination based on the Random Forest technique. The results indicate that when compared to image ads, video ads are more effective in attracting consumers' attention and creating more emotional arousal.
Keywords: Branding Reaction; Consumer Biosignal; Galvanic Skin Response; consumer decision-making; eye-tracking; neuromarketing; neurosciences

Tourist Sentiment Mining Based on Deep Learning - Li, Weijun; Yang, Qun; Du, Wencai (Artificial Intelligence, 2022)
Mining the sentiment of the user on the internet via the context plays a significant role in uncovering the human emotion and in determining the exactness of the underlying emotion in the context. An increasingly enormous number of user-generated content (UGC) in social media and online travel platforms lead to development of data-driven sentiment analysis (SA), and most extant SA in the domain of tourism is conducted using document-based SA (DBSA). However, DBSA cannot be used to examine what specific aspects need to be improved or disclose the unknown dimensions that affect the overall sentiment like aspect-based SA (ABSA). ABSA requires accurate identification of the aspects and sentiment orientation in the UGC. In this book chapter, we illustrate the contribution of data mining based on deep learning in sentiment and emotion detection.

Exploratory Research on Key Technology of Human-Computer Interactive 2.5-Minute Fast Digital Early Warning for Mild Cognitive Impairment - Li, Nan; Yang, Xiaotong; Du, Wencai; Ogihara, Atsushi; Zhou, Siyu; Ma, Xiaowen; Wang, Yujia; Li, Shuwu; Li, Kai (Computational Intelligence and Neuroscience, 2022)
Objective. As the preclinical stage of Alzheimer’s disease (AD), Mild Cognitive Impairment (MCI) is characterized by hidden onset, which is difficult to detect early. Traditional neuropsychological scales are main tools used for assessing MCI. However, due to its strong subjectivity and the influence of many factors such as subjects’ educational background, language and hearing ability, and time cost, its accuracy as the standard of early screening is low. Therefore, the purpose of this paper is to propose a new key technology of fast digital early warning for MCI based on eye movement objective data analysis. Methodology. Firstly, four exploratory indexes (test durations, correlation degree, lengths of gaze trajectory, and drift rate) of MCI early warning are determined based on the relevant literature research and semistructured expert interview; secondly, the eye movement state is captured based on the eye tracker to realize the data extraction of four exploratory indexes. On this basis, the human-computer interactive 2.5-minute fast digital early warning paradigm for MCI is designed; thirdly, the rationality of the four early warning indexes proposed in this paper and their early warning effectiveness on MCI are verified. Results. Through the small sample test of human-computer interactive 2.5 fast digital early warning paradigm for MCI conducted by 32 elderly people aged 70–90 in a medical institution in Hangzhou, the two indexes of “correlation degree” and “drift rate” with statistical differences are selected. The experiment results show that AUC of this MCI early warning paradigm is 0.824. Conclusion. The key technology of human-computer interactive 2.5 fast digital early warning for MCI proposed in this paper overcomes the limitations of the existing MCI early warning tools, such as low objectification level, high dependence on professional doctors, long test time, requiring high educational level, and so on. The experiment results show that the early warning technology, as a new generation of objective and effective digital early warning tool, can realize 2.5-minute fast and high-precision preliminary screening and early warning for MCI in the elderly.

Uma Questão de Arquitectura: Programa (Café da Manhã, 2022)

Getting out of a problem - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau should be proud of its protective handling of the Covid-19 pandemic, as it has managed to contain its spread, and many of its citizens have been able to lead a more normal life than in other parts of the world. We should be grateful for this.

A touristic habitation: automobilities of Chinese driving tourists - Yang, Peng; Xu, Honggang; Hannam, Kevin (Tourism Geographies, 2022)
As an emergent tourism sector, driving tourism connects car use and touristic activities intimately. Following the notion of the ‘inhabited car’, this article explores how and why Chinese tourists inhabit a travelling car for drivers/passengers in the leisure automobility and driving tourism context. Through three different road trips and ‘mobile methods’, it was found that Chinese tourists inhabit the car in four ways: driving, gazing, listening, and communicating. Through this embodied habitation, the car is turned into a ‘touristic inhabitation’ space for protecting the tourists generating touristic emotions、social interactions, and tourism meanings. The study contributes to automobility and tourism literature and provides implications for driving tourism development in China.
Publisher: Routledge _eprint: https://doi.org/10.1080/14616688.2022.2046148
Keywords: Automobilities; China; cars; driving tourism; habitation

INNOVATING IN OPEN DISTANCE TEACHING WITH FACE-TO-FACE RETREATS WITHIN A DOCTORAL PROGRAM IN DIGITAL MEDIA ART - Fernandes-Marcos, A; Tavares, M (Proceedings of 16th annual International Technology, Education and Development Conference (INTED2022, 2022)
0 citations (Crossref) [2022-09-21] OCLC: 1325332377

Southern Inner Harbour Public Domain – Conceptual Design: Zone 01 –Manduco (University of Saint Joseph, 2022)

Southern Inner Harbour Public Domain – Conceptual Design: Zone 02 - Padre António (University of Saint Joseph, 2022)

Southern Inner Harbour Public Domain – Conceptual Design: Zone 03 – Ponte e Horta (University of Saint Joseph, 2022)

Southern Inner Harbour Public Domain – Conceptual Design Zone 04 – Harbou (University of Saint Joseph, 2022)

Southern Inner Harbour Public Domain – Conceptual Design: Zone 05 - Felicidade (University of Saint Joseph, 2022)

Southern Inner Harbour Public Domain – Conceptual Design: Zone 06 – Santo Agostinho (University of Saint Joseph, 2022)

Southern Inner Harbour Public Domain – Conceptual Master Plan (University of Saint Joseph, 2022)

內港南部公共領域 – 概念性總體規劃 (University of Saint Joseph, 2022)

內港南部公共領域 - 概念設計：區域 01下環街區 (University of Saint Joseph, 2022)

內港南部公共領域 - 概念設計：區域 02高樓街區 (University of Saint Joseph, 2022)

內港南部公共領域 - 概念設計：區域 03司打口街區 (University of Saint Joseph, 2022)

內港南部公共領域 - 概念設計：區域 04海濱街區 (University of Saint Joseph, 2022)

內港南部公共領域 - 概念設計：區域 05福隆街區 (University of Saint Joseph, 2022)

內港南部公共領域 - 概念設計：區域 06崗頂街區 (University of Saint Joseph, 2022)

Study of the Compositional Rules of Design in Chaoshan Traditional House: A Computational Approach - Afonso, Filipe (10th International Conference on Digital and Interactive Arts, 2022)
This study is an attempt to understand and describe the compositional principles of Chaoshan traditional houses (CTH) through a computational space syntax. In this approach, the space syntax is used to describe and verify the compositional rules of Chaoshan houses. Chaoshan rural residence is a classical Lingnan style building in Chaoshan area of eastern Guangdong province, associated with Teo-Swa people, a Han Chinese minority. This study takes the example the prototypes existing in the village of Zhupu, Haojiang District, Shantou city as a case study, to analyse the spatial form of the residences. The Zhupu village houses date from the Qing Dynasty - Qianlong period, around 1700 AD. The hypothesis of this study is that CTH buildings are a result of a space compositional rule system that can be described and replicated through a computational design methodology. This study will establish a computational architectural syntax, and is the first stage of an extended research work on the evolution of Chaoshan residential types. The understanding of this evolution may help, as future work, to develop urban strategies for adaptation of the CTH heritage buildings to the contemporary living conditions. As the result of this study is a computational 3D graphics modelling algorithm, the ability of the system to generate the house layouts is not limited to the reconstruction of existing typologies of CTH and its variations. The same algorithm will allow the generation of new housing schemes, with adaptation to design variables extracted from a particular site and region.
Keywords: Chaoshan house; Qing dynasty; Space syntax; computational design; courtyard house

The scourge of construction - Morrison, Keith (Macau Business, 2022)

Conceptual replications, research, and the “what works” agenda in education - Morrison, Keith (Educational Research and Evaluation, 2022)
2 citations (Crossref) [2022-09-21]

Uma Questão de Arquitectura: Público e Privado (Café da Manhã, 2022)

An Exploratory Study on the Possibility of Harmonizing Investment Protection Regimes within the OHADA Zone - Diakité, A. D.; Thiam, A. B. (Transnational Dispute Management (TDM), 2022)
Abstract With its large population and natural resources, Africa needs investors who can sustain its development. At the same time, foreign investors expect returns on their investments. In ...
Publisher: Maris BV

Towards a framework of teacher professional development: The case of early literacy education in Macau - Tse, T. P. M.; Mak, M. C. K; Chu, K. W.; Cheng, P. W.; Ho, G. W. S.; Chan, A. O. K; Ng, M. H.; Leong, K. I. Q. (2022)

Tipping points and economic recovery in Macau - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | New year; old problem. As the pandemic rolls on, so many calls for economic diversification in Macau as a survival strategy have been heard, loud and long, that, as the law of diminishing returns tells us, their effects recede.

How can environmental conditions influence dicofol genotoxicity on the edible Asiatic clam, Meretrix meretrix? - Ivorra, Lucia; Cruzeiro, Catarina; Ramos, Alice; Tagulao, Karen; Cardoso, Patricia G. (Environmental Pollution, 2022)
Genotoxic effects of dicofol on the edible clam Meretrix meretrix were investigated through a mesocosm experiment. Individuals of M. meretrix, were exposed to environmental concentration (D1 = 50 ng/L) and supra-environmental concentration (D2 = 500 ng/L) of dicofol for 15 days, followed by the same depuration period. DNA damage (i.e., strand breaks and alkali-labile sites) was evaluated at day 1, 7 and 15, during uptake and depuration, using Comet assay (alkaline version) and nuclear abnormalities (NAs) as genotoxicity biomarkers. The protective effects of dicofol against DNA damage induced by ex vivo hydrogen peroxide (H2O2) exposure were also assessed. Comet assay results revealed no significant DNA damages under dicofol exposure, indicating 1) apparent lack of genotoxicity of dicofol to the tested conditions and/or 2) resistance of the animals due to optimal adaptation to stress conditions. Moreover, ex vivo H2O2 exposure showed an increase in the DNA damage in all the treatments without significant differences between them. However, considering only the DNA damage induced by H2O2 during uptake phase, D1 animals had significantly lower DNA damage than those from other treatments, revealing higher protection against a second stressor. NAs data showed a decrease in the % of cells with polymorphic, kidney shape, notched or lobbed nucleus, along the experiment. The combination of these results supports the idea that the clams used in the experiment were probably collected from a stressful environment (in this case Pearl River Delta region) which could have triggered some degree of adaptation to those environmental conditions, explaining the lack of DNA damages and highlighting the importance of organisms’ origin and the conditions that they were exposed during their lives.
Keywords: Bivalves; Comet assay; DNA damage; Nuclear abnormalities; Organochlorine pesticides

Constructing an aesthetic discourse: Aesthetic education where Daoism meets postmodernism - Ho, Ka Lee Carrie (Education Inquiry, 2022)
Despite the prevalence of aesthetic education as one of the main developmental objectives in curricular worldwide, the mainstream philosophical discourse on its definition is predominately framed by western philosophy due to a paucity of cross-cultural studies on the subject. The article aims to achieve a contemporary understanding of aesthetic education from both the Chinese and Western aesthetic perspectives. Through the lens of postmodernism, the relationship between Daoist aesthetics and the western postmodern aesthetic perspectives, particularly the Deleuzian concept of rhizome, is identified. Both aesthetic perspectives concern de-authorship and promote self-consciousness/self-awareness. The study reconceptualises the functions of aesthetic education with the Chinese aesthetic philosophy that promotes the nurture of better people through benevolence.
Publisher: Routledge _eprint: https://doi.org/10.1080/20004508.2020.1831286
Keywords: Aesthetic experiences; Daoism; Deleuze; aesthetic environments; rhizome

An Integrated Learning Platform Focusing on STEAM and Collaborative Modules for Macau - Cheng, Un Man; Abreu, Filipa C. A. Martins de (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
In Macau, the effectiveness of traditional classroom learning is questioned as the problem is discovered by the changes in technology advances, social media, and the varieties of learning methods. Learning experiences, interests, discoveries, and creativity development are considered essential to ac...
Publisher: IGI Global

An Integrated Learning Platform Focusing on STEAM and Collaborative Modules for Macau - Cheng, Un Man; Martins de Abreu, F. (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
In Macau, the effectiveness of traditional classroom learning is questioned as the problem is discovered by the changes in technology advances, social media, and the varieties of learning methods. Learning experiences, interests, discoveries, and creativity development are considered essential to ac...
Publisher: IGI Global

Trace-element compositions of sulfides from inactive Tianzuo hydrothermal field, Southwest Indian Ridge: Implications for ultramafic rocks hosting mineralization - Ding, Teng; Wang, Jia; Tao, Chunhui; Dias, Ágata Alveirinho; Liang, Jin; Wang, Yuan; Chen, Jie; Wu, Bin; Huang, Hui (Ore Geology Reviews, 2022)
The recently explored inactive Tianzuo hydrothermal field, in the amagmatic segment of the ultraslow-spreading Southwest Indian Ridge (SWIR), is closely associated with detachment faults. In this site, sulfide minerals are hosted by serpentine-bearing ultramafic rocks and include high-temperature (isocubanite, sphalerite, and minor pyrrhotite) and low-temperature (pyrite I, marcasite, pyrite II, and covellite) phases. In this study, trace-element concentrations of isocubanite and pyrite II were used to elucidate mineralization processes in ultramafic rocks hosting sulfides. Results show that isocubanite is enriched in metals such as Cu, Co, Sn, Te, Zn, Se, Pb, Bi, Cd, Ag, In, and Mn, and pyrite II is enriched in Mo and Tl. The marked enrichment in Te, Cu, Co, and In in isocubanite (compared with Se, Zn, Ni, and Sn, respectively) is most likely due to the contribution of magmatic fluids from gabbroic intrusions beneath the hydrothermal field. The intrusion of gabbroic magmas would have enhanced serpentinization reactions and provided a relatively oxidizing environment through the dissolution of anhydrite precipitated previously in the reaction zone, within high temperature and low pH conditions. This might have facilitated the extraction of metals by initial hydrothermal fluids, leading to the general enrichment of most metals in isocubanite. Metals in pyrite II have compositions similar to those of isocubanite, except for strong depletion in magmatically derived Te, Cu, Co, and In. This means that serpentinization processes had a dominating role in pyrite II precipitation as well. The enrichment of pyrite II in Mo and Tl is also indicative of seawater contribution in its composition. The study concludes that serpentinization reactions contribute effectively both to high- and low-temperature sulfide mineralization at Tianzuo hydrothermal field, with gabbroic intrusions further promoting high-temperature sulfide mineralization, providing additional metals, fluids and heat. In contrast, low-temperature sulfide mineralization occurred during the cooling of gabbroic intrusions, with decreasing rates of serpentinization reactions and a significant influence of seawater.
Keywords: SWIR; Serpentinization; Sulfide; Tianzuo; Trace-element; Ultramafic rocks

Design Explorations for 3D-Printed Modular Markers for eXtended-Reality Tangible User Interfaces: - Iok Fong, Chau; Cardoso, Jorge C. S.; Estadieu, Gerald Vincent (International Journal of Creative Interfaces and Computer Graphics, 2022)
Various materials, objects, and sensors have been explored earlier for creating tangible user interfaces (TUIs). However, there is little work on 3D-printed TUIs based on visual markers for smartphone-based extended reality (XR) experiences. The combination of visual markers and smartphones results in cheap, accessible XR systems within reach of many people. Combined with 3D printing, it could foster do-it-yourself (DIY) projects for XR experiences, which may further expand and open-up possibilities for accessible and tangible interaction. This work explores the design space of modular 3D-printed tangibles for smartphone-based XR. The authors report the design exploration process, provide several interactive 3D-printed markers, and reflect on the resulting possibilities.
0 citations (Crossref) [2022-10-27]

Quality of life during the pandemic: a cross sectional study about attitude, individual perspective and behavior change affecting general population in daily life - Khatoon, F.; Kumar, M.; Khalid, A. A.; Alshammari, A. D.; Khan, F.; Alshammari, R. D.; Balouch, Z.; Verma, D.; Mishra, P.; Abotaleb, M.; Makarovskikh, T.; El-kenawy, E. M.; et al. (2022)
Quality of life in general population before and during pandemic is topic need to be address by researcher in terms of mobility, self-care, usual activities, pain/discomfort and anxiety/depression. The study was carried out among Saudi population. Data were collected from general population using questionnaire during the period from 22 August 2021 to 10th January 2022. As a result, total 214 participants have included in this study. Among them prevalent age group include 40 years (n= 63, 29.4%) shadowed by the age group 25-35 (n= 61, 28.5%) while above 60 years group were least frequent (n= 1, 0.5%). On questioning the applicants whether they were satisfied with their health and how would they rate their quality of life, their answers were as follows: yes, or satisfied (n= 86, 40.2%), very Satisfied (n= 102, 47.7%) Dissatisfied (n= 11, 5.1%) and neither satisfied nor dissatisfied (n= 15, 7%). Due to pandemic, they were rate quality of life very good (n= 94, 43.9%), good (n= 63, 29.4 %) poor (n= 5, 2.3 %) and neither good and nor poor (n= 52, 24.3 %). During pandemic 96 participants feel no change in their weight but 110 participants respond that there is increase in coffee intake during the pandemic. Similarly increased in smoking habits and decrease rate in social activities (n=119,41.4%). The psychosomatic well-being of people has been interrupted by disturbing their social activities during pandemic.
Publisher: IET Digital Library

An Attempt to Examine Digital Native and Digital Immigrant Macau Graphic Designers' Perceptions of Adopting Generative Design - Lau, Ching Man; Caires, Carlos Sena (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
The manifestation of generating digital visuals through an algorithm is gaining worldwide attention in the graphic design industry. It is a new form of computing that visualizes data input by the designer or collected in the physical environment and turns them into artwork. The generative design of...
Publisher: IGI Global

AI and deep learning for processing the huge amount of patient-centric data that assist in clinical decisions - Lôbo Marques, João Alexandre; Bernardo Gois, Francisco Nauber; Nunes da Silveira, Jarbas Aryel; Li, Tengyue; Fong, Simon James (Cognitive and Soft Computing Techniques for the Analysis of Healthcare Data, 2022)
The area of clinical decision support systems (CDSS) is facing a boost in research and development with the increasing amount of data in clinical analysis together with new tools to support patient care. This creates a vibrant and challenging environment for the medical and technical staff. This chapter presents a discussion about the challenges and trends of CDSS considering big data and patient-centered constraints. Two case studies are presented in detail. The first presents the development of a big data and AI classification system for maternal and fetal ambulatory monitoring, composed by different solutions such as the implementation of an Internet of Things sensors and devices network, a fuzzy inference system for emergency alarms, a feature extraction model based on signal processing of the fetal and maternal data, and finally a deep learning classifier with six convolutional layers achieving an F1-score of 0.89 for the case of both maternal and fetal as harmful. The system was designed to support maternal–fetal ambulatory premises in developing countries, where the demand is extremely high and the number of medical specialists is very low. The second case study considered two artificial intelligence approaches to providing efficient prediction of infections for clinical decision support during the COVID-19 pandemic in Brazil. First, LSTM recurrent neural networks were considered with the model achieving R2=0.93 and MAE=40,604.4 in average, while the best, R2=0.9939, was achieved for the time series 3. Second, an open-source framework called H2O AutoML was considered with the “stacked ensemble” approach and presented the best performance followed by XGBoost. Brazil has been one of the most challenging environments during the pandemic and where efficient predictions may be the difference in saving lives. The presentation of such different approaches (ambulatory monitoring and epidemiology data) is important to illustrate the large spectrum of AI tools to support clinical decision-making.
Keywords: Artificial intelligence; Clinical decisions; Computer-aided diagnostic systems; Deep learning; Patient-centric data

Artificial neural network-based approaches for computer-aided disease diagnosis and treatment - Marques, João Alexandre Lôbo; Gois, Francisco Nauber Bernardo; Madeiro, João Paulo do Vale; Li, Tengyue; Fong, Simon James (Cognitive and Soft Computing Techniques for the Analysis of Healthcare Data, 2022)
The adoption of computer-aided diagnosis and treatment systems based on different types of artificial neural networks (ANNs) is already a reality in several hospital and ambulatory premises. This chapter aims to present a discussion focused on the challenges and trends of adopting these computerized systems, highlighting solutions based on different types and approaches of ANN, more specifically, feed-forward, recurrent, and deep convolutional architectures. One section is focused on the application of AI/ANN solutions to support cardiology in different applications, such as the classification of the heart structure and functional behavior based on echocardiography images; the automatic analysis of the heart electric activity based on ECG signals; and the diagnosis support of angiogram images during surgical interventions. Finally, a case study is presented based on the application of a deep learning convolutional network together with a recent technique called transfer learning to detect brain tumors using an MRI images data set. According to the findings, the model has a high degree of specificity (precision of 0.93 and recall of 0.94 for images with no brain tumor) and can be used as a screening tool for images that do not contain a brain tumor. The f1-score for images with brain tumor was 0.93. The results achieved are very promising and the proposed solution may be considered to be used as a computer-aided diagnosis tool based on deep learning convolutional neural networks. Future works will consider other techniques and compare them with the one presented here. With the comprehensive approach and overview of multiple applications, it is valid to conclude that computer-aided diagnosis and treatment systems are important tools to be considered today and will be an essential part of the trend of personalized medicine over the coming years.
Keywords: Artificial intelligence; Computer-aided diagnosis and treatment; Deep learning; Medical imaging; Neural networks

Multimodal Game Design Framework for Creativity in Macau's Educational System Through Digital and Tangible Games: Chinese, Portuguese, and English Languages - Martins de Abreu, F.; Barbosa, Álvaro Mendes (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
Creativity and collaboration are crucial to learning development in today's fast-paced educational environment. New technology can bridge humans and their natural needs through immersion in digital environments with physical objects. As knowledge and information evolve, digital interactive experienc...
Publisher: IGI Global

In Memorial and Serenity: Introducing VR Grave Mourning in the Chapel of St. Michael in Macao - Olga Ng Ka Man, Sandra; Caires, Carlos Sena (International Journal of Creative Interfaces and Computer Graphics, 2022)
Macao inhabit a population of 683,100. The birth rate has been dropping while the death rate has risen compared to two years ago. Cemeteries are becoming crowded, and burial spots are demanding. In this case, video calls and social media can be the solution. How about our beloved ancestors? Can we video call them on their memorial days? This paper presents a VR experience of immersing oneself in the 3D VR of the Chapel of St. Michael of Macao to create a peaceful atmosphere for grave mourning. The chapel is also a personal space where we can be truly isolated in serenity. It is a retreat to pray, disconnect, and reconnect to the beloved deaths that may not be buried in an easily accessible location. The authors propose a possible future of mourning our loved ones through virtual reality and telepresence: an immersive experience connected with Macao's extraordinary and cultural unicity.

Mangrove Conservation in Macao SAR, China: The Role of Environmental Education among School Students - Tagulao, Karen Araño; Bernardo, Allan B. I.; Kei, Loi Hoi; Calheiros, Cristina Sousa Coutinho (International Journal of Environmental Research and Public Health, 2022)
Mangrove forests are one of the most ecologically valuable ecosystems in the world and provide a wide variety of ecosystem services to coastal communities, including cities. Macao, a highly urbanized coastal city located on the southern coast of China west of the Pearl River, is home to several species of mangroves with many associated flora and fauna. Mangrove forests in Macao are vulnerable to threats due to pressure from rapid and massive urban developments in the area, which led to mangrove loss in the past decades. To address this issue, the local authorities established special Ecological Zones for the management of the local mangroves. To reinforce local conservation efforts, educating the local population about the value of mangroves, especially school students, is of utmost importance. To evaluate the impact of environmental education activities on the environmental orientation, knowledge, and values of students toward mangrove conservation in Macao, a quasi-experimental study was undertaken. The effectiveness of a mangroves exhibition and field visit were evaluated using the New Environmental Paradigm (NEP) Scale—Macao version in a group of local school students who participated in the activities. Overall, the results provided consistently positive evaluations of the impact of the environmental education program. The strongest improvements were found in the students’ pro-environmental orientations, knowledge about mangroves, and value for environmental protection.
0 citations (Crossref) [2023-03-15] Number: 6 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: NEP-New Ecological Paradigm; conservation; environmental orientation; environmental protection; urban mangroves

LISTENING TO CHILDREN’S IDEAS TO IMPROVE IN LEARNING AND DEVELOPING HIGHER-ORDER THINKING SKILLS THROUGH REFLECTION WITH DAILY DOCUMENTATION - Ae, Young Choi; Ho, Ka Lee Carrie (University of Saint Joseph, 2022)
Listening to children’s voices is still not considered an essential part of education in some schools, including many in Asian countries. The authority of schools and teachers is still highly valued under the continued influence of Confucian Heritage Culture in many Asian schools, including a significant number in Macao. Teachers in international schools in Asian countries often experience some difficulties when communicating with young children because of their low English proficiency and the traditional views supported by many parents who grew up with the Confucian Heritage Culture, which encourages children to be quiet in the classroom to be good listeners. This Action research took fifteen months between two school years, 2018- 2019 and 2019-2020, with two groups of four and five-year-old students in a kindergarten classroom. Documentation posters were created for young children to use the next morning to reflect on their learning. The pedagogy of listening and pedagogical documentation from the Reggio Emilia approach were implemented to discover and record young children’s ideas and interests, work with daily documentation posters, and help them reflect on documentation posters to improve their learning and develop their higher-order thinking skills. Photos and videos, observation notes with the children’s comments, documentation posters, and reflective discussions were used as interventions to collect the children’s ideas and record their learning activities. The children learned to use documentation posters to remember, think, share, and improve their learning. The children’s comments from Learning Centres, recess, and reflective discussions were used to examine their understanding of learning and higher-order thinking skills. During one Pilot Cycle and three structured data collection cycles, the children demonstrated improvement in learning for each learning project and development of their thinking skills both with and without the teacher’s support. The children demonstrated higher-order thinking skills more often from Learning Centres and recess when they had to solve problems. They also demonstrated higher-order thinking skills more often during the whole group reflective discussions than in small group reflections, when a bigger number of children joined or when they had enough time to think. The thinking skills when children were reflecting were observed to concentrate on remembering and understanding as they focused on remembering and sharing the previous day’s work. The children’s other higher-order thinking skills did not show an increase in frequency during reflective discussions. However, the children demonstrated active engagement and a range of higher-order thinking skills when the teacher asked openended questions and provided support and comments to help them to connect their learning to their past experiences. Findings indicated that the children’s learning from each Learning Centre showed change and improvement during their play over time according to their interests, indicated by their material use and comments. The research was limited by its small number of participants within their age group due to convenience sampling and the children’s relatively limited ability to demonstrate higher-order thinking skills. This study has shown how teachers could help children use daily documentation posters to develop their learning and thinking skills by visualizing their ideas and the teacher’s important role in supporting children’s learning with active listening and support in the classroom
Keywords: Bloom’s Taxonomy; Early Childhood Education; Pedagogical Documentation; Reggio Emilia Approach; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph

Study of management style in Canada - Ao, Ka Chon (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Quantum Field Formulation for a Pandemic Propagation - Arraut, Ivan; Marques, João Alexandre Lobo; Fong, Simon James; Li, Gloria; Gois, Francisco Nauber Bernardo; Neto, José Xavier (Epidemic Analytics for Decision Supports in COVID19 Crisis, 2022)
In this chapter, a mathematical model explaining generically the propagation of a pandemic is proposed, helping in this way to identify the fundamental parameters related to the outbreak in general. Three free parameters for the pandemic are identified, which can be finally reduced to only two independent parameters. The model is inspired in the concept of spontaneous symmetry breaking, used normally in quantum field theory, and it provides the possibility of analyzing the complex data of the pandemic in a compact way. Data from 12 different countries are considered and the results presented. The application of nonlinear quantum physics equations to model epidemiologic time series is an innovative and promising approach.
Keywords: COVID-19; Mathematical modeling; Nonlinear analysis; Quantum field theory

Maternal Postpartum Experience in Macao: The Relationship Between Demographics, Income, Social Support and Postpartum Depression - Bonthuis, Ana Maria Barradas Leitão Abril (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A Study of the Macau personal data protection legal regime - Cabanos, Leilani Oliver (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

To follow or overcome our nature? - Cai, Yulin (GREGORIANUM, 2022)
The doctrine of original sin gives people the impression that the goodness of human nature is under-evaluated in the Christian theological tradition. The Chinese philosopher Mencius is famous for his teaching on the goodness of human nature. Reading Mencius and Thomas Aquinas side by side, this article argues that the Mencian teaching on human nature brings us to affirm the goodness of human nature by recovering the significance of the image of God for the Christian doctrine of human nature. If we seek the goodness of human nature in the possibilities to become good, it is natural to see that even in the fallen state the possibilities of becoming like God remain in human nature imprinted with the image of God. It is open to the culmination of a gradual progression to its perfection.

How Might We Provide Students with Agility and Digital Literacy? Case Study of the Bachelor of Communication and Media at the University of Saint Joseph - Cathagne-Benventi, Sophie (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

A study on Children's Learning Evaluation in Macao Kindergarten——Taking a Kindergarten in Macao as an example =: 澳門幼師對幼兒學習評量之研究——以澳門某幼稚園為例 - Chan Ka Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Factors Influencing Disability Inclusion Practice in Social Media: A Case Study of MDA Service Centre for the Deaf - Chan Wai Peng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

A Study on the Relationship Between Positive Emotions and Work Stress in Private Kindergarten Teachers in Macau=: 澳門幼稚園教師正向情緒與工作壓力關係之研究 - Chan, Hio Tong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Till Death Do (Not) Us Part: Elderlies’ Preparation on Wealth Transmission and the Effectiveness of Testaments in Macao - Chan, Hong Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

The Perception of Skirt Wearing and Masculinity in Contemporary Society: A Case Study in São Paulo, Brazil and Shanghai, China - Chan, Jose Manuel Enesoe (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Interaction design for a contemporary learning and teaching environment: promoting independent learning at the primary level - Chan, Ka Chi (University of Saint Joseph, 2022)
The world is perpetually changing, and the COVID-19 pandemic has taught us that the future is full of unforeseen challenges and potentialities. What are the implications of the advancement in technology on education? How are teachers coping with contemporary educational expectations? Is there a need to redesign the learning environment? What is the exact nature of the forces driving such a change? Is there anything we can learn from successful innovations around the globe? The goals of this dissertation include designing a learning/teaching app and redesigning classroom furniture for primary-level education. A design thinking methodology is used, working through the phases of empathizing, defining, ideating, prototyping and testing the two potential designs
Keywords: Design; Interaction analysis in education; Interactive multimedia

Project-based Learning in the Subject of General Studies in a Grade Five Class: A Case Study Approach - Chan, Ka Ho (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門戲劇教育發展的演變及挑戰: 以澳門演藝學院戲劇學校為研究對象 =The Growth and Challenges of Theatre Education in Macau: A Case Study of The School of Theatre at the Macao Conservatory - Chan, Ka I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Online Gaming with Digital Currencies: A Comparative Legal Study - Chan, Ka Yuen (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

Work-Life Balance and Life Satisfaction in Macao: The Mediating Effect of Work Satisfaction - Chan, Lok Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

A Qualitative Research on Tutors' Attitudes Towards the Implementation of the Emotional Eduation in Macau Nurseries =: 澳門托兒所導師對幼兒情緒教育態度的質性研究 - Chan, Man Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Experience the Past in the Present with Immersive Technologies Case Study: “The Old Ladies’ House”, Albergue, Macau - Chang, Tin Lan (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

An Investigation on Macao Children with ASD and their Families needs on Social Support - Chau, Chin Fong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

澳門新入職教師在融合教育的學校中面對的挑戰 =: New Teachers' Challenges in School Which Provided Inclusive Education in Macao - Che, Ka Ian (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Park-meter: Designing an Innovative Macau System - Cheang, Chi Tat (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

從混合性研究中探討澳門長者對睡眠健康認知及其相關之因素 =: Exploring Perception on Sleep Health and its Related Factors among Older People in Macau - A Mixed Methods Study - Cheang, Ka Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

CCAAT/Enhancer-Binding Protein Alpha Is a Novel Regulator of Vascular Smooth Muscle Cell Osteochondrogenic Transition and Vascular Calcification - Chen, Pengyuan; Hong, Wanzi; Chen, Ziying; Gordillo-Martinez, Flora; Wang, Siying; Fan, Hualin; Liu, Yuanhui; Dai, Yining; Wang, Bo; Jiang, Lei; Yu, Hongjiao; He, PengCheng (Frontiers in Physiology, 2022)
AimsVascular calcification is a common clinical complication of chronic kidney disease (CKD), atherosclerosis (AS), and diabetes, which is associated with increased cardiovascular morbidity and mortality in patients. The transdifferentiation of vascular smooth muscle cells (VSMCs) to an osteochondrogenic phenotype is a crucial step during vascular calcification. The transcription factor CCAAT/enhancer-binding protein alpha (C/EBPα) plays an important role in regulating cell proliferation and differentiation, but whether it regulates the calcification of arteries and VSMCs remains unclear. Therefore, this study aims to understand the role of C/EBPα in the regulation of vascular calcification.Methods and ResultsBoth mRNA and protein expression levels of C/EBPα were significantly increased in calcified arteries from mice treated with a high dose of vitamin D3 (vD3). Upregulation of C/EBPα was also observed in the high phosphate- and calcium-induced VSMC calcification process. The siRNA-mediated knockdown of C/EBPα significantly attenuated VSMC calcification in vitro. Moreover, C/EBPα depletion in VSMCs significantly reduced the mRNA expression of the osteochondrogenic genes, e.g., sex-determining region Y-box 9 (Sox9). C/EBPα overexpression can induce SOX9 overexpression. Similar changes in the protein expression of SOX9 were also observed in VSMCs after C/EBPα depletion or overexpression. In addition, silencing of Sox9 expression significantly inhibited the phosphate- and calcium-induced VSMC calcification in vitro.ConclusionFindings in this study indicate that C/EBPα is a key regulator of the osteochondrogenic transdifferentiation of VSMCs and vascular calcification, which may represent a novel therapeutic target for vascular calcification.

How Does Employer Brand Affect Employer of Choice? A Case Study of Two Macau F&B Groups’ Employer Branding Comparisons - Chen, Zhi Yi (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

初中教師面對融合學生校園欺凌經驗及應對策略之研究 =: Research on the Experience and Coping Stratrgies of Junior High School Teachers in the Face of Integrated Students' Bullying in Schools - Cheok, Pou Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Mandatory Provident Fund Scheme: Prespectives of Macau Employees - Cheong, Kit I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The Relationship Between Stress and Emotion Regulation with Students’ Academic Achievement - Cheong, Sin Teng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

An Investigation into Play-Based Educational Support For The Developing Social-Communication Skills in Children with Autism Spectrum Disorder (ASD) in Kindergarten - Cheong, Tânia Guilherme (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Palate Consciousness: A Philosophical Analysis on the Cultivation of Gustatory Aesthetics Through the Framework of Phenomenology of Perception - Chiang, I. Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

Unity of Knowing and Acting from Christian and Confucian Ethical Practices: An Exegesis of Mark 4:1-20 - Chiang, Sau Kuan (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

Redefining Macau's Film Industry: Case Studies on local Film Marketing & Distribution - Choi Chi Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

The Application of Zhuangzi's View on Death to the Philosophical Counselling - Choi, Cheng In (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

An Action Research on the Influence of Flipped Classroom on Learning Achievement and Learning Motivation of Primary School Students in Programming Courses=: 翻轉教學對於小學程式設計學習成效與學習動機影響之行動研究 - Choi, Wan Chong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Knowledge and Attitude of Parents with Regular Primary Children Towards Inclusive Education in Macau =: 澳門小學普通生家長對澳門融合教育的認識及態度之調查報告 - Chong, Leng Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

E-Commerce in the Hospitality Industry: The Online Hotel Booking and Digital Marketing in Macau - Chowdee, Nattiya (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Exploring the participation and agency of students with special education needs in a Macau-Chinese secondary school - Correia, Ana M.; Forlin, Chris; Sio, Eva (Journal of Research in Special Educational Needs, 2022)
The research explores the perceptions of five secondary school students with special education needs (SEN) about their participation in learning, group membership, and agency within an inclusive school in Macau SAR. This goal is achieved by using students' voices documented in open-ended interviews and is underpinned by the conceptual framework of heutagogy. The aim is to shed light on students' perceptions on school effectiveness in supporting their needs through successful participation and agentic possibilities. Findings showed that students were more prone to social rejection and being isolated or bullied than their peers. They were struggling to feel included or participate, their needs were only partially being met, and they had few opportunities to exert influence on their educational trajectories. Recommendations are provided to assist educators and schools in enhancing students with SEN to connect to the learning process and community, with the provision of appropriate learning adjustments and more active approaches to ensure their acceptance by mainstream students, including the formation of coaching peers to assist in developing social and academic skills under teacher's scaffolding practices. This study highlights the contribution of the heutagogical perspective to advance research on the participation and agency of students with SEN in mainstream schools.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/1471-3802.12566
Keywords: Macau SAR; Special education needs; agency; disability; inclusive education; participation; students' voice

Perspectives and Practices of Macau Secondary School Teachers Regarding ICT in Teaching and Learning - Das, Amit (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Clothing and School Uniforms in Macau: Maria João Nunes Das - Das, Maria João Nunes (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploratory Case Study of Teacher's Perspectives in Assisting Students with Special Needs in Inclusive Schools in Macau - Diakité, Patrícia Dina Correia Silves Ferreira (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Bodhidharma i początki szkoły buddyzmu chan (Bodhidharma and the Origin of Chan School of Buddhism) - Duraj, Jaroslaw (Chiny Dzisiaj, 2022)

Narodziny buddyzmu humanistycznego na Tajwanie: Mistrz Shengyan i szkoła Góry Bębna Dharmy (Emergence of Humanistic Buddhism in Taiwan: Master Shengyan and the School of Dharma Drum Mountain) - Duraj, Jaroslaw (Chiny Dzisiaj, 2022)

Transformacja buddyzmu w kontekście chińskim (Transformation of Buddhism in the Chinese Context) - Duraj, Jaroslaw (Chiny Dzisiaj, 2022)

Editorial Preface - Estadieu, G; Marcos, Aderito; Caires, Carlos; Mendes, Daniel; Rodrigues, Nuno (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)

Book of Proceedings of ARTeFACTo2022MACAO, Third International Conference on Digital Creation in Arts, Media and Technology - Emerging Extended Realities. 24-25 Nov. 2022, Macao. IEEE ISBN 979-8-3503-1004-7 - Estadieu, Gerald (2022 Third International Conference on Digital Creation in Arts, Media and Technology (ARTeFACTo), 2022)

澳門年輕群體對性別多元態度與態度構成因素之研究 =: The Attitude of the Relative Influential Factors and Gender Diversity on Youth in Macau - Fion, Si Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Art-Based Intervention For Children with ADHD: Catina Fong Chi Cheng - Fong Chi Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Expansion of private tutoring centers in Macau: voice from parents of primary school students - Fong, Chan Seng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

合作學習法在小學中文科教學中的實施: 以澳門某小學為例 = The Implementation of Cooperative Learning in Primary School Chinese Teaching: A Case Study of a Primary School in Macao - Fong, Hio Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Study on inclusive Class Management by Nursery Teachers in Macau =: 澳門托兒所融合班教師班級經營之研究 - Fong, Ka Lei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Analysis of the COVID19 Pandemic Behaviour Based on the Compartmental SEAIRD and Adaptive SVEAIRD Epidemiologic Models - Fong, Simon James; Marques, João Alexandre Lobo; Li, G.; Dey, N.; Crespo, Rubén G.; Herrera-Viedma, E.; Gois, F. Nauber Bernardo; Neto, José Xavier (Epidemic Analytics for Decision Supports in COVID19 Crisis, 2022)
A significant number of people infected by COVID19 do not get sick immediately but become carriers of the disease. These patients might have a certain incubation period. However, the classical compartmental model, SEIR, was not originally designed for COVID19. We used the simple, commonly used SEIR model to retrospectively analyse the initial pandemic data from Singapore. Here, the SEIR model was combined with the actual published Singapore pandemic data, and the key parameters were determined by maximizing the nonlinear goodness of fit R2 and minimizing the root mean square error. These parameters served for the fast and directional convergence of the parameters of an improved model. To cover the quarantine and asymptomatic variables, the existing SEIR model was extended to an infectious disease model with a greater number of population compartments, and with parameter values that were tuned adaptively by solving the nonlinear dynamics equations over the available pandemic data, as well as referring to previous experience with SARS. The contribution presented in this paper is a new model called the adaptive SEAIRD model; it considers the new characteristics of COVID19 and is therefore applicable to a population including asymptomatic carriers. The predictive value is enhanced by tuning of the optimal parameters, whose values better reflect the current pandemic.
Keywords: Adaptive SEAIRD model; Adaptive SVEAIRD model; Asymptomatic cases; Prediction models

The Comparison of Different Linear and Nonlinear Models Using Preliminary Data to Efficiently Analyze the COVID-19 Outbreak - Fong, Simon James; Marques, João Alexandre Lobo; Li, G.; Dey, N.; Crespo, Rubén G.; Herrera-Viedma, E.; Gois, F. Nauber Bernardo; Neto, José Xavier (Epidemic Analytics for Decision Supports in COVID19 Crisis, 2022)
The COVID-19 pandemic spread generated an urgent need for computational systems to model its behavior and support governments and healthcare teams to make proper decisions. There are not many cases of global pandemics in history, and the most recent one has unique characteristics, which are tightly connected to the current society’s lifestyle and beliefs, creating an environment of uncertainty. Because of that, the development of mathematical/computational models to forecast the pandemic behavior since its beginning, i.e., with a restricted amount of data collected, is necessary. This chapter focuses on the analysis of different data mining techniques to allow the pandemic prediction with a small amount of data. A case study is presented considering the data from Wuhan, the Chinese city where the virus was first detected, and the place where the major outbreak occurred. The PNN + CF method (Polynomial Neural Network with Corrective Feedback) is presented as the technique with the best prediction performance. This is a promising method that might be considered in future eventual waves of the current pandemic or event to have a suitable model for future epidemic outbreaks around the world.
Keywords: Artificial neural networks; Epidemiology; Machine learning; Prediction models

Probabilistic Forecasting Model for the COVID-19 Pandemic Based on the Composite Monte Carlo Model Integrated with Deep Learning and Fuzzy System - Fong, Simon James; Marques, João Alexandre Lobo; Li, Gloria; Dey, Nilanjan; Crespo, Rubén González; Herrera-Viedma, Enrique; Gois, Francisco Nauber Bernardo; Neto, José Xavier (Epidemic Analytics for Decision Supports in COVID19 Crisis, 2022)
There are several techniques to support simulation of time series behavior. In this chapter, the approach will be based on the Composite Monte Carlo (CMC) simulation method. This method is able to model future outcomes of time series under analysis from the available data. The establishment of multiple correlations and causality between the data allows modeling the variables and probabilistic distributions and subsequently obtaining also probabilistic results for time series forecasting. To improve the predictor efficiency, computational intelligence techniques are proposed, including a fuzzy inference system and an Artificial Neural Network architecture. This type of model is suitable to be considered not only for the disease monitoring and compartmental classes, but also for managerial data such as clinical resources, medical and health team allocation, and bed management, which are data related to complex decision-making challenges.
Keywords: COVID-19; Composite Monte Carlo simulation; Healthcare decision-making systems; Prediction

The Application of Supervised and Unsupervised Computational Predictive Models to Simulate the COVID19 Pandemic - Fong, Simon James; Marques, João Alexandre Lobo; Li, Gloria; Dey, Nilanjan; Crespo, Rubén González; Herrera-Viedma, Enrique; Gois, Francisco Nauber Bernardo; Neto, José Xavier (Epidemic Analytics for Decision Supports in COVID19 Crisis, 2022)
The application of different tools for predicting COVID19 cases spreading has been widely considered during the pandemic. Comparing different approaches is essential to analyze performance and the practical support they can provide for the current pandemic management. This work proposes using the susceptible-exposed-asymptomatic but infectious-symptomatic and infectious-recovered-deceased (SEAIRD) model for different learning models. The first analysis considers an unsupervised prediction, based directly on the epidemiologic compartmental model. After that, two supervised learning models are considered integrating computational intelligence techniques and control engineering: the fuzzy-PID and the wavelet-ANN-PID models. The purpose is to compare different predictor strategies to validate a viable predictive control system for the COVID19 relevant epidemiologic time series. For each model, after setting the initial conditions for each parameter, the prediction performance is calculated based on the presented data. The use of PID controllers is justified to avoid divergence in the system when the learning process is conducted. The wavelet neural network solution is considered here because of its rapid convergence rate. The proposed solutions are dynamic and can be adjusted and corrected in real time, according to the output error. The results are presented in each subsection of the chapter.
Keywords: ANN predictor; COVID19; Epidemiology; Fuzzy predictor; PID control; SEAIRD

The Moderating Effect of Job Alternatives Perceptions in the Relationship Between Burnout and Turnover: A Study During the COVID-19 Pandemic in Macao - Fong, Sut Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

Macau's Historical House Taxonomy: The Shophouses at the Rua de Cinco de Outubro (Case Studies) - Fu Ho I (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Religious Vows in their Mystic and Prophetic Dimensions - Gallares, Judette (Religious Life Asia, 2022)

Learning God’s Mercy: Spiritual Transformation According to Hos 11:8 - Gassner, Franz (The Journal of the Macau Ricci Institute, 2022)
A growing focus on God’s mercy and forgiveness emerged in the wake of the recent Pontificates of John Paul II, Benedict XVI, and Francis. Our time with its multiple crises cries for healing, forgiveness, and the experience of God’s mercy. In social, political, and global terms, humanity craves for “lasting peace, born of the marriage of justice and mercy” (John Paul II, 2001, no. 15). The experience of God’s forgiveness, merciful healing and new life has been expressed many times in the Bible. But, theologically, it has never been formulated as directly as in Hosea 11:8, when God’s own heart becomes “turned over”, “converted” following the blaze of his own overwhelming compassion, paving the way for a fundamental spiritual transformation, rooted in forgiveness and mercy, that opens wellsprings of dignity, healing, and new life for all.

Journalism Ethics and the Common Good: The Formation of Values and Virtues for Just and Harmonious Societies - Gassner, Franz; Simoes, José Manuel (Disentangled Vision On Higher Education: Preparing The Generation Next, 2022)

The Association Between Interpersonal Relationships and Mental Health in College Students in Macao - Guo, Peiling (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門已婚人士的婚姻質量與社交媒體參與之研究 =: The Study of Marital Quality and Social Media Engagment Among Married People in Macau - Ho, I. Mei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The Idea of the Exemplary Salesian in the Twelve Recorded Dreams of St. John Bosco: A Spiritual and Psychological Consideration - Ho, Ka Fai (University of Saint Joseph, 2022)
This dissertation is an attempt to analyze the twelve selected dreams written or reviewed by St. John Bosco in order to present the notion of an exemplary Salesian. These dreams inspired Don Bosco’s vocation, charism, and dealing with his life’s contingencies and correlate with his pastoral ministry for youth under the social-ecclesiastical context of the nineteenth century. The methodology for this research consists of two approaches: an investigation of their spiritual theology, and Morton T. Kelsey’s approach. In the first part, five dimensions of spiritual theology are explored: (1) the conformity to the truth, (2) the humility and the docility to the Divine will, (3) the discretion and the gravity of seeking the glory of God, (4) the liberty of Spirit with joy, and (5) the guidance of the Spirit. In the latter part, three issues inspired by Kelsey are explored: (1) the personal issue, including the exploration of thought and feeling; (2) the correlation between the dream content and the reality, including images and archetypal symbols associated with experience and memory; (3) the spiritual issue, including one’s openness to God and relation with Him. Through this present research, a model of an exemplary Salesian has been conceptualized, which considers three virtues: health, wisdom, and sanctity. This present study is expected to be beneficial to enhance the faithful’s spirituality. Moreover it is hoped it will provide a healthy stimulus for Salesians to seek to live an excellent Salesian religious life, and to the faithful be devoted Christians in this world as well for the sake of glorifying the Divine mercy
Keywords: Thesis and Dissertations PhD in Religious Studies (D-RS); University of Saint Joseph

A Historical Invertigation into the Pentecostal and Charismatic Movement in Macau's Protestant Churches: From Thomas J. Mcintosh to the Present Day - Ho, Kei Tsui (University of Saint Joseph, 2022)
This dissertation is a comprehensive academic examination of the characteristics and complex historical progress within the Pentecostal and Charismatic Movement in Macau Protestant Churches. Since Macau hosted the first Pentecostal and Charismatic missionary, Thomas J. McIntosh, who entered China in 1907, the history of the Pentecostal and Charismatic Movement in Macau lacks a consistent and synthesized research until now. Thus, primary and secondary resources have been analyzed and reconstructed and historically interpreted to gain a better and deeper understanding of the emergence and development of the Pentecostal and Charismatic Movement within Macau’s Protestant Churches from the beginning up to the present day. This academic review makes an important contribution to Macau with respect to its historical development and will fill the gap in knowledge within the Global church history of the Pentecostal and Charismatic Movement. Key Words: Charismatic, Christianity in China, History of Missionaries in China, Macao, Macau, Pentecostalism, Protestant, T. J. McIntosh
Keywords: Thesis and Dissertations PhD in Religious Studies (D-RS); University of Saint Joseph

The Influence of Official Digital Infographics in Macao during the COVID-19 Pandemic - Ho, Weng In (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

A STUDY OF PRIMARY SCHOOL TEACHERS' TEACHING PROBLEMS AND THEIR COPING STRATEGIES FOR TEACHING INCLUSIVE STUDENTS IN MACAO =: 澳門小學教師面對融合學生的教學困擾及其因應策略之研究 - Hoi Ka Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Indirect Effect of Job Insecurity and COVID-19 Induced Stress on Mental Health through the Mediating Effect of Burnouts and the Moderating Effect of Perceived Social Support among Macau Gaming Employees - Hoi, Lok (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A Study on the Peer Relationship of Students Aged 9-12 with Special Educational Needs in Macao=: 澳門九至十二歲融合生與同儕關係之研究 - Hong Mei Na (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

General Teachers’ Attitude Towards Inclusive Education in Students with Dyslexia in High School Students=: 中學普通班教師對患有讀寫障礙學生的認識與其融合教育的態度 - Hong, Yufang (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Action Study of Using Game-Based Learning into English Learning to Improve the Lerning Outcomes of Primary Level Students in Macau =: 遊戲式教學融入澳門小學低年級英語課程以提升學生學習成效之行動研究 - Hsu, Hsiao Chien (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

New Great Learning Oneness Epistemic Model for the Greater Peace: A Philosophical Analysis on the Concept of Oneness and its Application with Veganism - Hun, Kuong U. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

A Qualitative Exploration of the Learning and Teaching Experiences of Teachers Who Completed A Post-Graduate Early Childhood Diploma in Macau =: 探討澳門學位後幼兒教育文憑教師的學習體驗及其教學實踐之質性研究 - Ieong, Weng Ian (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Conceptual Model of Behavioral Factors Affecting the Adoption of E-government Services in Macao SAR - Iong, Kit Yeng (University of Saint Joseph, 2022)
Information and communication technologies (ICTs) are highly associated with the study of e-government, and many scholars believe that within the coming decades, government operation and policy decision-making cannot persist without the use of ICTs (Van Dijk, 2018). This thesis aims to generate a conceptual framework of the behavioral factors that could contribute to the acceleration of the implementation of e-government services in Macao SAR. Rather than regarding e-government services as a goal to be realized in traditional practice through evaluating the outcome, a process-oriented study was conducted. The e-government services are regarded as advanced tools in the 21st century to transform Macao into a smart city. The design of the process-oriented approach and the comparative study of four groups of Macao citizens' behavioral intentions are solidly supported by the research gaps identified in the literature review of e-government studies in an international perspective and the actual context of local Macao studies. Under the framework of the Theory of Planned Behavior (Ajzen, 1985, 1991), the behavioral factors of the general public and civil servants are investigated through a qualitative approach, and the findings are triangulated from various aspects. Firstly, a systematic literature review of TPB was conducted thoroughly to better understand the current study of e-government around the world. Secondly, a content and thematic analysis of the official documents and articles from local press media and research institutes related to the topic of e-government services was carried out to demonstrate a more comprehensive picture of the current problems of implementing iv and adopting e-services in Macao SAR. Observations in some government premises that provided e-services and 40 in-depth interviews were conducted to generate detailed and first-hand data. Key issues were extracted from the interviewees’ narratives and daily actual usages. Different conceptual models for different age groups and civil servant group were formed. Special attention was paid to analyzing the "hard-to-reach" groups' behavioral intentions. Research limitations identified from the previous literature were overcome partially in this study too. After comparing the similarities and differences, a new conceptual model of significant behavioral factors that affect the behavioral intentions in adopting e-government services was built. Results and findings from the analysis could be used to develop effective interventions by the government policymakers in responding to the behavioral change of the general public in the aspect of e-government services acceptance and adoption
Keywords: Thesis and Dissertations PhD in Government Studies (D-GS); University of Saint Joseph

初探澳門更生人士在專業工作過程的成功因素=: Explore Successful Factors in Recognition of Professional Work Process for Ex-Offenders - Ip, Ka I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Lighting Up A Place with Good Stories: Heritage Interpretation Strategies and the Macau Historic Centre - Ip, Kin Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

An Analysis of Celebrities and KOLs Influence Consumer Decisions on the Luxury Fashion Market in Macau - Ip, San U. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Influence of Strengths-Based Intervention to Students’ Engagement and Self-Efficacy in Macau - Jr. Tabilas, Faustino T. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

Problematic Internet Use and Subjective Wellbeing Among University Students in Macao - Kam, Chi Fat (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

澳門普通學校教師任教融合生的教學困擾和支援服務需求之研究=: A Study of the Teaching Distress and Needs of Supportive Service of Students with Special Educational Needs Taught by General School Teachers in Macau - Kong, Chi Fong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門新任教師職業適應的研究：: 來自在內地與澳門接受師範培養的幼兒教師反饋= Research on the Career Adaptation of New Teachers in Macao Feedback from Kindergarten Teachers who Received Teacher Education in the Mainland and Macau - Kou Mei Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Use and Perception of Visual Communication on Instagram by Macau Residents - Ku, Kit Mei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Fintech Services in Guangdong-Macao in Depth Cooperation Zone in Hengqin: An investigation of Macao Users' Adoption - Kuan, Chi Hou (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Using Online Learning to Enhance Motivation in an English as a Second Language Classroom: An Action Research Study - Kuok, Weng Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Qualitative Research on The Career Choice, Current Situation and Prospects of Preschool Tutors Working in Nursery Schools and Kindergartens in Mainland China, Taiwan and Macau=: 中國內地、台灣、澳門幼兒導師從事托兒所和幼兒園工作的職業選擇、現況和前景之質性研究 - Lai Ka Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring the Problems and Strategy Use by Primary School Teachers in Conducting Classroom Management Under the Policies of Inclusive Education in Macau =: 探討澳門融合教育政策下小學老師面對班級經營的困難及策略 - Lam Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Illegal Immigration and Population Police in Macau: A Case Study of Fujianese Immigrants = 澳門非法移民問題及其治理——以澳門的福建移民為例 - Lam Lai Teng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The Influence of Society on the Behavioral Intention to Use a Technology: Evidence from the Battery Electric Vehicles Domain - Lampo, Alessandro; Silva, Susana C.; Duarte, Paulo (International Journal of Business Excellence, 2022)

Intention Towards Online Counseling among Service Provider in Macau=: 澳門社會服務提供者對應用線上輔導的意向 - Lao, Hoi Keong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The Impact of Father-Adolescent Relationship on Child Development in Macao - Lao, Pak Lun (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Classroom Supports For Primary 5 to Form 3 Students with Emotional and Behavioural Challenges: A Case Study Approach - Lao, Pek Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門長者對樂齡科技的感知及應用動機研究 =: Elderly's Perception and Motivation for the Application of Gerontechnology in Macau - Lee, Hou Sun (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

探討透過「五感教學」進行幼兒社交情緒教育之行動研究 =: Action Research on Teaching the Social Emotion in Children by Using on Five-Senses Teaching Approach - Lei Weng I (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Virtual Meetings: How to Increase Communication Effectiveness - Lei, Chio Lan (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Understanding Stakeholders’ Perspectives Towards Serious Games for Vocational Training for People with Intellectual Disabilities in Macau - Lei, Choi On; Cardoso, Jorge C. S. (Entertainment Computing – ICEC 2022, 2022)
People with intellectual disabilities need vocational training and support in order to be able to get into the work market and maintain their workplace. In Macau SAR, China, the vocational training ecosystem still operates in fully classic, in-person, fashion, which means it is susceptible to pandemic situations such as COVID-19. This causes a big disruption to the training when isolation measures are in place. Our goal is to study the introduction of serious games for vocational training of people with disabilities in Macau. This work presents a study to assess the training benefits of serious games and usability factors, understand the acceptability and adoption factors/benefits of serious games for vocational training for people with intellectual disabilities and associated stakeholders in Macau.
Keywords: People with intellectual disabilities; Serious games; Vocational training

Exploring Teachers' and Students' perceptions in Formative Assessment Through Project-based Learning for Students Included in Mainstream Schools - Lei, Lei Peng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring Teachers' Experiences and Perceptions of the Use of the IEP with Students with ASD in Primary Schools - Lei, Mei Seong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

土生葡人和亞洲葡裔在三藩市灣區 =: MACANESE AND LUSO-ASIANS IN THE SAN FRANCISCO BAY AREA - Leong Wong, Un Na (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations PhD in History (D-HIS); University of Saint Joseph; 三藩市; 亞洲葡裔; 土生葡人; 灣區; 身份認同

Parental Perspectives on Inclusive Education in Macau - Leong, Ka Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Study of the Professional Development of Mid-High Level Management Personnel of Non-Tertiary Education in Macau=: 澳門非高等教育中高層管理人員專業發展之研究 - Leong, Ka Na (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Financial Valuation of Under Armour - Leong, Ka Wa (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Moral Self-Regulation or Consistency: The Role of Cultural Values and Workplace Status - Leong, Kin Hei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

An exploration of building up the quality of parent-child relationship in residential childcare in Macao - Leong, On Na Ribeiro; Liu, Shu-Wen (Asian Social Work and Policy Review, 2022)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/aswp.12252

The Financial Valuation of Waste Management, Inc: Daniela Wai Ka, Leong - Leong, Wai Ka (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Financial Valuation of Walmart Inc - Lestro, Gonçalo Nuno das Neves Arrojado (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study of Macao's role as arbitration seat for commercial disputes between China and portuguese-speaking countries - Leung, Cheok Si (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

COP21 COMPLIANCE AND SUSTAINABLE DEVELOPMENT THROUGH INTEGRATED SOLID WASTE MANAGEMENT: IMPLEMENTATION PERSPECTIVES OF THE CIRCULAR ECONOMY IN THE PEARL RIVER DELTA AREA - Li, Warren Man Ho (University of Saint Joseph, 2022)
The global living standard improved significantly in the last decades and China moved 800 million people out of poverty since 1980. However, production and consumption in their current forms are unsustainable in matters of resource and energy use and involved emissions with their significant ecological impact. The global human community committed itself in the COP21 Agreement of Paris 2015 to reduce Green House Gas (GHG) emissions based on National Determined Contributions (NDCs) in order to limit the increase of global average temperature below 2°C or better 1.5°C above pre industrial levels. This commitment entails a comprehensive transformation of the current social and economic system in view of decoupling economic growth from both resource extraction and GHG emissions, in view of fostering a resource sensitive and CO2 neutral Circular Economy (CE) based on Sustainable Development (SD). China submitted its first Intended Nationally Determined Contributions (INDCs) in 2015 with policies and measures affecting 15 major areas. In 2020, President Xi Jinping announced the commitment to peak China’s carbon dioxide emissions before 2030 and achieving carbon neutrality before 2060. Proper and Integrated Resource and Waste Management is central on the way to achieve the transformation into a CE. The State Council of the People’s Republic of China (PRC) released its plan “生活垃圾分类制度实施方案” to promote source separation of household waste on March 30, 2017 aiming at the recycling rate for household waste to reach 35% by 2020 for the selected cities. The first China’s Mandatory Waste Source Separation Law “廣州 市生活垃圾分類管理條例” was enforced by the city of Guangzhou on July 1st, 2018. One of the key strategic plans in China is the development of the Greater Bay Area (GBA) with its comprehensive development plan released on February 18, 2019. Following the INDCs by China, parts of the GBA Development Plan emphasize that the development of the CE systems and the implementation of extended producer responsibility (EPR), are effective principles to provide financial incentives in view of reducing embedded emissions in material and processes. The present research studied, analysed, and compared the MSW treatment strategies, rules, regulations, and retrievable data, which lead to MSW source separation and the reverse logistic of separated waste among 4 selected cities Guangzhou, Zhuhai, and the 2 S.A.R.s of Hong Kong and Macao. The experience and comparison from Guangzhou and Hong Kong revealed that a Top-down approach in environmental policy decision making is more efficient and is able to implement necessary policies faster. However, the experiences from Guangzhou and Zhuhai indicate, that also a more participatory implementation process is crucial, as it enables the involved stakeholders to express their experiences and opinions properly, which can lead to a higher level of policy feasibility and acceptance and a smoother operation accompanied with a higher effectiveness. For the two SARs, to achieve the objective to increase the recycling rate, the local Government must seek approval from China’s Central Government to allow locally generated recyclable material, in their original form, to enter mainland China for further treatment and to be turned into secondary raw material. Without such a proper support by a reverse resource logistic from the mainland, the CE schemes, such as the Mandatory Waste Source Separation, Producer Responsibility Scheme (PRS), Waste Charging Scheme, are not able to be implemented effectively. The current approach of the Local Government purchasing of recycling and exportation services of recyclable materials from private companies, and the sole reliance on existing market forces to handle, process, and export recyclable material out of the S.A.R.s cannot ensure a reliable and continuous operation in view of mitigating involved emissions. By way of a comparative analyses, the present investigation works out and distils suggestions for best practices of implementing the CE to comply with targets of emission reductions
Keywords: Circular Economy (CE); Sustainable Development Goals (SDGs); Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph; Waste Hierarchy; Zeroand- Low-Waste-Systems

澳門幼稚園融合教育專責團隊合作模式之探究 =: A Study on the Cooperation Model of Kindergarten Inclusive Education Collaborative Team in Macau - Li, Xiao Hua (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

To Identify Buyer Behavior Towards Online Shopping Due to Covid-19 Pandemic in Hong Kong - Lio, Cheng Tong (University of Saint Joseph, 2022)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

澳門小學教師經營融合班級的困擾與特教專業知能之關係研究 =: The Relationship Between Teachers' Difficulties in Operating Inclusive Classes and the Professional Competence of Special Education in Macao Primary Schools - Lo Ka Chon (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

探討第29/2020號行政法規對特殊教育教師為特殊需求學生評估的影響 =: Exploring the impact of Administrative Regulation No. 29/2020 on the evalution of the special education teachers for students with special needs - Lo, Chon In (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門中年男士焦慮狀況、求助態度與自殺意念之相關研究 =: A Correlational Study Between Anxiety and Help-Seeking Attitudes on Suicidal Ideation of Middle-Aged Men in Macau - Lo, Kuan U. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The relationship between social support and death anxiety among elderly living alone in Macao - Lo, Pou Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

LIFE CYCLE ASSESSMENT OF CONSTRUCTED WETLAND SYSTEMS FOR TOURISM UNITS WASTEWATER TREATMENT - Lo, Weng In (University of Saint Joseph, 2022)
With water being an essential for life on Earth, it is vital to preserve it and regenerate it, in order to be available for a myriad of uses. Though many types of wastewater management and treatment are available, most rely on high energy input and are therefore not ideal for many circumstances. Constructed wetlands (CW) are an alternative nature-based solution to be applied to wastewater treatment. This study undertakes a Life-Cycle Assessment (LCA) of a CW as a means of wastewater treatment and aims to understand how these systems can be an environmentally conscious alternative. The CW under study is located in a rural mountain area in the north of Portugal. Receives wastewater from a tourism unit and operates with horizontal subsurface. The LCA analyses the CW through the construction, operation (treatment), and composting phases. This approach allows the entire scope of the life cycle to be included, of which, the composting phase has been absent in similar LCA previously undertaken. Analysis focuses on the impact categories: Ozone Layer Depletion Potential, Global Warming Potential, Acidification Potential, Eutrophication Potential and Human Toxicity Potential. Of the five categories, none increase during the treatment phase, and indeed, Acidification Potential, Eutrophication Potential, and Human Toxicity potential all decrease. Ozone Layer Depletion Potential and Global Warming Potential increase significantly during the construction and composting phases respectively. Both can be rationalized, with the former being a result of heavy diesel machinery use in construction and the latter a natural byproduct of composting. The results are net positive and display the ability for CW as a low energy wastewater treatment which can limit environmental impact by choice of construction and composting methodology
Keywords: Lifecycle assessment; Master of Environmental Sciences and Management (MESM); University of Saint Joseph; constructed wetland; wastewater treatment

Neuroeconomics Applications Based on Multiple Monitoring Tools. - Lobo Marques, J. A. (2022)

Epidemic analytics for decision supports in COVID19 crisis - Lobo Marques, Joao Alexandre; Fong, Simon (Springer, 2022)
Covid-19 has hit the world unprepared, as the deadliest pandemic of the century. Governments and authorities, as leaders and decision makers fighting against the virus, enormously tap on the power of AI and its data analytics models for urgent decision supports at the greatest efforts, ever seen from human history. This book showcases a collection of important data analytics models that were used during the epidemic, and discusses and compares their efficacy and limitations. Readers who from both healthcare industries and academia can gain unique insights on how data analytics models were designed and applied on epidemic data. Taking Covid-19 as a case study, readers especially those who are working in similar fields, would be better prepared in case a new wave of virus epidemic may arise again in the near future.

Exploring Current Collaboration Practices of Regular and Resource Teachers within Inclusive Education: An Analysis of Teacher Perspectives - Loi, Sio Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Career Development of People with Physical or Sensory Impairments in Macau - Ma I Mei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Message from Program Chairs - Ma, J.; Du, W.; Lu, W. (Proceedings - 2022 IEEE/ACIS 22nd International Conference on Computer and Information Science, ICIS 2022, 2022)
ISBN: 9781665494632

Influencer Industry Development in Macau: Case Study about Social Media Influences in Macau - Madan, Roberto (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Research and Technology Development Achievements During the COVID-19 Pandemic—An Overview - Marques, João Alexandre Lobo; Fong, Simon James; Li, G.; Arraut, Ivan; Gois, F. Nauber Bernardo; Neto, José Xavier (Epidemic Analytics for Decision Supports in COVID19 Crisis, 2022)
At the beginning of 2020, the World Health Organization (WHO) started a coordinated global effort to counterattack the potential exponential spread of the SARS-Cov2 virus, responsible for the coronavirus disease, officially named COVID-19. This comprehensive initiative included a research roadmap published in March 2020, including nine dimensions, from epidemiological research to diagnostic tools and vaccine development. With an unprecedented case, the areas of study related to the pandemic received funds and strong attention from different research communities (universities, government, industry, etc.), resulting in an exponential increase in the number of publications and results achieved in such a small window of time. Outstanding research cooperation projects were implemented during the outbreak, and innovative technologies were developed and improved significantly. Clinical and laboratory processes were improved, while managerial personnel were supported by a countless number of models and computational tools for the decision-making process. This chapter aims to introduce an overview of this favorable scenario and highlight a necessary discussion about ethical issues in research related to the COVID-19 and the challenge of low-quality research, focusing only on the publication of techniques and approaches with limited scientific evidence or even practical application. A legacy of lessons learned from this unique period of human history should influence and guide the scientific and industrial communities for the future.
Keywords: COVID-19; Research cooperation; Research ethics; Scientific research; Technology development

The Influence of Online Payment Methods on Consumers’ Online Purchase Behavior: The Case of Young People in Macau - Martins, Maria Cordes Aniceto (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Climate Alarmism or Lukewarming? How So-Called American Conservatives Should Think About Climate Change - McNabb, T. D; Devito, M (Ethics & the Environment, 2022)
In this essay we argue that, based on current scientific data, the most prudential course of future actions that an American conservative can take, is one that assumes what we call climate change alarmism. In order to establish this thesis, we first provide a basic overview of the relevant climate change science, as well as give an analysis of the alarmist and lukewarming dialectic (the two primary interpretations of the data). We then move to develop our environmental wager. Finally, following Roger Scruton, we end this work by proposing what sort of policies conservatives should endorse going further.

Classical theism and Buddhism: connecting metaphysical and ethical systems - McNabb, Tyler Dalton; Baldwin, Erik Daniel (Bloomsbury Academic, 2022)
"As an atheistic religious tradition, Buddhism conventionally stands in opposition to Christianity, and any bridge between them is considered to be riddled with contradictory beliefs on God the creator, salvific power and the afterlife. But what if a Buddhist could also be a Classical Theist? Showing how the various contradictions are not as fundamental as commonly thought, Tyler Dalton McNabb and Erik Baldwin challenge existing assumptions and argue that Classical Theism is, in fact, compatible with Buddhism. They draw parallels between the metaphysical doctrines of both traditions, synthesize their ethical and soteriological commitments and demonstrate that the Theist can interpret the Buddhist's religious experiences, specifically those of emptiness, as veridical, without denying any core doctrine of Classical Theism. By establishing that a synthesis of the two traditions is plausible, this book provides a bold, fresh perspective on the philosophy of religion and reinvigorates philosophical debates between Buddhism and Christianity"–
Keywords: Buddhism; Comparative studies; Relations Theism; Theism

Cognitive Science of Religion and Classical Theism: A Synthesis - McNabb, Tyler Dalton; DeVito, Michael (Religions, 2022)
Launonen and Mullins argue that if Classical Theism is true, human cognition is likely not theism-tracking, at least, given what we know from cognitive science of religion. In this essay, we develop a model for how classical theists can make sense of the findings from cognitive science, without abandoning their Classical Theist commitments. We also provide an argument for how our model aligns well with the Christian doctrine of general revelation.
0 citations (Crossref) [2022-09-21]

Breve Abordagem ao Percurso Vivencial e Poético de Um ‘Autor Maldito’: Carlos Augusto Montalto de Jesus (1863-1932) na China e pelo Mundo Fora - Morais, Isabel (Mapas Esquivos” no Centenário de Sophia de Mello Breyner Andresen (1919-2019): Navegação a Oriente, 2022)

Exploring The Influence of Culture on Parents’ Attitudes Towards Inclusive Education in Macao - Moreira, Irene Mitsiko Sadoyama (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Going to Church in Medieval England by Nicholas Orme (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2022)
0 citations (Crossref) [2023-01-27] Publisher: The Catholic University of America Press

The combat of truth and error: Newman and Chesterton on heresy - Morgan, Stephen (Lead Kindly Light. Essays for Ian Ker, 2022)

The Fire “Once Kindled on Moriah”: Wojtyła and Newman on the Conditions for the Proposal of Christ - Morgan, Stephen (Newman Studies Journal, 2022)
0 citations (Crossref) [2023-01-27] Publisher: The Catholic University of America Press

Alcatraz revisited - Morrison, Keith (Macau Business, 2022)

Replication research in education: a guide to designing, conducting and analysing studies - Morrison, Keith (Routledge, 2022)
"Providing an overview of key issues in theory and practice, Replication Research in Education is designed to identify and discuss the benefits and challenges facing replication studies in education. Both clear and practical, this ground-breaking volume covers how to introduce, develop, conduct, report and discuss these studies, and the issues they raise for policy and practice. Bridging theory and practice, this book considers what replication research should look like, how it should be conducted and how to judge when it has been successful. It enables researchers to plan and conduct studies successfully, from their earliest stages through to completion. This key text: brings together in a single volume, existing issues, claims and counter-claims, discourses and practices of replication introduces, covers, and extends this field of research, indicating its possibilities and limits expands and adds to existing discussions and practices will enable researchers to design, conduct, evaluate and critique studies. The comprehensive and exhaustive coverage of issues and practices within Replication Research in Education make it a "must read" for all novice and experienced educational researchers who are considering, conducting, and reviewing replication studies in education"–

Sustainable development or survival of Macau? - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | In June of this year, a publication entitled ‘Macau’s sustainability and diversification’ noted that Macau’s ‘economic volatility caused by an unbalanced industrial structure restricts the diversified development of society. Economic diversification is the only way for Macau to achieve sustainable development’. Nothing new there, and, anyway, such a singular view is unconvincing. What about other aspects of society? Diversity is not singular, and it requires inclusion.
Section: Macau Business

Automatic Classification System for Subjects Exposed to Short-Term Stress Based on Facial Expression Analysis and ElectroDermal Activity - Motta, P.; Silva, B.; Furtado, F.; Lobo Marques, J. A. (2022)

Traços transdisciplinares na obra do Padre Manuel Antunes: uma análise crítica à luz da Carta da Transdisciplinaridade /UNESCO-1994 - Mucheroni, M. L; Fernandes-Marcos, A (Repensar Portugal, a Europa e a Globalização – Saber Padre Manuel Antunes, SJ – 100 anos, 2022)
Toda a obra e pensamento do Padre Manuel Antunes se revestem de características de grande abrangência e de capacidade de abertura à inovação, na perspetiva de que o pensamento crítico, sendo perscrutador do desconhecido, enquanto questiona o conhecimento adquirido ou em pesquisa, não se pode fechar em si mesmo ou separar partes do conhecimento de um todo que constitui o universo, e o homem como parte deste, já que se objetiva a compreensão última do Todo. Encontramos, portanto, traços de transdisciplinaridade na obra e pensamento do Padre Manuel Antunes indicando um pioneirismo relativamente ao movimento da transdisciplinaridade que arranca com o primeiro congresso da área e a respetiva carta daí resultante. Neste artigo, os autores propõem uma análise crítica da obra do Padre Manuel Antunes à luz dos princípios fundacionais encontrados na Carta da Transdisciplinaridade de 1994.

The Future of Cosmetics Marketing Strategy: An Exploratory Study into How Neuromarketing Can Deepen its Understanding - Neto, Andreia Da Conceição (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

How Schools in Macau Create Intellectual Capital for Development - Ng, Shun-wing; Kwan, Yee-wan (Managing School Intellectual Capital for Strategic Development, 2022)
This chapter describes how intellectual capital comprising human capital, structural capital, and relational capital are being created for school development and quality assurance in Macau. Macau has aimed to catch up with the global education reform by subsidising majorities of the non-tertiary sectors and promulgating Decree Laws regarding education policies and development. Despite the significance of the intangible assets of the intellectual capital, the chapter also attempts to analyse the issues and challenges towards the management of intellectual capital emerging simultaneously in the transition process in the educational context of Macau. It suggests capitalising on the accumulated school knowledge for school effectiveness. This chapter depicts the chronological development of Macau's education reform by analysing how Macau has attempted to emancipate its education institutions from the period of quasi-closed system to that of the open system by creating different types of intellectual capital in school. It discusses the emerging issues and challenges simultaneously in the transition process of educational development in Macau, namely before and after returning its sovereignty to the Chinese government.
Num Pages: 12

The Emergence of Resources Seeking Chinese Firms’ Specific Advantages in Emerging Market - Ojo, Olukayode Iwaloye; Im, Hong Kei; Adeniyi, Damilola Olarewaju; Gbadamosi, Ayantunji; Alves, Jose; Link to external site, this link will open in a new window; Trimarchi, Michael (Sustainability, 2022)
It is argued that the role of the Chinese government to support the cross-border operations of Chinese firms is to assist these firms in overcoming their limited established brands, and their disadvantages in technology and managerial resources, which were also the reasons why such firms decided to enter emerging markets instead of developed markets. This strategic choice is preferred to avoid direct confrontation with established firms from developed countries endowed with superior ownership advantages. Therefore, Chinese resources seeking firms innovate by increasing investment in developing and emerging markets to develop unique ownership advantages for sustainable market development and competitive advantage. This research investigates the ownership advantages of resources seeking Chinese firms in these markets using the OLI theory. The paper contributes to explaining the specific advantages of Chinese MNEs when entering emerging markets. The study applied a two-stage qualitative methodology to examine Chinese firms operating in Nigeria. The first stage included an exploratory study based on interviews with key informants and experts while the second stage included a case study methodology. The study focused on resources seeking Chinese MNEs operating in Nigeria.
Num Pages: 8345 Place: Basel, Switzerland Publisher: MDPI AG
Keywords: OLI theory and Chinese firms; emerging markets; ownership advantages; resources seeking MNEs

Teacher Efficacy: Inclusive Practice to Support Learning English as a Foreign Language (EFL) among Chinese-Speaking Students with Dyslexia in Macau - Oksana, Zorina (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Applied Interactive Mindfulness: a virtual reality grave mourning user experience in the Chapel of St. Michael in Macao - Olga Ng Ka Man, Sandra; Caires, Carlos (The creative process: reflections on contemporary creativity, 2022)
It has been proven in numerous research that mindfulness can be helpful to reduce stress and chronic pain (Hall, 2014; Lindström, n.d.; Tong et al., 2015). While interactive mindfulness has been one of the focuses in the recent mobile applications market, usually tackling three essential human senses: audio, visual, and touch, each mobile application has quite some different approaches in terms of interactivity. Some focus on the touch and visual, and some on audio (environmental sounds or instructing meditation). Immersing oneself in virtual reality (VR) creates a constant stream of interactivity. Nonetheless, what are the conditions for an (in)tangible virtual reality to be more effective? Under the COVID-19 pandemic and lockdown since the end of 2019, Macao has been facing a social concern that we cannot travel easily to visit our decedents’ graves abroad, let alone the existing concerns of expensive burial services, lack of space, and alternative burial options. Also, taking into consideration that standard funeral service in Macao is often too brief, and getting briefer, thus lacking the opportunity to properly farewell the decedent, this research is proposing a virtual reality 3D model construction of the Chapel of St. Michael, located in St. Michael the Archangel Cemetery in Macao, to be streamed on a 360 virtual tour platform, Kuula. co. By immersing in this virtual reality, the participant is to have a single user experience for mindfulness with the decedent. To ensure valid and reliable results that address the research aims and objectives, a single-user experiment is going to be set up with multiple electronic devices, namely, the smartphone iPhone X with cardboard VR, the tablet iPad Pro, and the Oculus Quest 2. The methodology to collect the data will be using observation and simulation. The experiment will be started with an introduction to the project and conducted with no instruction, allowing users to explore and examine all features in this immersive experience. Along with a post-experience survey (interview + questionnaire), we seek its conditions and impacts on Macao residents in terms of interactive mindfulness and participants’ expectation of testing, for the first time in Macao, a virtual reality grave mourning experience.

(Un)Directed Reading, an interactive kiosk to encourage writing and reading - Olga Ng Ka Man, Sandra; Estadieu, Gerald; Farinha, Daniel (The creative process: reflections on contemporary creativity, 2022)
(Un)Directed Reading is an interactive installation (Edmonds, 2010) initially derived from the “Directed Reading” course, which all undergraduate students at the University must take during their final year. In this course, students are assigned different writing exercises and research assignments to open their creative and constructive minds in writing (EdwardsGroves, 2012; McVey, 2008). Every year, at the end of the course and after a selection process, a collection of stories is uploaded to a database of original stories. We then developed an open-source application to print a receipt ticket from a thermal printer with a randomly picked story every time a user pushes a button. An arcade game-style button is installed on a kiosk designed in collaboration with students and set on the university's campus (left photo). The printed receipt presents a short extract of one of the stories and a QR code that links to the full story decorated with illustrations. In a modern society where most of our interactions are audiovisual-based, young generations are less and less encouraged to read and even less to write. By offering a simple kiosk installation with short stories and graphical illustrations, we propose a new interactive interface that can easily engage passers-by to eventually stimulate their reading and creativity. By reading these stories, students, professors, staff, and visitors can be surprised by the talent of our students, as it stimulates students to write new pieces to be selected. The interactive kiosk was accessible to all for a period of 3 months with 23 stories during which we automatically collected some data to use in quantitative analysis. In this first run, we focused on data from the user's interactions such as story printed, story read, date and time. It allowed us to see the ratio between the printed receipt and the actual online reading of a story and more.

Job Satisfaction, Dilemmas and Causes of Hearing Impaired People in Macau =: 澳門聽障人士工作滿意度、困境及其原因 - Pang, Wan I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

A Study of Primary School Students’ Motivation to Learn English as a Foreign Language in the Context of Content and Language Integrated Learning (CLIL) – A Case Study - Pau Ka Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring Differentiated Teaching in Primary Mathematics Classes in Macau - Pearce, Josef Nicolai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Succession in Chinese family business: transgenerational transmission of social capital in Macao - Phillips, Jenny O. L. (University of Saint Joseph, 2022)
Macao is well known for its gaming industry. However, there are also many traditional small-to-medium enterprises which are family-owned and run. There is no doubt that social capital is one of the key competitive advantages that family businesses possess, particularly when it comes to Chinese businesses with strong family values that emphasize the importance of trustworthiness and guanxi (relationships). As opposed to other forms of capital, social capital cannot be passed from one generation to another through the will of the incumbents. So, how is social capital passed on in family businesses from one generation to the next? Based on an in-depth study of five cases of successful family businesses in Macao, this research identified the forms of social capital present in business families and the succession process of these firms. From the generalizations drawn from the five cases, a theoretical framework is proposed to understand the intergenerational transmission of social capital in Chinese family businesses
Keywords: China Macau (Special Administrative Region); Family-owned business enterprises

澳門唐餅文化研究 = A Study of the Culture of Traditional Chinese Pastry in Macau - Pong, Chio Fai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Teachers’Perceptions of Performance Appraisal in a Secondary School in Asia: A Case Study - Potger, Matthew Rodney (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Selection for winners impacts the endocrine system in the Siamese fighting fish - Ramos, A.; Gonçalves, D. (General and Comparative Endocrinology, 2022)
In southeast Asia, males of the Siamese fighting fish, Betta splendens, have been selected across centuries for winning paired staged fights and previous work has shown that males from fighter strains are more aggressive than wild-types. This strong directional selection for winners is likely to have targeted aggression-related endocrine systems, and a comparison between fighter and wild-type strains can bring into evidence the key hormones implicated in aggression. Here, we compared the plasma levels of the androgen 11-ketotestosterone (KT) and of the corticosteroid cortisol (F) in F2 males of a fighter and a wild-type strain raised under similar laboratory conditions. We show that F was generally lower in fighter as compared with wild-type males, while no overall differences in KT levels were detected between strains. When presented with a mirror-induced aggressive challenge, post-fight levels of F increased but more significantly so in wild-type males, while KT increased in males of both strains. After the challenge, fighter males had higher levels of KT as compared with wild-type males, while the pattern for F was opposite. As compared with animals in social groups, wild-type males placed under social isolation had lower F levels, while KT decreased for fighters. Taken together, this data suggests that while wild-type males responded to aggression with an increase in circulating levels of both androgens and corticosteroids, males selected for winning fights maintained a blunt F response, increasing only KT levels. These data agree with the hypothesis that a combination of high levels of androgens and low levels of corticosteroids is associated with high aggression. Overall, these results seem to indicate that selection for winning had a stronger impact in the hypothalamus-pituitary-interrenal axis than in the hypothalamus-pituitary–gonadal axis in B. splendens.

Environmental Education in Macau’s Schools: A Case Study on Teachers' Perceptions of Experiential Pedagogies - Reh, Paul Thu (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Replacement or plume fallout? Both, please! Evidence from active and fossil VMS systems - Relvas, J M R S; Barriga, F; Pinto, A; Marques, A F; Carvalho, J; Dias, A Á (The critical role of minerals in the carbon-neutral future, 2022)

A Financial Valuation of Realty Income Corporation - Rodrigues, Ricardo David Almeida Fernandes (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Crisis Management – Dystopic Scenario VS Real-World Pandemic: The Case of Saramago’s Blindness that Anticipated the Initial Managerial Approach to Covid-19 Pandemic Taken by Unprepared Governments Worldwide - Rouxinol, Hernâni Tiago Caveirinhas (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Analysis of the Impact of Environmentally Sustainable Practices on Macau Hotels Guest Engagement - Santos, Ana Sofia Kong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Impact and Attitude of Urban Renewal on Citizen Residents in Macau - Si Cheng Iok (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Macau: 7 desenhos, 7 artistas, 7 perfis, 7 pontes entre a China e o mundo lusófono - Simoes, José Manuel (Em português: falar, viver e pensar no século XXI, 2022)

Macau: Carlos Marreiros, macaense, luso-descendente – um testemunho de uma carreira internacional de um arquiteto e artista - Simoes, José Manuel (Em português: falar, viver e pensar no século XXI, 2022)

The Media in São Tomé and Príncipe and Its Contribution to the Country Development - Simoes, José Manuel (China, Guinea-Bissau, Mozambique and São Tomé and Príncipe – From sporadic bilateral exchanges to a comprehensive multilateral platform, 2022)

The pedagogical role of ethics and deontology for future professionals of communication and media: How to develop and nourish virtues - Simões, José Manuel (IV Jornadas Innovación Educativa en Comunicación y Alfabetización Mediática, 2022)
- Flipped classroom metodologiak eskaintzen dituen abantaila pedagogikoak (Ander Goikoetxea Pérez, Hannot Mintegia Beaskoa). - Conocimiento de la actualidad informativa a partir de la participación del alumnado que ejerce de periodista y lector crítico (María del Mar Rodríguez González, Iñigo Marauri Castillo, Guillermo Gurrutxaga Rekongo). - El papel del procesamiento dual de la información en la discriminación de noticias falsas (José Manuel Meza Cano, Cinthia Aranda-Solís, Blanca Olalde López de Arechavaleta, Santiago Palacios Navarro). - No trespassing: Arau, traba eta mugen bidezko metodologia sortzaile bat kazetaritza gradurako (Hannot Mintegia Beaskoa, Ander Goikoetxea Pérez). - Learning digital journalism: Analysing web media in comparative perspective to learn what is quality in digital communication (Javier Díaz-Noci). - El sistema híbrido vehículo de comunicación educativa (Antonio Vaquerizo Mariscal). - The pedagogical role of ethics and deontology for future professionals of communication and media: How to develop and nourish virtues (José Manuel Simões). - Desgaitasuna duten pertsonen Komunikazio ikasketetako prestakuntzari buruzko gogoetak (Terese Mendiguren, Jesús Ángel Pérez Dasilva, Koldobika Meso Ayerdi, Simón Peña, Ainara Larrondo, María Ganzabal). - Teaching Communication (and Journalism) History from Social History Theory: Some proposals (Javier Díaz-Noci).

Um país, dois sistemas: reflexões sobre o panorama mediático em língua portuguesa em Macau - Simoes, José Manuel (Em português: falar, viver e pensar no século XXI, 2022)

A Psychological and Phenomenological Analysis of Chinese People Who Are Not-Capable-Of-Saying-No - Song, Sok Fong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

Feasibility study of a Glamping Business in óbidos, Portugal - Sousa, Eugénio Ricardo de (University of Saint Joseph, 2022)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Study of the Macau Personal Data Protection Legal Regime - Sun, Wai Lon (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Mangroves as a nature-based solution for water and climate change issues in Macao: from scientific research to environmental education - Tagulao, Karen (Fostering applied research on the synergies between biodiversity and climate, 2022)
Publisher: Deutschland / Bundesamt für Naturschutz

Nature-Based Solutions for Environmental Education in the East Asian Context - Tagulao, Karen Araño (Enhancing Environmental Education Through Nature-Based Solutions, 2022)
Environmental education (EE) has long been practiced worldwide, while Nature-based solutions (NBS) is a relatively new concept. This chapter aims to provide an overview of the EE and NBS practices in East Asia and evaluate how these two valuable applications can be used concurrently. East Asia has a well developed environmental education (EE) programs and activities, both in formal and informal education. These ranges from developing green schools and campuses to establishing policies and acts. While EE has been actively practiced for decades in the region, the adoption of NBS to address environmental and societal challenges is limited. The educational benefits and opportunities from NBS are also lacking. Although there are some projects that can be classified as NBS, like the use of wetlands for wastewater treatment, they are not clearly categorized as one. These projects are also not integrated into environmental education programs. Considering this, the region should develop innovative environmental education programs for schools, universities and communities, that integrate NBS projects. Integrating the two together will boost the effectiveness of environmental education in raising environmental awareness and changing the environmental attitude and behavior of people, which will also help address societal issues.
Keywords: Environmental awareness; Environmental policies/acts; Green schools; Green universities; Sponge cities; Wetlands

Assessment of Methodologies Employed by Change Agents in Managing Organizational Change: A Case Study in the Hospitality-Gaming Industry - Tagulao, Thea Clarice Saavedra (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

街舞在澳門的在地化的研究1980-2020=: Localization of Street Dance in Macau 1980-2020 - Tai, Chou Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The Effects of an Aikido Based Psychological Intervention Program in Workplace Stress - Tam, Heng Kun (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Children's Learning Interest and Social Interaction Through Play: An Action Research Case Study in A Pre-School in Macau= 運用遊戲活動增進幼兒學習興趣與社交互動之行動研究 - 以澳門一幼兒班為例 - Tang Pui I (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Motivations of preservice teachers: a case study on career changers to teaching in Macau - Thang, Tony Mana (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Action Research on Supporting Children's Chinese Literacy Learning by Using Visualization Method - Tong, M. K.; Sun, C. R. (2022)

A Financial Valuation of Netflix, Inc - Tong, Si Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploring the Application of Online Learning Environment in the Teaching and Learning of Chinese in Elementary Education Sector in Macau=: 探討網上教學摸式在澳門小學中文科教與學的應用 - U Ka Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門融合教師職業壓力來源研究: 以澳門某私立小學教師為例 = Occupation al Stress sources of inclusive education teachers in Macau - A study on primary shcool teachers in a private school - U, Ka Chon (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Research study on the relationship between work stress and well-being of primary school teacher in Macau =: 澳門小學教師的工作壓力與幸福感之相關研究 - U, Ka Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Enhancing Secondary Students' English Language Skills and Engagement through Cooperative Learning: An Action Research Study - U, Tat Si (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Integrative Educational Platform Focusing on Steam Approaches: A Macau Case-Study - Un Man Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Applying Social Skills Improvement System Intervention Guide to Primary Students with ADHD and Problem Behaviors in Macau: A Case Study - Ung, Hou Cheang (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

The Relationship Between Work-Life-Balance and Burnout: Effect of Gender and Sector of Activity - Vai, Han Kuoc (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

Relationship Between the Academic Achievement and Extra-curricular Tutoring of Primary Students: Perspectives From the Parents = 課外補習與小學生學業成績之間的關係—-來自家長的視角 - Vong, Sok Kuan (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Key Issues for Digital Factory Designing and Planning: A Survey - Wang, Han; Du, Wencai; Li, Shaobin (Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing, 2022)
Digital Factory (DF) planning is the key of intelligent factory construction, where intelligent production technologies of big data analysis, cloud computing, blockchain, Internet of Things, artificial intelligence, 5G, Time Sensitive Network (TSN), Digital Twin (DT), additive manufacturing are included. By applying the modern techniques, DF performs great advantages on the aspects of product lifecycle management, enterprise resource planning, operation management, supply chain management, real-time database construction, advanced process control, as well as the new technologies of distributed control system and fieldbus control system. This article delivers a review of key issues of DF top-level design and planning from the aspects of networking, precision, automation and digitalization. Solutions are explored based on 5G, TSN and DT advanced technologies, literately and practically. Additionally, the article describes the method and application of efficient big data comprehensive solution. Therefore, this study contributes valuable decision-making support for DF applications.
Keywords: 5G; Big data comprehensive solution; Digital Factory; Digital twin; Time Sensitive Network

Exploring Macau Instagrammers’ Motivation for Using Instagram Story - Wong, Choi I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

澳門露宿者服務社工在新冠疫情情間的工作與挑戰 = The Opportunities and Challenges Facing Macau Social Workers Who Work with Homeless People During the Pandemic of 2020 : A Case Study - Wong, Choi Leng (University of Saint Joseph, 2022)
Edition: The Opportunities and Challenges Facing Macau Social Workers Who Work with Homeless People During the Pandemic of 2020
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Perception About Challenges and Opportunities of Social Enterprise in Macau - Wong, Chong Chio (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

A Study on Spiritual Well-Being of Secondary School Teachers in Macau - Wong, Kuan Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Parental Stress and Marital Satisfaction in Macao: The Mediating Effect of Parental Involvement - Wong, Pek Ieng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Effects of Family Support, Friends Support, Supervisor Support, Co-worker Support, and Organizational Support to Resilience and its Effects to Work Engagement - Wong, Sio Peng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

澳門普校教師對融合生的認知印象及接納態度之研究 =: A Study of Teachers's perceptions of cogitve impressions and aceptance attitudes on inclusive students in Macau - Wong, Tong Cheong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Effect of Organizational Justice on Work Engagement Between Foreigner and Local Workers in Macau: The Moderating Effect of Organizational Commitment - Wong, Wai Fai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

CASE STUDY ON ART INTERVENTION WITH CHILDREN WITH AUTISM SPECTRUM DISORDER - Wu, Hoi Pio (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Challenges of Nursery Teachers in the Early Childhood Inclusion Classes: A Qualitative Study of Macao Nursery Teachers - Wu, Ma Lei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門大學生在內地的就業意向及其影響因素調查=: A Study on Macau Undergraduate Students’ Working Intention in Mainland China - Wu, Zhi Ying (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Self-perception of primary students with dyslexia in Macao =: 探討澳門小學讀寫困難融合自我探索學習現況及挑戰 - 何素儀 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Impact of Macau Teaching Professionalism to Kindergarten teachers' Occupational Identity and Competency: A Study on In-service Teachers' Perception = 澳門教師專業化對幼兒教師職業身份認同和勝任感的影響：來自在職教師的看法 - 張翟 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

運用正念呼吸練習支援兒童專注力發展之行動研究 =: An Action Research on using mindfulness breathing exercise to support the development of children's concentration - 王嘉蘭 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

《學會閱讀》叢書第一輯 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

《學會閱讀》叢書第二輯 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文兒歌集 – 果子級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文學習卡 – 果子級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文學習卡 – 花兒級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文學習卡 – 葉芽級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

Macau Secondary School Teachers’ Attitudes Towards Inclusive Education and Concern Over It =: 澳門中學教師對融合教育的態度與憂慮之研究 - 陳瀅瀅 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Action Research on Drawing Guidance as an Intervention to Improve Chinese Writing of Primary Students with Dyslexia =: 繪畫活動介入引導讀寫障礙學生提升寫作能力之行動研究 - 黃郁羚 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Power Allocation for 5G Mobile Multiuser Cooperative Networks - Yin, Fagen; Du, Wencai (Journal of Advanced Transportation, 2021)
With the fifth generation (5G) communication technology, the mobile multiuser networks have developed rapidly. In this paper, the performance analysis of mobile multiuser networks which utilize decode-and-forward (DF) relaying is considered. We derive novel outage probability (OP) expressions. To improve the OP performance, we study the power allocation optimization problem. To solve the optimization problem, we propose an intelligent power allocation optimization algorithm based on grey wolf optimization (GWO). We compare the proposed GWO approach with three existing algorithms. The experimental results reveal that the proposed GWO algorithm can achieve a smaller OP, thus improving system efficiency. Also, compared with other channel models, the OP values of the 2-Rayleigh model are increased by 81.2% and 66.6%, respectively.
1 citations (Crossref) [2022-09-21]

Data Augmentation for Deep Neural Networks Model in EEG Classification Task: A Review - He, Chao; Liu, Jialu; Zhu, Yuesheng; Du, Wencai (Frontiers in Human Neuroscience, 2021)
Classification of electroencephalogram (EEG) is a key approach to measure the rhythmic oscillations of neural activity, which is one of the core technologies of brain-computer interface systems (BCIs). However, extraction of the features from non-linear and non-stationary EEG signals is still a challenging task in current algorithms. With the development of artificial intelligence, various advanced algorithms have been proposed for signal classification in recent years. Among them, deep neural networks (DNNs) have become the most attractive type of method due to their end-to-end structure and powerful ability of automatic feature extraction. However, it is difficult to collect large-scale datasets in practical applications of BCIs, which may lead to overfitting or weak generalizability of the classifier. To address these issues, a promising technique has been proposed to improve the performance of the decoding model based on data augmentation (DA). In this article, we investigate recent studies and development of various DA strategies for EEG classification based on DNNs. The review consists of three parts: what kind of paradigms of EEG-based on BCIs are used, what types of DA methods are adopted to improve the DNN models, and what kind of accuracy can be obtained. Our survey summarizes the current practices and performance outcomes that aim to promote or guide the deployment of DA to EEG classification in future research and development.
4 citations (Crossref) [2022-09-21]

Nowcasting Gross Domestic Product and Gross Gaming Revenue of Macau: a Theoretical and Conceptual Framework - Chau, Manuel; Lei, Weng Chi (2021)
This paper aimed to build up the theorical and conceptual understanding of future forecasting study of Macau’s GDP and Gross Gaming Revenue (GGR) by co-movement of economic indicators. Macau GDP and GGR showed co-movements with a number of time series economic indicators, including China’s exports and imports, China’s manufacturing PMI, non-manufacturing PMI, China's electricity production growth, share price of some Macau’s gaming operators, etc. These time series data can be found in statistics departments of China, Macau and Hong Kong, stock exchanges, and international organizations such as the International Monetary Fund (IMF), the World Bank, the World Trade Organization (WTO). Burns and Mitchell’s study in 1946 identified co-movements between economic indicators and being further carried out and developed leading, coincident and lagging indicators, which is essential for future econometric models and nowcasting techniques developments to study these co-movements. In particular, with the proper application of nowcasting techniques, future studies can exploit the data of leading and coincident economic indicators to forecast Macau’s GDP and GGR within an acceptable level of error. Since Macau is a “monotown,” where the gaming revenue makes a significant contribution to the economy. The forecasting of gaming revenue is crucial as it aids the gambling and tourism industries in preparing supply and provides information to policymakers to plan for the near future. This research also contributes to understand Macau’s economy by investigating its internal and external economic variables.

澳門教師文化回應教學認知與實踐研究 - Ge, Yun (2021)

IoT-Based Smart Health System for Ambulatory Maternal and Fetal Monitoring - Marques, João Alexandre Lobo; Han, Tao; Wu, Wanqing; Madeiro, João Paulo do Vale; Neto, Aloísio Vieira Lira; Gravina, Raffaele; Fortino, Giancarlo; de Albuquerque, Victor Hugo C. (IEEE Internet of Things Journal, 2021)
The adoption of IoT for smart health applications is a relevant tool for distributed and intelligent automatic diagnostic systems. This work proposes the development of an integrated solution to monitor maternal and fetal signals for high-risk pregnancies based on IoT sensors, feature extraction based on data analytics, and an intelligent diagnostic aid system based on a 1-D convolutional neural network (CNN) classifier. The fetal heart rate and a group of maternal clinical indicators, such as the uterine tonus activity, blood pressure, heart rate, temperature, and oxygen saturation are monitored. Multiple data sources generate a significant amount of data in different formats and rates. An emergency diagnostic subsystem is proposed based on a fog computing layer and the best accuracy was 92.59% for both maternal and fetal emergency. A smart health analytics system is proposed for multiple feature extraction and the calculation of linear and nonlinear measures. Finally, a classification technique is proposed as a prediction system for maternal, fetal, and simultaneous health status classification, considering six possible outputs. Different classifiers are evaluated and a proposed CNN presented the best results, with the F1-score ranging from 0.74 to 0.91. The results are validated based on the diagnosis provided by two specialists. The results show that the proposed system is a viable solution for maternal and fetal ambulatory monitoring based on IoT.
9 citations (Crossref) [2022-09-21] Conference Name: IEEE Internet of Things Journal
Keywords: Artificial intelligence (AI); Biomedical monitoring; Cloud computing; Feature extraction; Fetal heart rate; Internet of Things; Medical diagnostic imaging; Monitoring; convolutional neural networks (CNNs); feature extraction; fetal monitoring; health analytics; maternal monitoring

Monitor or On-site? Macau kindergartener parents’ learning experience in face-to-face and online parent education seminars - Ng, M. H.; Leong, K. I. Q.; Mak, M. C. K.; Cheng, P. W.; Ho, G. W. S; Chan, A. O. K.; Tse, T. P. M. (2021)

No templo de Hare Krishna - Simões, José Manuel (Aspectus. Revista de Arte & Ciência, 2021)

Chemical toxicity prediction based on semi-supervised learning and graph convolutional neural network - Chen, Jiarui; Si, Yain-Whar; Un, Chon-Wai; Siu, Shirley W. I. (Journal of Cheminformatics, 2021)
As safety is one of the most important properties of drugs, chemical toxicology prediction has received increasing attentions in the drug discovery research. Traditionally, researchers rely on in vitro and in vivo experiments to test the toxicity of chemical compounds. However, not only are these experiments time consuming and costly, but experiments that involve animal testing are increasingly subject to ethical concerns. While traditional machine learning (ML) methods have been used in the field with some success, the limited availability of annotated toxicity data is the major hurdle for further improving model performance. Inspired by the success of semi-supervised learning (SSL) algorithms, we propose a Graph Convolution Neural Network (GCN) to predict chemical toxicity and trained the network by the Mean Teacher (MT) SSL algorithm. Using the Tox21 data, our optimal SSL-GCN models for predicting the twelve toxicological endpoints achieve an average ROC-AUC score of 0.757 in the test set, which is a 6% improvement over GCN models trained by supervised learning and conventional ML methods. Our SSL-GCN models also exhibit superior performance when compared to models constructed using the built-in DeepChem ML methods. This study demonstrates that SSL can increase the prediction power of models by learning from unannotated data. The optimal unannotated to annotated data ratio ranges between 1:1 and 4:1. This study demonstrates the success of SSL in chemical toxicity prediction; the same technique is expected to be beneficial to other chemical property prediction tasks by utilizing existing large chemical databases. Our optimal model SSL-GCN is hosted on an online server accessible through: https://app.cbbio.online/ssl-gcn/home.
1 citations (Crossref) [2022-09-21]
Keywords: ADMET; Chemical toxicity; Deep learning; Graph convolutional neural network; Mean teacher; Semi-supervised learning; Tox21

「道」與「導」：與聖紐曼樞機反思生命中皈依與教學之使命 Leading the Way - Reflecting on the Mission of Learning and Conversion of Life with St John Henry Newman (1801-1890) - Law, Cyril Jerome (2021)

Constraints of Fe-S-C stable isotopes on hydrothermal and microbial activities during formation of sediment-hosted stratiform sulfide deposits - Qiu, Wenhong Johnson; Zhou, Mei-Fu; Li, Xiaochun; Huang, Fang; Malpas, John (Geochimica et Cosmochimica Acta, 2021)
Microbial and hydrothermal venting activities on the seafloor are important for the formation of sediment-hosted stratiform sulfide (SHSS) deposits. Fe isotopic compositions are sensitive to both microbial and hydrothermal activities and may be used to investigate the formation of these deposits. However, to the best of our knowledge, no Fe isotopic studies have been conducted on SHSS deposits. In the Devonian Dajiangping SHSS-type pyrite deposit (389 Ma), South China, laminated pyrite ores were precipitated from exhalative hydrothermal fluids, whereas black shales were deposited during intervals with no exhalation. Pyrite grains from black shales mostly display positive δ56Fe-py (0.01–0.73‰), higher than marine sediments (ca. 0‰), due to pyrite deriving Fe from basinal shuttled Fe(III) (hydr-)oxides and slowly crystallizing in pores of sediments with equilibrium fractionation, except for negative δ56Fe-py (−0.17‰ to −0.24‰) of two samples caused by mixing of Fe from underlain laminated ores. The positive δ34S-py (3.50–24.5‰) of black shales reflect that sulfur of pyrite originated from quantitative reduction of sulfate in closed pores of sediments. In contrast, pyrite grains of laminated ores have negative δ56Fe-py (−0.60‰ to −0.21‰), which were not only inherited from the negative δ56Fe of hydrothermal fluids but also caused by kinetic fractionation during rapid precipitation of a pyrite precursor (FeS) in hydrothermal plumes. These ores have negative δ34S-py (−28.7‰ to −1.82‰), because H2S for pyrite mineralization was produced by bacterial sulfate reduction (BSR) in a sulfate-rich seawater column or shallow sediments. The δ56Fe-py values of laminated ores co-vary positively with δ34S-py and δ13C-carbonate along the ore stratigraphy, with δ13C-carbonate values ranging from −12.0‰ to −2.50‰. However, they correlate negatively with aluminum-normalized total organic carbon (TOC/Al2O3). Organic carbon is thus considered to enhance the production of H2S by BSR activities, increase pyrite precipitation rates and promote the expression of kinetic fractionation of Fe isotopes. Intriguingly, in the ore units with vigorous hydrothermal venting activities, δ56Fe-py, δ34S-py and δ13C-carbonate values display a consistently increasing trend. Such results suggest that venting hydrothermal fluids significantly inhibited the H2S production of BSR, which then reduced the pyrite crystallization rate and decreased the kinetic fractionation of Fe isotopes. Our study reveals that the formation of SHSS deposits relies on H2S from microbial activities and metals from hydrothermal exhalation on the seafloor, but that vigorous exhalation can inhibit microbial activities and thus sulfide precipitation rates. The integrated use of Fe, S, and C isotopes can effectively elucidate these dynamic interactions between hydrothermal venting and microbial activities during the formation of SHSS deposits.
Keywords: Iron isotope; Isotope fractionation; Sediment-hosted stratiform sulfide deposit; Sulfur isotope

Towards an efficient prognostic model for fetal state assessment - Silva Neto, Manuel Gonçalves da; Madeiro, João Paulo do Vale; Marques, João Alexandre Lobo; Gomes, Danielo G. (Measurement, 2021)
Monitoring signals such as fetal heart rate (FHR) are important indicators of fetal well-being. Computer-assisted analysis of FHR patterns has been successfully used as a decision support tool. However, the absence of a gold standard for the building blocks decision-making in the systems design process impairs the development of new solutions. Here we propose a prognostic model based on advanced signal processing techniques and machine learning algorithms for the fetal state assessment within a comprehensive evaluation process. Feature-engineering-based and time-series-based machine learning classifiers were modeled into three data segmentation schemas for CTU-UHB, HUFA, and DB-TRIUM datasets and the generalization performance was assessed by a two-way cross-dataset evaluation. It has been shown that the feature-based algorithms outperformed the time-series ones on data-limited scenarios. The Support Vector Machines (SVM) obtained the best results on the datasets individually: specificity (85.6% ) and sensitivity (67.5%). On the other hand, the most effective generalization results were achieved by the Multi-layer perceptron (MLP) with a specificity of 71.6% and sensitivity of 61.7%. The overall process provided a combination of techniques and methods that increased the final prognostic model performance, achieving relevant results and requiring a smaller amount of data when compared to the state-of-the-art fetal status assessment solutions.
1 citations (Crossref) [2022-09-21]
Keywords: Cardiotocography; Classification; Fetal state assessment; Prognostic model; System design

‘Navigation for an ocean of interminable scepticism’ revisited: John Henry Newman and the place of theology in the university - Morgan, Stephen (International Journal for the Study of the Christian Church, 2021)
The place of theology is under threat in the modern university. It is denied a place, except insofar as it is useful in the training of religious professionals or as a phenomenon in its own right, on the grounds that relate to an unscientific scientism that both makes metaphysical assumptions it itself does not recognise as scientific or denies its own epistemological commitments. This article argues that the notion of education in ‘liberal knowledge’ or ‘universal knowledge’, the idea at the heart of John Henry Newman’s The Idea of a University provides a sufficiently robust counter to these assaults on the place of theology proper in the modern university and that refusing such a place to it undermines the claim of universities to use the name at all. It is precisely the uselessness of theology that guarantees its place in the university committed to universal knowledge and universal enquiry.
0 citations (Crossref) [2022-09-21] https://doi.org/10.1080/1474225X.2021.1997030
Keywords: Derrida; Newman; education; liberal education; religious studies; secularisation; theology; university

Uma Questão de Arquitectura: Materiais (Café da Manhã, 2021)

Relações entre o pós-digital e o complexo industrial do capitalismo: reformulações sobre a tecnologia como ideologia e lixo digital na arte - Paquete, Hugo; Fernandes-Marcos, Adérito; Bastos, Paulo Bernardino (AVANCA | CINEMA, 2021)
This essay presents a mapping of the historical concepts that contributed to the emergence of post-digital aesthetics and their connections to the concept of post-media in historical terms. It also analyzes the transition from techno-positivism to discourse of resistance against the effects of the capital technological industrial complex and how these advances in technology influence artistic discourses, practices and are the leverage of art and technology which is nothing more than a representation of the aesthetics of capital. Following art and capitalism as an ideology of innovation. Is proposed an unstinting theory about technology, geology, and the importance of these conditions to the post-digital aesthetics in terms of material disponible and conceptual articulation. Producing a reconfiguration of the post-digital conceptual approach as I propose beyond the dysfunctional aesthetics and connected with the concept of radical ecology centered in the usability of electronic garbage and technical obsolescent technologies in the arts.
0 citations (Crossref) [2022-09-21]

Study of the Compositional Rules of Design in Chaoshan Traditional House: A Computational Approach - Afonso, Filipe (2021)

Book of Proceedings of ARTECH 2021 - 10th International Conference on Digital and Interactive Arts (Hybrid Praxis – Art, Sustainability & Technology) - Lopes, Maria Manuela; Lopes, Paulo Bernardino; Araújo, António; Olivero, Lucas Fabian; Marcos, Adérito Fernandes (2021)

Orbital Eccentricity. Sound performance, using commercial and military satellites with real time tracking data - Paquete, Hugo; Bernardino Bastos, Paulo; Fernandes-Marcos, Adérito (10th International Conference on Digital and Interactive Arts, 2021)
0 citations (Crossref) [2022-09-21]
Keywords: Micro Sound; Performance; Sonification; Sound art

Inside the embroidery. The rematerialization of traditional embroidery in a post-digital approach: No interior do bordado. A rematerialização do bordado numa vertente pós-digital - Pereira, Selma; Fernandes-Marcos, Adérito (10th International Conference on Digital and Interactive Arts, 2021)
0 citations (Crossref) [2022-09-21]

Contemporary art as a factor for knowledge generation from video: A arte contemporânea como fator de geração de conhecimento a partir do vídeo - Urrutia, Hernando; Pérez, Pilar; Fernandes-Marcos, Adérito (10th International Conference on Digital and Interactive Arts, 2021)
0 citations (Crossref) [2022-09-21]

Uma Questão de Arquitectura: Pré-existência (Café da Manhã, 2021)

Sediments in the mangrove areas contribute to the removal of endocrine disrupting chemicals in coastal sediments of Macau SAR, China, and harbour microbial communities capable of degrading E2, EE2, BPA and BPS - Moreira, Irina S.; Lebel, Alexandre; Peng, Xianzhi; Castro, Paula M. L.; Gonçalves, David (Biodegradation, 2021)
The occurrence of endocrine disrupting chemicals (EDCs) is a major issue for marine and coastal environments in the proximity of urban areas. The occurrence of EDCs in the Pearl River Delta region is well documented but specific data related to Macao is unavailable. The levels of bisphenol-A (BPA), estrone (E1), 17α-estradiol (αE2), 17β-estradiol (E2), estriol (E3), and 17α-ethynylestradiol (EE2) were measured in sediment samples collected along the coastline of Macao. BPA was found in all 45 collected samples with lower BPA concentrations associated to the presence of mangrove trees. Biodegradation assays were performed to evaluate the capacity of the microbial communities of the surveyed ecosystems to degrade BPA and its analogue BPS. Using sediments collected at a WWTP discharge point as inoculum, at a concentration of 2 mg l−1 complete removal of BPA was observed within 6 days, whereas for the same concentration BPS removal was of 95% after 10 days, which is particularly interesting since this compound is considered recalcitrant to biodegradation and likely to accumulate in the environment. Supplementation with BPA improved the degradation of bisphenol-S (BPS). Aiming at the isolation of EDCs-degrading bacteria, enrichments were established with sediments supplied with BPA, BPS, E2 and EE2, which led to the isolation of a bacterial strain, identified as Rhodoccoccus sp. ED55, able to degrade the four compounds at different extents. The isolated strain represents a valuable candidate for bioremediation of contaminated soils and waters.
Keywords: Biodegradation; Bisphenols; EDCs-degrading bacteria; Endocrine disrupting chemicals (EDCs); Estrogens; Mangrove

A Comprehensive Review of Investor Sentiment Analysis in Stock Price Forecasting - Ma, Huawen; Ma, Jixin; Wang, Han; Li, Pengsheng; Du, Wencai (2021 IEEE/ACIS 20th International Fall Conference on Computer and Information Science (ICIS Fall), 2021)
Sentiment analysis technologies have a strong impact on financial markets. In recent years there has been increasing interest in analyzing the sentiment of investors. The objective of this paper is to evaluate the current state of the art and synthesize the published literature related to the financial sentiment analysis, especially in investor sentiment for prediction of stock price. Starting from this overview the paper provides answers to the questions about how and to what extent research on investor sentiment analysis and stock price trend forecasting in the financial markets has developed and which tools are used for these purposes remains largely unexplored. This paper represents the comprehensive literature-based study on the fields of the investors sentiment analytics and machine learning applied to analyzing the sentiment of investors and its influencing stock market and predicting stock price.
Keywords: Analytical models; Information science; Investor sentiment analysis; Machine learning; Market research; Predictive models; Reliability; Sentiment analysis; Social media; Stock price trend forecasting; Tools

Filosofia de comboio - Simões, José Manuel (Aspectus. Revista de Arte & Ciência, 2021)

The use Robotics in the intervention with children with ASD in Macao: a pilot study with Milo - Teixeira, Vitor; Lai, Michael (Revista Portuguesa de Investigação Educacional, 2021)
Robotics are being used in the intervention with children with Autism Spectrum Disorder (ASD) in many places and already for many years. Many robots were developed and different studies are being made in order to evaluate its effectiveness. “Socially Assistive Robotics” is shown to be effective in different areas mainly in social and emotional development. Milo, a robot developed by a team led by Richard Margolin for the Robots4Autism program (RoboKind, 2020), is one of the robots whose use is reported to be successful. In Macao there is no report of studies or experiences on the use of robots in the intervention with children with ASD. In a collaboration between the Macao Science Centre, the Macao Autism Association (MAA) and the University of Saint Joseph, an exploratory study was developed to understand the applicability of Milo to the work with children with ASD in Macao. The study showed that the robot is able to facilitate social and emotional competences of children with ASD. However, several limitations including language, cultural differences, the inexperienced facilitators and the level of sessions are too simple for the participants to be aware of that may affect the effectiveness of the intervention. It is important to show that the adoption of Milo in Macao for intervening children with ASD can be further implemented, with better practical solutions.
Number: 21

Macau’s gaming culture hits higher education - Morrison, Keith (Macau Business, 2021)

An improved ant colony optimization algorithm based on context for tourism route planning - Liang, Shengbin; Jiao, Tongtong; Du, Wencai; Qu, Shenming (PLOS ONE, 2021)
To solve the problem of one-sided pursuit of the shortest distance but ignoring the tourist experience in the process of tourism route planning, an improved ant colony optimization algorithm is proposed for tourism route planning. Contextual information of scenic spots significantly effect people’s choice of tourism destination, so the pheromone update strategy is combined with the contextual information such as weather and comfort degree of the scenic spot in the process of searching the global optimal route, so that the pheromone update tends to the path suitable for tourists. At the same time, in order to avoid falling into local optimization, the sub-path support degree is introduced. The experimental results show that the optimized tourism route has greatly improved the tourist experience, the route distance is shortened by 20.5% and the convergence speed is increased by 21.2% compared with the basic algorithm, which proves that the improved algorithm is notably effective.
3 citations (Crossref) [2022-09-21]

A Machine Learning Approach to Predict the Trend of Obesity Prevalence at a Global Level - Barzinji, Ala Othman; Ma, Chaoying; Du, Wencai; Ma, Jixin (2021 IEEE/ACIS 6th International Conference on Big Data, Cloud Computing, and Data Science (BCD), 2021)

Basic Beliefs, the Embryo Rescue Case, and Single-Issue Voting: A Response to Dustin Crummett - McNabb, Tyler; DeVito, Michael (The National Catholic Bioethics Quarterly, 2021)
In this essay, we respond to Dustin Crummett’s argument that one cannot consistently appeal to body count reasoning to justify being a single-issue pro-life voter if one is also committed to the usual response to the embryo rescue case. Specifically, we argue that a modified version of BCR we call BCR* is consistent with the usual response. We then move to address concerns about the relevance of BCR* to Crummett’s original thesis.
GSCC: 0000000

A Fast Lightweight Based Deep Fusion Learning for Detecting Macula Fovea Using Ultra-Widefield Fundus Images - Wang, Han; Yang, Jie; Wu, Yaoyang; Du, Wencai; Fong, Simon; Duan, Yutong; Yao, Xiaoping; Zhou, Xiaoshu; Li, Qingqian; Lin, Chen; Liu, Jiang; Huang, Lina; et al. (MATHEMATICS & COMPUTER SCIENCE, 2021)
Macula fovea detection is a crucial prerequisite towards screening and diagnosing macular diseases. Without early detection and proper treatment, any abnormality involving the macula may lead to blindness. However, with the ophthalmologist shortage and time-consuming artificial evaluation, neither accuracy nor effectiveness of the diagnose process could be guaranteed. In this project, we proposed a deep learning approach on ultra-widefield fundus (UWF) images for macula fovea detection. This study collected 2300 ultra-widefield fundus images from Shenzhen Aier Eye Hospital in China. Methods based on U-shape network (Unet) and Fully Convolutional Networks (FCN) are implemented on 1800 (before amplifying process) training fundus images, 400 (before amplifying process) validation images and 100 test images. Three professional ophthalmologists were invited to mark the fovea. A method from the anatomy perspective is investigated. This approach is derived from the spatial relationship between macula fovea and optic disc center in UWF. A set of parameters of this method is set based on the experience of ophthalmologists and verified to be effective. Results are measured by calculating the Euclidean distance between proposed approaches and the accurate grounded standard, which is detected by Ultra-widefield swept-source optical coherence tomograph (UWF-OCT) approach. Through a comparation of proposed methods, we conclude that, deep learning approach of Unet outperformed other methods on macula fovea detection tasks, by which outcomes obtained are comparable to grounded standard method.

International collaboration for mutual benefit: a Southwest China and Southeast United States partnership - Jackson, M. Sebrena; Gardell, Debra Nelson; Williams, Javonda; Tang, Ning; Yang, Fan (China Journal of Social Work, 2021)
China’s return to social work education, after a nearly 35-year absence, opened the door for partnerships like the 2012 China Collaborative partnership between the Council on Social Work Education’s (CSWE) Katherine A. Kendall Institute, the China Association of Social Work Education (CASWE) and the International Association of Schools of Social Work (IASSW). The University of Alabama School of Social Work (UA SSW) was selected to participate in the collaborative and was connected to the Southwest China Region, specifically partnered with Yunnan University. This manuscript will share the strategies used to engage faculty and students from each partnering institution. Data collected by UA SSW over the five-year partnership will be utilised to contribute to the discussion of the extent to which Western knowledge and theory about social work education might usefully be applied to the Chinese context.
Publisher: Routledge _eprint: https://doi.org/10.1080/17525098.2021.1909237
Keywords: China collaborative; International social work; University of Alabama; Yunnan University; social work education

Occurrence and remobilization of gold in the Dayingezhuang deposit in Jiaodong, North China Craton: Evidence from textural and geochemical features of pyrite - Yuan, Zhong-Zheng; Li, Zhan-Ke; Li, Jian-Wei; Zhao, Xin-Fu; Wu, Ya-Fei; Xu, Hai-Jun; Sun, Hua-Shan (Ore Geology Reviews, 2021)
The Dayingezhuang gold deposit in the Jiaodong district, eastern margin of the North China Craton is hosted in Mesozoic granitic rocks and consists of quartz-sulfide veins/veinlets and sulfide disseminations in alteration envelopes. Previous studies mainly focused on the geochronology, sources of ore-forming fluids and metals to investigate the ore genesis. However, enrichment mechanism of Au and other associated trace metals remain unclear. In this study, we present detailed textures and in-situ LA-ICP-MS trace-element compositions of different generations of pyrite, as well as EMP analysis of Au-bearing minerals to discuss the occurrence and enrichment mechanism of Au at this deposit. Three generations of pyrite (Py1, Py2 and Py3) formed during three hydrothermal ore stages (I, II, and III) at Dayingezhuang. Py1 occurs as disseminations in sericitic alteration assemblages and is characterized by low Au (mean 0.15 ppm), Ag, As and Te contents. The time-resolved depth-concentration profiles indicate that Au in Py1 mainly occurs as nanoparticles and/or micron-sized inclusions. Py2 can be further divided into the early undeformed Py2a and later Py2b, which is the product of deformed Py2a with different degrees of brittle to plastic deformation and recrystallization. Py2a in pyrite-siderite-quartz veins is relatively enriched in invisible Au (mean 0.41 ppm), Ag, As, and Te compared to Py1, and contains numerous micron-sized Au inclusions. In contrast, Py2b contains lesser invisible Au (0.21 ppm) and host abundant gold minerals along the grain boundaries and microfractures. Py3 in polymetallic sulfide veins has little Au. As a whole, Au in pyrite is positively correlated with Ag and Te, which is consistent with the results of EMP analysis showing the occurrence of Au as electrum, native gold and minor petzite in pyrite. Such evidences show that the deformation and recrystallization of auriferous Py2a potentially caused local remobilization of Au (mainly as micron-sized inclusion Au) via solid-state ductile flow and subsequent reconcentration of Au in microfractures of Py2b. The pyrite deformation and Au remobilization events were suggested to be related to the continuous reactivation of the regional Zhaoping Fault contemporaneous with gold mineralization. Our study highlights the importance of remobilization and reconcentration of Au triggered by syn-ore tectonic activities at Dayingezhuang and possibly other Au deposits in the Jiaodong district.
Keywords: Dayingezhuang; EBSD; Gold remobilization; Jiaodong; Pyrite deformation

Mangroves for phytoremediation of coastal water eutrophication in Macao, SAR China - Tagulao, Karen (2021)

Houston, Do We Have a Problem?: Extraterrestrial Intelligent Life and Christian Belief - McIntosh, C. A.; McNabb, Tyler Dalton (Philosophia Christi, 2021)
Would the existence of extraterrestrial intelligent life (ETI) conflict in any way with Christian belief? We identify six areas of potential conflict. If there be no conflict in any of these areas—and we argue ultimately there is not—we are confident in declaring that there is no conflict, period. This conclusion underwrites the integrity of theological explorations into the existence of ETI, which has become a topic of increasing interest among theologians in recent years.

Twilight of the idols - Morrison, Keith (Macau Business, 2021)

How Many Books Are There in the Bible? (Part 3) [In Traditional Chinese] - Leong, Andrew Chin Hei (St. Lazarus Parish Newsletter (New Series), 2021)

A network analysis investigation of the comorbidity between sleep dysfunction and PTSD symptomatology among Filipino domestic workers in Macao (SAR) China- ClinicalKey - Wang, Siyuan; Sit, Hao Fong; Garabiles, Melissa R.; Blum, Daniel; Hannam, Kevin; Armour, Chérie; Hall, Brian J. (Journal of Psychiatric Research, 2021)

Acculturative stress and coping among migrant workers: A global mixed-methods systematic review - Liem, Andrian; Renzaho, Andre M. N.; Hannam, Kevin; Lam, Agnes I. F.; Hall, Brian J. (Applied Psychology: Health and Well-Being, 2021)
No existing review has synthesized key questions about acculturation experiences among international migrant workers. This review aimed to explore (1) What are global migrant workers’ experiences with acculturation and acculturative stress? (2) What are acculturative stress coping strategies used by migrant workers? And (3) how effective are these strategies for migrant workers in assisting their acculturation in the host countries? Peer-reviewed and gray literature, without time limitation, were searched in six databases and included if the study: focused on acculturative stress and coping strategies; was conducted with international migrant workers; was published in English; and was empirical. Eleven studies met the inclusion criteria. Three-layered themes of acculturation process and acculturative stress were identified as: individual layer; work-related layer; and social layer. Three key coping strategies were identified: emotion-focused; problem-focused; and appraisal-focused. These coping strategies were used flexibly to increase coping effectiveness and evidence emerged that a particular type of acculturative stress might be solved more effectively by a specific coping strategy. Migrant workers faced numerous challenges in their acculturative process. Understanding this process and their coping strategies could be used in developing research and interventions to improve the well-being of migrant workers.
6 citations (Crossref) [2022-09-21] GSCC: 0000004
Keywords: acculturation; cultural adaptation; global mental health; health disparities; healthcare access; migrant health

How suitable are you for Macau’s workforce? - Morrison, Keith (Macau Business, 2021)

Post-Digital Fashion: The Evolution and Creation Cycle - Pereira, Selma; Fernandes-Marcos, Adérito (ZoneModa Journal, 2021)
In the face of the Covid-19 pandemic, the fashion industry was surprised and quickly had to adapt to digital media. However, the relationship between fashion and the multiplicity of screens is not new. Fashion emerged and took its first steps with Cinema, in Modernity. Although there are times when these two systems are further apart from each other, the alliance survived. To analyse contemporaneity, we take as main reference the studies of Gilles Lipovetsky, and his reflections on aesthetic capitalism. The fashion system has many Western fields of life, including art and technology. In this article we discuss how this relationship of fashion adapts and develops with aesthetic capitalism and post-digital art while we analyse representative artefacts from/about fashion. We propose to put the recent digital fashion artefacts in dialogue with post-digital aesthetics theories, discussing the blurred boundaries between the digital and the post-digital, and proposing the instantiation of a post-digital creation cycle applied to fashion artefacts.
Artwork Size: 71-89 Pages Publisher: ZoneModa Journal

«Em caso de dúvida ou persistência dos sintomas, consulte o médico ou farmacêutico» O género textual folheto informativo em Portugal - Rocha, Nuno (Universidade do Porto, 2021)
The main focus of this thesis was to characterize the patient information leaftlets as a text genre in Portugal, compare it with the same text genre in other countries and propose a new form of elaborating these documents in order to rise its comprehensibility levels. Therefore, we proceeded with an analysis of the patient information leaflet as a text genre and its relationship with text linguistics and translation. We also analyzed a corpus of 50 patient information leaflets with focus not only on its content, but also in the way they were created. In order to know the opinion of the general public, a survey about the situation of these documents in Portugal was distributed. In order to find the differences between these documents in different contexts, we made a comparison of a portuguese leaflet with leaflets from other countries. By last, we proposed a new writing scheme for these documents, reformulating one of the leaflets analyzed in the corpus and, to get the opinion of the general public, distributing a survey where the reformulated version was compared to the original one. The results point out to a lack of uniformity between documents and the way that they are created in pharmaceutical companies. The content of the patient informations leaflets in Portugal has an excess of text, technical language and a visual organization that is not appealing, problems that were also pointed out by the public in a survey. In the comparison between leaflets of different countries, big differences were found even when they were produced by the same company. When confronted with the original version and the reformulated version of the same document, the general public prefered the latter.
Accepted: 2022-09-09T20:44:50Z

A Prospective analysis about employee retention strategies for Macao Hotel Industry - Chong, Ka Yee; Lobo Marques, Joao A. (The 2021 12th International Conference on E-business, Management and Economics, 2021)
Human resources are essential to the survival, success, and long-term growth of a company. Hotel is an industry requiring a high level of human resources for delivering high-quality personal service to the hotel guests to maintain its competitiveness in the business environment. With the rapid economic growth in Macao started in 2002, all the industries have been growing fast and competing fiercely for the limited manpower in Macao. However, the Macao hotel industry has been losing its attractiveness in the Macao labor market and needs to rely on non-local workers with a limited stay in Macao. The management team of the Macao hotel industry is looking for a solution to maintain a stable workforce. Therefore, a study has been conducted on the effectiveness of its employee retention strategies. A questionnaire was designed to collect the preferences of the employees and interviews were conducted to understand the perspective of the management team toward the employee retention strategies. The study shows the employee strategies are focused on key employees’ interests such as career development and prospect. However, the communication between the management team and employees failed and led to employee turnover.
0 citations (Crossref) [2022-09-21]
Keywords: Employee retention; Employee turnover reasons; Macao hotel industry; Macao shortage of manpower

Sustainable Buildings’ Projects – A Perspective from Consultants and Contractors based in Macau SAR, China - J.P.P. Santos, Eduardo; Lobo Marques, Joao; Phyllips, Jenny O. L. (The 2021 12th International Conference on E-business, Management and Economics, 2021)
China growing awareness of sustainability has brought out relevant aspects to move towards a green environment. Since its subscription in 2016, China has been committed to implementing the Paris Agreement, and the Greater Bay Area (GBA) development plan prioritizes ecology and pursuing green development. The primary purpose of this research is to perceive the companies' insights concerning the implementation of sustainable buildings’ projects in Macau. For this multi-case study analysis, primary data was gathered from interviews with two groups involved in the construction projects’ lifecycle: Consultants and Contractors, to analyze different perceptions and concerns. The interviews considered two different themes about the main topic: (1) Perception on Companies’ Experience in Sustainable Projects; (2) Key Drivers towards Sustainable Buildings’ Projects’ Implementation. In conclusion, according to the analyzed data, it is essential to notice that companies’ background and the market particularities affect their corporate performance specially connected to the green construction frameworks. The data also indicate that it is necessary to move towards regulations and policies to change corporate and people's mindset.
0 citations (Crossref) [2022-09-21]
Keywords: Construction industry; Green building; Sustainable Policies; Sustainable building

Transforming struggling reform implementers into effectual reform agents: Hong Kong preschool teachers’ voices on process drama - Tam, Po Chi; Sun, C. R. (Youth Theatre Journal, 2021)

How Many Books Are There in the Bible? (Part 2) [In Traditional Chinese] - Leong, Andrew Chin Hei (St. Lazarus Parish Newsletter (New Series), 2021)

Elite athletes’ mental well-being and life satisfaction: a study of elite athletes’ resilience and social support from an Asian unrecognisedNational Olympic Committee - Kuok, A. C. H; K. I. Chio, David; C. H. Pun, Alan (Health Psychology Report, 2021)
Introduction This study aimed to investigate elite athletes’ mental well-being, and to ascertain whether the personal factor resilience and the social factor social support can play a role in promoting mental well-being and life satisfaction. In addition, this is one of the first studies to investigate well-being among elite athletes who are from a region belonging to an unrecognised National Olympic Committee and are not eligible to join the Olympic Games. Material and methods Eighty-four full-time elite athletes (37 males, 47 females) with mean age of 22.36 years old participated in this quantitative research study. Formal letters describing the purpose and organiser of the study were sent to the sport entities in Macao asking their permission for the researchers to contact the elite athletes to participate in this study. After gaining the permission, the elite athletes belonging to these entities were approached individually, to inform them of the purpose of the study and receive their consent. Results Regression revealed that emotional support and adaptability of resilience were strong positive predictors of mental well-being. Additionally, mental well-being was found to be a strong positive predictor of life satisfaction. The results reflected that in elite athletes possessing high adaptability and receiving more emotional support could help to maintain their mental well-being. Conclusions Implications (based on the findings) are discussed in order to provide insights for policy makers or coaches how to promote elite athletes’ mental well-being.
0 citations (Crossref) [2022-10-30]

Travel Sickness - Morrison, Keith (Macau Business, 2021)

How Many Books Are There in the Bible? (Part 1) [In Traditional Chinese] - Leong, Andrew Chin Hei (St. Lazarus Parish Newsletter (New Series), 2021)
Author Note: There is a typo in the title of the publication. It was published “上” but it should be “下” instead.

Androgens and corticosteroids increase in response to mirror images and interacting conspecifics in males of the Siamese fighting fish Betta splendens - Ramos, Andreia; Alex, Deepa; Cardoso, Sara D.; Gonçalves, David (Hormones and Behavior, 2021)
The role of hormones as modulators of aggressive behavior in fish remains poorly understood. Androgens and corticosteroids, in particular, have been associated with aggressive behavior in fish but it is still not clear if animals adjust the secretion of these hormones to regulate behavior during ongoing fights, in response to fight outcomes in order to adjust aggressive behavior in subsequent fights, or both. With its stereotyped displays and high aggression levels, the Siamese fighting fish Betta splendens is an excellent model to investigate this question. Here, we compared the behavioral and endocrine response of male B. splendens to fights where there is no winner or loser by presenting them with a size-matched live interacting conspecific behind a transparent partition or with a mirror image. The aggressive response started with threat displays that were overall similar in frequency and duration towards both types of stimuli. Fights transitioned to overt attacks and interacting with a live conspecific elicited a higher frequency of attempted bites and head hits, as compared with the mirror image. There was a pronounced increase in plasma androgens (11-ketotestosterone and testosterone) and corticosteroids (cortisol) levels in response to the aggression challenge, independent of stimulus type. Post-fight intra-group levels of these hormones did not correlate with measures of physical activity or aggressive behavior. A linear discriminant analysis including all behavioral and endocrine data was a poor classifier of fish from the conspecific and mirror trials, showing that overall the behavioral and endocrine response to mirror images and conspecifics was similar. The results show that fight resolution is not necessary to induce an evident increase in peripheral levels of androgens and corticosteroids in B. splendens. However, the function of these hormones during present and future aggressive contests remains to be clarified.
Keywords: Aggression; Androgens; Corticosteroids; Live conspecific test; Mirror test

Origin of the Qiyugou gold deposit in the southern margin of the North China Craton: Insights from trace elements of pyrite and mineralogy of Bi-minerals - Wu, Qiang; Zhao, Tai-Ping; Chen, Wei Terry; Gao, Xin-Yu; Meng, Lei; Qiu, Wenhong Johnson (Ore Geology Reviews, 2021)
The Qiyugou gold deposit, located in the Xiong’ ershan area of the North China Craton, contains abundant bismuth-sulfosalts that are closely associated with gold mineralization. Pyrite is the dominant Au-hosted mineral, and has been formed in three generations (Py1, Py2, and Py3). Py1 grains, generally intergrown with milky quartz, are coarse (>1 mm), euhedral in shape, and Au-depleted in composition. In contrast, subhedral Py2 grains, associated with light gray quartz, are medium to coarse (0.2–3 mm) and are enriched in gold that is both invisible and visible. Py3 grains (0.1–0.5 mm), intergrown with abundant sulfide minerals, are relatively fine and Au-depleted. The time-resolved LA-ICP-MS depth profiles of the Py2 grains indicate that invisible gold occurs as either solid solution or nano-particles of native gold and electrum. Visible gold occurs as small blebs in the Py2 grains where inclusions of native bismuth, galenobismutite, lillianite homologs, tetradymite, and galena are also present. In addition, it is common that electrum in microfracture infillings or along grain boundaries of the Py1 and Py2, are intergrown with bismuthinite derivatives, Bi-Cu sulfosalts, emplectite, tetradymite, chalcopyrite, galena, and Py3. Based on textural relationships and mineral assemblages, calculation of physicochemical conditions show that gold was formed in conditions of fTe2 = ~10−11 and fS2 = ~10−11 to 10−12 for Py2, and fTe2 = ~10−9 to 10-11and fS2 = ~10−10 to 10−11 for Py3. We thus proposed that such physicochemical conditions may have triggered the precipitation of Bi melt, and sulfidation driven by cooling or increase in sulfur content results in the transformation of the Au-Bi liquid into a stable assemblage of native gold and bismuthinite. These bismuth minerals are associated with native gold/Au-bearing minerals, indicating that the Au mineralization of the Qiyugou gold deposit might be genetically associated with Bi melt. The present study highlights the role of Bi as important gold scavengers in arsenic-deficient ore-forming fluid.
Keywords: Bi melts scavenging Au; Bismuth minerals; Qiyugou gold deposit; The southern margin of the North China craton; Trace element of pyrite

Prefeace for Espectros Inquietos, Elis Bodêgo - Simoes, José Manuel (2021)

The Influence of Society on the Behavioral Intention to Use a Technology: Evidence from the Battery Electric Vehicles Domain - Lampo, Alessandro; Silva, Susana C. (Proceedings of the 50th European Marketing Academy (EMAC), 2021)
Despite the general good intentions towards the environment, individuals tend to adopt traditional internal combustion vehicles. Drawing from technology research, this study focuses on the impact of society - in the form of subjective norm and image – on the behavioral intention to adopt a technology. More precisely, this study seeks to explore to which extent societal influences drive the behavioral intention to adopt battery electric vehicles (BEV) technology. A self-administered survey was used for this purpose. The analysis of the data from a sample of 111 respondents showed significant relationships between the predictors and the target behavioral outcome. The study also revealed that subjective norm and image are particularly significant factors for the segment of BEV owners. The findings suggest that marketers and practitioners incorporate social elements into their product communication strategies in order to encourage the uptake of environmentally-sound technologies.

CRISIS BREEDS CREATIVITY - Afonso, Filipe (2021)

Copycat Macau? - Morrison, Keith (Macau Business, 2021)

Public Matters: Identity, Design, and Placemaking in Macau’s Inner Harbou - Soares, Nuno (2021)

Contemplation and Leadership: In the Footsteps of Fr. Yves Raguin, S.J. - Duraj, Jarosław (2021)

Can mangroves work as an effective phytoremediation tool for pesticide contamination? An interlinked analysis between surface water, sediments and biota - Ivorra, Lucia; Cardoso, Patricia G.; Chan, Shek Kiu; Cruzeiro, Catarina; Tagulao, Karen Arano (Journal of Cleaner Production, 2021)
Mangroves are a unique group of plants growing along tropical and sub-tropical coastlines, with the ability to remove several types of contaminants such as heavy metals and other persistent organic compounds in coastal waters. However, little attention has been given to the possible role of mangroves in the removal of organochlorinated pesticides (OCPs) from the environment. Used worldwide, these pesticides were banned in the late 80s, withal they can still be quantified in aquatic environments due to their high stability. Moreover, as persistent and lipophilic compounds, OCPs are known for their tendency to bioaccumulate and biomagnify through the food chain, affecting local ecosystems, and potentially human health. This work aimed to investigate the potential benefits of mangrove ecosystems as OCP phytoremediators. For this purpose, a total of seventy-three articles from non-mangrove and mangrove areas around the world were gathered, integrated and re-analysed as a whole. These data include information from four different matrices (water, sediment, benthic fauna and mangrove plants). A common trend of less pesticide contamination in mangrove areas was observed for all the selected matrices. As a complement, average concentrations were discussed considering International Directives, such as the European legislation 2013/39/EU for water policy and the Dutch List together with the International Sediment Quality Guideline, for sediments. Additionally, theoretical risk assessments were also included. Since information regarding OCPs in mangroves ecosystem is very scarce compared to non-mangrove areas, this review provides valuable insights regarding these environments, and the importance of preserving them as a relevant remediation unit.
Keywords: Benthic fauna; Intertidal environments; Organochlorinated pesticides; Persistent organic compounds; Toxicological assessment

COVID-19: Short-Run Impacts of the Pandemic on the Integrated Resort Oligopoly of Macao - Lei, Weng Chi (2021)
Objective: As a world tourist destination, Macao is inevitably under the impact of the COVID-19 pandemic. However, the market of integrated resorts in Macao are shared by only a few casino concessionaries, together forming an oligopoly. While the firms attempted to adjust price, quantity and quality of their hotel services in response to the pandemic, they could not overlook the strategic interactions with other players in the market. Hence, this paper aims to investigate the possible impact of the pandemic on the oligopolistic strategies in the integrated resort market in Macao. Methodology: Application of a theoretical model of differentiated oligopoly to this six-firm case shows that price differences across firms depend on their quality differentiation. In order to analyze these price differences empirically, this paper collects data of hotel room rates of the integrated resorts from November, 2019 to mid-August, 2020, covering the periods before and after the outbreak of COVID-19. Originality: In the existing literature, there is a lack of studies of the oligopoly in the hospitality industry of Macao. Furthermore, the effect of COVID-19 is still ongoing, so this present paper is one of the first to perform such analysis. Results: The regression of each of the hotel price differentials on the COVID-19 dummy variable shows that COVID-19 has statistically significant impacts on almost all the price differentials. Intuitively, MGM and Wynn were in the high-price segment before and after the outbreak, while other firms switched positions in the low-price segment during the pandemic. One obvious downstream movement was by Conrad. According to the proposition derived from the theory, these imply that COVID-19 should have significant impact on the quality differentiation of the firms. Practical implications: The results are in line with the observations that the integrated resorts have rolled out staycation packages according to preferences of local residents. These quality adjustments observed in Macao’s hospitality industry currently only involved variable inputs rather than fixed inputs of production; therefore, the impact of COVID-19 should be seen as short-term effects. Keywords: Covid-19; Differentiated oligopoly; Hospitality industry; Hotel room rate; Oligopolistic market structure; Pricing strategy.

Resource estimation of the sulfide-rich deposits of the Yuhuang-1 hydrothermal field on the ultraslow-spreading Southwest Indian Ridge - Yu, Junyu; Tao, Chunhui; Liao, Shili; Dias, Ágata; Liang, Jin; Yang, Weifang; Zhu, Chuanwei (Ore Geology Reviews, 2021)
Seafloor massive sulfide (SMS) deposits are important deep-sea mineral resources expected to occur predominantly on slow- and ultraslow-spreading mid-ocean ridges. Resource estimates are already available for some of the largest SMS deposits on slow-spreading ridges but not on ultraslow-spreading ridges. Based on geological mapping and sampling, this study investigates the distribution and content of sulfide-rich deposits in the Yuhuang-1 hydrothermal field (YHF), located on the ultraslow-spreading Southwest Indian Ridge. The sulfide-rich deposits in the YHF are composed of two areas ∼500 m apart: the southwest sulfide area (SWS) and the northeast sulfide area (NES). We calculated the volume of sulfide-rich mounds in the YHF and arrived at a total accumulation of ∼10.6 × 106 tons, including at least ∼7.5 × 105 tons of copper and zinc and ∼18 tons of gold. Furthermore, considering the coverage of layered hydrothermal sediment mixed with sulfide-rich breccias, which may have underlying massive sulfide deposits, the maximum total mass was estimated at ∼45.1 × 106 tons. This suggests that the YHF is one of the largest SMS deposits worldwide and confirm that ultraslow-spreading ridges have the greatest potential to form large-scale SMS deposits.
3 citations (Crossref) [2022-09-21]
Keywords: Resource estimate; Seafloor massive sulfide deposits; Southwest Indian Ridge; Yuhuang-1 hydrothermal field

Forming Intercultural Missionaries - Gallares, Judette (Becoming Intercultural: Perspectives on Mission, 2021)

Three cheers for critical thinking | Macau Business - Morrison, Keith (Macau Business, 2021)

Malacca Portuguese Creole - Pillai, Stefanie; Baxter, Alan N.; Soh, Wen-Yi (Journal of the International Phonetic Association, 2021)
Malacca Portuguese Creole (MPC) (ISO 639-3; code: mcm), popularly known as Malacca Portuguese or locally as (Papiá) Cristang, belongs to the group of Portuguese-lexified creoles of (South)east Asia, which includes the extinct varieties of Batavia/Tugu (Maurer 2013) and Bidau, East Timor (Baxter 1990), and the moribund variety of Macau (Baxter 2009). MPC has its origins in the Portuguese presence in Malacca, and like the other creoles in this subset, it is genetically related to the Portuguese Creoles of South Asia (Holm 1988, Cardoso, Baxter & Nunes 2012).
Publisher: Cambridge University Press

Southern Inner Harbour Public Domain – Strategic Vision (University of Saint Joseph, 2021)

內港南部公共領域 - 策略願景 (University of Saint Joseph, 2021)

The Role of Metaxy in the Political Philosophy of Eric Voegelin - Duraj, Jarosław (Peter Lang, 2021)
This book is a study of Eric Voegelin (1901-1985) and of the role played by metaxy in his vision of political philosophy. Metaxy, already defined by ...

Who’s kidding whom in Macau’s English performance? - Morrison, Keith (Macau Business, 2021)

Impact of noise on development, physiological stress and behavioural patterns in larval zebrafish - Lara, Rafael A.; Vasconcelos, Raquel O. (Scientific Reports, 2021)
Noise pollution is increasingly present in aquatic ecosystems, causing detrimental effects on growth, physiology and behaviour of organisms. However, limited information exists on how this stressor affects animals in early ontogeny, a critical period for development and establishment of phenotypic traits. We tested the effects of chronic noise exposure to increasing levels (130 and 150 dB re 1 μPa, continuous white noise) and different temporal regimes on larval zebrafish (Danio rerio), an important vertebrate model in ecotoxicology. The acoustic treatments did not affect general development or hatching but higher noise levels led to increased mortality. The cardiac rate, yolk sac consumption and cortisol levels increased significantly with increasing noise level at both 3 and 5 dpf (days post fertilization). Variation in noise temporal patterns (different random noise periods to simulate shipping activity) suggested that the time regime is more important than the total duration of noise exposure to down-regulate physiological stress. Moreover, 5 dpf larvae exposed to 150 dB continuous noise displayed increased dark avoidance in anxiety-related dark/light preference test and impaired spontaneous alternation behaviour. We provide first evidence of noise-induced physiological stress and behavioural disturbance in larval zebrafish, showing that both noise amplitude and timing negatively impact key developmental endpoints in early ontogeny.
7 citations (Crossref) [2022-09-21] Number: 1 Publisher: Nature Publishing Group
Keywords: Embryology; Environmental impact; Freshwater ecology

Identification of Latent Risk Clinical Attributes for Children Born Under IUGR Condition Using Machine Learning Techniques - Nguyen Van, Sau; Lobo Marques, J. A.; Biala, T. A.; Li, Ye (Computer Methods and Programs in Biomedicine, 2021)
Background and objective Intrauterine Growth Restriction (IUGR) is a condition in which a fetus does not grow to the expected weight during pregnancy. There are several well documented causes in the literature for this issue, such as maternal disorder, and genetic influences. Nevertheless, besides the risk during pregnancy and labour periods, in a long term perspective, the impact of IUGR condition during the child development is an area of research itself. The main objective of this work is to propose a machine learning solution to identify the most significant features of importance based on physiological, clinical or socioeconomic factors correlated with previous IUGR condition after 10 years of birth. Methods In this work, 41 IUGR (18 male) and 34 Non-IUGR (22 male) children were followed up 9 years after the birth, in average (9.1786 ± 0.6784 years old). A group of machine learning algorithms is proposed to classify children previously identified as born under IUGR condition based on 24-hours monitoring of ECG (Holter) and blood pressure (ABPM), and other clinical and socioeconomic attributes. In additional, an algorithm of relevance determination based on the classifier is also proposed, to determine the level of importance of the considered features. Results The proposed classification solution achieved accuracy up to 94.73%, and better performance than seven state-of-the-art machine learning algorithms. Also, relevant latent factors related to HRV and BP monitoring are proposed, such as: day-time heart rate (day-time HR), day-night systolic blood pressure (day-night SBP), 24-hour standard deviation (SD) of SBP, dropped, morning cortisol creatinine, 24-hour mean of SDs of all NN intervals for each 5 minutes segment (24-hour SDNNi), among others. Conclusion With outstanding accuracy of our proposed solutions, the classification system and the indication of relevant attributes may support medical teams on the clinical monitoring of IUGR children during their childhood development.
2 citations (Crossref) [2022-09-21]
Keywords: ABPM (Ambulatory Blood Pressure Monitoring); HRV (Heart Rate Variability); IUGR (Intrauterine Growth Restriction); Machine Learning

Students’ wellbeing during the Covid-19 pandemic - Ikegami, Kiiko (Riau University, 2021)

Divine foreknowledge and human free will: Embracing the paradox - DeVito, Michael; McNabb, Tyler Dalton (International Journal for Philosophy of Religion, 2021)
0 citations (Crossref) [2022-09-21] GSCC: 0000000

An Improved Double Channel Long Short-Term Memory Model for Medical Text Classification - Liang, Shengbin; Chen, Xinan; Ma, Jixin; Du, Wencai; Ma, Huawei (Journal of Healthcare Engineering, 2021)
There are a large number of symptom consultation texts in medical and healthcare Internet communities, and Chinese health segmentation is more complex, which leads to the low accuracy of the existing algorithms for medical text classification. The deep learning model has advantages in extracting abstract features of text effectively. However, for a large number of samples of complex text data, especially for words with ambiguous meanings in the field of Chinese medical diagnosis, the word-level neural network model is insufficient. Therefore, in order to solve the triage and precise treatment of patients, we present an improved Double Channel (DC) mechanism as a significant enhancement to Long Short-Term Memory (LSTM). In this DC mechanism, two channels are used to receive word-level and char-level embedding, respectively, at the same time. Hybrid attention is proposed to combine the current time output with the current time unit state and then using attention to calculate the weight. By calculating the probability distribution of each timestep input data weight, the weight score is obtained, and then weighted summation is performed. At last, the data input by each timestep is subjected to trade-off learning to improve the generalization ability of the model learning. Moreover, we conduct an extensive performance evaluation on two different datasets: cMedQA and Sentiment140. The experimental results show that the DC-LSTM model proposed in this paper has significantly superior accuracy and ROC compared with the basic CNN-LSTM model.
1 citations (Crossref) [2022-09-21]

Un nuovo paradigma economico.(“Ideas for a New Economic Paradigm”) - Rothlin, Stephan (La Civiltà Cattolica, 2021)
La crisi del Covid-19 ha evidenziato il disagio e il divario sempre più ampio tra ricchi e poveri. La crisi finanziaria del 2007-2009 era già risuonata come un campanello d'allarme sulla necessità di

Higher Education in Macau: waxing or waning? - Morrison, Keith (Macau Business, 2021)

COVID-19: Psychological and Psychosocial Impact, Fear, and Passion - Dey, Nilanjan; Mishra, Rishabh; Fong, Simon James; Santosh, K. C.; Tan, Stanna; Crespo, Rubén González (Digital Government: Research and Practice, 2021)

Soka Education Philosophy as a Foundation for Teacher Preparation in Creating Inclusive Education - Agbenyega, Joseph Seyram; Ikegami, Kiiko; Rivalland, Corine (International Perspectives on Inclusive Education, 2021)
Current global shifts in education towards inclusive early childhood education are deeply engineered by the crisis of educational exclusion. In responding to exclusion, teachers have mainly utilized dominant western theories to plan and implement inclusive teaching. In this chapter, we draw on a non-western philosophy, a Nichiren Buddhist (Soka) philosophy, to provide a ‘kaleidoscopic’ lens through which to create inclusive educational learning spaces that engender full participation of all children. The Soka education philosophy is a humanist concept which can guide teachers when preparing to create inclusive education. The aims of this chapter are threefold: The first is an exploration of the Nichiren Buddhist (Soka) philosophy. The second aim is to highlight how this philosophy can enable teachers to unleash the unlimited potential of children in inclusive learning settings. Thirdly, we argue that grounding early childhood teacher education in this philosophy can help improve the effectiveness of inclusive educational experience for all children.

Enhancing Teacher Education by Utilizing a Revised PGDE Curriculum as a Fundamental Resource for Inclusive Practices in Macao - Monteiro, Elisa; Forlin, Chris (International Perspectives on Inclusive Education, 2021)
Keywords: Inclusive education; Knowledge transfer; Pedagogical practice; Post-graduate diploma in education; Programme design; Teachers

The Genesis of a New Year | Macau Business - Morrison, Keith (Macau Business, 2021)

The Political and Economic Dependence of the Press in Macao under Portuguese and Chinese Rule: Continuity and Change - Costa-Ribeiro, Nelson; Simões, José Manuel (Communication & Society, 2021)
The article analyses the media system in Macao, a special administrative region of China that transitioned from Portuguese to Chinese sovereignty in 1999, becoming one of cities in the world with the largest number of published newspapers per capita. Combining historical research with the analysis of contemporary empirical data collected through interviews with journalists working on the ground, the research demonstrates how there is a long tradition of state control that goes back to the colonial era and that has assumed different forms, ranging from outright censorship to physical intimidation of journalists and economic dependence on the government. Limitations and control strategies imposed on news reporting during the Portuguese administration continue to be practiced today by the Chinese authorities. Even so, journalists operating on the Macao media market tend to overstate the level of freedom they are given, which can be attributed to media outlets being economically dependent on the state. Nevertheless, the level of freedom attributed to the press is today higher than it had been during the colonial period with some critical voices being allowed to reach the media. This needs to be understood in the context of what has been defined as the Chinese safety valve strategy.
Number: 1
Keywords: Censorship; Journalism Practice; Media Systems; Press Freedom; Press Subsidies

Predictive models to the COVID-19 - Bernardo Gois, Francisco Nauber; Lima, Alex; Santos, Khennedy; Oliveira, Ramses; Santiago, Valdir; Melo, Saulo; Costa, Rafael; Oliveira, Marcelo; Henrique, Francisco das Chagas Douglas Marques; Neto, José Xavier; Martins Rodrigues Sobrinho, Carlos Roberto; Lôbo Marques, João Alexandre (Data Science for COVID-19, 2021)
Following the World Health Organization proclaims a pandemic due to a disease that originated in China and advances rapidly across the globe, studies to predict the behavior of epidemics have become increasingly popular, mainly related to COVID-19. The critical point of these studies is to discuss the disease's behavior and the progression of the virus's natural course. However, the prediction of the actual number of infected people has proved to be a difficult task, due to a wide range of factors, such as mass testing, social isolation, underreporting of cases, among others. Therefore, the objective of this work is to understand the behavior of COVID-19 in the state of Ceará to forecast the total number of infected people and to aid in government decisions to control the outbreak of the virus and minimize social impacts and economics caused by the pandemic. So, to understand the behavior of COVID-19, this work discusses some forecast techniques using machine learning, logistic regression, filters, and epidemiologic models. Also, this work brings a new approach to the problem, bringing together data from Ceará with those from China, generating a hybrid dataset, and providing promising results. Finally, this work still compares the different approaches and techniques presented, opening opportunities for future discussions on the topic. The study obtains predictions with R2 score of 0.99 to short-term predictions and 0.93 to long-term predictions.
Keywords: COVID-19; Forecast; Holt Winters; Kalman filter; Machine learning; Prophet; SEIR

Evidence for mixed contribution of mantle and lower and upper crust to the genesis of Jurassic I-type granites from Macao, SE China - Quelhas, Pedro; Mata, João; Dias, Ágata (GSA Bulletin, 2021)
Abstract Much controversy has occurred in the past few decades regarding the nature of the sources, the petrogenetic processes, and the tectonic regime(s) of the Jurassic magmatism within the Southeast China magmatic belt. This study aims to contribute to the discussion with mineral chemistry, and whole-rock element and Sr-Nd-Hf-Pb isotopic geochemical data from granitic rocks and microgranular mafic enclaves from Macao, where two discrete groups of I-type biotite granites have been identified (referred to as Macao Group I [MGI] and Macao Group II [MGII]). It is proposed that the granitic magmas were generated by partial melting of infracrustal medium- to high-K, basaltic Paleoproterozoic to Mesoproterozoic protoliths (Nd depleted mantle model age [TDM2] = 1.7–1.6 Ga and Hf TDM2 = 1.8–1.6 Ga), triggered by underplating of hot mantle-derived magmas in an extensional setting related to the foundering of a previously flat slab (paleo–Pacific plate) beneath the SE China continent. The main differences between the two groups of Macao granites are attributed to assimilation and fractional crystallization processes, during which upper-crustal Paleozoic metasediments were variably assimilated by MGI magmas. This is evidenced by an increase in initial 87Sr/86Sr ratios with degree of evolution, presence of metasedimentary enclaves, and high percentage of zircon xenocrysts with Paleozoic ages. In addition, other processes like late-stage fluid/melt interaction and magma mixing also left some imprints on granite compositions (rare earth element tetrad effect plus non–charge-and-radius-controlled behavior of trace elements and decoupling between different isotope systems, respectively). The distribution of isotopically distinct granites in SE China reflects the nature of the two Cathaysia crustal blocks juxtaposed along the Zhenghe-Dapu fault.
7 citations (Crossref) [2022-09-21]

The Probability Flow in the Stock Market and Spontaneous Symmetry Breaking in Quantum Finance - Arraut, Ivan; Lobo Marques, João Alexandre; Gomes, Sergio (Mathematics, 2021)
The spontaneous symmetry breaking phenomena applied to Quantum Finance considers that the martingale state in the stock market corresponds to a ground (vacuum) state if we express the financial equations in the Hamiltonian form. The original analysis for this phenomena completely ignores the kinetic terms in the neighborhood of the minimal of the potential terms. This is correct in most of the cases. However, when we deal with the martingale condition, it comes out that the kinetic terms can also behave as potential terms and then reproduce a shift on the effective location of the vacuum (martingale). In this paper, we analyze the effective symmetry breaking patterns and the connected vacuum degeneracy for these special circumstances. Within the same scenario, we analyze the connection between the flow of information and the multiplicity of martingale states, providing in this way powerful tools for analyzing the dynamic of the stock markets.
Number: 21 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Hermiticity; conservation of the information; degenerate vacuum; flow of information; martingale condition; random fluctuations; spontaneous symmetry breaking; vacuum condition

Pandemic (Im)mobilities - Adey, Peter; Hannam, Kevin; Sheller, Mimi; Tyfield, David (Mobilities, 2021)
33 citations (Crossref) [2022-09-21] GSCC: 0000029

Post-disaster Temporary Housing System based on Generative Design Method - Afonso, Filipe G.; Lu, Jun C. (International Journal of Structural and Civil Engineering Research, 2021)

Single-Use Plastic Assessment in Macau Hospitality Industry: Bottled Water as a Case Study - Ao Ieong, Kin San (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Personal Care and Cosmetic Products as a Potential Source of Environmental Contamination by Microplastics in a Densely Populated Asian City - Bashir, Saidu M.; Kimiko, Sam; Mak, Chu-Wa; Fang, James Kar-Hei; Gonçalves, David (Frontiers in Marine Science, 2021)
The prevalence of microplastics in the environment has become a major global conservation issue. One primary source of environmental microplastics is personal care and cosmetic products (PCCPs) containing microbeads. The market availability of PCCPs containing microbeads and the level of contamination of coastal sediments by microplastics was studied in one of the most densely populated cities in the world, Macao in China. We found that PCCPs containing microbeads are still widely available for sale in the region, with over 70% of surveyed PCCPs containing at least one type of microbeads as an ingredient, with polyethylene (PE) being the most common one. In an estimate, the use of PCCPs in the territory may release over 37 billion microbeads per year into the environment via wastewater treatment plants. The density of microplastics in coastal sediments varied between 259 and 1,743 items/L of sediment, amongst the highest reported in the world. The fraction of < 1 mm was the most abundant, representing an average of 98.6% of the total, and correlated positively with the abundance of larger sized fragments. The results show that although environmental pollution with microplastics released from PCCPs usage is significant, other sources, namely fragmentation of larger plastic debris, likely contribute more to the issue. The study highlights the magnitude of the problem at a local level and suggests possible mitigating strategies.

Movie Censorship – A Legitimate Tool or a Dictatorial Technique - Borges, Rui Carlos Moura (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Towards an Approach to the Interactive Filmic Narrative - Caires, Carlos Sena (Image in the post-millennium: mediation, process and critical tension, 2021)

Father’s Involvement and Parenting Styles in Macao - Chan, Ieng Chong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Existential Psychotherapy and Irvin D. Yalom’s Perspective: A Systematic Literature Review - Chan, In Leng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Interaction Design for a Contemporary Learning and Teaching Environment: Promoting Independent Learning at the Primary Level - Chan, Ka Chi (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Influence of Parenting Styles Across Generations in Chinese Families in Macao - Chan, Lai Teng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

IoT Application into Macau Secondary School - Chan, Long Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

A Financial Valuation of Alibaba Group Holding Limited - Chan, Man Hong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Family Support, Job Insecurity, Coronavirus Stress and Leadership Styles Effects on Burnout and Work Engagement in Hospitality during Covid-19 Pandemic in Macau - Chang, Pou I. (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

Modular 3D-Printed Tangibles for Children’s VR Toys - Chau, Iok Fong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Virtual Guia Fortress: A 3D-printed eXtended Reality Playset - Chau, Iok Fong; Cardoso, Jorge C. S.; Estadieu, Gerald (Entertainment Computing – ICEC 2021, 2021)
Series Title: Lecture Notes in Computer Science

The Understanding and the Attitudes Toward Life Education Among Macau Citizens: A Case Study - Che, Iok Seng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

澳門幼稚園老師在融合教育班級經營中面對的挑戰 =: The Challenge of Managing Inclusive Education Classrooms Faced by the Kindergarten teachers in Macau - Cheang, Hoi Son (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Examining the Itinerant Support Teachers’ Program in the Implementation of Inclusive Education in Macau - Cheang, Mei Chan (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Mediation Effect of Organisational Commitment on Job Autonomy and Turnover Intentions - Cheong, Lai Ieng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

A Comparative Study of Sympathy in David Hume, Karuna in Buddhism, and Ren in Confucianism - Chon, Iao Pang (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

An Investigation on the Effectiveness of Enhancing Public Relations Through the Use of Facebook by the Public Sector of Macau - Chong, Chan U. (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Home–School Collaboration in Assessment, Placement, and Individual Education Plan Development for Children With Special Education Needs in Macao: The Views of Parents - Correia, Ana; Teixeira, Vitor; Forlin, Chris (School Community Journal, 2021)
The aim of this study was to explore home–school collaboration in the areas of assessment, placement, and Individual Education Plan (IEP) development for children identified with disabilities or special educational needs (SEN) in Macao. Despite the noted benefits of parent–school partnerships from prior research, minimal research has been conducted from the perspective of parents of children with SEN to examine whether these partnerships materialize in the context of Macao. Participants included 115 parents of school-aged children diagnosed with SEN. They provided demographic information and completed a 36-item questionnaire derived from two validated instruments. The research identified a range of factors which hinder parental involvement in decision-making and in the inclusion of children with SEN in optimal ways in Macao schools. Parents indicated they were not receiving relevant information and assessment feedback from the teachers; they were minimally involved in the IEP process, and their children were not receiving one-to-one support, regardless of the type of placement. Parents also underlined issues related to the timing of assessment procedures. Parents of children attending special classes in regular schools voiced more satisfaction with support provision than parents of children following the full inclusion model. Recommendations about how services could be improved for greater parental involvement are discussed. Key Words: parental involvement, school–family collaboration, inclusion, special educational needs, Macao, Individual Education Plans, IEP

The Metaxological Philosophy of Dialogue with Buddhism - Duraj, Jaroslaw (The Wheel & The Cross: An Anthology by Jesuits & Friends on Buddhism and Dialogue, 2021)

The Role of Metaxy in the Political Philosophy of Eric Voegelin - Duraj, Jarosław (Peter Lang US, 2021)
This book is a study of Eric Voegelin (1901-1985) and of the role played by metaxy in his vision of political philosophy. Metaxy, already defined by Plato as the "in-between" matrix of the human condition, is for Voegelin a powerful notion that symbolizes the intermediate state in which man experiences diverse and opposing tensions such as the ones between immanence and transcendence or mortality and immortality. The metaxy constitutes the realm of the divine-human mutual participation (methexis), and its locus resides in human consciousness (nous), there where the divine reality manifests itself as the origin of being. Being the field of intermediation between opposing forces, man has to keep the balance of consciousness in order to differentiate the noetic and pneumatic dimensions and so attune his life to the divine ground of being. This book claims that for Voegelin metaxy shapes the possibility of the philosophical, historical, political and religious orientation in life. Indeed, Voegelin’s approach deserves recognition as an option adequate for addressing the intellectual challenges engendered by modern and postmodern philosophies.

Zen-Ignatian Training Program in Japan: A Personal Experience - Duraj, Jaroslaw (The Wheel & The Cross: An Anthology by Jesuits & Friends on Buddhism and Dialogue, 2021)

Aristotle, Lubich And Ratzinger On A New Economic Paradigm - Eh, Edmond (The Journal of the Macau Ricci Institute, 2021)
GSCC: 0000000

Parents’ Experiences in Macau: From Assessment to Inclusive Placement for Children with SEN - Estadieu, Karine Anne Marie Thepot (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門特殊教育教師助理員的工作現狀與工作滿意之探討: 基於質性之實踐分析析 - Fong, I. Mei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門小學常識科教師在融合生班級上運用 STEM 教學方法之研究 =: Human-Belongings Behaviour Analysis: A Smart Interactive Cabinet - Fong, Sao Hong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Challenges and Learning Strategy for young children with special needs during the pandemic in Indonesia - Fridani, L.; Ikegami, Kiiko (Anthology Challenges in Management of Early Childhood Education during Pandemic, 2021)

An Exploratory Study into How the Application of Neurosciences can Assist in Understanding the Decision-Making Process Under Stress - Furtado, Filipa Magalhães de Moura e Mota (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Ethical Investment’s Visible Hand: Methods And Transformative Potentials - Gassner, Franz (The Journal of the Macau Ricci Institute, 2021)

“To Listen to the Language of Nature and to Act Accordingly” :: Natural Law as Beacon guiding to Human Flourishing and Ecological Civilization - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2021)
The article sets off from a speech given by Benedict XVI in the German Bundestag in 2011, where he requested an ecological learning process to aim at sustainable human development. Appreciating the Ecological Movement, he asked to learn to listen to Nature’s language and act accordingly, which he applies analogically to “human ecology”. The article bridges elements of “Listening to Nature” and the Natural Moral Law Tradition in Benedict’s speech and in Francis’ Encyclical Letter Laudatu Si’ inview of serving human flourishing in an ecological civilization. Keywords: Natural Moral Law; Nature, Laudatu Si’, Benedict XVI, Francis; Ecological Civilization/生態文明, Sustainable Development, Ecology of Man.
Number: 6

Continuing Education in Macau: The Meanings and Experiences of Students Pursuing a Master’s Degree - Gil, Sofia do Carmo (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Bioethics : ethics of life - Gomez, Fausto B. (University of Saint Tomas Publishing House, 2021)

Research on Quality Control of Intelligent Injection Molding System Based on Process Monitoring - Han, Wang; Shasha, Lv; Shaobin, Li; Wencai, Du; Qinggu, Li; Bo, Wang (2021 8th International Conference on Computational Science/Intelligence and Applied Informatics (CSII), 2021)

Tourist’s mobilities: Walking, cycling, driving and waiting - Hannam, Kevin; Butler, Gareth; Witte, Alexandra; Zuev, Dennis (Tourist Studies, 2021)
This commentary reviews recent research in terms of tourist’s mobilities in terms practices of walking, cycling and driving. It concludes by reflecting on the contemporary lock down of travel in terms of the global pandemic and its consequences for waiting, stillness and immobility – particularly in terms of flying.
4 citations (Crossref) [2022-09-21] GSCC: 0000003

Time, authenticity and photographic storytelling in The Museum of Innocence. - Hannam, Kevin; Ryan, Edward (Authenticity and authentication of heritage, 2021)
GSCC: 0000014

A Study of Social Enterprises in Macau: The Contributing Factors to The Development of Hybrid Social Enterprises - Hau, Pak Kei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

澳門幼兒園教師對推行美感教育的態度=Kindergarten Teachers’ Attitudes Towards the implementation of Aesthetic Education in Macau - Ho, Ka Kio (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Preliminary Psychometric Investigation of a Chinese Version of the Engaged Teachers Scale (C-ETS) - Ho, Sammy K.; Chan, Hang; Chan, Edmund Sze-Shing; Fung, Kwok-Kin; Hung, Shirley Suet-Lin (Frontiers in Education, 2021)
This study examines the psychometric properties of a Chinese version of the Engaged Teacher Scale (C-ETS). A translated questionnaire with 16 items was administered to a sample of 341 primary and secondary school teachers in Hong Kong. A series of confirmatory factor analyses were performed to assess the construct, convergent, and discriminant validity of the scale in alternative models. Results provide support for a second-order model with teacher engagement as an overarching construct with four hypothesized dimensions: emotional engagement, cognitive engagement, social engagement (students), and social engagement (colleagues). The C-ETS provides a useful measure for teacher engagement in Chinese societies. Contributions and limitations of the study are discussed.

The Mediating Role of Empathy on the Impact of Perceived Parenting Styles on Prosocial Behaviors of Adults - Hoi, Mei Pui (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A Financial Valuation of Marriott International, Inc - Ian, Kin Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Culture, History, and Hospitality Public-Private Partnership of the Gaming Industry and the Macau SAR Government in the Cultural Tourism /Natural Kou, Chi In - Kou, Chi In (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The Effect of Temporal Variation in Noise Exposure on Hearing and Inner Ear in the Zebrafish Model - Kuan, Chi Kin (University of Saint Joseph, 2021)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Parental Involvement and Child Development in Macao: Association with Family Income, Parental Education and Working in the Gambling Industry - Kung, Hang I (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Classroom Interior Design and Creativity: The Contribution of Multifunctional Furniture for Higher Education Institutions in Macau - Kuok, Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

An Evaluation of the Treasure of Sacred Art of St. Joseph’s Seminary - Kwak, Maria Sheli (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Nostalgia in Flux From the Perspective of Chinese Jia and Heidegger’s Heimat - Lai, Tong Chon (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

Mangroves as a Nature-Based Solution for Coastal Water Eutrophication in Macao Sar China - Lai, Wai Ian (University of Saint Joseph, 2021)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Why did Uber Fail in Macau? Causes and Consequences of a New Digital Business Model Application - Lai, Weng Ian (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

澳門教師專業發展研究 –基於《非高等教育私立學校教學人員制度框架》的政策分析 - Lam, Iek Fei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門融合教育教師專業培訓與融合教育發展路向之研究 - Lam, Kin Ian (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門普通幼兒家長對融合教育的態度 =: Attitude of parents with regular childern towards inclusive education in Macau - Lam, Ngai Meng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門普通教師對融合教育的信念和實踐經驗: 一間融合教育資助計劃之幼稚園的個案研究=Macau Ordinary Kindergarten Teachers’ Belief and Practical Experience in Inclusive Education: A Case Study of a Kindergarten that Has Just Joined the Inclusive Education Funding Scheme - Lao, Cíntia da Rosa (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Association Between Early/ Emerging Adult-Parent Attachment and Problematic Internet Use Among College Students in Macao - Lao, Sio Mei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Translating Two Minds in the Tradition of One Faith: Considerations of Intercultural Dynamics in the parallels of John Henry Newman (1801-1890) and Joseph Ma Xiangbo (1840-1939) - Law, Cyril Jerome (Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular, 2021)
Interculturality is considered a constant given in the development of most major religious movements during the process of propagation coming into contact with diverse tongues, mores, and sentiments. And one of the chief, if not decisive, instruments contributing to this ever dynamic spread and reception of beliefs and cultures is translation. Christianity purports to be an incarnational religion, where the Word made flesh expresses the di-vine in human terms. Its doctrines are enshrined in a faith tradition that is developed largely through interpretation and translation. This short paper will cut into this sacral literary tradition by paralleling two influential mod-ern Christian thinkers, John Henry Newman from the Anglophone school, and Joseph Ma Xiangbo from the Orient, to see how attempts at translating the ideas and works of people from distinct cultural milieux is both reflec-tive of the necessary developmental nature of Christian teachings in the historical continuum of time and space, and indicative of the intellectual challenges that never cease to accompany the literary effervescence stem-ming from comparative religious studies.

Grammar of Macao Creole Portuguese with Typological and Semiotic Considerations - Lebel, Alexandre (University of Saint Joseph, 2021)
Macao Creole Portuguese (MacCP) is a critically endangered language spoken in Southeastern China. The formation of MacCP is attributed to the speakers of Portuguese-based creole languages in Asia (Asian CPs), especially Papia Kristang, the Malayo-Portuguese of Malacca (MalCP). Since the 19th century, MacCP has been traditionally classified as Sino-Portuguese, but comparative methods incited some authors to treat MacCP within the Malayo-Portuguese group. In Macao, the Malaccan origin of MacCP, known as Patúa or Maquista, is generally underestimated or misunderstood by the local population, including the Macanese/Maquista community. The main goal of this research is to clarify the origin of MacCP from a typological perspective on grammatical features. Secondly, while considering a possible revitalization of Maquista, the research should assess the significance of the Malayo- and Sino-Portuguese classifications in popular narratives and relate the language to current practices. The grammar of MacCP emerged from the complex linguistic ecology of the Portuguese colonial expansion in Asia. The documentation of Asian CPs allows us to sketch possible scenarios that explain the formation of MacCP according to linguistic, historical and social factors. A digital corpus of MacCP containing archive documents, contemporary literature, and oral transcriptions was assembled in order to produce a systematic review of 130 grammatical features, as defined in the Atlas of Pidgin and Creole Language Structures Online (APiCS Online – Michaelis et al. [eds] 2013). MacCP and MalCP share certain features that are not found in South Asian CPs, such as the in situ position of interrogative words, the reduplication for nominal plural, the form of reciprocal constructions, and the verb serialization of motion constructions, thus pointing to the Malayo-Portuguese origin. At the same time, other features suggest a certain influence from Sinitic languages, mainly Cantonese and Hokkien, such as the convergence between the genitive, adjective and relative clause constructions, the double-object construction, the verb-neg-verb polar question, the copular focus construction, the reduplication inducing a change of word class or semantics, and the use of certain deontic, imperative, and prohibitive verbal markers. The comparative analysis of the grammars of MacCP, MalCP and other Asian CPs can be represented quantitatively by the means of a phylogenetic network (SplitsTree4 – Huson & Bryant 2006). The results clearly indicate that, from a structural perspective, MacCP belongs to the Malayo-Portuguese group and the presence of Sinitic elements did not affect the core of the grammar. In fact, MacCP and MalCP appear to be more similar to each other than to the former Malayo-Portuguese of Batavia. However, the Malayo-Portuguese classification of MacCP does not resonate with the Macanese community. By contrast, the Sino-Portuguese classification translates current linguistic, social and semiotic practices. A socio-semiotic survey among the millennial generation of Macanese and the consideration of themes and motifs in Maquista literature indicates that the revitalization of Maquista simultaneously implies, in their views, the preservation of the Cantonese and Portuguese heritage
Keywords: Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph

The Caluation of Microsoft Coproration - Lee, Ka Lou (University of Saint Joseph, 2021)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Study of the Valuation of ManpowerGroup Inc - Lei, Choi Ieng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Statistical Methods to Forecast Air Quality in Taipa Ambient and Taipa Residential of Macao - Lei, Man Tat; Monjardino, Joana; Mendes, Luisa; Gonçalves, David; Ferreira, Francisco (Air Pollution Modeling and its Application XXVII, 2021)
Air pollution is a major concern issue on Macao since the concentration levels of several of the most common pollutants are frequently above the internationally recommended values. The low air quality episodes impacts on human health paired with highly populated urban areas are important motivations to develop forecast methodologies in order to anticipate pollution episodes, allowing establishing warnings to the local community to take precautionary measures and avoid outdoor activities during this period. Using statistical methods (multiple linear regression (MLR) and classification and regression tree (CART) analysis) we were able to develop forecasting models for the main pollutants (NO2, PM2.5, and O3) enabling us to know the next day concentrations with a good skill, translated by high coefficients of determination (0.82–0.90) on a 95% confidence level. The model development was based on six years of historical data, 2013 to 2018, consisting of surface and upper-air meteorological observations and surface air quality observations. The year of 2019 was used for model validation. From an initially large group of meteorological and air quality variables only a few were identified as significant dependent variables in the model. The selected meteorological variables included geopotential height, relative humidity and air temperature at different altitude levels and atmospheric stability characterization parameters. The air quality predictors used included recent past hourly levels of mean concentrations for NO2 and PM2.5 and maximum concentrations for O3. The application of the obtained models provides the expected daily mean concentrations for NO2 and PM2.5 and maximum hourly concentrations O3 for the next day in Taipa Ambient air quality monitoring stations. The described methodology is now operational, in Macao, since 2020.
0 citations (Crossref) [2022-09-21]

A cognitive semantic study of biblical Hebrew: the root šlm for completeness-balance - Leong, Andrew Chin Hei (Brill, 2021)
"Semantic studies of the Biblical Hebrew verb "whole" have been influenced by those of its most invoked nominal form "whole". In this volume Andrew Chin Hei Leong shows that the concepts of balance, alliance, and completeness form the basic semantic structure of "whole". Previous studies on "whole" employed either historical or textual methodology, which has been dominant in biblical lexical studies. In addition to these methods, in Leong develops a systematic semantic methodology from Cognitive Semantics and Frame Semantics, to demonstrate that it is balance, rather than completeness, that is the most central concept in holding the semantic network together"–
Keywords: Bible; Hebrew language; Language; style; Semantics; Shlm (The Hebrew root)

What Goes Around Comes Around? The (Non-)Existence of (Divine) Retribution in Ancient Chinese Literature and the Hebrew Bible - Leong, Andrew Chin Hei (Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular, 2021)

Does Romans 2:14 Refer to the Natural Law? - Leong, Chi Hei (Orientis Aura: Macau Perspectives in Religious Studies, 2021)
Whilst after decades of research, exegetes have all agree on the complexity of Paul’s line of thinking in Rom 2:14–16, the ITC in its 2009 document, In Search of a Universal Ethic, still in an oversimplified manner propagates the view that Rom 2:14 presupposes a theory/theology of the natural law. This article makes plain the major disagreements among Pauline exegetes whether such presupposition stands by reviewing some major contributions to the discussion by raising major questions regarding the issue of φύσει in those verses, the nature of the law mentioned by Paul, the identity of the people Paul calls “Gentiles.” This article offers a more nuanced understanding of Rom 2:14. Keywords: Rom 2:14, ITC, Universal Ethic, Natural Law, φύσει, Gentiles
Number: 6

Act as Animal in Virtual Reality - Leong, Chi Hoi (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Oligopolistic Strategies in the Gaming and Hospitality Industries of Macau - Leong, Chi Leng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An Exploration of Building Up the Quality Parent-Child Relationship in Childcare Service in Macao - Leong, On Na (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

A Study on the Educational Policy Reform Implementation of ''The Requirements of Basic Academic Attainments'' in Early Childhood Theme Teaching Curriculum in Macau =: 澳門幼兒教育在主題教學課程實行教育政策改革「基本學力要求」之研究 - Lin, Hou U. (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Attitudes, Acceptance, and Registration toward Organ Donation in Macao - Lou, Kin Heng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Quality Detection Method for Controller Process Based on Mask R-CNN Network Model - Ma, Xinlei; Chen, Yanyu; Li, Shaobin; Du, Wencai; Tan, Zehan; Li, Qinggu; Ma, Yaqi; Deng, Haiyan (2021 8th International Conference on Computational Science/Intelligence and Applied Informatics (CSII), 2021)

Corporate Social Resopnsibility Practices in Macau - Marcelo, Nicole Chantal Clemente (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Predictive Models for Decision Support in the COVID-19 Crisis - Marques, João Alexandre Lobo; Gois, Francisco Nauber Bernardo; Xavier-Neto, Jose; Fong, Simon James (Springer International Publishing, 2021)
COVID-19 has hit the world unprepared, as the deadliest pandemic of the century. Governments and authorities, as leaders and decision makers fighting the virus, enormously tap into the power of artificial intelligence and its predictive models for urgent decision support. This book showcases a collection of important predictive models that used during the pandemic, and discusses and compares their efficacy and limitations. Readers from both healthcare industries and academia can gain unique insights on how predictive models were designed and applied on epidemic data. Taking COVID19 as a case study and showcasing the lessons learnt, this book will enable readers to be better prepared in the event of virus epidemics or pandemics in the future.

Papal Bull: A Response to Contemporary Papal Scholarship - McNabb, Tyler Dalton (Journal of Biblical and Theological Studies, 2021)

Religious Epistemology in Analytic Theology - McNabb, Tyler Dalton; Baldwin, Erik (T&T Clark Handbook of Analytic Theology, 2021)
GSCC: 0000003

Ceremonies of the Sarum Missal: A Careful Conjecture by R. J. Urquhart (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2021)
0 citations (Crossref) [2023-01-27] Publisher: The Catholic University of America Press

‘Em Procissão Solene a Deus Orando, para os Batéis Viemos Caminhando’—The Long Ebb-Tide of Catholic Public Piety in the Former-Portuguese Enclave of Macao - Morgan, Stephen (Religions, 2021)
When the City of the Name of God of Macao marked 400 years of Portuguese administration in 1956, the Catholic community’s participation was marked by a wide range of activities that included liturgical celebrations, public processions and other devotions that involved large numbers of the lay faithful, members of confraternities, in addition to the clergy and religious of the enclave. Twenty-one years later the Diocese of Macao celebrated its own quatercentenary with celebrations of a decidedly more sober character and at the retrocession of Macao to Chinese control in December 1999, other than a few liturgical events and hierarchical presence at civic ceremonies, the Church was all but invisible. As the Diocese of Macao plans for its 450th anniversary, some of the former richness has begun to return. This paper outlines the long ebb tide and now-nascent flow of the tide of Catholic public piety in Macao over this period by reference to the Catholic religious processions of the City and seeks to offer tentative explanations grounded in the theological, ecclesial, political and cultural winds that have blown across the Pearl River Delta since the end of the Second World War.
0 citations (Crossref) [2022-09-21] GSCC: 0000000
Keywords: Catholic Church; China; Macao; Portugal; Vatican II; confrarias; processions; public piety

John Henry Newman and the development of doctrine: encountering change, looking for continuity - Morgan, Stephen (The Catholic University of America Press, 2021)
"In focusing on the gestation of "An Essay on the Development of Christian Doctrine" (1845), John Henry Newman's last work as an Anglican and presaging his transition to Catholicism, this book examines how Newman accounted for doctrinal continuity in the face of evidence of change in the history of the church"–

Liturgical Text as Mandorla: windows from the Everyday to the Sacred, from the Sacred to the Everyday - Morgan, Stephen (Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular, 2021)

Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular - Morgan, Stephen (USJ Press, 2021)

The Anglican Patrimony in Catholic Communion ed. by Tracey Rowland (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2021)
Publisher: The Catholic University of America Press

Taming randomized controlled trials in education: exploring key claims, issues and debates - Morrison, Keith (Routledge, Taylor & Francis Group, 2021)
"There is a recent surge in the use of randomized controlled trials (RCTs) within education globally, with disproportionate claims being made about what they show, 'what works', and what constitutes the best 'evidence'. Drawing on up-to-date scholarship from across the world, Taming Randomized Controlled Trials in Education critically addresses the increased use of RCTs in education, exploring their benefits, limits and cautions, and ultimately questioning the prominence given to them. While acknowledging that randomized controlled trials do have some place in education, the book nevertheless argues that this place should be limited. Drawing together all arguments for and against RCTs in a comprehensive and easily accessible single volume, the book also adds new perspectives and insights to the conversation; crucially, the book considers the limits of their usefulness and applicability in education, raising a range of largely unexplored concerns about their use. Chapters include discussions on: The impact of complexity theory and chaos theory Design issues and sampling in randomized controlled trials Learning from clinical trials Data analysis in randomized controlled trials Reporting, evaluating and generalizing from randomized controlled trials. Considering key issues in understanding and interrogating research evidence, this book is ideal reading for all students on Research Methods modules, as well as those interested in undertaking and reviewing research in the field of education"–
Keywords: Clinical trials; Education; Educational indicators; Research Data processing; Research Methodolgy

Employee Motivation in Social Enterprise: The Case of Caritas Elderly Care Services in Macau - Mui, Un Kei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Green Roof Application in Macao SAR - Noblesala, Marco Paulo R. (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Study and Analysis of English Press in Macau: Its Impact and Challenges - Pangan, Cheila Alexis Clemente (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

A performance académica como ritual de criação e ativismo na era pós-digital - Pérez, P; Pereira, S; Fernandes-Marcos, A (AVANCA CINEMA, 2021)

Ritual and the Sacred in Peter Shaffer's Theatre - Phillips, Jenny O. L. (Sacred and the Everyday: Comparative approaches to literature, religious and secular, 2021)

Geological Map of the Macao Special Administrative Region (China) - Quelhas, P; Borgens, R; Dias, Ágata; Ribeiro, L; Costa, P; Mata, J (Journal of Maps, 2021)
0 citations (Crossref) [2022-09-21]

Geology of the Macao Special Administrative Region (China) - Quelhas, Pedro; Borges, Ricardo; Dias, Ágata Alveirinho; Ribeiro, Maria Luísa; Costa, Pedro; Mata, João (Journal of Maps, 2021)
A 1:12,000 geological map of the Macao Special Administrative Region has been produced through detailed field work supported by petrographic, mineralogical, geochronological and geochemical data obtained in previous studies. This map aims to represent a reliable tool to understand the geological evolution of the region and for management of the territory. The geology of Macao is dominated by two groups of Jurassic granitic rocks belonging to an intrusive suite located along the coast of Southeast China: Macao Group I (MGI: 164.5 ± 0.6 to 162.9 ± 0.7 Ma) and Macao Group II (MGII: 156.6 ± 0.2 to 155.5 ± 0.8 Ma), including the associated microgranite, aplite and pegmatite dikes and quartz veins. Remnants of the metasedimentary wall-rock are present as Devonian xenoliths enclosed within the granites. Younger Jurassic to Cretaceous andesite to dacite dikes (150.6 ± 0.6 to <120 Ma) intrude the granitic rocks. Additionally, Quaternary sedimentary deposits cover the older lithologies.
0 citations (Crossref) [2022-09-21] Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/17445647.2021.1906340
Keywords: Jurassic; Macao (South China); Mesozoic; geological map; granites; magmatic rocks

Magmatic Evolution of Garnet-Bearing Highly Fractionated Granitic Rocks from Macao, Southeast China: Implications for Granite-Related Mineralization Processes - Quelhas, Pedro; Mata, João; Dias, Ágata (Journal of Earth Science, 2021)
The widespread W-(Mo)-Sn-Nb-Ta polymetallic mineralization in Southeast (SE) China is genetically associated with Mesozoic highly fractionated granitic rocks. Such rocks have enigmatic mineralogical and geochemical features, making its petrogenesis an intensely debated topic. To better understand the underlying magma evolution processes, petrography, garnet chemistry and whole-rock major and trace element data are reported for Jurassic highly fractionated granitic rocks and associated microgranite and aplitepegmatite dikes from Macao and compared with coeval similar granitic rocks from nearby areas in SE China. Despite the fact that the most evolved rocks in Macao are garnet-bearing aplite-pegmatite dikes, the existence of coeval two-mica and garnet-bearing biotite and muscovite granites displaying more evolved compositions (e.g, lower Zr/Hf ratios) indicates that the differentiation sequence reached higher degrees of fractionation at a regional scale. Although crystal fractionation played an important role, late-stage fluid/melt interactions, involving F-rich fluids, imparted specific geochemical characteristics to Macao and SE China highly fractionated granitic rocks such as the non-CHARAC (CHArge-and-RAdius-Controlled) behavior of trace elements, leading, for example, to non-chondritic Zr/Hf ratios, Rare Earth Elements (REE) tetrad effects and Nb-Ta enrichment and fractionation. Such process contributed to the late-stage crystallization of accessory phases only found in these highly evolved facies. Among the latter, two populations of garnet were identified in MGI (Macao Group I) highly fractionated granitic rocks: small grossular-poor euhedral grains and large grossular-rich skeletal garnet grains with quartz inclusions. The first group was mainly formed through precipitation from highly evolved Mn-rich slightly peraluminous melts under low-pressure and relatively low temperature (∼700 °C) conditions. Assimilation of upper crust metasedimentary materials may have contributed as a source of Mn and Al to the formation of garnet. The second group has a metasomatic origin related to the interaction of magmatic fluids with previously crystallized mineral phases and, possibly, with assimilated metasedimentary enclaves or surrounding metasedimentary strata. The highly fractionated granitic rocks in Macao represent the first stage in the development of granite-related W-(Mo)-Sn-Nb-Ta mineralization associated with coeval more evolved lithotypes in SE China.
1 citations (Crossref) [2022-09-21]

Behavioural and endocrine impact of artificial selection for winning in the siamese fighting fish - Ramos, Andreia Maria Cerejo; Gonçalves, David (University of Saint Joseph, 2021)
Aggression clearly has an adaptive value as it is necessary to secure resources for survival, growth, and reproduction. The Siamese fighting fish, Betta splendens, have endured a prolonged process of artificial selection for winning paired-fight contests across Southeast Asia, resulting in strains of short-fin aggressive “fighters”. Across centuries, Thai breeders have been selecting these strains by discarding loser batches and allowing winner batches to breed, claiming that they are significantly more aggressive than wild-types. This natural experiment provides a powerful context to investigate the biological basis of aggressive behaviour in fish, the topic of this thesis. To study aggression, it is important to validate and standardize behavioural assays appropriate for the species under study. Further, different aggression-eliciting stimuli, such as live opponents, 3D models, video playback, or mirror images, may elicit non-equivalent behavioural and physiological responses. For B. splendens, in particular, quantifying aggression from live fights is not ethically acceptable as the high levels of aggression of this species usually result in injuries or even death of the opponent. In Chapter II, it was shown that mirror images elicit very similar aggressive displays and endocrine responses to an interacting opponent behind a transparent partition, validating the use of this test to measure aggression in this model species. Further, it was shown that circulating levels of both androgens (11-ketotestosterone and testosterone) and corticosteroids (cortisol) increased in response to the aggression challenge, even in the absence of conflict resolution, questioning the role of these hormones during present and future aggressive contests. Using the previously validated mirror assay and also tests with live conspecifics, we assessed the impact of selection for winning by comparing, in Chapter III, male and female aggressive behaviour of lab-raised fighter and wild-type strains. The hypothesis that selection for male winners enhanced aggressive displays was confirmed, suggesting that the duration and frequency of threat and attack behaviour correlates with winning probability. However, females of the fighter strain, which are not selected for fights, were also more aggressive than wild-type females. This suggests that male and female aggression share common genetic pathways and physiological mechanisms and raises the possibility that selection for alleles that favour male aggression may have promoted intersexual genetic conflict in this species. After confirming the expected differences in aggressive behaviour between fighter and wild-type fish, the following question was whether endocrine systems, in particular those previously shown to respond to aggression, could have been targeted by the selection process. From previous studies in fish and other vertebrates, it was hypothesised that selection for winners could have increased constitutive levels of androgens or led to an enhanced androgen response to a social challenge. However, in chapter IV, it was shown that levels of 11-ketotestosterone and its response to aggression was similar in males of both strains, questioning the role of androgens in the modulation of aggression in B. splendens. On the contrary, constitutive levels of cortisol and the response of this hormone to an aggression challenge were higher in wild-type compared with fighter fish, supporting previous findings that associated high aggression with a blunted cortisol response. Overall, results from Chapter IV suggest that selection for winning had a stronger impact on the hypothalamus-pituitary-interrenal axis than in the hypothalamus-pituitary-gonadal axis. My results support the assumption of the “Challenge Hypothesis” proposed by John Wingfield and collaborators in 1990 to explain the relationship between androgens and aggression, according to which androgen levels above a reproductive baseline are a consequence of the frequency and intensity of social interactions, in particular of male-male agonistic encounters. It is becoming clear that androgens increase rapidly after an aggressive contest, independently of fight outcome. However, the function of this increase remains unclear as the frequency of aggressive displays was unrelated with post-fight androgen levels and constitutive levels of androgens, and androgen responsiveness, were similar between fighter and wild-type males. Results obtained for cortisol agree with a “corticosteroid-mediated dominance hypothesis” whereby low baseline levels and a blunted response of corticosteroids would be associated with a dominant status and high aggression. The work advances our knowledge about the endocrine regulation of aggressive behaviour in B. splendens and opens several testable hypotheses about the role of androgens and corticosteroids in the regulation of fish aggressive behaviour
Keywords: Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph

Triggering a Change of The Economic Paradigm - Rothlin, Stephan (The Journal of the Macau Ricci Institute, 2021)

How Do Chinese Manufactured Products Affect Purchase Intention in a SAR of PRC? The Case of Macao - Silva, Márcio Rossano Pegado da (University of Saint Joseph, 2021)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Physiology, endocrinology and chemical communication in aggressive behaviour of fishes - Silva, Melina Coelho da; Canário, Adelino Vicente Mendonça; Hubbard, Peter Colin; Gonçalves, David (Journal of Fish Biology, 2021)
Fishes show remarkably diverse aggressive behaviour. Aggression is expressed to secure resources; adjusting aggression levels according to context is key to avoid negative consequences for fitness and survival. Nonetheless, despite its importance, the physiological basis of aggression in fishes is still poorly understood. Several reports suggest hormonal modulation of aggression, particularly by androgens, but contradictory studies have been published. Studies exploring the role of chemical communication in aggressive behaviour are also scant, and the pheromones involved remain to be unequivocally characterized. This is surprising as chemical communication is the most ancient form of information exchange and plays a variety of other roles in fishes. Furthermore, the study of chemical communication and aggression is relevant at the evolutionary, ecological and economic levels. A few pioneering studies support the hypothesis that aggressive behaviour, at least in some teleosts, is modulated by “dominance pheromones” that reflect the social status of the sender, but there is little information on the identity of the compounds involved. This review aims to provide a global view of aggressive behaviour in fishes and its underlying physiological mechanisms including the involvement of chemical communication, and discusses the potential use of dominance pheromones to improve fish welfare. Methodological considerations and future research directions are also outlined.
3 citations (Crossref) [2022-09-21]

Modelling the barriers that are preventing e-commerce to thrive – a case study from Portugal, international journal of business excellence - Silva, Susana Costa e; Machado, Joana Costa; Martins, Carla; Duarte, Paulo; Marques, João Alexandre Lobo (International Journal of Business Excellence, 2021)
The identification of barriers for e-commerce to thrive in specific countries is a topic of great interest. This work proposes two models to study the barriers to B2C e-commerce adoption in Portugal, highlighting obstacles less exploited by previous research: the impact of offline shopping pleasure and the influence of the distance to shopping malls on online shopping intent. An online survey was conducted based on different constructs. A multivariate OLS hierarchical regression was used to analyse the proposed models regarding the intention to buy online and the number of online purchases. The results revealed that customer satisfaction is a strong predictor of intent to buy online and that perceived product risk remains a barrier to e-commerce. Consumers living in high urbanised areas have more propensity to buy online. Helpful information is provided regarding the impact of context, culture, product, and individual barriers, showing that multichannel strategies are best suited for success.
Keywords: E-commerce barriers; Online shopping; Portugal; Retail

A Study of the Perspectives and Experiences of Macau Secondary School Students with Special Education Needs in Inclusive Education - Sio, Man Cheng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Parental Stress and Family Relations in Macao: The Mediating Role of Parenting Styles - Siu Kuan Lei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The Lotus Network – Masterplan and Design Guidelines for Iao Hon and Toi San Community Public Spaces (University of Saint Joseph, 2021)

O Autoconceito no Pré-Escolar em Contexto Educativo Multicultural e Plurilinguίstico=Preschool Children’s Self-concept in a Multicultural and Multilingual Educational Context - Sousa, Joana Luísa Dourado de (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Small Action Research of Using Flipped Classroom Approach to Supporting Diversity Students’ Learning in University. - Sun, C. R. (2021)

Kindergarten Teachers' Attitudes towards Inclusive Education: Perspectives from Macau. - Sun, C. R. (2021)

探討澳門輟學生經歷之研究 =: A Qualitative Study on the Experiences of School Dropouts in Macau - Tam, Sok Man (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Positive Approach in Preventing Depression in Adolescents: Comparing Local Chinese and Filipino Migrant Adolescents in Macao - Tejada, Anali Jane Gabala (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Development of Cultural Tourism in Macau through the Visual and Performing Arts - Tique, Ana Teresa Leal (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An Exploratory Study of Factors Influencing the Consumer Behaviour of Macau Chinese Millennial Women in their Purchasing on Taobao - Tong, Ka Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Experiences and Reflections Related to Mental Health Among University Students during Covid-19: A Case Study - Tou, Un Ieng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Role of Cognition as a Mediator for Narcissism and Trait Aggression as Predictors of Aggressive Driving Behavior - Van, Hou Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Roles and Functions of Social Worker Within Crisis Management of the Pandemic COVID-19 in Long-Term Care Facilities of Macau: A Case Study - Wong Oi Lin (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Social Integration and the Screening of the Early-Stage Dementia in Older Adults: The Mediation Role of Mental Health - Wong Wai Hong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

認知情緒調節策略在澳門家長的童年創傷經驗與專制式教養模式之間的中介作用 =: Childhood Trauma on Authoritarian Parenting among Macao Parents: The Mediating Role of Cognitive Emotional Regulation Strategy - Wong, Ka Kei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Retrieving the Sense of the Sacred: a Paradigm of Silence in the Liturgy - Wong, Lee Chun (University of Saint Joseph, 2021)
Keywords: Catholic Church; Liturgy Theology; Religious aspects Catholic Church; Silence

Impact of Vessel Traffic on Underwater Soundscape and Marine Mammals in the Pearl River Delta - Wong, Man Ieng (University of Saint Joseph, 2021)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

澳門小學教師性別意識與實踐性別平等教育的研究 =: A study on gender consciousness and practice in gender equality education of primary school teacher in Macau - Wong, Nga Lam (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploratory Study of a Postpartum Confinement Centre: An Adaptation of Emerging Practice in Macao, SAR - Wong, Wai Sam (University of Saint Joseph, 2021)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Experience of Happiness: Grasping Bliss through Buddhism and Kierkegaard’s Existentialism - Wu, Wai Han (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Philosophy; University of Saint Joseph

Learning dynamics of kernel-based deep neural networks in manifolds - Wu, Wei; Jing, Xiaoyuan; Du, Wencai; Chen, Guoliang (Science China Information Sciences, 2021)

A Case Study on Using House-Tree-Person (HTP) Projective Drawing Technique to Identify the Personality Traits of Children with Socio-Emotional Challenges - Yee, Seong Wa (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Pilgrimage Christian and Secular: a Phenomenological Approach - Yuan, Haojun (University of Saint Joseph, 2021)
In the light of the many kinds of journeys that have been considered pilgrimages, this book uses phenomenology as a method to examine the claim that pilgrimage is a journey to the ‘center’ during which pilgrims seek meaning s for themselves. First, by analyzing a phenomenology of Christian pilgrimage, this work attempts to identify what commonalities, as well as differences, exist between Christian pilgrimage and secular pilgrimage in terms of ‘natural attitude’. Next, by using a phenomenological method, such as transcendental reduction, the distinction between these two types of pilgrimage could be clarified that the happiness sought in Christian pilgrimage is both intentionally spiritual and sustainable, while primarily intellectual or sensory in secular pilgrimage. Lastly, this work seeks to establish whether or not ‘being at leisure’ is the primary element for pilgrims whose aim is to attain an understanding of happiness during a pilgrimage
Keywords: Christian pilgrims and pilgrimages; Phenomenology

Prize-giving time for Macau - Morrison, Keith (Macau Business, 2020)

Mary and Fátima: A Modest C-Inductive Argument for Catholicism - Mcnabb, Tyler Dalton; Blado, Joseph E. (Perichoresis, 2020)
AbstractC-Inductive arguments are arguments that increase the probability of a hypothesis. In this paper, we offer a C-Inductive argument for the Roman Catholic hypothesis. We specifically argue that one would expect the Miracle of Fátima on Roman Catholicism more so than on alternative hypotheses. Since our argument draws on confirmation theory, we first give a primer for how confirmation theory works. We then, provide the historical facts surrounding the Miracle of Fátima. We offer up two competing naturalistic explanations that attempt to explain the historical facts, but then, argue that a supernatural explanation is superior. Having established that something miraculous likely occurred at Fátima, we move to argue for the overall thesis of the paper. Finally, we engage several objections to our argument.

Artificial Intelligence Prediction for the COVID-19 Data Based on LSTM Neural Networks and H2O AutoML - Marques, Joao Alexandre Lobo; Gois, Francisco Nauber Bernardo; Xavier-Neto, José; Fong, Simon James (Predictive Models for Decision Support in the COVID-19 Crisis, 2020)

Epidemiology Compartmental Models—SIR, SEIR, and SEIR with Intervention - Marques, Joao Alexandre Lobo; Gois, Francisco Nauber Bernardo; Xavier-Neto, José; Fong, Simon James (Predictive Models for Decision Support in the COVID-19 Crisis, 2020)

Forecasting COVID-19 Time Series Based on an Autoregressive Model - Marques, Joao Alexandre Lobo; Gois, Francisco Nauber Bernardo; Xavier-Neto, José; Fong, Simon James (Predictive Models for Decision Support in the COVID-19 Crisis, 2020)

Nonlinear Prediction for the COVID-19 Data Based on Quadratic Kalman Filtering - Marques, Joao Alexandre Lobo; Gois, Francisco Nauber Bernardo; Xavier-Neto, José; Fong, Simon James (Predictive Models for Decision Support in the COVID-19 Crisis, 2020)

Predicting the Geographic Spread of the COVID-19 Pandemic: A Case Study from Brazil - Marques, Joao Alexandre Lobo; Gois, Francisco Nauber Bernardo; Xavier-Neto, José; Fong, Simon James (Predictive Models for Decision Support in the COVID-19 Crisis, 2020)

Prediction for Decision Support During the COVID-19 Pandemic - Marques, Joao Alexandre Lobo; Gois, Francisco Nauber Bernardo; Xavier-Neto, José; Fong, Simon James (Predictive Models for Decision Support in the COVID-19 Crisis, 2020)

Analysis of reading errors in Portuguese : digraphs and complex syllabic structures - Simões, Edlia; Martins, Margarida Alves (Análise Psicológica, 2020)
Abstract: The Portuguese language poses several challenges for children in the initial phase of learning how to read, particularly in the case of letters that may correspond to more than one phoneme, two letters that correspond to a single phoneme and in the case of words containing complex syllabic structures. The objective of this study was to perform a psycholinguistic analysis of the reading errors of children, attending the 1st (n=175) and 2nd year (n=137) of schooling, specifically in the case of words containing digraphs or complex syllabic structures and to analyse the differences between children’s reading errors in these two years. An oral reading test was used for data collection. A quantitative and qualitative analysis of the type of reading errors was conducted using words with consonant digraphs (ch, nh, lh, gu, rr, ss), and words with complex syllables <CVC and CCV>. This analysis showed that children presented greater difficulties in some specific digraphs and tended to simplify complex syllables, either by adding or deleting phonemes. The quantity and quality of the reading errors of children attending both grades were discussed in light of reading acquisition theories and children’s phonological development.
0 citations (Crossref) [2023-03-15] Accepted: 2021-01-20T11:46:39Z Publisher: Edições ISPA

Reframing the Urban Edge - Design Strategies for Macau x Zhuhai Waterfront - Soares, Nuno (2020)

Methods, understandings, and expressions of causality in educational research - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)
0 citations (Crossref) [2022-09-21]

澳門品德與公民教育校本課程初探 - Tchiang, I.; Ge, Yun (2020)

Sulfur isotopic compositions of sulfides along the Southwest Indian Ridge: implications for mineralization in ultramafic rocks - Dias, Ágata; Ding, Teng; Tao, Chunhui; Liang, Jin; Chen, Jie; Wu, Bin; Ma, Dongsheng; Zhang, Rongqing; Wang, Jia; Liao, Shili; Wang, Yuan; Yang, Weifang; et al. (Mineralium Deposita, 2020)
11 citations (Crossref) [2022-09-21]

Post Disaster Temporary Housing System based on Generative Design Method - Afonso, Filipe (2020)

Cross Border Lab: Reframing the Urban Edge - Macau x Zhuhai - Soares, Nuno (2020)

The Effect of Self-Efficacy and Role Understanding on Teachers’ Emotional Exhaustion and Work Engagement in Inclusive Education in Macao (SAR) - Kuok, A. C. H.; Teixeira, Vitor; Forlin, Chris; Monteiro, Elisa; Correia, Ana (International Journal of Disability, Development and Education, 2020)
This study examined responses from 508 full-time teachers working in inclusive schools in Macao (SAR). The intention was to understand the teachers’ perceptions about their roles and how they responded to inclusive practices in their school. Teachers’ perceived levels of emotional exhaustion and cognitive work engagement were assessed in relation to several professional competencies (self-efficacy with using inclusive instruction, collaborating with parents and paraprofessionals, and managing disruptive behaviours), as well as the organisational variable of role understanding. Regression analysis showed that teachers’ self-efficacy with using inclusive instruction was found to be the most powerful negative predictor of emotional exhaustion; while self-efficacy for managing disruptive behaviours was a positive predictor of teachers’ cognitive work engagement. Teachers’ level of understanding of their role and that of their schools was a negative predictor of emotional exhaustion and a positive predictor of cognitive work engagement. Moreover, it further confirmed that the concept of co-existence between work engagement and burnout can be applied to inclusive teachers. Results were interpreted in relation to management in inclusive schools in Macao and were followed by a discussion on the implications of enhancing inclusive education.
1 citations (Crossref) [2022-09-21]

Local Matters - Design Driven by Urban Conditions [Video] - Soares, Nuno (2020)

Parental stress and parenting in Chinese immigrant families: The mediating role of social support - Liu, Shu-Wen; Zhai, Fuhua; Gao, Qin (Child & Family Social Work, 2020)
Abstract As the population of Chinese immigrants has been growing rapidly in the United States, it has been understudied on the parenting behaviours as well as the roles parental stress and social support playing in parenting in this group. This study investigated whether parental stress was associated with parenting and whether this relationship was mediated by social support in a sample of 255 Chinese immigrant parents from the Survey of Asian American Families in New York City. Regression analyses with a rich array of control variables found that a higher level of parental stress and the presence of one or more stressors such as unemployment, low income, and low education were positively associated with the use of harsh discipline and parent?child conflicts and negatively associated with positive parenting practices. Social support functioned as a significant mediator in the relationships between parental stress and positive parenting practices but not in the relationships of parental stress with parent?child conflict or the use of harsh discipline.
8 citations (Crossref) [2022-09-21] Publisher: John Wiley & Sons, Ltd
Keywords: Chinese immigrants; harsh discipline; parental stress; parenting practices; parent–child conflict; social support

Trip to a dejà vu place - Simões, José Manuel (Aspectus. Revista de Arte & Ciência, 2020)

Editorial: On Cinema - Ribas, Daniel; Crespo, Nuno; Caires, Carlos Sena (Journal of Science and Technology of the Arts, 2020)
In the past decades, the field of cinema has undergone several transformations. The digital turn increasingly called for new forms of production, distribution, and exhibition, which imply different ways of thinking, doing, and experimenting cinema. These new forms also reduced the gap between cinema to other so-called visual arts. If cinema and visual arts were already in the process of merging, the last years forced the naturalization of thinking in similar theoretical grounds. This special issue aims to be a forum for the discussion of new practices of researching cinema, and the changes in cinema’s forms of experience and production.
Number: 2
Keywords: Art and cinema; Cinema; Contemporary cinema; Digital turn; Visual Arts

Psychometric properties of a Chinese version of the Constructivist Learning Environment Survey among secondary-school students in Hong Kong - Kwan, Yee Wan (Learning Environments Research, 2020)
The study examined the factor structure, reliability and validity of a Chinese version of the Constructivist Learning Environment Survey (C-CLES), an instrument for assessing students’ perceptions of the extent of constructivist approaches prevalent in classrooms. A convenience sample of 967 students in Secondary Three (Grade 9) in Hong Kong participated in this study by completing a self-administered questionnaire in their class time. Exploratory and confirmatory factor analyses supported the hypothesised factor structure, indicating five theoretical constructivist environment dimensions that showed goodness-of-fit to 25 items: Personal Relevance, Uncertainty, Critical Voice, Shared Control, and Student Negotiation. Criterion-related validity, involving evidence based on relations to other variables, was assessed by correlations between the constructivist environment dimensions and cognitive strategies and academic ability. Most correlations were statistically significant and in the positive direction. The C-CLES with 25 items provides a useful measure for educational practice and research among school students.
Keywords: Cognitive outcomes; Constructivist learning environment; Secondary schools; Validation

Health and Well-Being Education: Extending the SCARF Learning Analytics Model for Identifying the Learner Happiness Indicators - Li, Tengyue; Marques, Joao Alexandre Lobo; Fong, Simon (International Journal of Extreme Automation and Connectivity in Healthcare (IJEACH), 2020)
The use of learning analytics (LA) in real-world educational applications is growing very fast as academic institutions realize the positive potential that is possible if LA is integrated in decision making. Education in schools on public health need to evolve in response to the new knowledge and th...
0 citations (Crossref) [2022-09-21] Publisher: IGI Global

Crowdsensing-Based Gamification for Collective Assistance for Post-Era of Coronavirus Epidemic in Community Living - Luo, Renfei; Marques, João Alexandre Lôbo; Ong, Kok-Leong; Fong, Simon (International Journal of Extreme Automation and Connectivity in Healthcare (IJEACH), 2020)
Crowdsensing exploits the sensing abilities offered by smart phones and users' mobility. Users can mutually help each other as a community with the aid of crowdsensing. The potential of crowdsensing has yet to be fully realized for improving public health. A protocol based on gamification to encoura...
0 citations (Crossref) [2022-09-21] Publisher: IGI Global

Enhancing Student Learning and Teacher Development: Does “Assessment for Learning” Matter? - Ng, Shun Wing; Kwan, Yee Wan; Huey Lei, Ka Hio (International Journal of Educational Reform, 2020)
This paper aims to report a case study of exploring the effect of ?assessment for learning? on improving student learning and facilitating teachers? professional development in the examination-oriented context of Hong Kong. By adopting Variation Theory of the Lesson Study approach, data were collected through pre- and post-tests, interviews with students and teacher participants and observation field-notes in order to help diagnose students? learning difficulties and provide evidence for teachers to refine their teaching strategies to enhance students? learning effectiveness. The students? improvement in learning performance informed the teacher participants of the usefulness of ?assessment for learning? in the classroom.
Publisher: SAGE Publications Inc

「紐曼樞機：兩心對話，一生皈依」澳門紐曼樞機藝文館開幕活動系列專題講座 （Special Lecture on Cardinal Newman for the Opening of the Centro de Cultura e Artes Performartivas Cardeal Newman de Macau） - Law, Cyril Jerome (2020)

Validating the use of the 24-item long version and the 12-item short version of the Teachers’ Sense of Efficacy Scale (TSES) for measuring teachers’ self-efficacy in Macao (SAR) for inclusive education - Monteiro, Elisa; Forlin, Chris (Emerald Open Research, 2020)
Validation of the Teachers’ Sense of Efficacy Scale (TSES) for use with teachers in Macao (SAR) was undertaken to determine its usefulness as a measure of teacher self-efficacy for inclusive education. This paper discusses the results found by analyzing various versions of the TSES and TSES-C in a Chinese format with 200 pre-service teachers in Macao (SAR).  Psychometric analyses were undertaken to investigate the validity of the existing scales and the three and two factor solutions. The results indicated a preferred 9-item version that produced improved factor loadings and reliabilities. The use of a relatively quick and short scale to measure such a complex phenomenon as teacher self-efficacy is discussed. Issues are raised regarding generalizability of scales and the impact of culture, demographics, and edifying issues that may impact on the usefulness of such scales.
Type: article
Keywords: Inclusive education; Macao; scale development; self-efficacy

Resources for Future in a Caring Economy - Gassner, Franz (Menschenrechte und Gerechtigkeit als bleibende Aufgaben, 2020)

Noise-induced hearing loss in zebrafish: investigating structural and functional inner ear damage and recovery - Breitzler, Lukas; Lau, Ieng Hou; Fonseca, Paulo J.; Vasconcelos, Raquel O. (Hearing Research, 2020)
Exposure to continuous moderate noise levels is known to impair the auditory system leading to Noise-Induced Hearing Loss (NIHL) in animals including humans. The mechanism underlying noise-dependent auditory Temporary Threshold Shifts (TTS) is not fully understood. In fact, only limited information is available on vertebrates such as fishes, which share homologous inner ear structures to mammals and have the ability to regenerate hair cells. The zebrafish Danio rerio is a well-established model in hearing research providing an unmatched opportunity to investigate the molecular and physiological mechanisms of NIHL at the sensory receptor level. Here we investigated for the first time the effects of noise exposure on TTS and functional recovery in zebrafish, as well as the associated morphological damage and regeneration of the inner ear saccular hair cells. Adult specimens were exposed for 24h to white noise at various amplitudes (130, 140 and 150 dB re. 1 μPa) and their auditory sensitivity was subsequently measured with the Auditory Evoked Potential (AEP) recording technique. Sensory recovery was tested at different times post-treatment (after 3, 7 and 14 days) and compared to individuals kept under quiet lab conditions. Results revealed noise level-dependent TTS up to 33 dB and increase in response latency. Recovery of hearing function occurred within 7 days for fish exposed to 130 and 140 dB noise levels, while fish subject to 150 dB only returned to baseline thresholds after 14 days. Hearing impairment was accompanied by significant loss of hair cells only at the highest noise treatment. Full regeneration of the sensory tissue (number of hair cell receptors) occurred within 7 days, which was prior to functional recovery. We provide first baseline data of NIHL in zebrafish and validate this species as an effective vertebrate model to investigate the impact of noise exposure on the structure and function of the adult inner ear and its recovery process.
14 citations (Crossref) [2022-09-21]
Keywords: Fish; Hair cells; Hearing sensitivity; Noise; Sound pressure level; Temporary threshold shift

Review of Biesta. G. (2020) Educational research: an unorthodox introduction, Educational Research and Evaluation - Morrison, Keith (Educational Research and Evaluation, 2020)
0 citations (Crossref) [2022-09-21]

The truth, the whole truth, and nothing but the truth - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)
0 citations (Crossref) [2022-09-21]

Evaluation of mathematical models for QRS feature extraction and QRS morphology classification in ECG signals - do Vale Madeiro, João Paulo; Lobo Marques, João Alexandre; Han, Tao; Coury Pedrosa, Roberto (Measurement, 2020)
It is plausible to assume that the component waves in ECG signals constitute a unique human characteristic because morphology and amplitudes of recorded beats are governed by multiple individual factors. According to the best of our knowledge, the issue of automatically classifying different ’identities’ of QRS morphology has not been explored within the literature. This work proposes five alternative mathematical models for representing different QRS morphologies providing the extraction of a set of features related to QRS shape. The technique incorporates mechanisms of combining the mathematical functions Gaussian, Mexican-Hat and Rayleigh probability density function and also a mechanism for clipping the waveform of those functions. The searching for the optimal parameters which minimize the normalized RMS error between each mathematical model and a given QRS search window enables to find an optimal model. Such modeling behaves as a robust alternative for delineating heartbeats, classifying beat morphologies, detecting subtle and anomalous changes, compression of QRS complex windows among others. The validation process evaluates the ability of each model to represent different QRS morphology classes within 159 full ECG signal records from QT database and 584 QRS search windows from MIT-BIH Arrhythmia database. From the experimental results, we rank the winning rates for which each mathematical model best models and also discriminates the most predominant QRS morphologies Rs, rS, RS, qR, qRs, R, rR’s and QS. Furthermore, the average time errors computed for QRS onset and offset locations when using the corresponding winner mathematical models for delineation purposes were, respectively, 12.87±8.5 ms and 1.47±10.06 ms.
13 citations (Crossref) [2022-09-21]
Keywords: ECG feature extraction; Mathematical modeling; Morphology classification; QRS complex delineation

Design for Classroom Units: A Collaborative Multicultural Studio Development with Chinese Students - Caires, C. S.; Barbosa, A.; Hanyou, W. (International Journal of Educational and Pedagogical Sciences, 2020)
Design for Classroom Units: A Collaborative Multicultural Studio Development with Chinese Students

Inclusive Education Teachers—Strategies of Working Collaboratively With Parents of Children With Special Educational Needs in Macau - Ng, Shun Wing; Kwan, Yee Wan (International Journal of Educational Reform, 2020)
Education for learners with special education needs has become one of the major concerns of education policies in every corner of the world. In Macau, however, the transformation of schools into inclusive environments is reported to be slow because many teachers in Macau have not accepted the key values of inclusive education and possess little knowledge of their responsibilities as inclusive education teachers. Despite being nonempirical, the aim of this article is twofold: to inform inclusive education teachers, especially those in Macau and other developing regions, of the necessary knowledge, skills and strategies of working collaboratively with parents of children with SEN and provide policy makers concerned with practical ideas of designing effective professional development programmes for teachers working in the inclusive environment. The ultimate aim is to ensure that children with SEN benefit from an education process that includes quality learning opportunities.
Publisher: SAGE Publications Inc

Statistical Forecast Applied to Two Macao Air Monitoring Stations - Lei, M.; Monjardino, J.; Mendes, L.; Gonçalves, D.; Ferreira, F. (IOP Conference Series: Earth and Environmental Science, 2020)
The levels of air pollution in Macao often exceeded the levels recommended by WHO. In order for the population to take precautionary measures and avoid further health risks under high pollutant exposure, it is important to develop a reliable air quality forecast. Statistical models based on multiple regression (MR) analysis were developed successfully for Macao to predict the next day concentrations of PM10, PM2.5, and NO2. All the developed models were statistically significantly valid with a 95% confidence level with high coefficients of determination (from 0.89 to 0.92) for all pollutants. The models utilized meteorological and air quality variables based on five years of historical data, from 2013 to 2017. The data from 2013 to 2016 were used to develop the statistical models and data from 2017 were used for validation purposes. A wide range of meteorological and air quality variables were identified, and only some were selected as significant dependent variables. Meteorological variables were selected from an extensive list of variables, including geopotential height, relative humidity, atmospheric stability, and air temperature at different vertical levels. Air quality variables translate the resilience of the recent past concentrations of each pollutant and usually are maximum and/or the average of latest 24-hour levels. The models were applied in forecasting the next day average daily concentrations for PM10, PM2.5, and NO2 for the air quality monitoring stations. The results are expected to be an operational air quality forecast for Macao.
0 citations (Crossref) [2022-09-21] Publisher: IOP Publishing

Are Work Engaged Employees Perceive Career Success? A Study of Hospitality at Macau - Kuok, A. C. H (Journal of Hospitality, 2020)
This study examined 206 casino dealers in hospitality at Macau to investigate the extent of their subjective career success and work engagement. Casino dealers were work engaged, but their subjective career success was fairly low, with significant difference between them, which indicates they have cognitive dissonance about their jobs. Several personality variables (emotional suppression and work ethic), organizational variables, i.e., organizational socialization (training, understanding, coworker support, future prospects), and distributive justice, were assessed in relation to subjective career success and work engagement. Organizational socialization, work ethic, and distributive justice were positively correlated with and predictors of subjective career success and work engagement; while emotion suppression was negatively correlated with and predictor of work engagement. This study provides evidence of extending the theories of subjective career success and work engagement in Chinese society and hospitality. Also, it identifies factors that could resolve the employees’ cognitive dissonance, and implementations for management were discussed.
Number: 1-2
Keywords: Subjective career success; emotion suppression; hospitality; human resources; socialization; work engagement

Who has the power? A reflection on teaching drama improvisation with young children - Ho, Ka Lee Carrie (Journal of Early Childhood Research, 2020)
The following study reflects and explores the dynamics of aesthetic experiences within drama improvisations. This arts-based research was carried out in Hong Kong with six Cantonese children who were aged 3?5?years. Data were collected from the video transcripts of five workshops and the researcher?s own research journal. Two significant milieus were observed: switching in-between roles and intuitive creativity is not talkback. I argue that because each of these two milieus provide the foreground for the complex ? and at times contradictory ? nature of children?s aesthetic experiences where Deleuzian power is at play, opportunities arise for both, challenging the traditional adult?child power relations, and in so doing, educators can be able to reconfigure and reconceptualise teaching goals and practices, both generally and specifically, within the context of early childhood education.
Publisher: SAGE Publications

Multilingual freedom of the press in Macau - Simões, José Manuel; Mayes, Lee ([RMd] RevistaMultidisciplinar, 2020)
There can be no conclusive determining regarding true press freedom in Macau, and perhaps this statement can be applied elsewhere as well. Issues of self-censorship, partisanship, or cultural loyalty exist in cities and countries around the world, and most of the time there is simply no reliable measurement to determine their impact. The Special Administrative Region (SAR) of Macau is separate and distinct from mainland China, but that does not mean that it is entirely without question regarding its freedom of the press, ethical journalistic practices, and interference by non-authorized agencies at the three languages local newspapers.
Number: 1 Publisher: NMd, Núcleo Multidisciplinar, UAlg
Keywords: autocensura; ingerência; liberdade de imprensa; partidarismo; práticas éticas

Group work and cultural characteristics in a Chinese school - Morrison, Keith; Garcia, Alejandro Salcedo; Wong, Sin Teng (Educational Research and Evaluation, 2020)
0 citations (Crossref) [2022-09-21]

The scalpel model of educational research - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)
0 citations (Crossref) [2022-09-21]

XRD Identification of Ore Minerals during Cruises: Refinement of Extraction Procedure with Sodium Acetate Buffer - Milinovic, Jelena; Dias, Ágata; Janeiro, Ana I.; Pereira, Manuel F. C.; Martins, Sofia; Petersen, Sven; Barriga, Fernando J. A. S. (Minerals, 2020)
The on-board identification of ore minerals during a cruise is often postponed until long after the cruise is over. During the M127 cruise, 21 cores with deep-seafloor sediments were recovered in the Trans-Atlantic Geotraverse (TAG) field along the Mid Atlantic Ridge (MAR). Sediments were analyzed on-board for physicochemical properties such as lightness (L*), pH and Eh. Selected samples were studied for mineral composition by X-ray powder diffraction (XRD). Based on XRD data, sediment samples were separated into high-, low- and non-carbonated. Removal of carbonates is a common technique in mineralogical studies in which HCl is used as the extraction agent. In the present study, sequential extraction was performed with sodium acetate buffer (pH 5.0) to remove carbonates. The ratio between the highest calcite XRD reflection in the original samples (Iorig) vs its XRD-reflection in samples after their treatment with the buffer (Itreat) was used as a quantitative parameter of calcite removal, as well as to identify minor minerals in carbonated samples (when Iorig/Itreat > 24). It was found that the lightness parameter (L*) showed a positive correlation with calcite XRD reflection in selected TAG samples, and this could be applied to the preliminary on-board determination of extraction steps with acetate buffer (pH 5.0) in carbonated sediment samples. The most abundant minerals detected in carbonated samples were quartz and Al- and Fe-rich clays. Other silicates were also detected (e.g., calcic plagioclase, montmorillonite, nontronite). In non-carbonated samples, Fe oxides and hydroxides (goethite and hematite, respectively) were detected. Pyrite was the dominant hydrothermal mineral and Cu sulfides (chalcopyrite, covellite) and hydrothermal Mn oxides (birnessite and todorokite) were mineral phases identified in few samples, whereas paratacamite was detected in the top 20 cm of the core. The present study demonstrates that portable XRD analysis makes it possible to characterize mineralogy at cored sites, in particular in both low- and high-carbonated samples, before the end of most cruises, thus enabling the quick modification of exploration strategies in light of new information as it becomes available in near-real time.
7 citations (Crossref) [2022-09-21]

Unravelling potentials and limitations of sharing economy in reducing unnecessary consumption: A social science perspective - Lai, Michael K. W.; Ho, Amy P. Y. (Resources, Conservation and Recycling, 2020)
Hyper-consumption in capitalist economies has had a severe impact on the environment that no one can escape. In recent year, there has been a high degree of optimism in sharing economy with regard to coping with the environmental problems caused by consumption. However, most of the current literature focuses on business perspectives in which a sharing economy is portrayed as a new business model, but not as a way to curb environmental degradation. This paper, based on a social science perspective, investigates the potentials and limitations of the strategies adopted in sharing economy projects towards social transformation (especially coping with environmental degradation and hyper-consumption), with the adoption of Erik Olin Wright’s concept of real utopia. A case study approach has been adopted in terms of a sharing economy project named ‘Waste-no-mall (Yuen Long)’ in Hong Kong. The project founder embraces ideological-led strategies based on collective responsibility, self-determination and reflexivity, encouraging the participants to reflect on their consumption behaviours, and thus increasing the level of awareness of the need to reduce unnecessary consumption. However, it is a double-edge sword that limits its impact to those who are active participants, without spreading to others the need for change. It is also limited for their interstitial strategies within the project, and is unable to call for a concrete symbiotic transformation when it comes to policy. The significance of this paper is two-fold. First, it adopts a social science perspective that centres on exploring the proclaimed social implications of sharing economy, an aspect which is under-studied given that most of current studies are from a business perspective; second, it extends Wright’s concept to an operational level by showing an important pathway aiming to solve environmental problems through the simultaneous achievement of both horizontal and vertical balancing strategies, based on Wright’s concept of real utopia.
Keywords: Hong Kong; Mindful consumption; Real utopia; Sharing economy; Social transformation

Reawakening Macanese identity: the impact of Chinese outbound tourism - Lou, Lai-Chu Ivy; Xie, Philip Feifan (Journal of Policy Research in Tourism, Leisure and Events, 2020)
The purpose of this paper examines the potential role of Chinese outbound tourism as a catalyst of change for the Macanese identity. There is an emerging trend to have a new identity amongst Macanese residents to valorize cultural and heritage assets. By using Bourdieu’s concept of habitus, it proposes that the social media space is built to voice concerns of language, place attachment and induced public participation. The study utilizes a mixed method approach comprising a survey for netizens and content analysis of online discussions, in order to fully understand changes due to Chinese outbound tourism.
Publisher: Routledge _eprint: https://doi.org/10.1080/19407963.2018.1505106
Keywords: China; Identity; Macau; linguistic sensitivity; place attachment; public participation

The Importance of Readiness for Change, a Leadership Perspective Based on a Case Study in Macau, SAR China - Marques, João; Reis, Joana; Phillips, Jenny O. L.; Diakite, Ansoumane (Journal of Advanced Management Science, 2020)
0 citations (Crossref) [2022-09-21]

Statistical Forecast of Pollution Episodes in Macao during National Holiday and COVID-19 - Lei, Man Tat; Monjardino, Joana; Mendes, Luisa; Gonçalves, David; Ferreira, Francisco (International Journal of Environmental Research and Public Health, 2020)
Statistical methods such as multiple linear regression (MLR) and classification and regression tree (CART) analysis were used to build prediction models for the levels of pollutant concentrations in Macao using meteorological and air quality historical data to three periods: (i) from 2013 to 2016, (ii) from 2015 to 2018, and (iii) from 2013 to 2018. The variables retained by the models were identical for nitrogen dioxide (NO2), particulate matter (PM10), PM2.5, but not for ozone (O3) Air pollution data from 2019 was used for validation purposes. The model for the 2013 to 2018 period was the one that performed best in prediction of the next-day concentrations levels in 2019, with high coefficient of determination (R2), between predicted and observed daily average concentrations (between 0.78 and 0.89 for all pollutants), and low root mean square error (RMSE), mean absolute error (MAE), and biases (BIAS). To understand if the prediction model was robust to extreme variations in pollutants concentration, a test was performed under the circumstances of a high pollution episode for PM2.5 and O3 during 2019, and the low pollution episode during the period of implementation of the preventive measures for COVID-19 pandemic. Regarding the high pollution episode, the period of the Chinese National Holiday of 2019 was selected, in which high concentration levels were identified for PM2.5 and O3, with peaks of daily concentration exceeding 55 μg/m3 and 400 μg/m3, respectively. The 2013 to 2018 model successfully predicted this high pollution episode with high coefficients of determination (of 0.92 for PM2.5 and 0.82 for O3). The low pollution episode for PM2.5 and O3 was identified during the 2020 COVID-19 pandemic period, with a low record of daily concentration for PM2.5 levels at 2 μg/m3 and O3 levels at 50 μg/m3, respectively. The 2013 to 2018 model successfully predicted the low pollution episode for PM2.5 and O3 with a high coefficient of determination (0.86 and 0.84, respectively). Overall, the results demonstrate that the statistical forecast model is robust and able to correctly reproduce extreme air pollution events of both high and low concentration levels.
8 citations (Crossref) [2022-09-21] Number: 14 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: COVID-19; air pollution; air quality forecast; modelling; national holiday; pollution episodes

The Financial Evaluation of Amazon.com, Inc - Ao Ieong, Sio Tai (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

On the probability flow in the Stock market I: The Black-Scholes case - Arraut, Ivan; Au, Alan; Tse, Alan Ching-biu; Marques, Joao Alexandre Lobo (arXiv.org, 2020)
It is known that the probability is not a conserved quantity in the stock market, given the fact that it corresponds to an open system. In this paper we analyze the flow of probability in this system by expressing the ideal Black-Scholes equation in the Hamiltonian form. We then analyze how the non-conservation of probability affects the stability of the prices of the Stocks. Finally, we find the conditions under which the probability might be conserved in the market, challenging in this way the non-Hermitian nature of the Black-Scholes Hamiltonian.
Place: Ithaca, United States Publisher: Cornell University Library, arXiv.org Section: Quantitative Finance University: Cornell University Library arXiv.org
Keywords: General Finance

The Film Sound Analysis Framework: A Conceptual tool to Interpret the Cinematic Experience - Barbosa, Álvaro; Dizon, Kristine (Journal of Science and Technology of the Arts, 2020)
GSCC: 0000001
Keywords: Analysis framework; Film studies; Sound and music design

Couple Satisfaction in Partners of Male Shift Working Pilots - Bredenhann, Andri (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Original Sin and Reprobation in Renaissance Thomism: The Cases of Domingo Bañez and John of St. Thomas - Cai, Thomas Yilun (Nos sumus tempora, 2020)

The concept of “Object-image” revisited through the interactive-film installation “Sense of Place” - Caires, C. S; Estadieu, G (2020)

The concept of “Object-image” revisited through the interactive-film installation “Sense of Place - Caires, C. S; Estadieu, G (2020)

澳門青少年沉迷網絡遊戲之研究 - Chai, Chin (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Financial Evaluation of the Coca-Cola Company - Chan, Cheok Hei (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Conservation and Restoration of Pith Painting: A Case Study of Five Art Pieces from Private Collections - Chan, Chi Leong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The Financial Evaluation of the Estée Lauder Companies Inc - Chan, Hoi Ieng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

澳門小學階段新入職教師在融合教育中的挑戰 =: Challenges Encountered by Newly Recruited Teachers in Inclusive Education of Primary Schools in Macau - Chan, Pan Pan (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

How Social Media Affects the Purchase Intentions of Female Consumers in Macao: Watching Beauty and Cosmetic Product Experience Videos on Youtube - Chan, Velda (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

臺灣地區融合教育政策與實施對澳門融合教育推行啟示之研究 - Chang, Hei Man (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Impacts of Burnout and Work Engagement on Performance: a Study of a Surveillance Team - Chang, Pou I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門小學教師與資源教師合作現況與挑戰 - Chao, Cheng I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Look Before You Eat: An Augmented Reality Menu - Cheang, Ka Pui (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

The Financial Valuation of Nike Inc - Cheng, Kin San (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

不同社經地位之家長和教師對親師溝通的意見: 一間澳門幼稚園的個案研究 - Cheong, Man Hong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

對於澳門特殊需求學生教育的體驗: 來自自閉症兒童家長的聲音 - Choi Chi Wai (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education(MED); University of Saint Joseph

Rewriting Life Story and Career Development: a Case Study Using a Narrative Approach - Choi, Ka Lok (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Financial Valuation of Starbucks Corporation - Chong, Cecilia (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A figura feminina na ficção de Senna Fernandes: identidade, subalternidade e agência - Correia, Ana (O Macaense. Identidade e cultura e quotidiano, 2020)

Oxyhydroxide Hydrothermal Crusts from Saldanha Hydrothermal Field - Costa, Pedro; Dias, Ágata (Goldschmidt Abstracts, 2020)
0 citations (Crossref) [2022-09-21]

Approaches to Customer due Diligence of Anti-Money Laundering Compliance of Banks in Macao - Couto, Miguel Angelo (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Sub-Seafloor Sulfide Mineralization in the Saldanha Hydrothermal Field, Mid-Atlantic Ridge (MAR) - Dias, Ágata; Qiu, Wenhong; Barriga, Fernando J A S; Tao, Chunhui (Goldschmidt Abstracts, 2020)
0 citations (Crossref) [2022-09-21]

Ore-Forming Process of the Menez Gwen Hydrothermal Field: In situ S Isotopes and Trace Metals Constraints - Dias, Ágata; Qiu, Wenhong; Costa, Isabel Maria Amaral; Barriga, Fernando J A S (Goldschmidt Abstracts, 2020)
0 citations (Crossref) [2022-09-21]

Biculturalism and Parenting Styles among Filipino Mothers and Young Adult Offspring in Macao - Doctor, Ana Catarina Alvarez (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Re-thinking Chinese Ecumene in the Global Age - Duraj, Jaroslaw (Eric Voegelin’s Asian Political Thought, 2020)
The rise of Asia in global affairs has forced western thinkers to rethink their assumptions, theories, and conclusions about the region. Eric Voegelin’s Asian Political Thought brings together a mixture of established and rising scholars from both Asia and the West to reflect upon the political philosopher’s thought about China, Japan, Korea, Central Asia, and India. From Voegelin’s writings, readers will not only understand how Voegelin’s approach can illuminate the fundamental principles and issues about Asia but also what are the challenges and possibilities that Asia offers in the twentieth-first century. For those who want to move past the superficial commentary and clichés about Asia, Eric Voegelin’s Asian Political Thought is the book for you.

A Financial Valuation of Jacobs Engineering Group Inc - Encarnação, Bruno Miguel Arantes da (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

O trabalho de recuperação de crianças resgatadas do tráfico humano no Nepal=Recovery work for rescued children from human trafficking in Nepal - Espindola, Marcelo Gonçalves (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

探討澳門托兒所推行融合托兒服務的策略與挑戰 - Fong, Sou Lei (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Interculturality and formation - Gallares, Judette (Engaging our diversity : interculturality and consecrated life today, 2020)

Walking with John: the go-along as ethnographic tool to explore the lives of adolescents with autism spectrum disorder - Gnanaraj, Steffi (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Entry Into the Mainland China Market: a Case Study of Macau's Portuguese Wine Companies - Gonçalves, Daniela Filipa Atraca dos Santos (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Roles of the Mangroves on the Bioaccumulation and Citogenotoxic Effects of Heavy Metals and Pesticides in the Food Web of a Tropical System - Gonzalez, Lucia Ivorra (University of Saint Joseph, 2020)
Mangroves are a unique group of plants, which offer a great variety of goods and services to the ecosystem and to the society. Regrettably, they have been globally threatened by urbanization and industrialization, among others, triggering overexploitation of the world’s mangrove forests despite their ecological and economic importance. As a result, mangroves are often under pollution stress as sinks or receivers for numerous man-made pollutants such as pesticides, which are the main focus of this thesis. One of the most widely applied chemicals in the word are the organochlorine pesticides (OCPs) that even after their supposedly worldwide ban between 1950s-1990s, they can still be detected in the environment. Numerous studies have been done in phytoremediation of pollutants by mangroves, but little attention has been given to the role of mangroves in the remediation of OCPs. For this reason, part of this thesis will focus on the occurrence and distribution of OCPs in intertidal tropical and sub-tropical areas around the world with and without mangroves. As a first goal (I), we evaluate —in a theoretical way— if the presence of mangroves affects or modifies the levels of OCPs in the surrounding environment. For this purpose, data from different matrices, such as water, sediment, benthic fauna and plants were included and discussed in this work. Moreover, and considering Macao’s location, we also quantified OCPs from surface waters of this region from areas with and without mangroves and included in this task. Besides this theoretical approach, this thesis also included some laboratoy and field work specifically focused on dicofol and 4,4’-dichlorobenzophenone (4,4’-DCBP, its main metabolite). Dicofol is an OCP strongly related to dichlorodiphenyltrichloroethane (DDT), which has been extensively used in China and more specifically, in the Pearl River Delta (PRD), a region under anthropogenic pressure. However, due to dicofol’s instability (i.e., sensitive to low pH, light exposure and high temperature), we expected to quantify 4,4′-DCBP (which is also common to DDT) as the main form present in the environment. As a second goal (II), we conducted a monitoring study in surface waters from Macao and Hong Kong, to evaluate the contamination status and water quality of these regions. Concentrations of 4,4’-DCBP, nutrients and physicochemical parameters were measured during transition and wet season, and at high and low tide. In addition, since the toxicity of this metabolite was totally unknown, we assessed it via two biological models: Daphnia magna and Artemia salina. Since 4,4’-DCBP was detected and quantified in both regions (2.8-30.0 ng/L), this thesis also includes experimental work focused on the assimilation and depuration pattern by a marine organism. For that purpose and as a final goal (III), we selected the common edible bivalve Meretrix as a model to evaluate the dynamics of accumulation and depuration of the pesticide dicofol. The Vietnamese clams were exposed during 15 days under two different concentrations of dicofol, and decontaminated for the same period of time. Quantification of 4,4’-DCBP was done during both phases (uptake and depuration) and at different sampling times. In summary, all these different works helped us to conclude that: I.1) As expected, vegetated areas with mangroves presented lower concentrations of OCPs for all the matrices, and also better quality in terms of pesticide pollution for water and sediments. Results obtained from Macao’s waters also revealed the same pattern, with mangroves areas having lower levels of contamination. Although the gathered data presented methodological variability (i.e. different quantification methods, extraction protocols, equipment used), the same pattern was observed among matrices, showing how robust and solid the results herein obtained are. II.1). Hong Kong presented higher concentrations of 4,4’-DCBP than Macao, which may be due to the use of dicofol as a pesticide and the use of antifouling-paint for ships. Moreover, concentrations of 4,4’-DCBP during wet season were below limits of quantification, demonstrating a seasonal pattern and a dilution effect due to higher river discharges during this period. II.2). Both regions showed possible eutrophication problems due to the high nutrient concentrations. These levels presented also a seasonal variability, with dissolved inorganic nitrogen and total dissolved solids higher during transition; and dissolved inorganic phosphorous, total suspended solids and chlorophyll a higher during wet season. II.3). Toxicity of 4,4’-DCBP was lower than the parent compound dicofol, and the levels quantified indicated a low environmental risk. However, it is important to pay attention to this compound since interaction with other contaminants could enhance their toxicity, or processes such as biomagnification or bioaccumulation could make low concentrations a threat for the environment. III.1). Different concentrations of dicofol presented different uptake and depuration kinetics. Animals exposed to higher concentrations (500 ng/L), had levels above limits of quantification (LOQ) after 24h exposure, unlike the ones exposed to lower concentrations (50 ng/L), which had levels <LOQ after the same period. The first ones also, presented lower uptake rates, and this could indicate that high dicofol concentrations in the system could affect the respiration rates of the organism. In addition, this work also showed that animals exposed to high concentrations of dicofol will need more than 15 days to depurate in order to reach safe levels for human consumption. The compilation of the work done in this thesis allowed us to better understand the role of mangroves ecosystems on the accumulation of OCPs and to provide solid information that could create strategies for mangroves management and conservation. Moreover, and as a first attempt, we were able to quantify this pesticide metabolite in the PRD (one of the most seriously contaminated areas in China), to determine its toxicity and to define its kinetics in an important organism such as the edible bivalve M. meretrix. We intend that this thesis will be helpful for the scientific community providing new insights regarding metabolite interactions (within and with other molecules) and toxicity (LC50 and theoretical risk assessment), which were unknown until now
Keywords: Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph

The Impact of E-Commerce in Local Flower Consumers in Macao: Online Stores vs Physical Stores - Guerreiro, Diana Macedo (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Smart Home Interactive Design: How can Interactive Design be Combined with a Smart Home System to help Human Future? - He, Min Yi (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

The Financial Valuation of Dunkin' Brands Group, Inc - Ho, Hon U. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Effectiveness of Art Therapy for Children with Special Educational Needs - Ho, Weng Chong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門幼稚園教師對融合教育的態度 - Ieong, Leng San (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Financial Valuation of Vitasoy International Holding's Limited - Iong, Sio Ieng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Effect of Peers, School Connectedness, Parents on Internet Gaming Addiction in Adolescents - Ip, Tan Long (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A Study of the Management Style in Macau - Kong, Angela Maria (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

初探澳門初任幼稚園教師對融合教育生問題行為的處理方法及其心理狀態 - Kuan, Wai Leng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Two Projective Drawing Tests as a Consolidated Measure to Identify and Understand the Underlying Problems of Primary Children with Emotional-Behavioral Issues of Concern - Kuok, Ka Lai (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Children's with SEN Views About Their Experience in Inclusive Education - Lai, Hoi Lam (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Community Participation of Cultural Heritage Management in a Rapid Growing Economy: A Case Study of Macao, China - Lam, San (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The Financial Valuation of Facebook, Inc - Lam, Weng I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Adapting the Unified Theory of Acceptance and Use of Technology 2 (Utaut 2) to Explain Acceptance of Battery Electric Vehicles: Evidence From Macau - Lampo, Alessandro (University of Saint Joseph, 2020)
Vehicles solely powered by electricity are a major technological innovation that combines individual transportation needs and environmental sustainability, yet their market penetration is low. Research has traditionally indicated factors such as the vehicle’s purchasing price, driving range, and charging time as the main barriers to adoption. However, the decision to adopt a technology also depends on what the technology represents to the user; therefore, other factors may be important to explain individuals’ behavior. This study is a quantitative and cross-sectional look at the behavioral intention to adopt battery electric vehicles (BEVs) technology in the context of Macau. The research builds on the unified theory of acceptance and use of technology 2 (UTAUT 2) (Venkatesh et. al., 2012) to explain the characteristics of the local consumers. Besides the addition of image and environmental concern to the theoretical model, the study also put forward and evaluate the construct of technology show-off, an original measure of the visible and experiential characteristics of a technology. A sample of 236 Macau residents was analyzed by structural equation modeling (SEM). The analysis of the data supported the explanatory and predictive power of our model and helped to describe the idiosyncrasies of local residents. The results provide insights related to individual technology acceptance that could be useful in designing more accurate strategies and fostering the uptake of BEVs in Macau or markets that share similarities
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; Thesis and Dissertations PhD in Business Administration (D-BA); University of Saint Joseph

Multi-view convolutional neural network with leader and long-tail particle swarm optimizer for enhancing heart disease and breast cancer detection - Lan, K.; Liu, L.; Li, T.; Chen, Y.; Fong, S.; Marques, J.A.L.; Wong, R.K.; Tang, R. (Neural Computing and Applications, 2020)
8 citations (Crossref) [2022-09-21]

澳門融合生家長參與個別化教育計劃之現況分析 - Lao, Sin Ian (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Impact of Noise on Early Development and Hearing in Zebrafish (Danio rerio) - Lara, Rafael Ayala (University of Saint Joseph, 2020)
Fishes are highly specialized in extracting ecologically relevant information from their diverse acoustic habitats since early developmental stages. The zebrafish (Danio rerio) is a valuable and well-stablished vertebrate model for investigating hearing functioning and disorders, development of the inner ear in vertebrates including humans, drug discovery, ecotoxicology assessments and behavioral research. Although the acoustic environment is known to shape the structure and sensitivity of auditory systems, there is no information on the natural soundscape of this species. Zebrafish are typically reared in large-scale artificial housing systems, which acoustic properties and potential effects on hearing remain largely unknown. Even though elevated levels of noise are widely present in most aquatic soundscapes and to an even greater extent in artificial environments, very limited information is known on how this important environmental stressor impacts species’ development and physiology, hearing capabilities and inner ear morphology, and behaviour. Considering that noise pollution is rapidly increasing in aquatic ecosystems, causing detrimental effects on survivability and growth and altering physiology and behaviour of organisms, it is of paramount importance to assess how this stressor affects wildlife, especially in early ontogeny, a critical period for development and establishment of phenotypic traits. For this thesis I aimed to 1) characterize the soundscape of both zebrafish natural habitats and laboratory captive conditions, and discuss possible impact on auditory sensitivity. Sound recordings were conducted in five distinct zebrafish habitats (Southwest India), from quieter stagnant environments with diverse biological/abiotic sounds to louder watercourses characterized by current and moving substrate, while artificial environmental characterization was conducted on three typical zebrafish housing systems. 8 In order to assess the impact of noise exposure on early development, my next goal was to 2) perform a split-brood experiment to test the effects of chronic noise exposure to increasing levels (130 and 150 dB re 1 μPa, continuous white noise) and different temporal regimes (mimicking shipping activity) on larval zebrafish in regards to general development, physiological stress, and behavioural patterns. Finally, the last objective consisted on 3) testing the effects of chronic noise exposure on auditory sensitivity measured based on inner ear saccular microphonics and acoustic-evoked startle responses (prepulse inhibition paradigm) in larval zebrafish, as well as evaluating whether sensitivity changes were paralleled by altered inner ear morphology. Based on bioacoustics methods, my first study found that zebrafish natural soundscape varied between 98 and 126 dB re 1 lPa in sound pressure levels. Sound spectra presented most energy below 3000 Hz and quieter noise windows were found in the noisiest habitats matching the species best hearing range. Contrastingly, recordings from zebrafish housing systems revealed higher sound levels (122–143 dB) and most energy below 1000Hz with more spectral peaks, which might cause significant impact such as auditory masking or even hearing loss. In my second research work, the acoustic treatments did not affect general development or hatching but increased noise levels led to a significant increase in mortality of larval zebrafish. The cardiac rate, yolk sac consumption and cortisol levels increased significantly with increasing noise level at both 3 and 5 dpf (days post fertilization). Variations in noise time presentations (different random noise periods similar to shipping activity) suggested that the presence of longer silent intervals is important to down-regulate physiological stress. Moreover, 5 dpf larvae exposed to 150 dB continuous noise regimes displayed increased dark avoidance in an anxiety-related dark/light preference test and displayed a significant 9 impairment in spontaneous alternation behaviour (SAB) a memory and sensorimotor related behaviour. Finally, in the last thesis goal, I found that noise-exposed specimens displayed significantly lower hair cell number and saccular epithelial area. This change in sensory morphology was paralleled by a significant decrease in inner ear saccular sensitivity at lower frequencies (100 to 200 Hz) in 5 dpf larvae. Sensorimotor hearing assessment revealed a hypersensitisation effect in noise-exposed group that displayed higher startle swimming velocity, but also significant decrease in sensitivity at 200 Hz. Altogether, this thesis provides an important ground for future research on the adaptation of zebrafish auditory system to the natural soundscapes, and highlights the importance of controlling noise conditions in captivity systems. Furthermore, results provide first evidence of noise-induced physiological stress, anxiety-driven behaviours and memory impairment in larval zebrafish larvae, showing that both noise amplitude and timing may negatively impact key physiological and behavioural endpoints in early ontogeny. The thesis also reports new findings on how acoustic stress may impact the structure and function of the inner ear in larval fish, which was followed by decreased sensitivity in sensorimotor responses to acoustic stimuli. My research highlights the importance of investigating how altered soundscapes and associated physiological and behavioural stress may affect important sensitive windows in development and impose new evolutionary challenges under a scenario of global change
Publisher: University of Saint Joseph
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Enhancing Learning of Accounting for Non-Accounting students: Through Lens of Theory of Planned Behavior and Experiential Learning Styles - Lau, Meng Chan (University of Saint Joseph, 2020)
This thesis aims to explore how learning accounting for non-accounting major students could be enhanced through a comprehensive framework connecting individual attributes and learning approaches. While accounting is considered an important and mandatory discipline for business students, it is also considered a difficult subject which deters students’ engagement in the subject. Although the issue has been widely recognized, there are relatively less discussions on possible remedies. Learning accounting is a dynamic process that go beyond the traditional one-to-many learning and teaching settings, all factors revolving the students’ learning environment and process, altogether determine and affect the learning efficiencies. A meta-analysis was first performed to understand the standings of accounting education and to identify gaps within existing literatures in the field of management, accounting, tourism and general education researches. A documentary review on the curricula of all Macau HEI programs involving compulsory accounting courses was also conducted to understand the role and significance of accounting courses for non-accounting college students in Macau. Based on the literature review, this study borrows constructs from theory of planned behavior (TPB) models in its research framework. It attempts to provide a comprehensive framework to understand how students learn accounting efficiently by delving into individual learning styles of the students and their perceived helpfulness and self-efficacy, in respective to different learning techniques. Due to its exploratory nature, a mixed method of qualitative and quantitative methodology is adopted, where both focus group discussions and in-depth interviews are performed with non-accounting students to elicit understandings on student’s difficulties in learning accounting and their preferences for different learning styles. Then, a full-scale quantitative survey is conducted in a Macau higher education institute to assess the learning efficiencies of accounting in different situations. A triangulation with feedback from faculties and administrators are also elicited to provide alternate dimensions on the issues. With no surprise, there is no one best 3 teaching style or method for all students, this thesis contributes to accounting education research by provide a comprehensive diagnosis on the all-round learning stimulus and hindrance in learning accounting. At the end, recommendations are provided for accounting educators to emphasize on the uniqueness of students and to encourage a more dynamic and open environment for learning. Limitations of the studies are also discussed
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

Air Quality Management in Macao: Assessment, Development of an Operational Forecast, and Future Perspectives - Lei, Man Tat (University of Saint Joseph, 2020)
A combination of assessment, operational forecast, and future perspective was thoroughly explored to provide an overview of the existing air quality problems in Macao. The levels of air pollution in Macao often exceed those recommended by the World Health Organization (WHO). In order for the population to take precautionary measures and avoid further health risks during high pollution episodes, it is important to develop a reliable air quality forecast. Statistical models based on linear multiple regression (MLR) and classification and regression trees (CART) analysis were successfully developed for Macao, to predict the next day concentrations of NO2, PM10, PM2.5, and O3. Meteorological variables were selected from an extensive list of possible variables, including geopotential height, relative humidity, atmospheric stability, and air temperature at different vertical levels. Air quality variables translate the resilience of the recent past concentrations of each pollutant and usually are maximum and/or the average of latest 24-hour levels. The models were applied in forecasting the next day average daily concentrations for NO2 and PM and maximum hourly O3 levels for five air quality monitoring stations. The results are expected to support an operational air iv quality forecast for Macao. The work involved two phases. On a first phase, the models utilized meteorological and air quality variables based on five years of historical data, from 2013 to 2017. Data from 2013 to 2016 were used to develop the statistical models and data from 2017 was used for validation purposes. All the developed models were statistically significantly valid with a 95% confidence level with high coefficients of determination (from 0.78 to 0.93) for all pollutants. On a second phase, these models were used with 2019 validation data, while a new set of models based on a more extended historical data series, from 2013 to 2018, were also validated with 2019 data. There were no significant differences in the coefficients of determination (R2) and minor improvements in root mean square errors (RMSE), mean absolute errors (MAE) and biases (BIAS) between the 2013 to 2016 and the 2013 to 2018 data models. In addition, for one air quality monitoring station (Taipa Ambient), the 2013 to 2018 model was applied for two days ahead (D2) forecast and the coefficient of determination (R2) was considerably less accurate to the one day ahead (D1) forecast, but still able to provide a reliable air quality forecast for Macao. To understand if the prediction model was robust to extreme variations in v pollutants concentration, a test was performed under the circumstances of a high pollution episode for PM2.5 and O3 during 2019, and a low pollution episode during 2020. Regarding the high pollution episode, the period of the Chinese National Holiday of 2019 was selected, in which high concentration levels were identified for PM2.5 and O3, with peaks of daily concentration for PM2.5 levels exceeding 55 μg/m3 and the maximum hourly concentration for O3 levels exceeding 400 μg/m3. For the low pollution episode, the 2020 period of implementation of the preventive measures for COVID-19 pandemic was selected, with a low record of daily concentration for PM2.5 levels at 2 μg/m3 and maximum hourly concentration for O3 levels at 50 μg/m3. The 2013 to 2018 model successfully predicted the high pollution episode with high coefficients of determination (0.92 for PM2.5 and 0.82 for O3). Likewise, the low pollution episode was also correctly predicted with high coefficients of determination (0.86 and 0.84 for PM2.5 and O3, respectively). Overall, the results demonstrate that the statistical forecast model is robust and able to correctly reproduce extreme air pollution events of both high and low concentration levels. Machine learning methods maybe adopted to provide significant improvements in combination of multiple linear regression (MLR) and classification and regression vi tree (CART) to further improve the accuracy of the statistical forecast. The developed air pollution forecasting model may be combined with other measures to mitigate the impact of air pollution in Macao. These may include the establishment of low emission zones (LEZ), as enforced in some European cities, license plate restrictions and lottery policy, as used in some Asian, tax exemptions on electric vehicles (EVs) and exclusive corridors for public transportations. Keywords: Air pollution; Particulate Matter; Ozone; Macao; Statistical air quality forecast; Pollution episodes; Chinese national holiday; COVID-19
Keywords: Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph

Designing an Optimized Constructed Wetland System with Circular Sustainability for Wastewater Treatment in Macao - Lei, Micaela (University of Saint Joseph, 2020)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

The Theory of Educational Curriculum of Confucius and Plato - Lei, Wai Seng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Philosophy; University of Saint Joseph

The Road to Service Export Diversification: Gambling and Convention in Macao - Lei, Weng Chi (Economics and Finance Readings: Selected Papers from Asia-Pacific Conference on Economics & Finance, 2019, 2020)
This book is a compilation of the best papers presented at the APEF 2019 conference which was held on 25th and 26th July 2019 at the Grand Copthorne Waterfront in Singapore. With a great number of submissions, it presents the latest research findings in economics and finance and discusses relevant issues in today's world. The book is a useful resource for readers who want access to economics, finance and business research focusing on the Asia-Pacific region.

Interactive bedside lamp design - Leong, Kit Teng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Analyzing Intercultural Romantic Relationships of Filipinos in Macao: Informing Counseling Strategies - Li, Anne Michelle Sia (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Hypnotherapeutic Treatment as a Way to Enhance Sleep Quality: Case Study on a Clinical Counseling Professional in Macao - Li, Hiu Yung (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Role and Influence of External Stakeholders on the Corporate Governance Practices of Gaming Companies in Macao - Limbo, Lem Anne Agnas (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Role of Sponsorship in Corporate Social Responsible Practice in the Macao Gaming Industry - Lo, Hoi Man (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Status of Mangroves in Macao and the Efficacy of Localized Environmental Educational Intervention on School Students' Environmental Knowledge - Loi Hoi Kei (University of Saint Joseph, 2020)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Parenting Training for Enhancing Self-Esteem, Self-Efficacy, and Emotional Regulation of Mothers Who Were Victims of Domestic Violence - Lou, On I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門合作學習實踐情況: 一所小學的個案研究 - Lou, Wai Leng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Analysis of Teachers' Perceptions of Professional Development Activities in Macao: A Mixed Methods Study - Ma, Babolal Choi I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education(MED); University of Saint Joseph

Family Life Cycle and Number of Children in A Family Affecting Parent’s Parenting Style, Parental Stress, Life and Marital Satisfaction - Mak, Chong Hin (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Nonlinear characterization and complexity analysis of cardiotocographic examinations using entropy measures - Marques, J.A.L.; Cortez, P.C.; Madeiro, J.P.V.; Albuquerque, V.H.C.; Fong, S.J.; Schlindwein, F.S. (Journal of Supercomputing, 2020)
17 citations (Crossref) [2022-09-21]

Enhancing Sustainability Development in Macao Through a Green Educational Program: An Action Research Study - Martins, Cíntia Pacheco Leite (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Pestilent Popes or a Pestilent Church? Judaism, Catholicism, and Skeptical Theism - McNabb, Tyler Dalton (The Heythrop Journal, 2020)
0 citations (Crossref) [2022-09-21] GSCC: 0000000

Has Oppy Done Away with the Aristotelian Proof? - McNabb, Tyler; DeVito, Michael (The Heythrop Journal, 2020)
0 citations (Crossref) [2022-09-21] GSCC: 0000000

Quality of Life and Wellbeing of the Foreign Communities in Macao - Mohr, Silvia Isabel (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Ogień zapalony niegdyś na górze Moria: Woltyła i Newman o warunkach dla propozycju Chrystusa'=The fire once kindled on Moriah: Wojtyła and Newman on the conditions for the proposal of Christ - Morgan, Stephen (Jan Paweł II: Komunikacja i Kultura, 2020)

Review of Gorard, S. (2020) Getting evidence into education: evaluating the routes to policy and practice - Morrison, Keith (Educational Research and Evaluation, 2020)

The Social Welfare Services of the Diocese of Macau in the 20th Century: The Macau Cooperation Model of Social Welfare Work - Mou, Chi Chong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Seeing the True Self: A Comparison of Arthur Schopenhauer and Japanese Zen - Ng, Fong Man (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Philosophy; University of Saint Joseph

澳門數學教師學科教學知識之個案研究 - Ng, Ka Io (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Preservation and Rehabilitation of Macao Industrial Heritage: A Case Study of the Iec Long Firecracker Factory - Ng, Kit Leng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Teacher Burnout: Applying the Job Demands and Resources Model in Macao - Ng, Kun Keong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Teachers' Approaches to Ethical Dilemmas in Catholic Schools - Ngo, Van Thu Giang (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

How does Fake News Affect People in Asia & Europe During a Pandemic? A Case Study About Macao and Portugal - Nicolau, Claúdia de Almeida Henriques (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Caregivers of Persons with Neurodevelopmental Conditions: Understanding Their Perspectives of the Need of Clinical Counselling Intervention - Pagdanganan, Paula Ramos (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Macau Mobility: Empowering the Commuter in Partial: Case study: E.Mobility Application - Pereira, Julieta Soares Gomes (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

A Financial Valuation of 3M Company - Poon, Hung Kong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

High-precision geochronology of Mesozoic magmatism in Macao, Southeast China: Evidence for multistage granite emplacement - Quelhas, Pedro; Dias, Ágata; Mata, João; Davis, Donald Wayne; Ribeiro, Maria Luísa (Geoscience Frontiers, 2020)
5 citations (Crossref) [2022-09-21]

Exploring the Distinctive Identity of Catholic Education in Three Catholic Secondary Schools in Macau - Ribeiro, Daniel Antonio De Carvalho (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Anticipare il Futuro della Cina. L’eredità del vescovo gesuita Jin Luxian SJ (“Anticipating the Future of China. The Heritage of the Jesuit Bishop Jin Luxian SJ”) - Rothlin, Stephan (La Civiltà Cattolica, 2020)

The Trend and Characteristics of Deviant Behavior of Young People in Macao Between 2001 and 2019 - Sam, Lek I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Risk Analysis in Sustainable Buildings' Construction Projects: A Perspective from Macau and Hong Kong - Santos, Eduardo José Piteira Paulo dos (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Unequal Access to Shadow Education in South Korea: Selection Processes of Parents from Different Socio-Economic Statuses - Seok-Hoon Jeon (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

探討澳門及香港華德福學前教育的實踐: 來自教師的視角 - Sio, Ka I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Contribution for the Public Consultation on the Macao SAR Masterplan 2020-2024 (University of Saint Joseph, 2020)

Macao’s mangroves - Tagulao, Karen; Chan, Sek Kiu (University of Saint Joseph, 2020)

The Role of Parents in the Referral Process to Inclusive Education in Macao - Tam, Ka In (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門小學資源教師的工作壓力及其應對方法之個案研究 - Tam, Lai Si (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Macau Sound Gallery: Soundscapes of Macau An Immersive Interactive Installation - U, Chin Cheng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

The Development of Brand Equity in the Five-star Hotel Industry of Macao - U, Weng I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Mangroves as ecosystem services providers in an urban context: case study of Macao, SAR China - Vanessa, W. L.; Calheiros, Cristina S. C.; Tagulao, Karen (University of Porto, 2020)

Mangroves as nature-based solution for coastal water eutrophication in Macao, SAR China - Vanessa, W. L.; Calheiros, Cristina S. C.; Tagulao, Karen (Blue Think Conference: Share Science, Spread Knowledge, 2020)

The History of Macau’s Portuguese Radio Case study of the first thirty episodes of the programme Frequência Académica - Vidinha, Margarida Sajara (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

A Content Analysis of School Bullying: A Review of Macau Newspaper Reports - Vong, Fan Nei (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Post-Divorce Parent-Child Relationships Impacts and Coping Mechanisma: Qualitative Study In Macao - Vong, Iek Chong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Place Marketing: Macao as the Art City for the Future Direction - Wong Ka I (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Socio-economic Impacts of Low Unemployment in Macau - Wong, Leng Cheng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Human-Belongings Behaviour Analysis: A Smart Interactive Cabinet - Wong, Nga Ieng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

A Financial Evaluation of Walmart Inc - Wong, Sut Man (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Green Space in Macau: Comparative Analyses and Suggestions for New Reclamation Areas - Xiao, Yuan Bin (University of Saint Joseph, 2020)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

'Being at Leisure' as a Primary Element of Pilgrimage: A phenomenological study of the Distinction between Christian and Secular Pilgrimage - Yuan, Haojun (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Philosophy; University of Saint Joseph

Anxious immobilities: an ethnography of coping with contagion (Covid-19) in Macau - Zuev, Dennis; Hannam, Kevin (Mobilities, 2020)
In February 2020, Macau became one of the first regions where the pandemic of coronavirus or Covid-19 affected the totality of social and economic life leading to increased anxieties over movement and distance. Although Macau has had very few actual cases of the virus – 46 in total –and no deaths from it, the Macau government rapidly instituted a lock down. The aim of this article is to reflect on how the social experience of being in lockdown can provide insights into understanding the type of experience or condition that we provisionally term ‘anxious immobility.’ Such a condition is characterized by a total disruption of everyday rhythms and specifically anxious waiting for the normalization of activity while being the subject of biosocial narratives of quarantine and socially responsible. The paper is based upon 3 months of ethnographic research conducted by two researchers based in Macau. We also reflect upon some aspects of the politics of mobilities in the light of disruptions and friction points between Hong Kong, Macau, mainland China, and the rest of the world.
13 citations (Crossref) [2022-09-21] GSCC: 0000008

運用音樂遊戲增進幼兒情緒調節及人際互動之行動研究 - 張麗嬋 (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

以行動研究探討遊戲學習對小學三年級學生數學問題解決能力之影響 - 曾威遠 (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education(MED); University of Saint Joseph

澳門小學中文科基本學力要求的實施現況研究: 個案研究 - 鄧樂怡 (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

探討澳門中學生學習困難、師生關係及學習動機之個案混合研究 - 陳思匯 (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph